Surveillance and ascertainment of cardiovascular events. The Cardiovascular Health Study. - Ives, D G; Fitzpatrick, A L; Bild, D E; Psaty, B M; Kuller, L H; Crowley, P M; Cruise, R G; Theroux, S (Ann Epidemiol, 1995)
While previous prospective multicenter studies have conducted cardiovascular disease surveillance, few have detailed the techniques relating to the ascertainment of and data collection for events. The Cardiovascular Health Study (CHS) is a population-based study of coronary heart disease and stroke in older adults. This article summarizes the CHS events protocol and describes the methods of surveillance and ascertainment of hospitalized and nonhospitalized events, the use of medical records and other support documents, organizational issues at the field center level, and the classification of events through an adjudication process. We present data on incidence and mortality, the classification of adjudicated events, and the agreement between classification by the Events Subcommittee and the medical records diagnostic codes. The CHS techniques are a successful model for complete ascertainment, investigation, and documentation of events in an older cohort.
Keywords: Aged; Cerebrovascular Disorders; Coronary Disease; Epidemiologic Methods; Female; Hospitalization; Humans; Incidence; Longitudinal Studies; Male; Population Surveillance; Quality Control; United States

Relationship of C-reactive protein to risk of cardiovascular disease in the elderly. Results from the Cardiovascular Health Study and the Rural Health Promotion Project. - Tracy, R P; Lemaitre, R N; Psaty, B M; Ives, D G; Evans, R W; Cushman, M; Meilahn, E N; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Markers of inflammation, such as C-reactive protein (CRP), are related to risk of cardiovascular disease (CVD) events in those with angina, but little is known about individuals without prevalent clinical CVD. We performed a prospective, nested case-control study in the Cardiovascular Health Study (CHS; 5201 healthy elderly men and women). Case subjects (n = 146 men and women with incident CVD events including angina, myocardial infarction, and death) and control subjects (n = 146) were matched on the basis of sex and the presence or absence of significant subclinical CVD at baseline (average follow-up, 2.4 years). In women but not men, the mean CRP level was higher for case subjects than for control subjects (P < or = .05). In general, CRP was higher in those with subclinical disease. Most of the association of CRP with female case subjects versus control subjects was in the subgroup with subclinical disease; 3.33 versus 1.90 mg/L, P < .05, adjusted for age and time of follow-up. Case-control differences were greatest when the time between baseline and the CVD event was shortest. The strongest associations were with myocardial infarction, and there was an overall odds ratio for incident myocardial infarction for men and women with subclinical disease (upper quartile versus lower three quartiles) of 2.67 (confidence interval [CI] = 1.04 to 6.81), with the relationship being stronger in women (4.50 [CI = 0.97 to 20.8]) than in men (1.75 [CI = 0.51 to 5.98]). We performed a similar study in the Rural Health Promotion Project, in which mean values of CRP were higher for female case subjects than for female control subjects, but no differences were apparent for men. Comparing the upper quintile with the lower four, the odds ratio for CVD case subjects was 2.7 (CI = 1.10 to 6.60). In conclusion, CRP was associated with incident events in the elderly, especially in those with subclinical disease at baseline.
Keywords: Aged; Aging; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Male; Prospective Studies; Sex Factors

The Sleep Heart Health Study: design, rationale, and methods. - Quan, S F; Howard, B V; Iber, C; Kiley, J P; Nieto, F J; O'Connor, G T; Rapoport, D M; Redline, S; Robbins, J; Samet, J M; Wahl, P W (Sleep, 1997)
The Sleep Heart Health Study (SHHS) is a prospective cohort study designed to investigate obstructive sleep apnea (OSA) and other sleep-disordered breathing (SDB) as risk factors for the development of cardiovascular disease. The study is designed to enroll 6,600 adult participants aged 40 years and older who will undergo a home polysomnogram to assess the presence of OSA and other SDB. Participants in SHHS have been recruited from cohort studies in progress. Therefore, SHHS adds the assessment of OSA to the protocols of these studies and will use already collected data on the principal risk factors for cardiovascular disease as well as follow-up and outcome information pertaining to cardiovascular disease. Parent cohort studies and recruitment targets for these cohorts are the following: Atherosclerosis Risk in Communities Study (1,750 participants), Cardiovascular Health Study (1,350 participants), Framingham Heart Study (1,000 participants), Strong Heart Study (600 participants), New York Hypertension Cohorts (1,000 participants), and Tucson Epidemiologic Study of Airways Obstructive Diseases and the Health and Environment Study (900 participants). As part of the parent study follow-up procedures, participants will be surveyed at periodic intervals for the incidence and recurrence of cardiovascular disease events. The study provides sufficient statistical power for assessing OSA and other SDB as risk factors for major cardiovascular events, including myocardial infarction and stroke.
Keywords: Adult; Aged; Aged, 80 and over; Arteriosclerosis; Cohort Studies; Coronary Disease; Female; Humans; Hypertension; Longitudinal Studies; Male; Middle Aged; Polysomnography; Positive-Pressure Respiration; Prospective Studies; Research Design; Sleep Apnea Syndromes

Factors Associated With Hospital Utilization in the Elderly: From the Cardiovascular Health Study. - Robbins, J. A.; Yanez, D.; Powe, N. R.; Savage, P. J.; Ives, D. G.; Gardin, J. M.; Lyles, M. (Am J Geriatr Cardiol, 1998)
OBJECTIVE: Analyze clinical, accepted biochemical, physiologic, and socioeconomic risk factors and correlate them with hospital utilization in an elderly population. DESIGN: Prospective, observational study in a defined, randomly recruited population. PARTICIPANTS: 5201 Medicare participants enrolled in the Cardiovascular Health Study (CHS). METHODS: Medicare recipients were randomly assigned to participate in an observational study. Baseline data were compared to hospital admissions and days of hospitalization over four years. DATA ANALYSIS: Data were grouped by type of risk factor and analyzed by Tobit analysis and logistic regression. RESULTS: Baseline variables associated with hospital use (p is less than 0.0001) were history of CHF, stroke, angina, hypertension, ln (timed walk), ln (blocks walked/week), age, gender, and clinic site. Factors not entering the model (p is greater than 0.05) were income, education, smoking, diabetes, weight, dietary fat, marital status, depression, and measures of mental function. CONCLUSIONS: In the elderly, existing health status is the major determinant of hospitalization and overwhelms many classic "risk factors" for morbidity.

Methods for obtaining and analyzing unattended polysomnography data for a multicenter study. Sleep Heart Health Research Group. - Redline, S; Sanders, M H; Lind, B K; Quan, S F; Iber, C; Gottlieb, D J; Bonekat, W H; Rapoport, D M; Smith, P L; Kiley, J P (Sleep, 1998)
This paper reviews the data collection, processing, and analysis approaches developed to obtain comprehensive unattended polysomnographic data for the Sleep Heart Health Study, a multicenter study of the cardiovascular consequences of sleep-disordered breathing. Protocols were developed and implemented to standardize in-home data collection procedures and to perform centralized sleep scoring. Of 7027 studies performed on 6697 participants, 5534 studies were determined to be technically acceptable (failure rate 5.3%). Quality grades varied over time, reflecting the influences of variable technician experience, and equipment aging and modifications. Eighty-seven percent of studies were judged to be of "good" quality or better, and 75% were judged to be of sufficient quality to provide reliable sleep staging and arousal data. Poor submental EMG (electromyogram) accounted for the largest proportion of poor signal grades (9% of studies had <2 hours artifact free EMG signal). These data suggest that with rigorous training and clear protocols for data collection and processing, good-quality multichannel polysomnography data can be obtained for a majority of unattended studies performed in a research setting. Data most susceptible to poor signal quality are sleep staging and arousal data that require clear EEG (electroencephalograph) and EMG signals.
Keywords: Electroencephalography; Electromyography; Feasibility Studies; Humans; Licensure; Polysomnography; Research Design; Sleep Apnea Syndromes; Teaching

Relation of sleepiness to respiratory disturbance index: the Sleep Heart Health Study. - Gottlieb, D J; Whitney, C W; Bonekat, W H; Iber, C; James, G D; Lebowitz, M; Nieto, F J; Rosenberg, C E (Am J Respir Crit Care Med, 1999)
Obstructive sleep apnea syndrome is a well recognized cause of excessive sleepiness; however, the relation of sleepiness to mild sleep-disordered breathing (SDB), which affects as much as half the adult population, is uncertain. In order to explore this relation, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study, a longitudinal study of the cardiovascular consequences of SDB. The study sample comprises 886 men and 938 women, with a mean age of 65 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Sleep-disordered breathing was quantified by the respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, measured during in-home polysomnography. When RDI was categorized into four groups (< 5, 5 to < 15, 15 to < 30, >/= 30), a significantly progressive increase in mean ESS score was seen across all four levels of SDB, from 7.2 (4.3) in subjects with RDI < 5 to 9.3 (4.9) in subjects with RDI >/= 30 (p < 0.001). There was no significant modification of this effect by age, sex, body mass index, or evidence of chronic restriction of sleep time or periodic limb movement disorder. The percentage of subjects with excessive sleepiness, defined as an ESS score >/= 11, increased from 21% in subjects with RDI < 5 to 35% in those with RDI >/= 30 (p < 0. 001). We conclude that SDB is associated with excess sleepiness in community-dwelling, middle-aged and older adults, not limited to those with clinically apparent sleep apnea.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Respiration; Retrospective Studies; Severity of Illness Index; Sleep Apnea Syndromes; Surveys and Questionnaires

Association between depression and mortality in older adults: the Cardiovascular Health Study. - Schulz, R; Beach, S R; Ives, D G; Martire, L M; Ariyo, A A; Kop, W J (Arch Intern Med, 2000)
BACKGROUND: Studies of the association between depressive symptoms and mortality in elderly populations have yielded contradictory findings. To address these discrepancies, we test this association using the most extensive array of sociodemographic and physical health control variables ever studied, to our knowledge, in a large population-based sample of elderly individuals. OBJECTIVE: To examine the relation between baseline depressive symptoms and 6-year all-cause mortality in older persons, systematically controlling for sociodemographic factors, clinical disease, subclinical disease, and health risk factors. METHODS: A total of 5201 men and women aged 65 years and older from 4 US communities participated in the study. Depressive symptoms and 4 categories of covariates were assessed at baseline. The primary outcome measure was 6-year mortality. RESULTS: Of the 5201 participants, 984 (18.9%) died within 6 years. High baseline depressive symptoms were associated with a higher mortality rate (23.9%) than low baseline depression scores (17.7%) (unadjusted relative risk [RR], 1.41; 95% confidence interval [CI], 1.22-1.63). Depression was also an independent predictor of mortality when controlling for sociodemographic factors (RR, 1.43; 95% CI, 1.23-1.66), prevalent clinical disease (RR, 1.25; 95% CI, 1.07-1.45), subclinical disease indicators (RR, 1.35; 95% CI, 1.15-1.58), or biological or behavioral risk factors (RR, 1.42; 95% CI, 1.22-1.65). When the best predictors from all 4 classes of variables were included as covariates, high depressive symptoms remained an independent predictor of mortality (RR, 1.24; 95% CI, 1.06-1.46). CONCLUSIONS: High levels of depressive symptoms are an independent risk factor for mortality in community-residing older adults. Motivational depletion may be a key underlying mechanism for the depression-mortality effect.
Keywords: Aged; Alcohol Drinking; Depression; Depressive Disorder; Female; Health Status Indicators; Humans; Male; Motivation; Prevalence; Risk Factors; Smoking; Socioeconomic Factors; United States

Effects of varying approaches for identifying respiratory disturbances on sleep apnea assessment. - Redline, S; Kapur, V K; Sanders, M H; Quan, S F; Gottlieb, D J; Rapoport, D M; Bonekat, W H; Smith, P L; Kiley, J P; Iber, C (Am J Respir Crit Care Med, 2000)
Varying approaches to measuring the respiratory disturbance index (RDI) may lead to discrepant estimates of the severity of sleep-disordered breathing (SDB). In this study, we assessed the impact of varying the use of corroborative data (presence and degree of desaturation and/or arousal) to identify hypopneas and apneas. The relationships among 10 RDIs defined by various definitions of apneas and hypopneas were assessed in 5,046 participants in the Sleep Heart Health Study (SHHS) who underwent overnight unattended 12-channel polysomnography (PSG). The magnitude of the median RDI varied 10-fold (i.e., 29.3 when the RDI was based on events identified on the basis of flow or volume amplitude criteria alone to 2.0 for an RDI that required an associated 5% desaturation with events). The correlation between RDIs based on different definitions ranged from 0.99 to 0.68. The highest correlations were among RDIs that required apneas and hypopneas to be associated with some level of desaturation. Lower correlations were observed between RDIs that required desaturation as compared with RDIs defined on the basis of amplitude criteria alone or associated arousal. These data suggest that different approaches for measuring the RDI may contribute to substantial variability in identification and classification of the disorder.
Keywords: Adult; Aged; Aged, 80 and over; Arousal; Diagnosis, Differential; Female; Humans; Lung Volume Measurements; Male; Middle Aged; Observer Variation; Oxygen; Oxyhemoglobins; Polysomnography; Risk Factors; Sleep Apnea Syndromes

Rates of sensor loss in unattended home polysomnography: the influence of age, gender, obesity, and sleep-disordered breathing. - Kapur, V K; Rapoport, D M; Sanders, M H; Enright, P; Hill, J; Iber, C; Romaniuk, J (Sleep, 2000)
OBJECTIVES: To evaluate study failure and sensor loss in unattended home polysomnography and their relationship to age, gender, obesity, and severity of sleep-disordered breathing (SDB). DESIGN: A cross-sectional analysis of data gathered prospectively for the Sleep Heart Health Study (SHHS). SETTING: Unattended polysomnography was performed in participants' homes by the staff of the sites that are involved in SHHS. PARTICIPANTS: 6,802 individuals who met the inclusion criteria (age >40 years, no history of treatment of sleep apnea, no tracheostomy, no current home oxygen therapy) for SHHS. RESULTS: A total of 6802 participants had 7151 studies performed. 6161 of 6802 initial studies (90.6%) were acceptable. Obesity was associated with a decreased likelihood of a successful initial study. After one or more attempts, 6440 participants (94.7%) had studies that were judged as acceptable. The mean duration of scorable signals for specific channels ranged from 5.7 to 6.8 hours. The magnitudes of the effects of age, gender, BMI, and RDI on specific signal durations were not clinically significant. CONCLUSION: Unattended home PSG as performed for SHHS was usually successful. Participant characteristics had very weak associations with duration of scorable signal. This study suggests that unattended home PSG, when performed with proper protocols and quality controls, has reasonable success rates and signal quality for the evaluation of SDB in clinical and research settings.
Keywords: Age Factors; Cross-Sectional Studies; Electroencephalography; Electromyography; Electrooculography; Equipment Failure; Female; Humans; Male; Middle Aged; Obesity; Polysomnography; Prospective Studies; Severity of Illness Index; Sex Factors; Sleep Apnea Syndromes

Incidence and predictors of coronary heart disease among older African Americans--the Cardiovascular Health Study. - Jackson, S A; Burke, G L; Thach, C; Cushman, M; Ives, D; Powe, N; Manolio, T A (J Natl Med Assoc, 2001)
Although coronary heart disease (CHD) is the leading cause of death and morbidity in older African Americans, relatively little is known about the incidence and predictors of CHD in this population. This study was undertaken to determine the incidence and predictors of CHD in African-American men and women aged 65 years and older. The participants in this study included a total of 924 African-American men and women aged 65 years of age and older who participated in the Cardiovascular Health Study (CHS). The overall CHD incidence was 26.6 per 1,000 person-years of risk. Rates were higher in men than women (35.3 vs. 21.6) and in those 75 years or older than in those less than 75 years (31.3 vs. 24.5). In multivariate analysis, factors associated with higher risk of incident disease were male gender [relative risk (RR) = 1.8, 95% confidence interval (CI) = 1.1, 2.7], diabetes mellitus (RR = 1.9, 95% CI = 1.2, 2.9), total cholesterol (RR for 40 mg/dL increment = 1.3, 95% CI = 1.0, 1.5), and low (i.e., <0.9) ankle-arm index (RR = 2.1, 95% CI = 1.3, 3.4) after adjusting for age. Within this cohort of older African Americans, male gender, diabetes mellitus, total cholesterol, and low ankle-arm index and were independently predictive of incident events. These results suggest that the ankle-arm index, a measure of advanced atherosclerosis, should be further evaluated for its efficacy in identifying older African Americans at risk for incident clinical events.
Keywords: Age Distribution; Aged; Black or African American; Coronary Disease; Female; Health Status; Humans; Incidence; Male; Predictive Value of Tests

Measures of cognitive function in persons with varying degrees of sleep-disordered breathing: the Sleep Heart Health Study. - Boland, Lori L; Shahar, Eyal; Iber, Conrad; Knopman, David S; Kuo, Tracy F; Nieto, F Javier (J Sleep Res, 2002)
Epidemiologic literature suggests that persons with clinically diagnosed sleep apnoea frequently have impaired cognitive function, but whether milder degrees of sleep-disordered breathing (SDB) are associated with cognitive dysfunction in the general population is largely unknown. Approximately 1700 subjects free of clinically diagnosed SDB underwent at-home polysomnography (PSG) as part of the Sleep Heart Health Study (SHHS) and completed three cognitive function tests within 1-2 years of their PSG: the Delayed Word Recall Test (DWR), the WAIS-R Digit Symbol Subtest (DSS), and the Word Fluency test (WF). A respiratory disturbance index (RDI) was calculated as the number of apnoeas and hypopnoeas per hour of sleep. After adjustment for age, education, occupation, field centre, diabetes, hypertension, body-mass index, use of CNS medications, and alcohol drinking status, there was no consistent association between the RDI and any of the three cognitive function measures. There was no evidence of a dose-response relation between the RDI and cognitive function scores and the adjusted mean scores by quartiles of RDI never differed from one another by more than 5% for any of the tests. In this sample of free-living individuals with mostly mild to moderate levels of SDB, the degree of SDB appeared to be unrelated to three measures of cognitive performance.
Keywords: Aged; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Hypoxia; Male; Middle Aged; Neuropsychological Tests; Oxygen; Polysomnography; Severity of Illness Index; Sleep Apnea, Central

Short-term variability of respiration and sleep during unattended nonlaboratory polysomnography--the Sleep Heart Health Study. [corrected]. - Quan, Stuart F; Griswold, Michael E; Iber, Conrad; Nieto, F Javier; Rapoport, David M; Redline, Susan; Sanders, Mark; Young, Terry (Sleep, 2002)
STUDY OBJECTIVES: To determine the short-term variability of indices of disturbed respiration and sleep during 2 nights of unattended nonlaboratory polysomnography conducted several months apart. DESIGN: Participants were randomly selected using a block design with stratification on preliminary estimates of 2 criteria: respiratory disturbance index [RDI3% (apnea or hypopnea events associated with > or = 3% O2 desaturation): < 15/hour total sleep time, > or = 15/hour total sleep time] and sleep efficiency (SEff: < 85% and > or = 85%). The RDI and sleep data from initial and repeated polysomnography were compared. SETTING: NA. PARTICIPANTS: A subset of 99 participants in the Sleep Heart Health Study who agreed to have a repeat polysomnogram within 4 months of their original study. INTERVENTIONS: NA. MEASUREMENTS AND RESULTS: Acceptable repeat polysomnograms were obtained in 91 subjects (mean study interval: 77 +/- 18 [sd] days; range: 31-112 days). There was no significant bias in RDI between study nights using several different RDI definitions including RDI3% and RDI4% (apnea or hypopnea events associated with > or = 4% O2 desaturation). Variability between studies estimated using intraclass correlations (ICC) ranged from 0.77 to 0.81. For subjects with a RDI3% < 15, variability increased as a function of increasing RDI, but for those with a RDI3% > or = 15, variability was constant. Body mass index, SEff, gender, or age did not directly predict RDI variability. Using RDI4% cutpoints of < or = 5, < or = 10 and < or = 15 events per hour of sleep demonstrated that 79.1%, 85.7%, and 87.9% of subjects, respectively, had the same classification of SDB status on both nights of study. There also was no significant bias in sleep staging, sleep efficiency, or arousal index between studies. However, variability was greater with ICC values ranging from 0.37 (% time in REM) to 0.76 (arousal index). CONCLUSION: In the Sleep Heart Health Study, accurate estimates of the severity of sleep-disordered breathing and the quality of sleep were obtained from a single night of unattended nonlaboratory polysomnography. These findings may be applicable to other large epidemiologic studies provided that similar recording techniques and quality-assurance procedures are followed.
Keywords: Adult; Aged; Aged, 80 and over; Apnea; Arousal; Body Mass Index; Circadian Rhythm; Electrocardiography; Electromyography; Electrooculography; Female; Humans; Male; Middle Aged; Oxygen Consumption; Polysomnography; Respiration; Sleep Apnea Syndromes; Sleep Stages; Time Factors

Underdiagnosis of sleep apnea syndrome in U.S. communities. - Kapur, Vishesh; Strohl, Kingman P; Redline, Susan; Iber, Conrad; O'Connor, George; Nieto, Javier (Sleep Breath, 2002)
We hypothesize that clinical recognition rates for obstructive sleep apnea-hypoapnea syndrome (OSAHS) are influenced by comorbidity and demographic factors. Data on medical disorders, symptoms of sleep disorders, and cardiovascular risk factors gathered from 15,699 individuals in the Sleep Heart Health Study were compared. Participants were classified into three groups: those with a self-reported physician diagnosis of OSAHS, those with self-reported physician-diagnosed and -treated OSAHS, and those reporting both frequent snoring and daytime sleepiness (two-symptom group). Among all participants, 4.1% reported two symptoms (range across sites: 1.55 to 7.23%), whereas 1.6% reported a physician diagnosis of OSAHS (range: 0.66 to 2.88%) and 0.6% reported physician diagnosis and treatment (range: 0.11 to 0.88%). Recognized OSAHS groups were similar to the two-symptom group in age, having a sleeping partner, measured blood pressure, total cholesterol, and race. In a logistic model that included age along with characteristics found to vary significantly among the three groups (gender, body mass index [BMI], high-density lipoprotein cholesterol levels, hypertension), only male gender and BMI were increased in those with physician-diagnosed and -treated OSAHS. We conclude that disparities (especially in women and in those with lower BMI) exist between current recognition rates for OSAHS and the estimated prevalence by symptom report across the United States.
Keywords: Diagnosis, Differential; Diagnostic Errors; Female; Humans; Male; Middle Aged; Prevalence; Sleep Apnea Syndromes; United States

Evaluation of dementia in the cardiovascular health cognition study. - Lopez, Oscar L; Kuller, Lewis H; Fitzpatrick, Annette; Ives, Diane; Becker, James T; Beauchamp, Norman (Neuroepidemiology, 2003)
OBJECTIVE: To describe a methodology to evaluate dementia and frequency of different types of dementia and prevalence of the Cardiovascular Health Study (CHS). METHODS: The CHS is a longitudinal study of cardiovascular disease among community-dwelling individuals over the age of 65. Of the 5,888 participants in the original study, 3,608 had a magnetic resonance imaging (MRI) of the brain in 1991, and formed the cohort for the dementia study. The CHS included yearly measures of cognitive function and, from 1998 to 2000, participants were evaluated for dementia by detailed neurological, and neuropsychological examinations. The possible cases of dementia and mild cognitive impairment (MCI) were adjudicated by a review committee of neurologists and psychiatrists. RESULTS: There were 480 cases of (13.3%) incident dementia in the total sample, 227 (6.3%) prevalent dementia, 577 (16.0%) MCI, and 2,318 (64.4%) normal. The adjudication committee classified 69% of the incident dementia as Alzheimer's disease (AD), 11% as vascular dementia (VaD), 16% as both, and 4% as other types. There was a substantial agreement between pre- and postMRI diagnosis of types of dementia. The frequency of dementia within the CHS cohort which survived to the end of the study in 1998-1999, was 13.5% for white men, 14.5% for white women, 22.2% for black men and 23.4% for black women. CONCLUSION: The CHS has developed a methodology for longitudinal studies of dementia in large cohorts and represents the largest study of dementia including cognitive testing, MRI and genetic markers.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prevalence; Risk Factors; Sex Distribution

Barriers to health care access among the elderly and who perceives them. - Fitzpatrick, Annette L; Powe, Neil R; Cooper, Lawton S; Ives, Diane G; Robbins, John A (Am J Public Health, 2004)
OBJECTIVES: We evaluated self-perceived access to health care in a cohort of Medicare beneficiaries. METHODS: We identified patterns of use and barriers to health care from self-administered questionnaires collected during the 1993-1994 annual examination of the Cardiovascular Health Study. RESULTS: The questionnaires were completed by 4889 (91.1%) participants, with a mean age of 76.0 years. The most common barriers to seeing a physician were the doctor's lack of responsiveness to patient concerns, medical bills, transportation, and street safety. Low income, no supplemental insurance, older age, and female gender were independently related to perceptions of barriers. Race was not significant after adjustment for other factors. CONCLUSIONS: Psychological and physical barriers affect access to care among the elderly; these may be influenced by poverty more than by race.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Female; Health Behavior; Health Services Accessibility; Humans; Logistic Models; Male; Medicare; Patients; Surveys and Questionnaires; United States

Incidence and prevalence of dementia in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Kuller, Lewis H; Ives, Diane G; Lopez, Oscar L; Jagust, William; Breitner, John C S; Jones, Beverly; Lyketsos, Constantine; Dulberg, Corinne (J Am Geriatr Soc, 2004)
OBJECTIVES: To estimate the incidence and prevalence of dementia, Alzheimer's disease (AD), and vascular dementia (VaD) in the Cardiovascular Health Study (CHS) cohort. DESIGN: Longitudinal cohort study using prospectively and retrospectively collected data to evaluate dementia. SETTING: Four U.S. communities. PARTICIPANTS: There were 3,602 CHS participants, including 2,865 white and 492 African-American participants free of dementia, who completed a cranial magnetic resonance image between 1992 and 1994 and were followed for an average of 5.4 years. MEASUREMENTS: Dementia was classified by neurologist/psychiatrist committee review using neuropsychological tests, neurological examinations, medical records, physician questionnaires, and proxy/informant interviews. Demographics and apolipoprotein E (APOE) genotype were collected at baseline. Incidence by type of dementia was determined using National Institute of Neurological and Communicative Disorders and Stroke-Alzheimer's Disease and Related Disorders Association criteria for AD and Alzheimer's Disease Diagnostic and Treatment Center's State of California criteria for VaD. RESULTS: Classification resulted in 227 persons with prevalent dementia at entry into the study and 480 incident cases during follow-up. Incidence rates of dementia scaled to age 80 were 34.7 per 1,000 person-years for white women, 35.3 for white men, 58.8 for African-American women, and 53.0 for African-American men. Sex differences were not significant within race. Adjusted for age and education, racial differences were only of borderline significance and may have been influenced by ascertainment methodology. Rates differed substantially by educational attainment but were only significant for whites. Those with the APOE epsilon4 allele had an incidence rate at age 80 of 56.4, compared with 29.6 for those without this allele (P<.001). In whites, type-specific incidence at age 80 was 19.2 for AD versus 14.6 for VaD. These rates were 34.7 and 27.2 for African Americans. At termination of observation, women had only a slightly higher prevalence of dementia (16.0%) than men (14.7%). CONCLUSION: Sex and racial differences were not found, and VaD was higher than reported in other studies. These data provide new estimates of dementia incidence in a community sample for projection of future burden.
Keywords: African Americans; Age Distribution; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Dementia; Dementia, Vascular; Education; European Continental Ancestry Group; Female; Humans; Incidence; Longitudinal Studies; Male; Prevalence; Proportional Hazards Models; Risk Factors; Sex Distribution; United States

Polysomnography performed in the unattended home versus the attended laboratory setting--Sleep Heart Health Study methodology. - Iber, Conrad; Redline, Susan; Kaplan Gilpin, Adele M; Quan, Stuart F; Zhang, Lin; Gottlieb, Daniel J; Rapoport, David; Resnick, Helaine E; Sanders, Mark; Smith, Philip (Sleep, 2004)
STUDY OBJECTIVE: To compare polysomnographic recordings obtained in the home and laboratory setting. DESIGN AND SETTING: Multicenter study comparing unsupervised polysomnography performed in the participant's home with polysomnography supervised at an academic sleep disorders center, using a randomized sequence of study setting. Sleep Heart Health Study (SHHS) standardized polysomnographic recording and scoring techniques were used for both settings. PARTICIPANTS: 64 of 76 non-SHHS participants recruited from 7 SHHS field sites who had both a laboratory and home polysomnogram meeting acceptable quality criteria. MEASUREMENTS AND RESULTS: Median sleep duration was greater in the home than in the laboratory (375 vs 318 minutes, respectively, P < .0001) as was sleep efficiency (86% vs 82%, respectively, P < .0024). Very small, but significant increases in percentage of rapid eye movement sleep and decreases in stage 1 sleep were noted in the laboratory. Employing multiple definitions of respiratory disturbance index (RDI), median RDI was similar in both settings (for example, RDI with 3% desaturation: home 12.4, range 0.6-67; laboratory 9.5, range 0.1-93.4, P = .41). Quartile analysis of laboratory RDI showed moderate agreement with home RDI measurements. Based on the mean of laboratory and home RDI and using a cutpoint of 20, there was a biphasic distribution, with the RDI 3% above 20 being more common in the recordings performed in the laboratory than in the home and below 20 being more common in the recordings performed in the home than in the laboratory. These differences could not be attributed to quality of recording, age, sex, or body mass index. CONCLUSIONS: Using SHHS methodology, median RDI was similar in the unattended home and attended laboratory setting with differences of small magnitude in some sleep parameters. Differences in RDI between settings resulted in a rate of disease misclassification that is similar to repeated studies in the same setting.
Keywords: Adult; Aged; Body Mass Index; Clinical Laboratory Techniques; Cohort Studies; Health Status; Home Care Services; Humans; Middle Aged; Polysomnography; Sleep Apnea Syndromes; Sleep, REM

Dementia and Alzheimer's disease incidence in relationship to cardiovascular disease in the Cardiovascular Health Study cohort. - Newman, Anne B; Fitzpatrick, Annette L; Lopez, Oscar; Jackson, Sharon; Lyketsos, Constantine; Jagust, William; Ives, Diane; DeKosky, Steven T; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether coronary artery disease, peripheral arterial disease (PAD), or noninvasive markers of cardiovascular disease (CVD) predict the onset of dementia and Alzheimer's disease (AD). DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Men and women (N=3,602) with a brain magnetic resonance imaging (MRI) scan but no dementia were followed for 5.4 years. Participants with stroke were excluded. MEASUREMENTS: Neurologists and psychiatrists classified incident cases of dementia and subtype using neuropsychological tests, examination, medical records and informant interviews. CVD was defined at the time of the MRI scan. Noninvasive tests of CVD were assessed within 1 year of the MRI. Apolipoprotein E allele status, age, race, sex, education, Mini-Mental State Examination score, and income were assessed as potential confounders. RESULTS: The incidence of dementia was higher in those with prevalent CVD, particularly in the subgroup with PAD. The rate of AD was 34.4 per 1,000 person-years for those with a history of CVD, versus 22.2 per 1,000 person-years without a history of CVD (adjusted hazard ratio (HR)=1.3, 95% confidence interval (CI)=1.0-1.7). Rates of AD were highest in those with PAD (57.4 vs 23.7 per 100 person-years, adjusted HR=2.4, 95% CI=1.4-4.2). Results were similar with further exclusion of those with vascular dementia from the AD group. A gradient of increasing risk was noted with the extent of vascular disease. CONCLUSION: Older adults with CVD other than stroke had a higher risk of dementia and AD than did those without CVD. The risk was highest in people with PAD, suggesting that extensive peripheral atherosclerosis is a risk factor for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Peripheral Vascular Diseases; Risk Factors

Predictors of heartburn during sleep in a large prospective cohort study. - Fass, Ronnie; Quan, Stuart F; O'Connor, George T; Ervin, Ann; Iber, Conrad (Chest, 2005)
BACKGROUND AND AIMS: Nocturnal gastroesophageal reflux, which may result in nocturnal heartburn, has been demonstrated to be associated with a more severe form of gastroesophageal reflux disease (GERD). The aim of this study was to determine the clinical predictors of heartburn during sleep in a large prospective cohort study. METHODS: Study subjects were members of the parent cohorts from which the Sleep Heart Health Study (SHHS) recruited participants. SHHS is a multicenter, longitudinal, cohort study of the cardiovascular consequences of sleep-disordered breathing. As part of the recruitment process, parent cohort members completed a questionnaire that permitted an assessment of the relationships between heartburn during sleep, and patient demographics, sleep abnormalities, medical history, and social habits in nine community-based parent cohorts across the United States. All variables, significant at the p < 0.05 level, were included as independent variables in multivariate logistic regression models with heartburn during sleep status included as the dependent variable RESULTS: A total of 15,314 subjects completed the questions about heartburn during sleep, and of these, 3,806 subjects (24.9%) reported having this symptom. In four increasingly comprehensive multivariate models, increased body mass index (BMI), carbonated soft drink consumption, snoring and daytime sleepiness (Epworth sleepiness scale score), insomnia, hypertension, asthma, and usage of benzodiazepines were strong predictors of heartburn during sleep. In contrast, college education decreased the risk of reporting heartburn during sleep. CONCLUSIONS: Heartburn during sleep is very common in the general population. Reports of this type of symptom of GERD are strongly associated with increased BMI, carbonated soft drink consumption, snoring and daytime sleepiness, insomnia, hypertension, asthma, and usage of benzodiazepines. Overall, heartburn during sleep may be associated with sleep complaints and excessive daytime sleepiness.
Keywords: Aged; Body Mass Index; Carbonated Beverages; Cohort Studies; Educational Status; Female; Gastroesophageal Reflux; Heartburn; Humans; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Sleep; Surveys and Questionnaires

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

Anemia is associated with the progression of white matter disease in older adults with high blood pressure: the cardiovascular health study. - Inzitari, Marco; Studenski, Stephanie; Rosano, Caterina; Zakai, Neil A; Longstreth, William T; Cushman, Mary; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To investigate whether anemia predicts worsening white matter hyperintensities (WMHs) in older community-dwellers. DESIGN: Prospective cohort study. SETTING: Older community-dwellers. PARTICIPANTS: One thousand eight hundred forty-six Cardiovascular Health Study (CHS) participants (mean age 73.7 +/- 4.4, 41% male, 15.6% African American). MEASUREMENTS: Participants had hemoglobin measured and brain magnetic resonance imaging (MRI) in 1992/93 and a second brain MRI in 1997/98. Anemia was defined according to World Health Organization criteria (hemoglobin <12 g/dL in women and <13 g/dL in men). Worsening WMHs were determined according to standardized side-by-side readings. RESULTS: After 5 years, WMHs worsened in 517 participants (28%). Progression was not associated with anemia in the whole sample, in sex or race strata, or in other prespecified subgroups (participants with renal dysfunction or diabetes mellitus), except in participants with high blood pressure (>or=140/90 mmHg). Of the 678 participants with high blood pressure, those with anemia (10.5%) had a 1.79 times greater risk of WMHs worsening (95% confidence interval=1.06-2.98; P for interaction between anemia and high blood pressure=.01) independent of demographics, baseline WMHs, cardiovascular risk factors and comorbidities, medications, renal function, inflammation, and incident stroke (logistic regression models). There was no greater risk in participants with anemia with normal blood pressure. CONCLUSION: Anemia may contribute to worsening of WMHs in older adults with high blood pressure.
Keywords: Aged; Anemia; Brain; Cardiovascular Diseases; Disease Progression; Female; Humans; Hypertension; Leukoaraiosis; Magnetic Resonance Imaging; Male

Association of gene variants with incident myocardial infarction in the Cardiovascular Health Study. - Shiffman, Dov; O'Meara, Ellen S; Bare, Lance A; Rowland, Charles M; Louie, Judy Z; Arellano, Andre R; Lumley, Thomas; Rice, Kenneth; Iakoubova, Olga; Luke, May M; Young, Bradford A; Malloy, Mary J; et al. (Arterioscler Thromb Vasc Biol, 2008)
OBJECTIVE: We asked whether single nucleotide polymorphisms (SNPs) that had been nominally associated with cardiovascular disease in antecedent studies were also associated with cardiovascular disease in a population-based prospective study of 4522 individuals aged 65 or older. METHODS AND RESULTS: Based on antecedent studies, we prespecified a risk allele and an inheritance model for each of 74 SNPs. We then tested the association of these SNPs with myocardial infarction (MI) in the Cardiovascular Health Study (CHS). The prespecified risk alleles of 8 SNPs were nominally associated (1-sided P<0.05) with increased risk of MI in White CHS participants. The false discovery rate for these 8 was 0.43, suggesting that about 4 of these 8 are likely to be true positives. The 4 of these 8 SNPs that had the strongest evidence for association with cardiovascular disease before testing in CHS (association in 3 antecedent studies) were in KIF6 (CHS HR=1.29; 90%CI 1.1 to 1.52), VAMP8 (HR=1.2; 90%CI 1.02 to 1.41), TAS2R50 (HR=1.13; 90%CI 1 to 1.27), and LPA (HR=1.62; 90%CI 1.09 to 2.42). CONCLUSIONS: Although most of the SNPs investigated were not associated with MI in CHS, evidence from this investigation combined with previous studies suggests that 4 of these SNPs are likely associated with MI.
Keywords: African Americans; Aged; Aged, 80 and over; Coronary Disease; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Coronary artery calcium and physical function in older adults: the Cardiovascular Health Study. - Inzitari, Marco; Naydeck, Barbara L; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults without clinical cardiovascular disease, coronary artery calcium (CAC) is associated with other subclinical vascular diseases, which, in turn, predict physical dysfunction. However, the association between CAC and physical function is unstudied. METHODS: In 387 older community-dwellers from the Cardiovascular Health Study without clinical cardiovascular diseases (mean age +/- standard deviation = 78.7 +/- 3.7, 35% men, 22% African Americans), CAC was measured using electron beam tomography, and physical performance was assessed by usual pace gait speed, chair stand, and tandem stand. Differences in physical performance across CAC quartiles were investigated in the whole cohort and by gender. Associations with gait speed (m/s) were assessed in multivariable models using both the continuous form of CAC score (log(CAC)) and quartiles of CAC, adjusting for demographics and comorbidities. RESULTS: No differences in physical performance were observed across CAC quartiles in the whole group. In gender-stratified analyses, a significant association was shown among women, who had progressively lower gait speed across CAC quartiles: Those with CAC > 220 walked more than 0.1 m/s slower than those with CAC < 35 (age-adjusted ptrend =.017). After multivariable adjustment, the association remained statistically significant for women in both linear (log(CAC) and gait speed, p =.025) and logistic models: Each of the top three CAC quartiles (35-220, 221-659, and > or = 660) had a more than twofold odds of walking slower than 1 m/s, compared to the lowest CAC quartile (< 35; p =.021). CONCLUSIONS: In this sample of older community-dwellers without overt cardiovascular disease, CAC was inversely related to gait speed in women, but not in men.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Calcinosis; Coronary Artery Disease; Female; Geriatric Assessment; Humans; Male; Regression Analysis; Risk Factors; Tomography, X-Ray Computed; Walking

Coronary artery calcium, carotid artery wall thickness, and cardiovascular disease outcomes in adults 70 to 99 years old. - Newman, Anne B; Naydeck, Barbara L; Ives, Diane G; Boudreau, Robert M; Sutton-Tyrrell, Kim; O'Leary, Daniel H; Kuller, Lewis H (Am J Cardiol, 2008)
Few population studies have evaluated the associations of both coronary artery calcium (CAC) and carotid ultrasound with cardiovascular events, especially in adults >70 years of age. At the Pittsburgh Field Center of the Cardiovascular Health Study, 559 men and women, mean age 80.2 (SD 4.1) years had CAC score assessed by electron beam computerized tomographic scan and common and internal carotid artery intimal medial wall thickness (CCA-IMT and ICA-IMT) by carotid ultrasound between 1998 and 2000 and were followed for total and incident cardiovascular disease events through June 2003. Crude rates and hazard ratios for total and incident events were examined with and without adjustment for cardiovascular risk factors. After 5 years, there were 127 cardiovascular disease events, 48 myocardial infarctions or cardiovascular disease deaths, and 28 strokes or stroke deaths. Total and incident cardiovascular disease event rates were higher in each quartile of CAC and CCA-IMT, but not of ICA-IMT. For total cardiovascular disease, the adjusted hazard ratio for the fourth versus first quartile of CAC was 2.1 (95% confidence interval 1.2 to 3.9) and for CCA-IMT was 2.3 (95% confidence interval 1.3 to 4.1). The CCA-IMT was more strongly related to stroke risk than was CAC, although CAC was also an important predictor of stroke. No significant gender differences were found, although relative risks appeared to be stronger in women, especially for stroke. In conclusion, in adults >70 years of age, CAC and CCA-IMT had similar hazard ratios for total cardiovascular disease and coronary heart disease. The CCA-IMT was more strongly related to stroke than CAC, but CAC was also a predictor of stroke.
Keywords: Aged; Aged, 80 and over; Carotid Artery Diseases; Carotid Artery, Common; Carotid Artery, Internal; Coronary Artery Disease; Coronary Vessels; Female; Humans; Male; ROC Curve; Severity of Illness Index; Survival Analysis; Ultrasonography; United States

Enhanced risk for Alzheimer disease in persons with type 2 diabetes and APOE epsilon4: the Cardiovascular Health Study Cognition Study. - Irie, Fumiko; Fitzpatrick, Annette L; Lopez, Oscar L; Kuller, Lewis H; Peila, Rita; Newman, Anne B; Launer, Lenore J (Arch Neurol, 2008)
BACKGROUND: Diabetes and the apolipoprotein E epsilon4 allele (APOE epsilon4) increase the risk for Alzheimer disease (AD). We hypothesize that APOE epsilon4 may modify the risk for AD in individuals with diabetes. OBJECTIVE: To examine the joint effect of type 2 diabetes and APOE epsilon4 on the risk of AD, AD with vascular dementia (mixed AD), and vascular dementia without AD. DESIGN: The Cardiovascular Health Study (CHS) Cognition Study (1992-2000) is a prospective study designed to identify all existing and new cases of dementia among study participants. Diagnoses were made according to international criteria for dementia and subtypes. There were 2547 dementia-free participants in the CHS Cognition Study cohort with complete information on APOE epsilon4 and type 2 diabetes status; among these, 411 new cases of dementia developed. Risk of dementia was estimated with a Cox proportional hazard model adjusted for age and other demographic and cardiovascular risk factors. RESULTS: Compared with those who had neither type 2 diabetes nor APOE epsilon4, those with both factors had a significantly higher risk of AD (hazard ratio, 4.58; 95% confidence interval, 2.18-9.65) and mixed AD (hazard ratio, 3.89; 95% confidence interval, 1.46-10.40). CONCLUSION: These data suggest that having both diabetes and APOE epsilon4 increases the risk of dementia, especially for AD and mixed AD.
Keywords: African Americans; Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Cognition; Cohort Studies; Confidence Intervals; Dementia, Vascular; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Genotype; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors

Agreement between nosologist and cardiovascular health study review of deaths: implications of coding differences. - Ives, Diane G; Samuel, Paulraj; Psaty, Bruce M; Kuller, Lewis H (J Am Geriatr Soc, 2009)
OBJECTIVES: To compare nosologist coding of underlying cause of death according to the death certificate with adjudicated cause of death for subjects aged 65 and older in the Cardiovascular Health Study (CHS). DESIGN: Observational. SETTING: Four communities: Forsyth County, North Carolina (Wake Forest University); Sacramento County, California (University of California at Davis); Washington County, Maryland (Johns Hopkins University); and Pittsburgh, Pennsylvania (University of Pittsburgh). PARTICIPANTS: Men and women aged 65 and older participating in CHS, a longitudinal study of coronary heart disease and stroke, who died through June 2004. MEASUREMENTS: The CHS centrally adjudicated underlying cause of death for 3,194 fatal events from June 1989 to June 2004 using medical records, death certificates, proxy interviews, and autopsies, and results were compared with underlying cause of death assigned by a trained nosologist based on death certificate only. RESULTS: Comparison of 3,194 CHS versus nosologist underlying cause of death revealed moderate agreement except for cancer (kappa=0.91, 95% confidence interval (CI)=0.89-0.93). kappas varied according to category (coronary heart disease, kappa=0.61, 95% CI=0.58-0.64; stroke, kappa=0.59, 95% CI=0.54-0.64; chronic obstructive pulmonary disease, kappa=0.58, 95% CI=0.51-0.65; dementia, kappa=0.40, 95% CI=0.34-0.45; and pneumonia, kappa=0.35, 95% CI=0.29-0.42). Differences between CHS and nosologist coding of dementia were found especially in older ages in the sex and race categories. CHS attributed 340 (10.6%) deaths due to dementia, whereas nosologist coding attributed only 113 (3.5%) to dementia as the underlying cause. CONCLUSION: Studies that use only death certificates to determine cause of death may result in misclassification and potential bias. Changing trends in cause-specific mortality in older individuals may be a function of classification process rather than incidence and case fatality.
Keywords: Aged; Aged, 80 and over; Cause of Death; Coronary Disease; Death Certificates; Female; Forms and Records Control; Humans; Longitudinal Studies; Male; Stroke

Association of chronic kidney disease with the spectrum of ankle brachial index the CHS (Cardiovascular Health Study). - Ix, Joachim H; Katz, Ronit; de Boer, Ian H; Kestenbaum, Brian R; Allison, Matthew A; Siscovick, David S; Newman, Anne B; Sarnak, Mark J; Shlipak, Michael G; Criqui, Michael H (J Am Coll Cardiol, 2009)
OBJECTIVES: This study sought to determine the association of chronic kidney disease (CKD) with high ankle brachial index (ABI) measurement and to compare its strength with that of CKD with a low ABI. BACKGROUND: CKD is an important risk factor for cardiovascular disease (CVD) events. A high ABI, a marker of lower extremity arterial stiffness, is associated with CVD events and mortality. The association between CKD and high ABI is unknown. METHODS: The CHS (Cardiovascular Health Study) enrolled community-living people >65 years of age and measured kidney function and ABI. Glomerular filtration rate (GFR) was estimated using equations that incorporated either cystatin C or creatinine, and CKD was defined by estimated GFR <60 ml/min/1.73 m(2). The ABI was categorized as low (<0.90), low-normal (0.90 to 1.09), normal (1.10 to 1.40), and high (>1.40 or incompressible). Multinomial logistic regression was used to evaluate the associations of CKD with ABI categories. RESULTS: Among 4,513 participants, 23% had CKD, 13% had a low ABI, and 3% had a high ABI. In models adjusted for age, sex, race, hypertension, diabetes, smoking, body mass index, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and C-reactive protein, cystatin C-based CKD was associated with both low ABI (relative risk [RR]: 2.0; 95% confidence interval [CI]: 1.6 to 2.5; p <0.001) and high ABI (RR: 1.6; 95% CI: 1.0 to 2.3; p = 0.03). Results were similar when CKD was defined by creatinine. CONCLUSIONS: CKD is associated with both the high and the low extremes of ABI in community-living older people. Future studies should evaluate whether arterial stiffness is an important mechanism leading to CVD in people with CKD.
Keywords: Aged; Aged, 80 and over; Ankle Brachial Index; C-Reactive Protein; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Female; Glomerular Filtration Rate; Humans; Kidney Diseases; Lipids; Male; Risk Factors

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Hypertension genes and retinal vascular calibre: the Cardiovascular Health Study. - Sun, C; Wang, J J; Islam, F M; Heckbert, S R; Klein, R; Siscovick, D S; Klein, B E K; Wong, T Y (J Hum Hypertens, 2009)
We examined the associations of single nucleotide polymorphisms (SNPs) in three candidate hypertension genes, alpha-adducin (ADD1/G460W), beta2-adrenergic receptor (ADRB2/Arg16Gly and Gln27Glu) and G-protein beta3 subunit (GNB3/C825T), with retinal arteriolar calibre (an intermediate marker of chronic hypertension) and venular calibre. Data in 1842 participants (1554 whites and 288 African Americans) aged 69-96 years from the Cardiovascular Health Study with genotype and retinal vascular calibre data were included. A computer-assisted method was used to measure retinal vascular calibre. We analysed four SNPs and multilocus interaction for three genes. All SNPs were in Hardy-Weinberg equilibrium in whites and African Americans. The study had sufficient power to detect 0.5% of the total variance of retinal vascular calibre contributed by each SNP in the total population, except for the GNB3 gene variant. No significant associations between these SNPs in the genes studied and mean retinal arteriolar and venular calibre were found in single-gene or multilocus analysis (for example, age-, gender-, race-adjusted mean retinal arteriolar calibre was similar between participants who were ADD1/460W homozygotes and ADD1/G allele carriers, 166.2 vs 167.7 microm). In conclusion, this study found no evidence of an association of SNPs in candidate hypertension genes studied here with retinal vascular calibre.
Keywords: African Americans; Aged; Aged, 80 and over; Arterioles; Calmodulin-Binding Proteins; European Continental Ancestry Group; Heterotrimeric GTP-Binding Proteins; Humans; Hypertension; Longitudinal Studies; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-2; Retinal Vessels

Joint modeling of self-rated health and changes in physical functioning. - Hubbard, Rebecca A; Inoue, Lurdes Y T; Diehr, Paula (J Am Stat Assoc, 2009)
Self-rated health is an important indicator of future morbidity and mortality. Past research has indicated that self-rated health is related to both levels of and changes in physical functioning. However, no previous study has jointly modeled longitudinal functional status and self-rated health trajectories. We propose a joint model for self-rated health and physical functioning that describes the relationship between perceptions of health and the rate of change of physical functioning or disability. Our joint model uses a non-homogeneous Markov process for discrete physical functioning states and connects this to a logistic regression model for "healthy" versus "unhealthy" self-rated health through parameters of the physical functioning model. We use simulation studies to establish finite sample properties of our estimators and show that this model is robust to misspecification of the functional form of the relationship between self-rated health and rate of change of physical functioning. We also show that our joint model performs better than an empirical model based on observed changes in functional status. We apply our joint model to data from the Cardiovascular Health Study (CHS), a large, multi-center, longitudinal study of older adults. Our analysis indicates that self-rated health is associated both with level of functioning as indicated by difficulty with activities of daily living (ADL) and instrumental activities of daily living (IADL), and the risk of increasing difficulty with ADLs and IADLs.

Long-term function in an older cohort--the cardiovascular health study all stars study. - Newman, Anne B; Arnold, Alice M; Sachs, Michael C; Ives, Diane G; Cushman, Mary; Strotmeyer, Elsa S; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Fried, Linda P; Robbins, John (J Am Geriatr Soc, 2009)
OBJECTIVES: To evaluate shared and unique risk factors for maintaining physical and cognitive function into the ninth decade and beyond. DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: One thousand six hundred seventy-seven participants in the Cardiovascular Health Study All Stars Study, assessed in 2005/06. Median age was 85 (range 77-102), 66.5% were women, and 16.6% were black. MEASUREMENTS: Intact function was defined as no difficulty with any activities of daily living and a score of 80 or higher on the Modified Mini-Mental State Examination. Baseline characteristics assessed in 1992/93 included demographics, behavioral health factors, chronic disease history, subclinical disease markers, cardiovascular risk factors, and inflammatory markers. Multinomial logistic regression was used to compare risk for physical disability, cognitive impairment,and combined impairments with no functional impairment. RESULTS: Of the 1,677 participants evaluated in both domains, 891 (53%) were functionally intact. Continuous measures of function, including the Digit Symbol Substitution Test and gait speed, showed that all groups, including the most functional, had declined over time. The functional group had less decline but also tended to have higher starting values. Functional individuals had a higher baseline health profile than those with either or cognitive impairment or both impairments combined. Women and individuals with greater weight had higher rates of physical impairment but not cognitive impairment. Risk factors common to both types of impairment included cardiovascular disease and hypertension. CONCLUSION: Intact function was found in only approximately half of these older adults in the ninth decade and beyond. High baseline function and low vascular disease risk characterized functional aging.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Attention; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Follow-Up Studies; Gait; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Male; Memory, Short-Term; Mental Status Schedule; Proportional Hazards Models; Psychometrics; Risk Factors; United States

Meta-analysis: retinal vessel caliber and risk for coronary heart disease. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; Dejong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Ann Intern Med, 2009)
BACKGROUND: Retinal vessel caliber may be a novel marker of coronary heart disease (CHD) risk. However, the sex-specific effect, magnitude of association, and effect independent of traditional CHD disease risk factors remain unclear. PURPOSE: To determine the association between retinal vessel caliber and risk for CHD. DATA SOURCES: Relevant studies in any language identified through MEDLINE (1950 to June 2009) and EMBASE (1950 to June 2009) databases. STUDY SELECTION: Studies were included if they examined a general population, measured retinal vessel caliber from retinal photographs, and documented CHD risk factors and incident CHD events. DATA EXTRACTION: 6 population-based prospective cohort studies provided data for individual participant meta-analysis. DATA SYNTHESIS: Proportional hazards models, adjusted for traditional CHD risk factors, were constructed for retinal vessel caliber and incident CHD in women and men. Among 22,159 participants who were free of CHD and followed for 5 to 14 years, 2219 (10.0%) incident CHD events occurred. Retinal vessel caliber changes (wider venules and narrower arterioles) were each associated with an increased risk for CHD in women (pooled multivariable-adjusted hazard ratios, 1.16 [95% CI, 1.06 to 1.26] per 20-microm increase in venular caliber and 1.17 [CI, 1.07 to 1.28] per 20-microm decrease in arteriolar caliber) but not in men (1.02 [CI, 0.94 to 1.10] per 20-microm increase in venular caliber and 1.02 [CI, 0.95 to 1.10] per 20-microm decrease in arteriolar caliber). Women without hypertension or diabetes had higher hazard ratios. LIMITATION: Error in the measurement of retinal vessel caliber and Framingham variables was not taken into account. CONCLUSION: Retinal vessel caliber changes were independently associated with an increased risk for CHD events in women.
Keywords: Adult; Aged; Arterioles; Biomarkers; Coronary Disease; Female; Humans; Male; Middle Aged; Proportional Hazards Models; Retinal Vessels; Risk Factors; Sex Factors; Venules

Obesity and change in estimated GFR among older adults. - de Boer, Ian H; Katz, Ronit; Fried, Linda F; Ix, Joachim H; Luchsinger, Jose; Sarnak, Mark J; Shlipak, Michael G; Siscovick, David S; Kestenbaum, Bryan (Am J Kidney Dis, 2009)
BACKGROUND: The prevalence of chronic kidney disease is growing most rapidly among older adults; however, determinants of impaired kidney function in this population are not well understood. Obesity assessed in midlife has been associated with chronic kidney disease. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 4,295 participants in the community-based Cardiovascular Health Study, aged >or= 65 years. PREDICTORS: Body mass index, waist circumference, and fat mass measured using bioelectrical impedance. OUTCOME: Change in glomerular filtration rate (GFR) during 7 years of follow-up. MEASUREMENTS: Longitudinal estimates of GFR calculated using the 4-variable Modification of Diet in Renal Disease (MDRD) Study equation. RESULTS: Estimated GFR decreased by an average of 0.4 +/- 3.6 mL/min/1.73 m(2)/y, and rapid GFR loss (>3 mL/min/1.73 m(2)/y) occurred in 693 participants (16%). Baseline body mass index, waist circumference, and fat mass were each associated with increased risk of rapid GFR loss: ORs, 1.19 (95% CI, 1.09-1.30) per 5 kg/m(2), 1.25 (95% CI, 1.16-1.36) per 12 cm, and 1.14 (95% CI, 1.05-1.24) per 10 kg after adjustment for age, sex, race, and smoking. The magnitude of increased risk was larger for participants with estimated GFR < 60 mL/min/1.73 m(2) at baseline (P for interaction < 0.05). Associations were substantially attenuated by further adjustment for diabetes, hypertension, and C-reactive protein level. Obesity measurements were not associated with change in GFR estimated using serum cystatin C level. LIMITATIONS: Few participants with advanced chronic kidney disease at baseline, no direct GFR measurements. CONCLUSION: Obesity may be a modifiable risk factor for the development and progression of kidney disease in older adults.
Keywords: Aged; Aging; Body Composition; Body Mass Index; Chronic Disease; Cohort Studies; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Longitudinal Studies; Male; Obesity; Risk Factors

Prediction of incident stroke events based on retinal vessel caliber: a systematic review and individual-participant meta-analysis. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; de Jong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Am J Epidemiol, 2009)
The caliber of the retinal vessels has been shown to be associated with stroke events. However, the consistency and magnitude of association, and the changes in predicted risk independent of traditional risk factors, are unclear. To determine the association between retinal vessel caliber and the risk of stroke events, the investigators combined individual data from 20,798 people, who were free of stroke at baseline, in 6 cohort studies identified from a search of the Medline (National Library of Medicine, Bethesda, Maryland) and EMBASE (Elsevier B.V., Amsterdam, the Netherlands) databases. During follow-up of 5-12 years, 945 (4.5%) incident stroke events were recorded. Wider retinal venular caliber predicted stroke (pooled hazard ratio = 1.15, 95% confidence interval: 1.05, 1.25 per 20-micron increase in caliber), but the caliber of retinal arterioles was not associated with stroke (pooled hazard ratio = 1.00, 95% confidence interval: 0.92, 1.08). There was weak evidence of heterogeneity in the hazard ratio for retinal venular caliber, which may be attributable to differences in follow-up strategies across studies. Inclusion of retinal venular caliber in prediction models containing traditional stroke risk factors reassigned 10.1% of people at intermediate risk into different, mostly lower, risk categories.
Keywords: Aged; Fluorescein Angiography; Humans; Middle Aged; Predictive Value of Tests; Proportional Hazards Models; Retinal Artery; Retinal Vein; Retinal Vessels; Risk Factors; Stroke

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Association between adiposity in midlife and older age and risk of diabetes in older adults. - Biggs, Mary L; Mukamal, Kenneth J; Luchsinger, José A; Ix, Joachim H; Carnethon, Mercedes R; Newman, Anne B; de Boer, Ian H; Strotmeyer, Elsa S; Mozaffarian, Dariush; Siscovick, David S (JAMA, 2010)
CONTEXT: Adiposity is a well-recognized risk factor for type 2 diabetes among young and middle-aged adults, but the relationship between body composition and type 2 diabetes is not well described among older adults. OBJECTIVE: To examine the relationship between adiposity, changes in adiposity, and risk of incident type 2 diabetes in adults 65 years of age and older. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study (1989-2007) of 4193 men and women 65 years of age and older in the Cardiovascular Health Study. Measures of adiposity were derived from anthropometry and bioelectrical impedance data at baseline and anthropometry repeated 3 years later. MAIN OUTCOME MEASURE: Incident diabetes was ascertained based on use of antidiabetic medication or a fasting glucose level of 126 mg/dL or greater. RESULTS: Over median follow-up of 12.4 years (range, 0.9-17.8 years), 339 cases of incident diabetes were ascertained (7.1/1000 person-years). The adjusted hazard ratio (HR) (95% confidence interval [CI]) of type 2 diabetes for participants in the highest quintile of baseline measures compared with those in the lowest was 4.3 (95% CI, 2.9-6.5) for body mass index (BMI [calculated as weight in kilograms divided by height in meters squared]), 3.0 (95% CI, 2.0-4.3) for BMI at 50 years of age, 4.2 (95% CI, 2.8-6.4) for weight, 4.0 (95% CI, 2.6-6.0) for fat mass, 4.2 (95% CI, 2.8-6.2) for waist circumference, 2.4 (95% CI, 1.6-3.5) for waist-hip ratio, and 3.8 (95% CI, 2.6-5.5) for waist-height ratio. However, when stratified by age, participants 75 years of age and older had HRs approximately half as large as those 65 to 74 years of age. Compared with weight-stable participants (+/-2 kg), those who gained the most weight from 50 years of age to baseline (> or = 9 kg), and from baseline to the third follow-up visit (> or = 6 kg), had HRs for type 2 diabetes of 2.8 (95% CI, 1.9-4.3) and 2.0 (95% CI, 1.1-3.7), respectively. Participants with a greater than 10-cm increase in waist size from baseline to the third follow-up visit had an HR of type 2 diabetes of 1.7 (95% CI, 1.1-2.8) compared with those who gained or lost 2 cm or less. CONCLUSION: Among older adults, overall and central adiposity, and weight gain during middle age and after the age of 65 years are associated with risk of diabetes.
Keywords: Adiposity; Age Factors; Aged; Body Mass Index; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Male; Prospective Studies; Risk Factors; United States; Weight Gain

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Change in circulating adiponectin in advanced old age: determinants and impact on physical function and mortality. The Cardiovascular Health Study All Stars Study. - Kizer, Jorge R; Arnold, Alice M; Strotmeyer, Elsa S; Ives, Diane G; Cushman, Mary; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Cross-sectional studies show that adiponectin is higher in older than in younger adults but long-term change in adiponectin, its determinants, and its relationship to functional decline or survival in the elderly population have not been evaluated. METHODS: We investigated predictors of longitudinal change in adiponectin, and the association of this adipokine or its antecedent change with physical deterioration and all-cause mortality in 988 participants in a population-based study who completed examinations in 1996-1997 and 2005-2006, had serial adiponectin measurements and underwent follow-up through June 2009. RESULTS: Adiponectin level rose significantly during follow-up, but the increase was smaller in blacks, was associated with declining weight or fasting glucose and, in men, lower albumin, and was affected by medications. Adiponectin was independently associated with greater physical decline, but the relationship for adiponectin change was driven by concomitant weight decrease. Both adiponectin and its change independently predicted mortality, even after adjustment for weight change. The association for adiponectin and mortality was observed in whites but not in blacks and only for levels in the upper range (hazard ratio = 1.85, 95% confidence interval = 1.36-2.52 per SD ≥ 20 mg/L), whereas that for adiponectin change was linear throughout in both racial groups (hazard ratio = 1.30, 95% confidence interval = 1.10-1.52 per SD). CONCLUSIONS: Adiponectin levels increase over time in long-lived adults and are associated with greater physical disability and mortality. Such increases may occur in response to age-related homeostatic dysregulation. Additional investigation is required to define the underlying mechanisms and whether this represents a marker or causal factor for mortality in this age group.
Keywords: Adiponectin; Age Factors; Aged; Aging; Analysis of Variance; Cardiovascular Diseases; Cause of Death; Chi-Square Distribution; Cohort Studies; Cross-Sectional Studies; Female; Health Status; Humans; Linear Models; Male; Physical Fitness; Proportional Hazards Models; Risk Factors; Sex Factors; Time Factors; United States

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies. - Sarwar, N; Gao, P; Seshasai, S R Kondapally; Gobin, R; Kaptoge, S; Di Angelantonio, E; Ingelsson, E; Lawlor, D A; Selvin, E; Stampfer, M; Stehouwer, C D A; Lewington, S; et al. (Lancet, 2010)
BACKGROUND: Uncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances. METHODS: We undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined within-study regressions that were adjusted for age, sex, smoking, systolic blood pressure, and body-mass index to calculate hazard ratios (HRs) for vascular disease. FINDINGS: Analyses included data for 698 782 people (52 765 non-fatal or fatal vascular outcomes; 8.49 million person-years at risk) from 102 prospective studies. Adjusted HRs with diabetes were: 2.00 (95% CI 1.83-2.19) for coronary heart disease; 2.27 (1.95-2.65) for ischaemic stroke; 1.56 (1.19-2.05) for haemorrhagic stroke; 1.84 (1.59-2.13) for unclassified stroke; and 1.73 (1.51-1.98) for the aggregate of other vascular deaths. HRs did not change appreciably after further adjustment for lipid, inflammatory, or renal markers. HRs for coronary heart disease were higher in women than in men, at 40-59 years than at 70 years and older, and with fatal than with non-fatal disease. At an adult population-wide prevalence of 10%, diabetes was estimated to account for 11% (10-12%) of vascular deaths. Fasting blood glucose concentration was non-linearly related to vascular risk, with no significant associations between 3.90 mmol/L and 5.59 mmol/L. Compared with fasting blood glucose concentrations of 3.90-5.59 mmol/L, HRs for coronary heart disease were: 1.07 (0.97-1.18) for lower than 3.90 mmol/L; 1.11 (1.04-1.18) for 5.60-6.09 mmol/L; and 1.17 (1.08-1.26) for 6.10-6.99 mmol/L. In people without a history of diabetes, information about fasting blood glucose concentration or impaired fasting glucose status did not significantly improve metrics of vascular disease prediction when added to information about several conventional risk factors. INTERPRETATION: Diabetes confers about a two-fold excess risk for a wide range of vascular diseases, independently from other conventional risk factors. In people without diabetes, fasting blood glucose concentration is modestly and non-linearly associated with risk of vascular disease. FUNDING: British Heart Foundation, UK Medical Research Council, and Pfizer.
Keywords: Adult; Aged; Blood Glucose; Coronary Disease; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Humans; Male; Middle Aged; Risk Factors; Stroke

Differential white blood cell count and type 2 diabetes: systematic review and meta-analysis of cross-sectional and prospective studies. - Gkrania-Klotsas, Effrossyni; Ye, Zheng; Cooper, Andrew J; Sharp, Stephen J; Luben, Robert; Biggs, Mary L; Chen, Liang-Kung; Gokulakrishnan, Kuppan; Hanefeld, Markolf; Ingelsson, Erik; Lai, Wen-An; Lin, Shih-Yi; et al. (PLoS One, 2010)
OBJECTIVE: Biological evidence suggests that inflammation might induce type 2 diabetes (T2D), and epidemiological studies have shown an association between higher white blood cell count (WBC) and T2D. However, the association has not been systematically investigated. RESEARCH DESIGN AND METHODS: Studies were identified through computer-based and manual searches. Previously unreported studies were sought through correspondence. 20 studies were identified (8,647 T2D cases and 85,040 non-cases). Estimates of the association of WBC with T2D were combined using random effects meta-analysis; sources of heterogeneity as well as presence of publication bias were explored. RESULTS: The combined relative risk (RR) comparing the top to bottom tertile of the WBC count was 1.61 (95% CI: 1.45; 1.79, p = 1.5*10(-18)). Substantial heterogeneity was present (I(2) = 83%). For granulocytes the RR was 1.38 (95% CI: 1.17; 1.64, p = 1.5*10(-4)), for lymphocytes 1.26 (95% CI: 1.02; 1.56, p = 0.029), and for monocytes 0.93 (95% CI: 0.68; 1.28, p = 0.67) comparing top to bottom tertile. In cross-sectional studies, RR was 1.74 (95% CI: 1.49; 2.02, p = 7.7*10(-13)), while in cohort studies it was 1.48 (95% CI: 1.22; 1.79, p = 7.7*10(-5)). We assessed the impact of confounding in EPIC-Norfolk study and found that the age and sex adjusted HR of 2.19 (95% CI: 1.74; 2.75) was attenuated to 1.82 (95% CI: 1.45; 2.29) after further accounting for smoking, T2D family history, physical activity, education, BMI and waist circumference. CONCLUSIONS: A raised WBC is associated with higher risk of T2D. The presence of publication bias and failure to control for all potential confounders in all studies means the observed association is likely an overestimate.
Keywords: Adult; Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Leukocyte Count; Male; Middle Aged; Prospective Studies

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Fucosyltransferase 2 (FUT2) non-secretor status is associated with Crohn's disease. - McGovern, Dermot P B; Jones, Michelle R; Taylor, Kent D; Marciante, Kristin; Yan, Xiaofei; Dubinsky, Marla; Ippoliti, Andy; Vasiliauskas, Eric; Berel, Dror; Derkowski, Carrie; Dutridge, Deb; Fleshner, Phil; et al. (Hum Mol Genet, 2010)
Genetic variation in both innate and adaptive immune systems is associated with Crohn's disease (CD) susceptibility, but much of the heritability to CD remains unknown. We performed a genome-wide association study (GWAS) in 896 CD cases and 3204 healthy controls all of Caucasian origin as defined by multidimensional scaling. We found supportive evidence for 21 out of 40 CD loci identified in a recent CD GWAS meta-analysis, including two loci which had only nominally achieved replication (rs4807569, 19p13; rs991804, CCL2/CCL7). In addition, we identified associations with genes involved in tight junctions/epithelial integrity (ASHL, ARPC1A), innate immunity (EXOC2), dendritic cell biology [CADM1 (IGSF4)], macrophage development (MMD2), TGF-beta signaling (MAP3K7IP1) and FUT2 (a physiological trait that regulates gastrointestinal mucosal expression of blood group A and B antigens) (rs602662, P=3.4x10(-5)). Twenty percent of Caucasians are 'non-secretors' who do not express ABO antigens in saliva as a result of the FUT2 W134X allele. We demonstrated replication in an independent cohort of 1174 CD cases and 357 controls between the four primary FUT2 single nucleotide polymorphisms (SNPs) and CD (rs602662, combined P-value 4.90x10(-8)) and also association with FUT2 W143X (P=2.6x10(-5)). Further evidence of the relevance of this locus to CD pathogenesis was demonstrated by the association of the original four SNPs and CD in the recently published CD GWAS meta-analysis (rs602662, P=0.001). These findings strongly implicate this locus in CD susceptibility and highlight the role of the mucus layer in the development of CD.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Cohort Studies; Crohn Disease; Female; Fucosyltransferases; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Genetic predictors of medically refractory ulcerative colitis. - Haritunians, Talin; Taylor, Kent D; Targan, Stephan R; Dubinsky, Marla; Ippoliti, Andrew; Kwon, Soonil; Guo, Xiuqing; Melmed, Gil Y; Berel, Dror; Mengesha, Emebet; Psaty, Bruce M; Glazer, Nicole L; et al. (Inflamm Bowel Dis, 2010)
BACKGROUND: Acute severe ulcerative colitis (UC) remains a significant clinical challenge and the ability to predict, at an early stage, those individuals at risk of colectomy for medically refractory UC (MR-UC) would be a major clinical advance. The aim of this study was to use a genome-wide association study (GWAS) in a well-characterized cohort of UC patients to identify genetic variation that contributes to MR-UC. METHODS: A GWAS comparing 324 MR-UC patients with 537 non-MR-UC patients was analyzed using logistic regression and Cox proportional hazards methods. In addition, the MR-UC patients were compared with 2601 healthy controls. RESULTS: MR-UC was associated with more extensive disease (P = 2.7 × 10(-6)) and a positive family history of UC (P = 0.004). A risk score based on the combination of 46 single nucleotide polymorphisms (SNPs) associated with MR-UC explained 48% of the variance for colectomy risk in our cohort. Risk scores divided into quarters showed the risk of colectomy to be 0%, 17%, 74%, and 100% in the four groups. Comparison of the MR-UC subjects with healthy controls confirmed the contribution of the major histocompatibility complex to severe UC (peak association: rs17207986, P = 1.4 × 10(-16)) and provided genome-wide suggestive association at the TNFSF15 (TL1A) locus (peak association: rs11554257, P = 1.4 × 10(-6)). CONCLUSIONS: A SNP-based risk scoring system, identified here by GWAS analyses, may provide a useful adjunct to clinical parameters for predicting the natural history of UC. Furthermore, discovery of genetic processes underlying disease severity may help to identify pathways for novel therapeutic intervention in severe UC.
Keywords: Acute Disease; Adolescent; Adult; Cohort Studies; Colectomy; Colitis, Ulcerative; Female; Genetic Loci; Genome-Wide Association Study; Humans; Major Histocompatibility Complex; Male; Polymorphism, Single Nucleotide; Risk Factors; Severity of Illness Index; Tumor Necrosis Factor Ligand Superfamily Member 15; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies multiple ulcerative colitis susceptibility loci. - McGovern, Dermot P B; Gardet, Agnès; Törkvist, Leif; Goyette, Philippe; Essers, Jonah; Taylor, Kent D; Neale, Benjamin M; Ong, Rick T H; Lagacé, Caroline; Li, Chun; Green, Todd; Stevens, Christine R; et al. (Nat Genet, 2010)
Ulcerative colitis is a chronic, relapsing inflammatory condition of the gastrointestinal tract with a complex genetic and environmental etiology. In an effort to identify genetic variation underlying ulcerative colitis risk, we present two distinct genome-wide association studies of ulcerative colitis and their joint analysis with a previously published scan, comprising, in aggregate, 2,693 individuals with ulcerative colitis and 6,791 control subjects. Fifty-nine SNPs from 14 independent loci attained an association significance of P < 10(-5). Seven of these loci exceeded genome-wide significance (P < 5 x 10(-8)). After testing an independent cohort of 2,009 cases of ulcerative colitis and 1,580 controls, we identified 13 loci that were significantly associated with ulcerative colitis (P < 5 x 10(-8)), including the immunoglobulin receptor gene FCGR2A, 5p15, 2p16 and ORMDL3 (orosomucoid1-like 3). We confirmed association with 14 previously identified ulcerative colitis susceptibility loci, and an analysis of acknowledged Crohn's disease loci showed that roughly half of the known Crohn's disease associations are shared with ulcerative colitis. These data implicate approximately 30 loci in ulcerative colitis, thereby providing insight into disease pathogenesis.
Keywords: Colitis, Ulcerative; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Membrane Proteins; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Receptors, IgG

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Long-term retention of older adults in the Cardiovascular Health Study: implications for studies of the oldest old. - Strotmeyer, Elsa S; Arnold, Alice M; Boudreau, Robert M; Ives, Diane G; Cushman, Mary; Robbins, John A; Harris, Tamara B; Newman, Anne B (J Am Geriatr Soc, 2010)
OBJECTIVES: To describe retention according to age and visit type (clinic, home, telephone) and to determine characteristics associated with visit types for a longitudinal epidemiological study in older adults. DESIGN: Longitudinal cohort study. SETTING: Four U.S. clinical sites. PARTICIPANTS: Five thousand eight hundred eighty-eight Cardiovascular Health Study (CHS) participants aged 65 to 100 at 1989/90 or 1992/93 enrollment (58.6% female; 15.7% black). CHS participants were contacted every 6 months, with annual assessments through 1999 and in 2005/06 for the All Stars Study visit of the CHS cohort (aged 77-102; 66.5% female; 16.6% black). MEASUREMENTS: All annual contacts through 1999 (n=43,772) and for the 2005/06 visit (n=1,942). RESULTS: CHS had 43,772 total participant contacts from 1989 to 1999: 34,582 clinic visits (79.0%), 2,238 refusals (5.1%), 4,401 telephone visits (10.1%), 1,811 home visits (4.1%), and 740 other types (1.7%). In 2005/06, the All Stars participants of the CHS cohort had 36.6% clinic, 22.3% home, and 41.1% telephone visits. Compared with participants aged 65 to 69, odds ratios of not attending a CHS clinic visit were 1.82 (95% confidence interval (CI)=1.54-2.13), 2.94 (95% CI=2.45-3.57), 4.55 (95% CI=3.70-5.56), and 9.09 (95% CI=7.69-11.11) for those aged 70 to 74, 75 to 79, 80 to 84, and 85 and older, respectively, in sex-adjusted regression. In multivariable regression, participants with a 2005/06 clinic visit were younger, more likely to be male and in good health, and had had better cognitive and physical function 7 years earlier than participants with other visit types. Participants with home, telephone, and missing visits were similar on characteristics measured 7 years earlier. CONCLUSION: Offering home, telephone, and proxy visits are essential to optimizing follow-up of aging cohorts. Home visits increased in-person retention from 36.5% to 58.8% and diversified the cohort with respect to age, health, and physical functioning.
Keywords: Age Factors; Aged; Aged, 80 and over; Ambulatory Care Facilities; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Epidemiologic Studies; Female; Geriatric Assessment; House Calls; Humans; Logistic Models; Longitudinal Studies; Male; Multivariate Analysis; Patient Dropouts; Patient Selection; Research Subjects; Telephone; United States

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Subclinical hypothyroidism and the risk of coronary heart disease and mortality. - Rodondi, Nicolas; den Elzen, Wendy P J; Bauer, Douglas C; Cappola, Anne R; Razvi, Salman; Walsh, John P; Asvold, Bjørn O; Iervasi, Giorgio; Imaizumi, Misa; Collet, Tinh-Hai; Bremner, Alexandra; Maisonneuve, Patrick; et al. (JAMA, 2010)
CONTEXT: Data regarding the association between subclinical hypothyroidism and cardiovascular disease outcomes are conflicting among large prospective cohort studies. This might reflect differences in participants' age, sex, thyroid-stimulating hormone (TSH) levels, or preexisting cardiovascular disease. OBJECTIVE: To assess the risks of coronary heart disease (CHD) and total mortality for adults with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (1950 to May 31, 2010) were searched without language restrictions for prospective cohort studies with baseline thyroid function and subsequent CHD events, CHD mortality, and total mortality. The reference lists of retrieved articles also were searched. DATA EXTRACTION: Individual data on 55,287 participants with 542,494 person-years of follow-up between 1972 and 2007 were supplied from 11 prospective cohorts in the United States, Europe, Australia, Brazil, and Japan. The risk of CHD events was examined in 25,977 participants from 7 cohorts with available data. Euthyroidism was defined as a TSH level of 0.50 to 4.49 mIU/L. Subclinical hypothyroidism was defined as a TSH level of 4.5 to 19.9 mIU/L with normal thyroxine concentrations. RESULTS: Among 55,287 adults, 3450 had subclinical hypothyroidism (6.2%) and 51,837 had euthyroidism. During follow-up, 9664 participants died (2168 of CHD), and 4470 participants had CHD events (among 7 studies). The risk of CHD events and CHD mortality increased with higher TSH concentrations. In age- and sex-adjusted analyses, the hazard ratio (HR) for CHD events was 1.00 (95% confidence interval [CI], 0.86-1.18) for a TSH level of 4.5 to 6.9 mIU/L (20.3 vs 20.3/1000 person-years for participants with euthyroidism), 1.17 (95% CI, 0.96-1.43) for a TSH level of 7.0 to 9.9 mIU/L (23.8/1000 person-years), and 1.89 (95% CI, 1.28-2.80) for a TSH level of 10 to 19.9 mIU/L (n = 70 events/235; 38.4/1000 person-years; P <.001 for trend). The corresponding HRs for CHD mortality were 1.09 (95% CI, 0.91-1.30; 5.3 vs 4.9/1000 person-years for participants with euthyroidism), 1.42 (95% CI, 1.03-1.95; 6.9/1000 person-years), and 1.58 (95% CI, 1.10-2.27, n = 28 deaths/333; 7.7/1000 person-years; P = .005 for trend). Total mortality was not increased among participants with subclinical hypothyroidism. Results were similar after further adjustment for traditional cardiovascular risk factors. Risks did not significantly differ by age, sex, or preexisting cardiovascular disease. CONCLUSIONS: Subclinical hypothyroidism is associated with an increased risk of CHD events and CHD mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Coronary Disease; Female; Humans; Hypothyroidism; Male; Middle Aged; Mortality; Prospective Studies; Risk; Thyrotropin; Young Adult

Association of body mass index with peripheral arterial disease in older adults: the Cardiovascular Health Study. - Ix, Joachim H; Biggs, Mary L; Kizer, Jorge R; Mukamal, Kenneth J; Djoussé, Luc; Zieman, Susan J; de Boer, Ian H; Nelson, Tracy L; Newman, Anne B; Criqui, Michael H; Siscovick, David S (Am J Epidemiol, 2011)
The authors hypothesized that the absence of cross-sectional associations of body mass index (BMI; weight (kg)/height (m)(2)) with peripheral arterial disease (PAD) in prior studies may reflect lower weight among persons who smoke or have poor health status. They conducted an observational study among 5,419 noninstitutionalized residents of 4 US communities aged ≥ 65 years at baseline (1989-1990 or 1992-1993). Ankle brachial index was measured, and participants reported their history of PAD procedures. Participants were followed longitudinally for adjudicated incident PAD events. At baseline, mean BMI was 26.6 (standard deviation, 4.6), and 776 participants (14%) had prevalent PAD. During 13.2 (median) years of follow-up through June 30, 2007, 276 incident PAD events occurred. In cross-sectional analysis, each 5-unit increase in BMI was inversely associated with PAD (prevalence ratio (PR) = 0.92, 95% confidence interval (CI): 0.85, 1.00). However, among persons in good health who had never smoked, the direction of association was opposite (PR = 1.20, 95% CI: 0.94, 1.52). Similar results were observed between BMI calculated using weight at age 50 years and PAD prevalence (PR = 1.30, 95% CI: 1.11, 1.51) and between BMI at baseline and incident PAD events occurring during follow-up (hazard ratio = 1.32, 95% CI: 1.00, 1.76) among never smokers in good health. Greater BMI is associated with PAD in older persons who remain healthy and have never smoked. Normal weight maintenance may decrease PAD incidence and associated comorbidity in older age.
Keywords: Aged; Ankle Brachial Index; Body Mass Index; Cross-Sectional Studies; Health Status; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Obesity; Peripheral Arterial Disease; Prevalence; Sex Factors; Smoking; United States

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of HSP70 and its co-chaperones with Alzheimer's disease. - Broer, Linda; Ikram, Mohammad Arfan; Schuur, Maaike; DeStefano, Anita L; Bis, Joshua C; Liu, Fan; Rivadeneira, Fernando; Uitterlinden, André G; Beiser, Alexa S; Longstreth, William T; Hofman, Albert; Aulchenko, Yurii; et al. (J Alzheimers Dis, 2011)
The heat shock protein (HSP) 70 family has been implicated in the pathology of Alzheimer's disease (AD). In this study, we examined common genetic variations in the 80 genes encoding HSP70 and its co-chaperones. We conducted a study in a series of 462 patients and 5238 unaffected participants derived from the Rotterdam Study, a population-based study including 7983 persons aged 55 years and older. We genotyped a total of 12,053 Single Nucleotide Polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. Replication was performed in two independent cohort studies, the Framingham Heart study (FHS; n = 806) and Cardiovascular Health Study (CHS; n = 2150). When adjusting for multiple testing, we found a small but consistent, though not significant effect of rs12118313 located 32 kb from PFDN2, with an OR of 1.19 (p-value from meta-analysis = 0.003). However this SNP was in the intron of another gene, suggesting it is unlikely this SNP reflects the effect of PFDN2. In a formal pathway analysis we found nominally significant evidence for an association of BAG, DNAJA and prefoldin with AD. These findings corroborate with those of a study of 2032 AD patients and 5328 controls, in which several members of the prefoldin family showed evidence for association to AD. Our study did not reveal evidence for a genetic variant if the HSP70 family with a major effect on AD. However, our findings of the single SNP analysis and pathway analysis suggest that multiple genetic variants in prefoldin are associated with AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Genetic Association Studies; Genetic Variation; HSP70 Heat-Shock Proteins; Humans; Middle Aged; Molecular Chaperones; Polymorphism, Single Nucleotide

Association of polymorphisms in the hepatocyte growth factor gene promoter with keratoconus. - Burdon, Kathryn P; Macgregor, Stuart; Bykhovskaya, Yelena; Javadiyan, Sharhbanou; Li, Xiaohui; Laurie, Kate J; Muszynska, Dorota; Lindsay, Richard; Lechner, Judith; Haritunians, Talin; Henders, Anjali K; Dash, Durga; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: Keratoconus is a progressive disorder of the cornea that can lead to severe visual impairment or blindness. Although several genomic regions have been linked to rare familial forms of keratoconus, no genes have yet been definitively identified for common forms of the disease. METHODS: Two genome-wide association scans were undertaken in parallel. The first used pooled DNA from an Australian cohort, followed by typing of top-ranked single-nucleotide polymorphisms (SNPs) in individual DNA samples. The second was conducted in individually genotyped patients, and controls from the USA. Tag SNPs around the hepatocyte growth factor (HGF) gene were typed in three additional replication cohorts. Serum levels of HGF protein in normal individuals were assessed with ELISA and correlated with genotype. RESULTS: The only SNP observed to be associated in both the pooled discovery and primary replication cohort was rs1014091, located upstream of the HGF gene. The nearby SNP rs3735520 was found to be associated in the individually typed discovery cohort (P = 6.1 × 10(-7)). Genotyping of tag SNPs around HGF revealed association at rs3735520 and rs17501108/rs1014091 in four of the five cohorts. Meta-analysis of all five datasets together yielded suggestive P values for rs3735520 (P = 9.9 × 10(-7)) and rs17501108 (P = 9.9 × 10(-5)). In addition, SNP rs3735520 was found to be associated with serum HGF level in normal individuals (P = 0.036). CONCLUSIONS: Taken together, these results implicate genetic variation at the HGF locus with keratoconus susceptibility.
Keywords: Adult; Aged; Chromosomes, Human, Pair 7; Corneal Topography; Enzyme-Linked Immunosorbent Assay; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hepatocyte Growth Factor; Humans; Keratoconus; Middle Aged; Nucleic Acid Hybridization; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Tagged Sites

A bivariate genome-wide approach to metabolic syndrome: STAMPEED consortium. - Kraja, Aldi T; Vaidya, Dhananjay; Pankow, James S; Goodarzi, Mark O; Assimes, Themistocles L; Kullo, Iftikhar J; Sovio, Ulla; Mathias, Rasika A; Sun, Yan V; Franceschini, Nora; Absher, Devin; Li, Guo; et al. (Diabetes, 2011)
OBJECTIVE The metabolic syndrome (MetS) is defined as concomitant disorders of lipid and glucose metabolism, central obesity, and high blood pressure, with an increased risk of type 2 diabetes and cardiovascular disease. This study tests whether common genetic variants with pleiotropic effects account for some of the correlated architecture among five metabolic phenotypes that define MetS. RESEARCH DESIGN AND METHODS Seven studies of the STAMPEED consortium, comprising 22,161 participants of European ancestry, underwent genome-wide association analyses of metabolic traits using a panel of ∼2.5 million imputed single nucleotide polymorphisms (SNPs). Phenotypes were defined by the National Cholesterol Education Program (NCEP) criteria for MetS in pairwise combinations. Individuals exceeding the NCEP thresholds for both traits of a pair were considered affected. RESULTS Twenty-nine common variants were associated with MetS or a pair of traits. Variants in the genes LPL, CETP, APOA5 (and its cluster), GCKR (and its cluster), LIPC, TRIB1, LOC100128354/MTNR1B, ABCB11, and LOC100129150 were further tested for their association with individual qualitative and quantitative traits. None of the 16 top SNPs (one per gene) associated simultaneously with more than two individual traits. Of them 11 variants showed nominal associations with MetS per se. The effects of 16 top SNPs on the quantitative traits were relatively small, together explaining from ∼9% of the variance in triglycerides, 5.8% of high-density lipoprotein cholesterol, 3.6% of fasting glucose, and 1.4% of systolic blood pressure. CONCLUSIONS Qualitative and quantitative pleiotropic tests on pairs of traits indicate that a small portion of the covariation in these traits can be explained by the reported common genetic variants.
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Meta-Analysis as Topic; Metabolic Syndrome; Middle Aged; Phenotype; Polymorphism, Single Nucleotide

Candidate gene association study for diabetic retinopathy in persons with type 2 diabetes: the Candidate gene Association Resource (CARe). - Sobrin, Lucia; Green, Todd; Sim, Xueling; Jensen, Richard A; Tai, E Shyong; Tay, Wan Ting; Wang, Jie Jin; Mitchell, Paul; Sandholm, Niina; Liu, Yiyuan; Hietala, Kustaa; Iyengar, Sudha K; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: To investigate whether variants in cardiovascular candidate genes, some of which have been previously associated with type 2 diabetes (T2D), diabetic retinopathy (DR), and diabetic nephropathy (DN), are associated with DR in the Candidate gene Association Resource (CARe). METHODS: Persons with T2D who were enrolled in the study (n = 2691) had fundus photography and genotyping of single nucleotide polymorphisms (SNPs) in 2000 candidate genes. Two case definitions were investigated: Early Treatment Diabetic Retinopathy Study (ETDRS) grades ≥ 14 and ≥ 30. The χ² analyses for each CARe cohort were combined by Cochran-Mantel-Haenszel (CMH) pooling of odds ratios (ORs) and corrected for multiple hypothesis testing. Logistic regression was performed with adjustment for other DR risk factors. Results from replication in independent cohorts were analyzed with CMH meta-analysis methods. RESULTS: Among 39 genes previously associated with DR, DN, or T2D, three SNPs in P-selectin (SELP) were associated with DR. The strongest association was to rs6128 (OR = 0.43, P = 0.0001, after Bonferroni correction). These associations remained significant after adjustment for DR risk factors. Among other genes examined, several variants were associated with DR with significant P values, including rs6856425 tagging α-l-iduronidase (IDUA) (P = 2.1 × 10(-5), after Bonferroni correction). However, replication in independent cohorts did not reveal study-wide significant effects. The P values after replication were 0.55 and 0.10 for rs6128 and rs6856425, respectively. CONCLUSIONS: Genes associated with DN, T2D, and vascular diseases do not appear to be consistently associated with DR. A few genetic variants associated with DR, particularly those in SELP and near IDUA, should be investigated in additional DR cohorts.
Keywords: Cardiovascular Diseases; Diabetes Mellitus, Type 2; Diabetic Nephropathies; Diabetic Retinopathy; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Iduronidase; Odds Ratio; P-Selectin; Polymorphism, Single Nucleotide; Risk Factors

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Cystatin C identifies chronic kidney disease patients at higher risk for complications. - Peralta, Carmen A; Katz, Ronit; Sarnak, Mark J; Ix, Joachim; Fried, Linda F; de Boer, Ian; Palmas, Walter; Siscovick, David; Levey, Andrew S; Shlipak, Michael G (J Am Soc Nephrol, 2011)
Although cystatin C is a stronger predictor of clinical outcomes associated with CKD than creatinine, the clinical role for cystatin C is unclear. We included 11,909 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS) and assessed risks for death, cardiovascular events, heart failure, and ESRD among persons categorized into mutually exclusive groups on the basis of the biomarkers that supported a diagnosis of CKD (eGFR <60 ml/min per 1.73 m(2)): creatinine only, cystatin C only, both, or neither. We used CKD-EPI equations to estimate GFR from these biomarkers. In MESA, 9% had CKD by the creatinine-based equation only, 2% had CKD by the cystatin C-based equation only, and 4% had CKD by both equations; in CHS, these percentages were 12, 4, and 13%, respectively. Compared with those without CKD, the adjusted hazard ratios (HR) for mortality in MESA were: 0.80 (95% CI 0.50 to 1.26) for CKD by creatinine only; 3.23 (95% CI 1.84 to 5.67) for CKD by cystatin C only; and 1.93 (95% CI 1.27 to 2.92) for CKD by both; in CHS, the adjusted HR were 1.09 (95% CI 0.98 to 1.21), 1.78 (95% CI 1.53 to 2.08), and 1.74 (95% CI 1.58 to 1.93), respectively. The pattern was similar for cardiovascular disease (CVD), heart failure, and kidney failure outcomes. In conclusion, among adults diagnosed with CKD using the creatinine-based CKD-EPI equation, the adverse prognosis is limited to the subset who also have CKD according to the cystatin C-based equation. Cystatin C may have a role in identifying persons with CKD who have the highest risk for complications.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Chronic Disease; Creatinine; Cystatin C; Disease Progression; Female; Glomerular Filtration Rate; Heart Failure; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Predictive Value of Tests; Retrospective Studies; Risk Factors

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

Fatty acids in the de novo lipogenesis pathway and risk of coronary heart disease: the Cardiovascular Health Study. - Wu, Jason H Y; Lemaitre, Rozenn N; Imamura, Fumiaki; King, Irena B; Song, Xiaoling; Spiegelman, Donna; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2011)
BACKGROUND: De novo lipogenesis (DNL) is an endogenous pathway whereby carbohydrates and proteins are converted to fatty acids. DNL could affect coronary heart disease (CHD) or sudden cardiac arrest (SCA) via generation of specific fatty acids. Whether these fatty acids are prospectively associated with SCA or other CHD events is unknown. OBJECTIVE: The objective was to investigate the relations of 4 fatty acids in the DNL pathway-palmitic acid (16:0), palmitoleic acid (16:1n-7), 7-hexadecenoic acid (16:1n-9), and cis-vaccenic acid (18:1n-7)-with incident CHD, including fatal CHD, nonfatal myocardial infarction (NFMI), and SCA. DESIGN: A community-based prospective study was conducted in 2890 men and women aged ≥65 y, who were free of known CHD at baseline and who were followed from 1992 to 2006. Cardiovascular disease risk factors and plasma phospholipid fatty acids were measured at baseline by using standardized methods. Incident CHD was ascertained prospectively and was centrally adjudicated by using medical records. Risk was assessed by using multivariable-adjusted Cox proportional hazards. RESULTS: During 29,835 person-years of follow-up, 631 CHD and 71 SCA events occurred. Both 18:1n-7 and 16:1n-9 were associated with a higher risk of SCA [multivariable-adjusted hazard ratio (95% CI) for the interquintile range: 7.63 (2.58, 22.6) for 18:1n-7 and 2.30 (1.16, 4.55) for 16:1n-9] but not of total CHD, fatal CHD, or NFMI. In secondary analyses censored to mid-follow-up (7 y) to minimize the effects of changes in concentrations over time, 16:1n-9 was also associated with a significantly higher risk of total CHD (2.11; 1.76, 2.54), including a higher risk of CHD death, NFMI, and SCA; 16:0 and 16:1n-7 were not associated with clinical CHD outcomes. CONCLUSION: Higher plasma phospholipid 18:1n-7 and 16:1n-9 concentrations were prospectively associated with an elevated risk of SCA but not of other CHD events, except in secondary analyses.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Coronary Disease; Death, Sudden, Cardiac; Diet; Fatty Acids; Female; Humans; Lipogenesis; Male; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Factors

Gait speed and survival in older adults. - Studenski, Stephanie; Perera, Subashan; Patel, Kushang; Rosano, Caterina; Faulkner, Kimberly; Inzitari, Marco; Brach, Jennifer; Chandler, Julie; Cawthon, Peggy; Connor, Elizabeth Barrett; Nevitt, Michael; Visser, Marjolein; et al. (JAMA, 2011)
CONTEXT: Survival estimates help individualize goals of care for geriatric patients, but life tables fail to account for the great variability in survival. Physical performance measures, such as gait speed, might help account for variability, allowing clinicians to make more individualized estimates. OBJECTIVE: To evaluate the relationship between gait speed and survival. DESIGN, SETTING, AND PARTICIPANTS: Pooled analysis of 9 cohort studies (collected between 1986 and 2000), using individual data from 34,485 community-dwelling older adults aged 65 years or older with baseline gait speed data, followed up for 6 to 21 years. Participants were a mean (SD) age of 73.5 (5.9) years; 59.6%, women; and 79.8%, white; and had a mean (SD) gait speed of 0.92 (0.27) m/s. MAIN OUTCOME MEASURES: Survival rates and life expectancy. RESULTS: There were 17,528 deaths; the overall 5-year survival rate was 84.8% (confidence interval [CI], 79.6%-88.8%) and 10-year survival rate was 59.7% (95% CI, 46.5%-70.6%). Gait speed was associated with survival in all studies (pooled hazard ratio per 0.1 m/s, 0.88; 95% CI, 0.87-0.90; P < .001). Survival increased across the full range of gait speeds, with significant increments per 0.1 m/s. At age 75, predicted 10-year survival across the range of gait speeds ranged from 19% to 87% in men and from 35% to 91% in women. Predicted survival based on age, sex, and gait speed was as accurate as predicted based on age, sex, use of mobility aids, and self-reported function or as age, sex, chronic conditions, smoking history, blood pressure, body mass index, and hospitalization. CONCLUSION: In this pooled analysis of individual data from 9 selected cohorts, gait speed was associated with survival in older adults.
Keywords: Aged; Cohort Studies; Female; Gait; Geriatric Assessment; Humans; Life Expectancy; Male; Survival Analysis; United States

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variants of the NOTCH3 gene in the elderly and magnetic resonance imaging correlates of age-related cerebral small vessel disease. - Schmidt, Helena; Zeginigg, Marion; Wiltgen, Marco; Freudenberger, Paul; Petrovic, Katja; Cavalieri, Margherita; Gider, Pierre; Enzinger, Christian; Fornage, Myriam; Debette, Stephanie; Rotter, Jerome I; Ikram, Mohammad A; et al. (Brain, 2011)
Cerebral small vessel disease-related brain lesions such as white matter lesions and lacunes are common findings of magnetic resonance imaging in the elderly. These lesions are thought to be major contributors to disability in old age, and risk factors that include age and hypertension have been established. The radiological, histopathologic and clinical phenotypes of age-related cerebral small vessel disease remarkably resemble autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy, which is caused by mutations in NOTCH3. We hypothesized that genetic variations in NOTCH3 also play a role in age-related cerebral small vessel disease. We directly sequenced all 33 exons, the promoter and 3'-untranslated region of NOTCH3 in 195 participants with either coalescent white matter lesions or lacunes and compared the results to 82 randomly selected participants with no focal changes on magnetic resonance images in the Austrian Stroke Prevention Study. We detected nine common and 33 rare single nucleotide polymorphisms, of which 20 were novel. All common single nucleotide polymorphisms were genotyped in the entire cohort (n = 888), and four of them, rs1043994, rs10404382, rs10423702 and rs1043997, were associated significantly with both the presence and progression of white matter lesions. The association was confined to hypertensives, a result which we replicated in the Cohorts for Heart and Ageing Research in Genomic Epidemiology Consortium on an independent sample of 4773 stroke-free hypertensive elderly individuals of European descent (P = 0.04). The 33 rare single nucleotide polymorphisms were scattered over the NOTCH3 gene with three being located in the promoter region, 24 in exons (18 non-synonymous), three in introns and three in the 3'-untranslated region. None of the single nucleotide polymorphisms affected a cysteine residue. Sorting Intolerant From Tolerant, PolyPhen2 analyses and protein structure simulation consistently predicted six of the non-synonymous single nucleotide polymorphisms (H170R, P496L, V1183M, L1518M, D1823N and V1952M) to be functional, with four being exclusively or mainly detected in subjects with severe white matter lesions. In four individuals with rare non-synonymous single nucleotide polymorphisms, we noted anterior temporal lobe hyperintensity, hyperintensity in the external capsule, lacunar infarcts or subcortical lacunar lesions. None of the observed abnormalities were specific to cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy. This is the first comprehensive study investigating (i) the frequency of NOTCH3 variations in community-dwelling elderly and (ii) their effect on cerebral small vessel disease related magnetic resonance imaging phenotypes. We show that the NOTCH3 gene is highly variable with both common and rare single nucleotide polymorphisms spreading across the gene, and that common variants at the NOTCH3 gene increase the risk of age-related white matter lesions in hypertensives. Additional investigations are required to explore the biological mechanisms underlying the observed association.
Keywords: Aged; Aged, 80 and over; Alleles; Brain; Cerebral Small Vessel Diseases; Exons; Female; Follow-Up Studies; Genetic Association Studies; Genotype; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Promoter Regions, Genetic; Prospective Studies; Receptor, Notch3; Receptors, Notch

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Hypertension, white matter hyperintensities, and concurrent impairments in mobility, cognition, and mood: the Cardiovascular Health Study. - Hajjar, Ihab; Quach, Lien; Yang, Frances; Chaves, Paulo H M; Newman, Anne B; Mukamal, Kenneth; Longstreth, Will; Inzitari, Marco; Lipsitz, Lewis A (Circulation, 2011)
BACKGROUND: Our objective was to investigate the association between hypertension and concurrent impairments in mobility, cognition, and mood; the role of brain white matter hyperintensities in mediating this association; and the impact of these impairments on disability and mortality in elderly hypertensive individuals. METHODS AND RESULTS: -Blood pressure, gait speed, digit symbol substitution test, and the Center for Epidemiological Studies Depression Scale were measured yearly (1992-1999) on 4700 participants in the Cardiovascular Health Study (age: 74.7, 58% women, 17% blacks, 68% hypertension, 3600 had brain magnetic resonance imaging in 1992-1993, survival data 1992-2005). Using latent profile analysis at baseline, we found that 498 (11%) subjects had concurrent impairments and 3086 (66%) were intact on all 3 measures. Between 1992 and 1999, 651 (21%) became impaired in all 3 domains. Hypertensive individuals were more likely to be impaired at baseline (odds ratio 1.23, 95% confidence interval 1.04 to 1.42, P=0.01) and become impaired during the follow-up (hazard ratio=1.3, 95% confidence interval 1.02 to 1.66, P=0.037). A greater degree of white matter hyperintensities was associated with impairments in the 3 domains (P=0.007) and mediated the association with hypertension (P=0.19 for hypertension after adjusting for white matter hyperintensities in the model, 21% hazard ratio change). Impairments in the 3 domains increased subsequent disability with hypertension (P<0.0001). Hypertension mortality also was increased in those impaired (compared with unimpaired hypertensive individuals: HR=1.10, 95% confidence interval 1.04 to 1.17, P=0.004). CONCLUSIONS: Hypertension increases the risk of concurrent impairments in mobility, cognition, and mood, which increases disability and mortality. This association is mediated in part by microvascular brain injury.
Keywords: Aged; Aged, 80 and over; Brain; Cognition Disorders; Female; Humans; Hypertension; Kaplan-Meier Estimate; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Mobility Limitation; Mood Disorders; Nerve Fibers, Myelinated; Retrospective Studies; Risk Factors

Kidney function decline in the elderly: impact of lipoprotein-associated phospholipase A(2). - Peralta, Carmen A; Katz, Ronit; Shlipak, Michael; Dubin, Ruth; DeBoer, Ian; Jenny, Nancy; Fitzpatrick, Annette; Koro, Carol; Kestenbaum, Bryan; Ix, Joachim; Sarnak, Mark; Cushman, Mary (Am J Nephrol, 2011)
BACKGROUND: Whether lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) levels are associated with kidney function decline has not been well studied. METHODS: We investigated associations of Lp-PLA(2) antigen and activity with kidney function decline and rapid decline over 5.7 years in the Cardiovascular Health Study (n = 4,359). We estimated kidney function by cystatin C (eGFRcys) in repeated measures, and defined rapid decline as ≥3 ml/min/1.73 m(2) per year. We stratified by baseline preserved GFR (≥60 ml/min/1.73 m(2)). RESULTS: Mean age was 72 ± 5 years. Average eGFRcys decline was -1.79 ml/min/1.73 m(2) (SD = 2.60) per year. Among persons with preserved GFR, compared to the lowest quartile of Lp-PLA(2) antigen, eGFRcys decline was faster among persons in the second, β -0.31 (95% CI -0.52, -0.10), third -0.19 (-0.41, 0.02) and fourth quartiles -0.26 (-0.48, -0.04) after full adjustment. Persons in the highest quartile of Lp-PLA(2) antigen had increased odds of rapid decline 1.34 (1.03, 1.75), compared to the lowest. There was no significant association between levels of Lp-PLA(2) activity and eGFRcys decline or rapid decline. Associations were not statistically significant among persons with low eGFR (<60 ml/min/1.73 m(2)) at baseline. CONCLUSION: Higher levels of Lp-PLA(2) antigen but not activity were significantly associated with faster rates of kidney function decline. These findings may suggest a novel vascular pathway for kidney disease progression.
Keywords: Aged; Cardiovascular Diseases; Creatinine; Cystatin C; Disease Progression; Female; Geriatrics; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Middle Aged; Phospholipases A2; Risk Factors; Treatment Outcome

Longitudinal changes in adiponectin and inflammatory markers and relation to survival in the oldest old: the Cardiovascular Health Study All Stars study. - Kizer, Jorge R; Arnold, Alice M; Jenny, Nancy S; Cushman, Mary; Strotmeyer, Elsa S; Ives, Diane G; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Adiponectin has anti-inflammatory properties, and its production is suppressed by inflammatory factors. Although elevated levels of adiponectin and inflammatory markers each predict mortality in older adults, the implications of their interdependent actions have not been examined. METHODS: We investigated the joint associations of levels and interval changes in adiponectin, C-reactive protein (CRP), and interleukin 6 (IL-6) with risk of death in 840 older adults participating in a population-based study. Adiponectin, CRP, and IL-6 were measured in samples collected 8.9 (8.2-9.8) years apart, and all-cause mortality was subsequently ascertained (n = 176). RESULTS: Interval changes and end levels of adiponectin, CRP, and IL-6 showed mostly positive, independent associations with mortality, without evidence of multiplicative interaction. Joint models, however, showed an U-shaped relationship between end level of adiponectin and outcome (hazard ratio [HR] [95% CI] = 0.72 [0.52-0.99] per standard deviation [SD] for levels <20.0 mg/L; HR = 1.91 [1.61-3.44] per SD for levels ≥20.0 mg/L). Participants with the greatest longitudinal increases (upper quartile) in both adiponectin and inflammatory markers had a higher risk of death (HR = 2.85 [1.78-4.58]) than those with large increases in adiponectin alone (HR = 1.87 [1.20-2.92]) (p = .043), but not inflammatory markers alone (HR = 2.48 [1.67-3.67]) (p = .55), as compared with smaller changes for both. CONCLUSION: Higher levels or interval change in adiponectin and inflammatory markers predict increased mortality in older persons independent of each other, although for adiponectin, the association appears inverse below 20 mg/L. These findings suggest that inflammatory and noninflammatory mechanisms governing aging-related decline operate in parallel and provide a potential explanation for paradoxical adiponectin-outcome associations reported previously.
Keywords: Adiponectin; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Chi-Square Distribution; Enzyme-Linked Immunosorbent Assay; Female; Humans; Inflammation; Interleukin-6; Male; Mortality; Predictive Value of Tests; Risk Factors; Sensitivity and Specificity; Survival Analysis; United States

Measures of adiposity and future risk of ischemic stroke and coronary heart disease in older men and women. - Kizer, Jorge R; Biggs, Mary L; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; de Boer, Ian H; Mozaffarian, Dariush; Barzilay, Joshua I; Strotmeyer, Elsa S; Luchsinger, José A; Elkind, Mitchell S V; Longstreth, W T; et al. (Am J Epidemiol, 2011)
The relation between measures of general and central adiposity and individual cardiovascular endpoints remains understudied in older adults. This study investigated the association of measures of body size and composition with incident ischemic stroke or coronary heart disease (1989-2007) in 3,754 community-dwelling US adults aged 65-100 years. Standardized anthropometry and bioelectric impedance measurements were obtained at baseline. Body mass index at age 50 years (BMI50) was calculated on the basis of recalled weight. Although only waist/hip ratio was significantly associated with ischemic stroke in quintile analysis in women, dichotomized body mass index (BMI) (≥ 30 kg/m²) was the only significant predictor in men. For coronary heart disease, there were significant positive adjusted associations for all adiposity measures, without interaction by sex. This was true for both quintiles and conventional cutpoints for obesity, although BMI-defined overweight (25-29.9 kg/m² was significant at midlife but not at baseline. Strengths of association for extreme quintiles (quintile 5 vs. quintile 1) were broadly comparable, but the highest effect estimates were for waist/hip ratio (hazard ratio = 1.56, 95% confidence interval: 1.25, 1.94) and BMI50 (hazard ratio = 1.71, 95% confidence interval: 1.37, 2.14), both of which remained significant after adjustment for mediators, BMI, or each other. Whether these differences translate to better risk prediction will require meta-analytical approaches, as will determination of prognostic cutpoints.
Keywords: Adiposity; Age Factors; Aged; Aged, 80 and over; Brain Ischemia; Coronary Disease; Female; Humans; Incidence; Male; Middle Aged; Obesity; Prevalence; Retrospective Studies; Risk Factors; Sex Factors; United States

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

NK-like T cells and plasma cytokines, but not anti-viral serology, define immune fingerprints of resilience and mild disability in exceptional aging. - Vallejo, Abbe N; Hamel, David L; Mueller, Robert G; Ives, Diane G; Michel, Joshua J; Boudreau, Robert M; Newman, Anne B (PLoS One, 2011)
Exceptional aging has been defined as maintenance of physical and cognitive function beyond the median lifespan despite a history of diseases and/or concurrent subclinical conditions. Since immunity is vital to individual fitness, we examined immunologic fingerprint(s) of highly functional elders. Therefore, survivors of the Cardiovascular Health Study in Pittsburgh, Pennsylvania, USA were recruited (n = 140; mean age = 86 years) and underwent performance testing. Blood samples were collected and examined blindly for humoral factors and T cell phenotypes. Based on results of physical and cognitive performance testing, elders were classified as "impaired" or "unimpaired", accuracy of group assignment was verified by discriminant function analysis. The two groups showed distinct immune profiles as determined by factor analysis. The dominant immune signature of impaired elders consisted of interferon (IFN)-γ, interleukin (IL)-6, tumor necrosis factor-α, and T cells expressing inhibitory natural killer-related receptors (NKR) CD158a, CD158e, and NKG2A. In contrast, the dominant signature of unimpaired elders consisted of IL-5, IL-12p70, and IL-13 with co-expression of IFN-γ, IL-4, and IL-17, and T cells expressing stimulatory NKRs CD56, CD16, and NKG2D. In logistic regression models, unimpaired phenotype was predicted independently by IL-5 and by CD4(+)CD28(null)CD56(+)CD57(+) T cells. All elders had high antibody titers to common viruses including cytomegalovirus. In cellular bioassays, T cell receptor (TCR)-independent ligation of either CD56 or NKG2D elicited activation of T cells. Collectively, these data demonstrate the importance of immunological parameters in distinguishing between health phenotypes of older adults. NKR(+) T cells and cytokine upregulation indicate a unique physiologic environment in old age. Correlation of particular NKR(+) T cell subsets and IL-5 with unimpaired performance, and NKR-driven TCR-independent activation of T cells suggest novel immunopathway(s) that could be exploited to improve immunity in old age.
Keywords: Adolescent; Adult; Aged, 80 and over; Aging; Cardiovascular Physiological Phenomena; CD56 Antigen; Cognition Disorders; Cytokines; Gene Expression Regulation; Humans; Immunity, Humoral; Killer Cells, Natural; Longevity; Male; NK Cell Lectin-Like Receptor Subfamily K; Phenotype; Physical Fitness; T-Lymphocyte Subsets; Young Adult

Patterns and predictors of recovery from exhaustion in older adults: the cardiovascular health study. - Whitson, Heather E; Thielke, Stephen; Diehr, Paula; O'Hare, Ann M; Chaves, Paulo H M; Zakai, Neil A; Arnold, Alice; Chaudhry, Sarwat; Ives, Diane; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To estimate the likelihood of, and factors associated with, recovery from exhaustion in older adults. DESIGN: Secondary analysis of a cohort study. SETTING: Six annual examinations in four U.S. communities. PARTICIPANTS: Four thousand five hundred eighty-four men and women aged 69 and older. MEASUREMENTS: Exhaustion was considered present when a participant responded "a moderate amount" or "most of the time" to either of two questions: "How often have you had a hard time getting going?" and "How often does everything seem an effort?" RESULTS: Of the 964 participants who originally reported exhaustion, 634 (65.8%) were exhaustion free at least once during follow-up. When data from all time points were considered, 48% of those who reported exhaustion were exhaustion free the following year. After adjustment for age, sex, race, education, and marital status, 1-year recovery was less likely in individuals with worse self-rated health and in those who were taking six or more medications or were obese, depressed, or had musculoskeletal pain or history of stroke. In proportional hazards models, the following risk factors were associated with more persistent exhaustion over 5 years: poor self-rated health, six or more medications, obesity, and depression. Recovery was not less likely in participants with a history of cancer or heart disease. CONCLUSION: Exhaustion is common in old age but is dynamic, even in those with a history of cancer and congestive heart failure. Recovery is especially likely in seniors who have a positive perception of their overall health, take few medications, and are not obese or depressed. These findings support the notion that resiliency is associated with physical and psychological well-being.
Keywords: Aged; Aging; Cardiovascular Physiological Phenomena; Exercise Test; Exercise Tolerance; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Predictive Value of Tests; Recovery of Function; Retrospective Studies; United States

Plasma omega-3 fatty acids and incident diabetes in older adults. - Djoussé, Luc; Biggs, Mary L; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Ix, Joachim H; Mukamal, Kenneth J; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2011)
BACKGROUND: Although long-chain omega-3 fatty acid (n-3 FA) consumption estimated via food-frequency questionnaires has been associated with a higher incidence of diabetes, limited prospective data on diabetes risk are available that use objective biomarkers of n-3 FAs. OBJECTIVE: We sought to examine the relation between plasma phospholipid n-3 FAs and incident diabetes. DESIGN: We prospectively analyzed data in 3088 older men and women (mean age: 75 y) from the Cardiovascular Health Study (1992-2007). Plasma phospholipid n-3 FAs were measured by using gas chromatography, and incident diabetes was ascertained by using information on hypoglycemic agents and serum glucose. We used Cox proportional hazards models to estimate multivariable-adjusted relative risks. RESULTS: During a median follow-up of 10.6 y, 204 new cases of diabetes occurred. In a multivariable model that controlled for age, sex, race, clinic site, body mass index, alcohol intake, smoking, physical activity, LDL cholesterol, and linoleic acid, relative risks (95% CIs) for diabetes were 1.0 (reference), 0.96 (0.65, 1.43), 1.03 (0.69, 1.54), and 0.64 (0.41, 1.01) across consecutive quartiles of phospholipid eicosapentaenoic acid and docosahexaenoic acid (P for trend = 0.05). Corresponding relative risks (95% CIs) for phospholipid α-linolenic acid (ALA) were 1.0 (reference), 0.93 (0.65, 1.34), 0.99 (0.68, 1.44), and 0.57 (0.36, 0.90) (P for trend = 0.03). CONCLUSIONS: With the use of objective biomarkers, long-chain n-3 FAs and ALA were not associated with a higher incidence of diabetes. Individuals with the highest concentrations of both types of FAs had lower risk of diabetes.
Keywords: Aged; Aged, 80 and over; alpha-Linolenic Acid; Diabetes Mellitus; Fatty Acids, Omega-3; Female; Humans; Male; Phospholipids; Proportional Hazards Models; Prospective Studies

Serum 25-hydroxyvitamin D and change in estimated glomerular filtration rate. - de Boer, Ian H; Katz, Ronit; Chonchol, Michel; Ix, Joachim H; Sarnak, Mark J; Shlipak, Michael G; Siscovick, David S; Kestenbaum, Bryan (Clin J Am Soc Nephrol, 2011)
BACKGROUND AND OBJECTIVES: Mounting evidence suggests that 1,25-dihydroxyvitamin D prevents the progression of chronic kidney disease (CKD). It is not clear whether "nutritional" forms of vitamin D affect GFR. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We tested whether serum 25-hydroxyvitamin D concentration (25(OH)D), a measure of total vitamin D intake from cutaneous synthesis and dietary consumption, is associated with loss of estimated GFR among 1705 older adults with predominantly normal baseline kidney function participating in the Cardiovascular Health Study. Baseline 25(OH)D was measured by HPLC-tandem mass spectrometry. GFR was estimated at baseline and 4 years later using the CKD-EPI formula, with rapid GFR loss defined as 12 ml/min per 1.73 m(2) or more over 4 years. RESULTS: Rapid GFR loss was observed for 207 participants (12%). Each 10 ng/ml lower 25(OH)D was associated with a 25% greater risk of rapid GFR loss (95% confidence interval [CI] 5%, 49%, P = 0.01), adjusting for potential confounding characteristics. Compared with 25(OH)D ≥30 ng/ml, 25(OH)D concentrations 15 to 29 ng/ml and <15 ng/ml were associated with 29% (95% CI -13%, 91%) and 68% (95% CI 1%, 177%) greater adjusted risks of rapid GFR loss, respectively. Magnitudes of association were largest among participants with diabetes. RESULTS: were similar evaluating a composite outcome of rapid GFR loss, end stage renal disease, and death. Conclusions Insufficient 25(OH)D may be a modifiable risk factor for early GFR loss. We recommend clinical trials to determine whether vitamin D supplementation prevents the development and progression of CKD.
Keywords: Aged; Female; Glomerular Filtration Rate; Humans; Kidney Diseases; Male; Prospective Studies; Vitamin D

Subclinical vascular disease burden and risk for death and cardiovascular events in older community dwellers. - Inzitari, Marco; Arnold, Alice M; Patel, Kushang V; Mercer, Laina D; Karlamangla, Arun; Ding, Jingzhong; Psaty, Bruce M; Williamson, Jeff D; Kuller, Lewis H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Individual measures and previous composite measures of subclinical vascular disease defined high risk for cardiovascular events, but did not detect low and modest risk. A different approach might better describe the spectrum from low to high risk. Methods and Results. In the Cardiovascular Health Study, 3,252 participants without history of clinical cardiovascular disease (M ± SD 74.3 years ± 5.1, 63% women, 17% African Americans) had noninvasive vascular assessments in 1992-1993. We assigned a score of 0, 1, or 2 (no, mild, or severe abnormalities) to ankle-arm index, electrocardiogram, and common carotid intima-media thickness, based on clinical cutoffs. A summary index (range 0-6, absent to severe disease) summed individual scores. Abdominal aortic ultrasound and brain magnetic resonance imaging were collected in a subsample. Mortality and incident cardiovascular events were identified through June 2008. Event and death rates increased across index grades. Comparing grades 1 to 5+ with absent disease, and adjusting for demographics, hazard ratios for cardiovascular events within 8 years ranged from 1.1 (95% confidence interval 0.8-1.6) to 4.7 (3.4-6.9) and, for mortality, from 1.5 (1.0-2.3) to 5.0 (3.3-7.7) (p for trend across grades <.001 for both outcomes). Adjustment for cardiovascular risk factors did not substantially change the associations. The index improved mortality risk classification over demographics and risk factors in participants who did not die during the follow-up. Including in the index the aortic ultrasound and the brain magnetic resonance imaging further improved risk classification. CONCLUSIONS: Older adults with minimal subclinical vascular disease had low cardiovascular events risk and mortality. This approach might more fully account for vascular burden.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cost of Illness; Female; Humans; Male; Risk; Vascular Diseases

Total zinc intake may modify the glucose-raising effect of a zinc transporter (SLC30A8) variant: a 14-cohort meta-analysis. - Kanoni, Stavroula; Nettleton, Jennifer A; Hivert, Marie-France; Ye, Zheng; van Rooij, Frank J A; Shungin, Dmitry; Sonestedt, Emily; Ngwa, Julius S; Wojczynski, Mary K; Lemaitre, Rozenn N; Gustafsson, Stefan; Anderson, Jennifer S; et al. (Diabetes, 2011)
OBJECTIVE: Many genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants. RESEARCH DESIGN AND METHODS: We conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with dietary zinc intake (food sources) and a 5-cohort meta-analysis to assess the interaction with total zinc intake (food sources and supplements) on fasting glucose levels among individuals of European ancestry without diabetes. RESULTS: We observed a significant association of total zinc intake with lower fasting glucose levels (β-coefficient ± SE per 1 mg/day of zinc intake: -0.0012 ± 0.0003 mmol/L, summary P value = 0.0003), while the association of dietary zinc intake was not significant. We identified a nominally significant interaction between total zinc intake and the SLC30A8 rs11558471 variant on fasting glucose levels (β-coefficient ± SE per A allele for 1 mg/day of greater total zinc intake: -0.0017 ± 0.0006 mmol/L, summary interaction P value = 0.005); this result suggests a stronger inverse association between total zinc intake and fasting glucose in individuals carrying the glucose-raising A allele compared with individuals who do not carry it. None of the other interaction tests were statistically significant. CONCLUSIONS: Our results suggest that higher total zinc intake may attenuate the glucose-raising effect of the rs11558471 SLC30A8 (zinc transporter) variant. Our findings also support evidence for the association of higher total zinc intake with lower fasting glucose levels.
Keywords: Blood Glucose; Cation Transport Proteins; Cohort Studies; Humans; Polymorphism, Single Nucleotide; Zinc; Zinc Transporter 8

Adiposity and incident heart failure in older adults: the cardiovascular health study. - Djoussé, Luc; Bartz, Traci M; Ix, Joachim H; Zieman, Susan J; Delaney, Joseph A; Mukamal, Kenneth J; Gottdiener, John S; Siscovick, David S; Kizer, Jorge R (Obesity (Silver Spring), 2012)
While several studies have reported a positive association between overall adiposity and heart failure (HF) risk, limited and inconsistent data are available on the relation between central adiposity and incident HF in older adults. We sought to examine the association between waist circumference (WC) and incident HF and assess whether sex modifies the relation between WC and HF. Prospective study using data on 4,861 participants of the Cardiovascular Health Study (1989-2007). HF was adjudicated by a committee using information from medical records and medications. We used Cox proportional hazard models to compute hazard ratio (HR). The mean age was 73.0 years for men and 72.3 years for women; 42.5% were men and 15.3% were African Americans. WC was positively associated with an increased risk of HF: each standard deviation of WC was associated with a 14% increased risk of HF (95% CI: 3%-26%) in a multivariable model. There was not a statistically significant sex-by-WC interaction (P = 0.081). BMI was positively associated with incident HF (HR: 1.22 (95% CI: 1.15-1.29) per standard deviation increase of BMI); however, this association was attenuated and became nonstatistically significant upon additional adjustment for WC (HR: 1.09 (95% CI: 0.99-1.21)). In conclusion, a higher WC is associated with an increased risk of HF independent of BMI in community-living older men and women.
Keywords: Adiposity; Aged; Aging; Body Fat Distribution; Body Mass Index; Female; Heart Failure; Humans; Incidence; Independent Living; Male; Obesity; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; United States; Waist Circumference

Age and association of kidney measures with mortality and end-stage renal disease. - Hallan, Stein I; Matsushita, Kunihiro; Sang, Yingying; Mahmoodi, Bakhtawar K; Black, Corri; Ishani, Areef; Kleefstra, Nanne; Naimark, David; Roderick, Paul; Tonelli, Marcello; Wetzels, Jack F M; Astor, Brad C; et al. (JAMA, 2012)
CONTEXT: Chronic kidney disease (CKD) is prevalent in older individuals, but the risk implications of low estimated glomerular filtration rate (eGFR) and high albuminuria across the full age range are controversial. OBJECTIVE: To evaluate possible effect modification (interaction) by age of the association of eGFR and albuminuria with clinical risk, examining both relative and absolute risks. DESIGN, SETTING, AND PARTICIPANTS: Individual-level meta-analysis including 2,051,244 participants from 33 general population or high-risk (of vascular disease) cohorts and 13 CKD cohorts from Asia, Australasia, Europe, and North/South America, conducted in 1972-2011 with a mean follow-up time of 5.8 years (range, 0-31 years). MAIN OUTCOME MEASURES: Hazard ratios (HRs) of mortality and end-stage renal disease (ESRD) according to eGFR and albuminuria were meta-analyzed across age categories after adjusting for sex, race, cardiovascular disease, diabetes, systolic blood pressure, cholesterol, body mass index, and smoking. Absolute risks were estimated using HRs and average incidence rates. RESULTS: Mortality (112,325 deaths) and ESRD (8411 events) risks were higher at lower eGFR and higher albuminuria in every age category. In general and high-risk cohorts, relative mortality risk for reduced eGFR decreased with increasing age; eg, adjusted HRs at an eGFR of 45 mL/min/1.73 m2 vs 80 mL/min/1.73 m2 were 3.50 (95% CI, 2.55-4.81), 2.21 (95% CI, 2.02-2.41), 1.59 (95% CI, 1.42-1.77), and 1.35 (95% CI, 1.23-1.48) in age categories 18-54, 55-64, 65-74, and ≥75 years, respectively (P <.05 for age interaction). Absolute risk differences for the same comparisons were higher at older age (9.0 [95% CI, 6.0-12.8], 12.2 [95% CI, 10.3-14.3], 13.3 [95% CI, 9.0-18.6], and 27.2 [95% CI, 13.5-45.5] excess deaths per 1000 person-years, respectively). For increased albuminuria, reduction of relative risk with increasing age was less evident, while differences in absolute risk were higher in older age categories (7.5 [95% CI, 4.3-11.9], 12.2 [95% CI, 7.9-17.6], 22.7 [95% CI, 15.3-31.6], and 34.3 [95% CI, 19.5-52.4] excess deaths per 1000 person-years, respectively by age category, at an albumin-creatinine ratio of 300 mg/g vs 10 mg/g). In CKD cohorts, adjusted relative hazards of mortality did not decrease with age. In all cohorts, ESRD relative risks and absolute risk differences at lower eGFR or higher albuminuria were comparable across age categories. CONCLUSIONS: Both low eGFR and high albuminuria were independently associated with mortality and ESRD regardless of age across a wide range of populations. Mortality showed lower relative risk but higher absolute risk differences at older age.
Keywords: Adolescent; Adult; Age Factors; Aged; Albuminuria; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Risk; Young Adult

Assessment of gene-by-sex interaction effect on bone mineral density. - Liu, Ching-Ti; Estrada, Karol; Yerges-Armstrong, Laura M; Amin, Najaf; Evangelou, Evangelos; Li, Guo; Minster, Ryan L; Carless, Melanie A; Kammerer, Candace M; Oei, Ling; Zhou, Yanhua; Alonso, Nerea; et al. (J Bone Miner Res, 2012)
Sexual dimorphism in various bone phenotypes, including bone mineral density (BMD), is widely observed; however, the extent to which genes explain these sex differences is unclear. To identify variants with different effects by sex, we examined gene-by-sex autosomal interactions genome-wide, and performed expression quantitative trait loci (eQTL) analysis and bioinformatics network analysis. We conducted an autosomal genome-wide meta-analysis of gene-by-sex interaction on lumbar spine (LS) and femoral neck (FN) BMD in 25,353 individuals from 8 cohorts. In a second stage, we followed up the 12 top single-nucleotide polymorphisms (SNPs; p < 1 × 10(-5) ) in an additional set of 24,763 individuals. Gene-by-sex interaction and sex-specific effects were examined in these 12 SNPs. We detected one novel genome-wide significant interaction associated with LS-BMD at the Chr3p26.1-p25.1 locus, near the GRM7 gene (male effect = 0.02 and p = 3.0 × 10(-5) ; female effect = -0.007 and p = 3.3 × 10(-2) ), and 11 suggestive loci associated with either FN- or LS-BMD in discovery cohorts. However, there was no evidence for genome-wide significant (p < 5 × 10(-8) ) gene-by-sex interaction in the joint analysis of discovery and replication cohorts. Despite the large collaborative effort, no genome-wide significant evidence for gene-by-sex interaction was found to influence BMD variation in this screen of autosomal markers. If they exist, gene-by-sex interactions for BMD probably have weak effects, accounting for less than 0.08% of the variation in these traits per implicated SNP. © 2012 American Society for Bone and Mineral Research.
Keywords: Bone Density; Cohort Studies; Female; Genes; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Sex Characteristics

Association of fetuin-a with incident diabetes mellitus in community-living older adults: the cardiovascular health study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth J; Kizer, Jorge R; Zieman, Susan J; Siscovick, David S; Mozzaffarian, Dariush; Jensen, Majken K; Nelson, Lauren; Ruderman, Neil; Djoussé, Luc (Circulation, 2012)
BACKGROUND: The liver-secreted protein fetuin-A induces peripheral insulin resistance in vitro. In a pilot study, we observed that higher fetuin-A levels were associated with diabetes mellitus in older persons. However, this finding has not been confirmed in large cohorts. We sought to confirm the association of fetuin-A with incident diabetes mellitus in older persons and to determine whether the association differs by age, sex, and race and among persons with cardiovascular disease (CVD). METHODS AND RESULTS: Among 3710 community-living individuals ≥ 65 years of age without diabetes mellitus at baseline, fetuin-A was measured in serum collected in 1992 to 1993. Participants were followed up for 10.6 years (median) for incident diabetes mellitus. Cox regression models evaluated the association of fetuin-A with incident diabetes mellitus. Interaction terms evaluated heterogeneity by age, sex, race, and CVD. Mean age was 75 years; 60 were female; 15 were black; and 16 had CVD. Mean fetuin-A concentrations were 0.47 ± 0.10 g/L. During follow-up, 305 incident diabetes cases occurred. Each 0.10-g/L (SD)-greater fetuin-A was associated with 19 higher risk of diabetes mellitus (hazard ratio, 1.19; 95 confidence interval, 1.06-1.33) after adjustment for demographics, lifestyle factors, albumin, kidney function, and CVD. Further adjustment for potential mediators (body mass index, waist circumference, hypertension, lipids, and C-reactive protein) moderately attenuated the association (hazard ratio, 1.13; 95 confidence interval, 1.00-1.28). Results were similar by sex, race, and CVD status but were stronger in persons <75 years old (P for interaction=0.01). CONCLUSIONS: Higher fetuin-A is associated with incident diabetes mellitus in older persons regardless of sex, race, or prevalent CVD status. The association may be attenuated in those ≥ 75 years of age.
Keywords: African Continental Ancestry Group; Age Distribution; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Humans; Incidence; Life Style; Lipids; Male; Pilot Projects; Prevalence; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Distribution

Associations of total and high-molecular-weight adiponectin with all-cause and cardiovascular mortality in older persons: the Cardiovascular Health Study. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Mukamal, Kenneth J; Ix, Joachim H; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Mantzoros, Christos S; deFilippi, Christopher R; Newman, Anne B; Djoussé, Luc (Circulation, 2012)
BACKGROUND: Adiponectin shows opposite associations with adverse outcomes in healthy middle-aged populations (lower risk) and cohorts with prevalent cardiovascular disease, heart failure, or advanced age (higher risk). METHODS AND RESULTS: In a population-based study of older adults, we examined the relationships of total and high-molecular-weight adiponectin with mortality among subgroups defined by baseline cardiovascular status: No cardiovascular disease, heart failure, or atrial fibrillation (group 1); cardiovascular disease but no heart failure/atrial fibrillation (group 2); and heart failure/atrial fibrillation (group 3). We found significant differences in the associations with all-cause mortality across the groups. The association in group 1 was U-shaped; increasing levels of total adiponectin up to 12.4 mg/L were associated with lower mortality after adjustment for confounders (hazard ratio=0.81 per 1 SD [95% confidence interval, 0.65-0.95]), but above this cut point, higher levels conferred greater risk (hazard ratio=1.19 [95% confidence interval, 1.12-1.27]). Further adjustment for diabetes mellitus or insulin resistance, protection against which has been proposed to mediate the beneficial relationships of adiponectin with outcome, attenuated the association in the lower range. There was no significant association in group 2, but in group 3, total adiponectin showed a direct adjusted association. Additional adjustment for putative metabolic/inflammatory intermediates suggested a direct association for group 2, and magnified the one for group 3 (hazard ratio=1.31 [1.15-1.50]). Results were similar for high-molecular-weight adiponectin and for cardiovascular mortality. CONCLUSIONS: Adiponectin exhibits distinct associations with mortality in elders, which shift from U-shaped to flat to direct with greater baseline cardiovascular dysfunction but become more consistently adverse after accounting for metabolic/inflammatory factors presumed to be favorably regulated by the adipokine. These findings advance understanding of the adiponectin paradox as it relates to older adults.
Keywords: Adiponectin; Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Female; Health Surveys; Humans; Male; Molecular Weight

Chronic kidney disease, insulin resistance, and incident diabetes in older adults. - Pham, Hien; Robinson-Cohen, Cassianne; Biggs, Mary L; Ix, Joachim H; Mukamal, Kenneth J; Fried, Linda F; Kestenbaum, Bryan; Siscovick, David S; de Boer, Ian H (Clin J Am Soc Nephrol, 2012)
BACKGROUND AND OBJECTIVES: Insulin resistance is a complication of advanced CKD. Insulin resistance is less well characterized in earlier stages of CKD. The response of the pancreatic β cell, effects on glucose tolerance, and risk of diabetes are not clear. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The Cardiovascular Health Study included 4680 adults without baseline diabetes. The Chronic Kidney Disease Epidemiology Collaboration creatinine equation was used to obtain the estimated GFR (eGFR). Insulin resistance was evaluated as fasting insulin concentration. The insulin sensitivity index, β cell function, and glucose tolerance were assessed by oral glucose tolerance testing. Incident diabetes was defined as fasting glucose ≥126 mg/dl, nonfasting glucose ≥200 mg/dl, or use of glucose-lowering medications. RESULTS: Mean age was 72.5 years (range, 65-98 years). Mean eGFR was 72.2 (SD 17.1) ml/min per 1.73 m(2). After adjustment, each 10 ml/min per 1.73 m(2) lower eGFR was associated with a 2.2% higher fasting insulin concentration (95% confidence interval [CI], 1.4%, 2.9%; P<0.001) and a 1.1% lower insulin sensitivity index (95% CI, 0.03%, 2.2%; P=0.04). Surprisingly, eGFR was associated with an augmented β cell function index (P<0.001), lower 2-hour glucose concentration (P=0.002), and decreased risk of glucose intolerance (P=0.006). Over a median 12 years' follow-up, 437 participants (9.3%) developed diabetes. eGFR was not associated with the risk of incident diabetes. CONCLUSIONS: Among older adults, lower eGFR was associated with insulin resistance. However, with lower eGFR, β cell function was appropriately augmented and risks of impaired glucose tolerance and incident diabetes were not increased.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Chronic Disease; Creatinine; Diabetes Mellitus; Female; Glomerular Filtration Rate; Glucose Tolerance Test; Health Surveys; Humans; Hypoglycemic Agents; Incidence; Insulin; Insulin Resistance; Insulin-Secreting Cells; Kidney; Kidney Diseases; Linear Models; Male; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

Common genetic variants differentially influence the transition from clinically defined states of fasting glucose metabolism. - Walford, G A; Green, T; Neale, B; Isakova, T; Rotter, J I; Grant, S F A; Fox, C S; Pankow, J S; Wilson, J G; Meigs, J B; Siscovick, D S; Bowden, D W; et al. (Diabetologia, 2012)
AIMS/HYPOTHESIS: Common genetic variants have been associated with type 2 diabetes. We hypothesised that a subset of these variants may have different effects on the transition from normal fasting glucose (NFG) to impaired fasting glucose (IFG) than on that from IFG to diabetes. METHODS: We identified 16 type 2 diabetes risk variants from the Illumina Broad Candidate-gene Association Resource (CARe) array genotyped in 26,576 CARe participants. Participants were categorised at baseline as NFG, IFG or type 2 diabetic (n = 16,465, 8,017 or 2,291, respectively). Using Cox proportional hazards and likelihood ratio tests (LRTs), we compared rates of progression by genotype for 4,909 (NFG to IFG) and 1,518 (IFG to type 2 diabetes) individuals, respectively. We then performed multinomial regression analyses at baseline, comparing the risk of assignment to the NFG, IFG or diabetes groups by genotype. RESULTS: The rate of progression from NFG to IFG was significantly greater in participants carrying the risk allele at MTNR1B (p = 1 × 10(-4)), nominally greater at GCK and SLC30A8 (p < 0.05) and nominally smaller at IGF2BP2 (p = 0.01) than the rate of progression from IFG to diabetes by the LRT. Results of the baseline, multinomial regression model were consistent with these findings. CONCLUSIONS/INTERPRETATION: Common genetic risk variants at GCK, SLC30A8, IGF2BP2 and MTNR1B influence to different extents the development of IFG and the transition from IFG to type 2 diabetes. Our findings may have implications for understanding the genetic contribution of these variants to the development of IFG and type 2 diabetes.
Keywords: Adult; Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Disease Progression; Fasting; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Proportional Hazards Models; Regression Analysis; Risk

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Fibroblast growth factor-23 and death, heart failure, and cardiovascular events in community-living individuals: CHS (Cardiovascular Health Study). - Ix, Joachim H; Katz, Ronit; Kestenbaum, Bryan R; de Boer, Ian H; Chonchol, Michel; Mukamal, Kenneth J; Rifkin, Dena; Siscovick, David S; Sarnak, Mark J; Shlipak, Michael G (J Am Coll Cardiol, 2012)
OBJECTIVES: This study sought to determine the association of fibroblast growth factor (FGF)-23 with death, heart failure (HF), and cardiovascular disease (CVD) in the general population, as well as the influence of chronic kidney disease (CKD) in this setting. BACKGROUND: FGF-23 increases renal phosphorus excretion and inhibits vitamin D activation. In end-stage renal disease, high FGF-23 levels are associated with mortality. The association of FGF-23 with death, HF, and CVD in the general population, and the influence of CKD in this setting, are unknown. METHODS: Plasma FGF-23 was measured in 3,107 community-living persons ≥ 65 years of age in 1996 and 1997, and participants were followed through 2008. HF and CVD events were adjudicated by a panel of experts. Associations of FGF-23 with each outcome were evaluated using Cox proportional hazards models, and we tested whether associations differed by CKD status. RESULTS: Both lower estimated glomerular filtration rate and higher urine albumin to creatinine ratios were associated with high FGF-23 at baseline. During 10.5 years (median) follow-up, there were 1,730 deaths, 697 incident HF events, and 797 incident CVD events. Although high FGF-23 concentrations were associated with each outcome in combined analyses, the associations were consistently stronger for those with CKD (p interactions all <0.006). In the CKD group (n = 1,128), the highest FGF-23 quartile had adjusted hazards ratios (HR) of 1.87 (95% confidence interval [CI]: 1.47 to 2.38) for all-cause death, 1.94 (95% CI: 1.32 to 2.83) for incident HF, and 1.49 (95% CI: 1.02 to 2.18) for incident CVD events compared with the lowest quartile. Corresponding HRs in those without CKD (n = 1,979) were 1.29 (95% CI: 1.05 to 1.59), 1.37 (95% CI: 0.99 to 1.89), and 1.07 (95% CI: 0.79 to 1.45). CONCLUSIONS: FGF-23, a hormone involved in phosphorous and vitamin D homeostasis, is independently associated with all-cause death and incident HF in community-living older persons. These associations appear stronger in persons with CKD.
Keywords: Aged; Aged, 80 and over; Biomarkers; Female; Fibroblast Growth Factors; Heart Failure; Humans; Kidney Function Tests; Male; Mortality; Renal Insufficiency, Chronic; United States

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic risk factors for ischaemic stroke and its subtypes (the METASTROKE collaboration): a meta-analysis of genome-wide association studies. - Traylor, Matthew; Farrall, Martin; Holliday, Elizabeth G; Sudlow, Cathie; Hopewell, Jemma C; Cheng, Yu-Ching; Fornage, Myriam; Ikram, M Arfan; Malik, Rainer; Bevan, Steve; Thorsteinsdottir, Unnur; Nalls, Mike A; et al. (Lancet Neurol, 2012)
BACKGROUND: Various genome-wide association studies (GWAS) have been done in ischaemic stroke, identifying a few loci associated with the disease, but sample sizes have been 3500 cases or less. We established the METASTROKE collaboration with the aim of validating associations from previous GWAS and identifying novel genetic associations through meta-analysis of GWAS datasets for ischaemic stroke and its subtypes. METHODS: We meta-analysed data from 15 ischaemic stroke cohorts with a total of 12 389 individuals with ischaemic stroke and 62 004 controls, all of European ancestry. For the associations reaching genome-wide significance in METASTROKE, we did a further analysis, conditioning on the lead single nucleotide polymorphism in every associated region. Replication of novel suggestive signals was done in 13 347 cases and 29 083 controls. FINDINGS: We verified previous associations for cardioembolic stroke near PITX2 (p=2·8×10(-16)) and ZFHX3 (p=2·28×10(-8)), and for large-vessel stroke at a 9p21 locus (p=3·32×10(-5)) and HDAC9 (p=2·03×10(-12)). Additionally, we verified that all associations were subtype specific. Conditional analysis in the three regions for which the associations reached genome-wide significance (PITX2, ZFHX3, and HDAC9) indicated that all the signal in each region could be attributed to one risk haplotype. We also identified 12 potentially novel loci at p<5×10(-6). However, we were unable to replicate any of these novel associations in the replication cohort. INTERPRETATION: Our results show that, although genetic variants can be detected in patients with ischaemic stroke when compared with controls, all associations we were able to confirm are specific to a stroke subtype. This finding has two implications. First, to maximise success of genetic studies in ischaemic stroke, detailed stroke subtyping is required. Second, different genetic pathophysiological mechanisms seem to be associated with different stroke subtypes. FUNDING: Wellcome Trust, UK Medical Research Council (MRC), Australian National and Medical Health Research Council, National Institutes of Health (NIH) including National Heart, Lung and Blood Institute (NHLBI), the National Institute on Aging (NIA), the National Human Genome Research Institute (NHGRI), and the National Institute of Neurological Disorders and Stroke (NINDS).
Keywords: Brain Ischemia; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Stroke

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

A genome-wide association study identifies a potential novel gene locus for keratoconus, one of the commonest causes for corneal transplantation in developed countries. - Li, Xiaohui; Bykhovskaya, Yelena; Haritunians, Talin; Siscovick, David; Aldave, Anthony; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Hum Mol Genet, 2012)
Keratoconus is a condition in which the cornea progressively thins over time, and is a major cause for cornea transplantation. To identify keratoconus susceptibility regions, we performed a comprehensive genome-wide association study (GWAS) using a discovery and replication design. A discovery panel of 222 keratoconus Caucasian patients and 3324 Caucasian controls was genotyped using Illumina 370K beadchips. Further associated and fine-mapping single nucleotide polymorphisms (SNPs) (n= 4905) were genotyped in an independent replication case-control panel of 304 cases and 518 controls and a family panel of 307 subjects in 70 families. Logistic regression models implemented in PLINK were performed to test associations in case-control samples with and without principal component (PC) adjustments. Generalized estimation equation models accounting for familial correlations implemented in GWAF were used for association testing in families. No genome-wide associations were identified in the discovery GWAS panel. From the initial testing without adjustments for PCs, the top three SNPs located at 3p26 (rs6442925), 2q21.3 (rs4954218) and 19q13.3 (rs1428642) were identified with unadjusted P-values of 6.5 × 10(-8), 2.4 × 10(-7) and 3.1 × 10(-7), respectively. After adjustments for PCs, rs1428642 became the most significant through the genome with a P-value of 1.4 × 10(-6), while rs6442925 and rs4954218 were less significant (P= 1.9 × 10(-5) and 2.6 × 10(-4)). SNP rs4954218 was confirmed in two independent replication panels with P-values of 0.004 and 0.009, respectively. Meta-analysis revealed a highest association at rs4954218 with adjusted P= 1.6 × 10(-7) (unadjusted P= 1.2 × 10(-9)). These findings suggest SNP rs4954218, located near the RAB3GAP1 gene, previously reported to be associated with corneal malformation, is a potential susceptibility locus for keratoconus.
Keywords: Case-Control Studies; Chromosomes, Human, Pair 2; Cohort Studies; Corneal Transplantation; Developed Countries; Genome-Wide Association Study; Humans; Keratoconus; Polymorphism, Single Nucleotide

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Hemoglobin A1c and arterial and ventricular stiffness in older adults. - Zieman, Susan J; Kamineni, Aruna; Ix, Joachim H; Barzilay, Joshua; Djoussé, Luc; Kizer, Jorge R; Biggs, Mary L; de Boer, Ian H; Chonchol, Michel; Gottdiener, John S; Selvin, Elizabeth; Newman, Anne B; et al. (PLoS One, 2012)
OBJECTIVE: Arterial and ventricular stiffening are characteristics of diabetes and aging which confer significant morbidity and mortality; advanced glycation endproducts (AGE) are implicated in this stiffening pathophysiology. We examined the association between HbA(1c), an AGE, with arterial and ventricular stiffness measures in older individuals without diabetes. RESEARCH DESIGN & METHODS: Baseline HbA(1c) was measured in 830 participants free of diabetes defined by fasting glucose or medication use in the Cardiovascular Health Study, a population-based cohort study of adults aged ≥ 65 years. We performed cross-sectional analyses using baseline exam data including echocardiography, ankle and brachial blood pressure measurement, and carotid ultrasonography. We examined the adjusted associations between HbA(1c) and multiple arterial and ventricular stiffness measures by linear regression models and compared these results to the association of fasting glucose (FG) with like measures. RESULTS: HbA(1c) was correlated with fasting and 2-hour postload glucose levels (r = 0.21; p<0.001 for both) and positively associated with greater body-mass index and black race. In adjusted models, HbA(1c) was not associated with any measure of arterial or ventricular stiffness, including pulse pressure (PP), carotid intima-media thickness, ankle-brachial index, end-arterial elastance, or left ventricular mass (LVM). FG levels were positively associated with systolic, diastolic and PP and LVM. CONCLUSIONS: In this sample of older adults without diabetes, HbA(1c) was not associated with arterial or ventricular stiffness measures, whereas FG levels were. The role of AGE in arterial and ventricular stiffness in older adults may be better assessed using alternate AGE markers.
Keywords: Adult; African Continental Ancestry Group; Aged; Ankle Brachial Index; Arteries; Blood Glucose; Blood Pressure; Body Mass Index; Cross-Sectional Studies; Fasting; Female; Genetic Association Studies; Glycated Hemoglobin A; Glycation End Products, Advanced; Heart Ventricles; Humans; Male; Middle Aged; Ultrasonography; Vascular Stiffness

Insulin resistance and incident peripheral artery disease in the Cardiovascular Health Study. - Britton, Kathryn A; Mukamal, Kenneth J; Ix, Joachim H; Siscovick, David S; Newman, Anne B; de Boer, Ian H; Thacker, Evan L; Biggs, Mary L; Gaziano, J Michael; Djoussé, Luc (Vasc Med, 2012)
Type 2 diabetes is a risk factor for peripheral artery disease (PAD), and insulin resistance is a key feature of diabetes and pre-diabetes. No longitudinal epidemiological study has examined the relation between insulin resistance and PAD. Our study analyzed the association of quartiles of the homeostatic model of insulin resistance (HOMA-IR) and the development of PAD defined by two methods. PAD was first defined as the development of an abnormal ankle-brachial index (ABI) (dichotomous outcome) after 6 years of follow-up. PAD was alternatively defined as the development of clinical PAD (time-to-event analysis). The study samples included adults over the age of 65 years who were enrolled in the Cardiovascular Health Study, had fasting measurements of insulin and glucose, had ABI measurements, and were not receiving treatment for diabetes. Multivariable models were adjusted for potential confounders, including age, sex, field center and cohort, body mass index (BMI), smoking status, alcohol use, and exercise intensity. Additional models adjusted for potential mediators, including blood pressure, lipids, kidney function, and prevalent vascular disease. In the ABI analysis (n = 2108), multivariable adjusted models demonstrated a positive relation between HOMA-IR and incident PAD (odds ratio = 1.80 comparing the 4th versus 1st quartile of HOMA-IR, 95% confidence interval [CI] 1.20-2.71). In the clinical PAD analysis (n = 4208), we found a similar relation (hazard ratio = 2.30 comparing the 4th versus 1st quartile of HOMA-IR, 95% CI 1.15-4.58). As expected, further adjustment for potential mediators led to some attenuation of effect estimates. In conclusion, insulin resistance is associated with a higher risk of PAD in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Blood Glucose; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Fasting; Female; Health Surveys; Humans; Incidence; Insulin; Insulin Resistance; Logistic Models; Longitudinal Studies; Male; Odds Ratio; Peripheral Arterial Disease; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Insulin resistance, cystatin C, and mortality among older adults. - de Boer, Ian H; Katz, Ronit; Chonchol, Michel B; Fried, Linda F; Ix, Joachim H; Kestenbaum, Bryan; Mukamal, Kenneth J; Peralta, Carmen A; Siscovick, David S (Diabetes Care, 2012)
OBJECTIVE: Insulin resistance is a risk factor for cardiovascular and noncardiovascular diseases. Impaired kidney function is linked with insulin resistance and may affect relationships of insulin resistance with health outcomes. RESEARCH DESIGN AND METHODS: We performed a cohort study of 3,138 Cardiovascular Health Study participants (age ≥ 65 years) without diabetes. Insulin sensitivity index (ISI) was calculated from fasting and 2-h postload insulin and glucose concentrations. Associations of ISI and fasting insulin concentration with all-cause mortality were tested using Cox proportional hazards models, adjusting for demographic variables, prevalent cardiovascular disease, lifestyle variables, waist circumference, and LDL cholesterol. Subsequent models were additionally adjusted for or stratified by glomerular filtration rate estimated using serum cystatin C (eGFR). RESULTS: A total of 1,810 participants died during the 14.7-year median follow-up. Compared with the highest quartile of ISI, the lowest quartile (most insulin resistant) was associated with 21% (95% CI 6-41) and 11% (-3 to 29) higher risks of death without and with adjustment for eGFR, respectively. Compared with the lowest quartile of fasting insulin concentration, the highest quartile was associated with 22% (4-43) and 4% (-12 to 22) higher risks of death without and with adjustment for eGFR, respectively. Similar attenuation by eGFR was observed when blood pressure, triglycerides, HDL cholesterol, and C-reactive protein were included in models. CONCLUSIONS: Insulin resistance measured as ISI or fasting insulin concentration is associated with increased risk of death among older adults, adjusting for conventional confounding characteristics. Impaired kidney function may mediate or confound this relationship.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Blood Pressure; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Cystatin C; Fasting; Female; Glomerular Filtration Rate; Humans; Insulin Resistance; Life Style; Male; Mortality; Predictive Value of Tests; Proportional Hazards Models; Renal Insufficiency; Risk Factors; Triglycerides; Waist Circumference

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Large-scale international validation of the ADO index in subjects with COPD: an individual subject data analysis of 10 cohorts. - Puhan, Milo A; Hansel, Nadia N; Sobradillo, Patricia; Enright, Paul; Lange, Peter; Hickson, Demarc; Menezes, Ana M; ter Riet, Gerben; Held, Ulrike; Domingo-Salvany, Antonia; Mosenifar, Zab; Antó, Josep M; et al. (BMJ Open, 2012)
BACKGROUND: Little evidence on the validity of simple and widely applicable tools to predict mortality in patients with chronic obstructive pulmonary disease (COPD) exists. OBJECTIVE: To conduct a large international study to validate the ADO index that uses age, dyspnoea and FEV(1) to predict 3-year mortality and to update it in order to make prediction of mortality in COPD patients as generalisable as possible. DESIGN: Individual subject data analysis of 10 European and American cohorts (n=13 914). SETTING: Population-based, primary, secondary and tertiary care. PATIENTS: COPD GOLD stages I-IV. MEASUREMENTS: We validated the original ADO index. We then obtained an updated ADO index in half of our cohorts to improve its predictive accuracy, which in turn was validated comprehensively in the remaining cohorts using discrimination, calibration and decision curve analysis and a number of sensitivity analyses. RESULTS: 1350 (9.7%) of all subjects with COPD (60% male, mean age 61 years, mean FEV(1) 66% predicted) had died at 3 years. The original ADO index showed high discrimination but poor calibration (p<0.001 for difference between predicted and observed risk). The updated ADO index (scores from 0 to 14) preserved excellent discrimination (area under curve 0.81, 95% CI 0.80 to 0.82) but showed much improved calibration with predicted 3-year risks from 0.7% (95% CI 0.6% to 0.9%, score of 0) to 64.5% (61.2% to 67.7%, score of 14). The ADO index showed higher net benefit in subjects at low-to-moderate risk of 3-year mortality than FEV(1) alone. INTERPRETATION: The updated 15-point ADO index accurately predicts 3-year mortality across the COPD severity spectrum and can be used to inform patients about their prognosis, clinical trial study design or benefit harm assessment of medical interventions.

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Nonesterified fatty acids and risk of sudden cardiac death in older adults. - Djoussé, Luc; Biggs, Mary L; Ix, Joachim H; Kizer, Jorge R; Lemaitre, Rozenn N; Sotoodehnia, Nona; Zieman, Susan J; Mozaffarian, Dariush; Tracy, Russell P; Mukamal, Kenneth J; Siscovick, David S (Circ Arrhythm Electrophysiol, 2012)
BACKGROUND: Although nonesterified fatty acids (NEFA) have been positively associated with coronary heart disease risk factors, limited and inconsistent data are available on the relation between NEFA and sudden cardiac death. METHODS AND RESULTS: Using a prospective design, we studied 4657 older men and women (mean age, 75 years) from the Cardiovascular Health Study (1992-2006) to evaluate the association between plasma NEFA and the risk of sudden cardiac death in older adults. Plasma concentrations of NEFA were measured using established enzymatic methods, and sudden death was adjudicated using medical records, death certificates, proxy interview, and autopsy reports. We used Cox proportional hazard models to estimate multivariable-adjusted relative risks. During a median follow-up of 10.0 years, 221 new cases of sudden cardiac death occurred. In a multivariable model adjusting for age, sex, race, clinic site, alcohol intake, smoking, prevalent coronary heart disease and heart failure, and self-reported health status, relative risks (95% confidence interval) for sudden cardiac death were 1.0 (ref), 1.15 (0.81-1.64), 1.06 (0.72-1.55), and 0.91 (0.60-1.38) across consecutive quartiles of NEFA concentration. In secondary analyses restricted to the first 5 years of follow-up, we also did not observe a statistically significant association between plasma NEFA and sudden cardiac death. CONCLUSIONS: Our data do not provide evidence for an association between plasma NEFA measured late in life and the risk of sudden cardiac death in older adults.
Keywords: Aged; Aged, 80 and over; Biomarkers; Death, Sudden, Cardiac; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Retrospective Studies; Risk Factors

Novel circulating fatty acid patterns and risk of cardiovascular disease: the Cardiovascular Health Study. - Imamura, Fumiaki; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Lichtenstein, Alice H; Matthan, Nirupa R; Herrington, David M; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2012)
BACKGROUND: Complex interplays of diet and metabolism influence circulating fatty acids (FAs), possibly constituting FA patterns related to cardiovascular disease (CVD) risk. OBJECTIVES: We aimed to derive FA patterns from circulating FAs, relate the patterns to CVD incidence, and extend the derived patterns to atherosclerosis progression in another independent cohort. DESIGN: We used principal component analysis (PCA) to derive FA patterns from 38 plasma phospholipid FAs in 2972 older adults in the Cardiovascular Health Study (CHS). Identified patterns were evaluated for prospective associations with 14-y incidence of CVD [ischemic heart disease (IHD) or stroke]. In another independent cohort of postmenopausal women with IHD, we evaluated associations of the CHS-derived patterns with 3.2-y progression of angiographically defined coronary atherosclerosis. RESULTS: Three distinct patterns were identified, characterized by higher proportions of trans FAs, de novo lipogenesis (DNL) FAs, and long-chain MUFAs (LCMUFAs). During 32,265 person-years, 780 incident CVD events occurred. The trans FA pattern was associated with higher CVD risk (multivariable-adjusted HR for the highest compared with the lowest quintiles = 1.58; 95% CI: 1.17, 2.12; P-trend = 0.006), primarily attributable to higher risk of stroke (HR: 2.46; 95% CI: 1.54, 3.92; P-trend = 0.005). The DNL and LCMUFA patterns were not associated with CVD incidence or with IHD or stroke (P-trend > 0.11 each). In the second cohort, the trans FA pattern, but not the other 2 patterns, was positively associated with progression of coronary atherosclerosis (P-trend < 0.05). CONCLUSIONS: PCA appears to provide informative circulating FA patterns. A pattern driven mainly by trans FA levels related to greater CVD risk in older adults and coronary atherosclerosis progression in women with IHD.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Disease Progression; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Myocardial Ischemia; Principal Component Analysis; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Trans Fatty Acids; United States

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Plasma fatty acid-binding protein 4, nonesterified fatty acids, and incident diabetes in older adults. - Djoussé, Luc; Khawaja, Owais; Bartz, Traci M; Biggs, Mary L; Ix, Joachim H; Zieman, Susan J; Kizer, Jorge R; Tracy, Russell P; Siscovick, David S; Mukamal, Kenneth J (Diabetes Care, 2012)
OBJECTIVE: To examine the relation of fatty acid-binding protein (FABP)4 and nonesterified fatty acids (NEFAs) to diabetes in older adults. RESEARCH DESIGN AND METHODS: We ascertained incident diabetes among 3,740 Cardiovascular Health Study participants (1992-2007) based on the use of hypoglycemic medications, fasting glucose ≥ 126 mg/dL, or nonfasting glucose ≥ 200 mg/dL. FABP4 and NEFA were measured on specimens collected between 1992 and 1993. RESULTS: Mean age of the 3,740 subjects studied was 74.8 years. For each SD increase in log FABP4, hazard ratios (HRs) for diabetes were 1.35 (95% CI 1.10-1.65) for women and 1.45 (1.13-1.85) for men controlling for age, race, education, physical activity, cystatin C, alcohol intake, smoking, self-reported health status, and estrogen use for women (P for sex-FABP4 interaction 0.10). BMI modified the FABP4-diabetes relation (P = 0.009 overall; 0.02 for women and 0.135 for men), in that statistically significant higher risk of diabetes was mainly seen in men with BMI <25 kg/m(2) (HR per SD: 1.78 [95% CI 1.13-2.81]). There was a modest and nonsignificant association of NEFA with diabetes (P(trend) = 0.21). However, when restricted to the first 5 years of follow-up, multivariable-adjusted HRs for diabetes were 1.0 (ref.), 1.68 (95% CI 1.12-2.53), and 1.63 (1.07-2.50) across consecutive tertiles of NEFA (P(trend) = 0.03). CONCLUSIONS: Plasma FABP4 was positively associated with incident diabetes in older adults, and such association was statistically significant in lean men only. A significant positive association between plasma NEFA and incident diabetes was observed during the first 5 years of follow-up.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Diabetes Mellitus; Fatty Acid-Binding Proteins; Fatty Acids, Nonesterified; Female; Humans; Male; Prospective Studies

Plasma free fatty acids and risk of atrial fibrillation (from the Cardiovascular Health Study). - Khawaja, Owais; Bartz, Traci M; Ix, Joachim H; Heckbert, Susan R; Kizer, Jorge R; Zieman, Susan J; Mukamal, Kenneth J; Tracy, Russell P; Siscovick, David S; Djoussé, Luc (Am J Cardiol, 2012)
Atrial fibrillation (AF) is a highly prevalent cardiac arrhythmia in clinical practice, affecting approximately 2.3 million residents of the United States and 4.5 million residents of the European Union. It is unclear whether plasma free fatty acids (FFAs) influence the risk of AF in older adults. The aim of this study was to prospectively examine the association between plasma FFAs and incident AF in a prospective cohort of 4,175 men and women ≥65 years old from the Cardiovascular Health Study. Plasma concentrations of FFAs were measured 2 times during the 1992 to 1993 examination. Incident AF was ascertained based on study electrocardiographic and hospitalization records during follow-up. We used Cox regression to estimate relative risks of AF. Average age at baseline was 74.6 ± 5.1 years. During a mean follow-up of 10.0 years, 1,041 new cases of AF occurred. Crude incidence rates of AF were 23.7, 23.3, 23.9, and 29.7 cases/1,000 person-years across consecutive quartiles of plasma FFAs. There was a positive association between plasma FFAs and risk of AF. Multivariable adjusted hazard ratios (95% confidence intervals) for incident AF were 1.00 (referent), 1.02 (0.85 to 1.21), 1.05 (0.88 to 1.26), and 1.29 (1.08 to 1.55) from the lowest to highest quartiles of FFAs, respectively. In a secondary analysis restricted to the first 5 years of follow-up, this association persisted. In conclusion, our data show an increased risk of AF with higher plasma FFAs in community-dwelling older adults.
Keywords: Aged; Atrial Fibrillation; C-Reactive Protein; Diabetes Mellitus, Type 2; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Lipoproteins, HDL; Lipoproteins, LDL; Male; Natriuretic Peptide, Brain; Obesity; Peptide Fragments; Prospective Studies; Sex Factors; Triglycerides; United States

Subclinical hyperthyroidism and the risk of coronary heart disease and mortality. - Collet, Tinh-Hai; Gussekloo, Jacobijn; Bauer, Douglas C; den Elzen, Wendy P J; Cappola, Anne R; Balmer, Philippe; Iervasi, Giorgio; Asvold, Bjørn O; Sgarbi, José A; Völzke, Henry; Gencer, Bariş; Maciel, Rui M B; et al. (Arch Intern Med, 2012)
BACKGROUND: Data from prospective cohort studies regarding the association between subclinical hyperthyroidism and cardiovascular outcomes are conflicting.We aimed to assess the risks of total and coronary heart disease (CHD) mortality, CHD events, and atrial fibrillation (AF) associated with endogenous subclinical hyperthyroidism among all available large prospective cohorts. METHODS: Individual data on 52 674 participants were pooled from 10 cohorts. Coronary heart disease events were analyzed in 22 437 participants from 6 cohorts with available data, and incident AF was analyzed in 8711 participants from 5 cohorts. Euthyroidism was defined as thyrotropin level between 0.45 and 4.49 mIU/L and endogenous subclinical hyperthyroidism as thyrotropin level lower than 0.45 mIU/L with normal free thyroxine levels, after excluding those receiving thyroid-altering medications. RESULTS: Of 52 674 participants, 2188 (4.2%) had subclinical hyperthyroidism. During follow-up, 8527 participants died (including 1896 from CHD), 3653 of 22 437 had CHD events, and 785 of 8711 developed AF. In age- and sex-adjusted analyses, subclinical hyperthyroidism was associated with increased total mortality (hazard ratio[HR], 1.24, 95% CI, 1.06-1.46), CHD mortality (HR,1.29; 95% CI, 1.02-1.62), CHD events (HR, 1.21; 95%CI, 0.99-1.46), and AF (HR, 1.68; 95% CI, 1.16-2.43).Risks did not differ significantly by age, sex, or preexisting cardiovascular disease and were similar after further adjustment for cardiovascular risk factors, with attributable risk of 14.5% for total mortality to 41.5% forAF in those with subclinical hyperthyroidism. Risks for CHD mortality and AF (but not other outcomes) were higher for thyrotropin level lower than 0.10 mIU/L compared with thyrotropin level between 0.10 and 0.44 mIU/L(for both, P value for trend, .03). CONCLUSION: Endogenous subclinical hyperthyroidism is associated with increased risks of total, CHD mortality, and incident AF, with highest risks of CHD mortality and AF when thyrotropin level is lower than 0.10 mIU/L.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Atrial Fibrillation; Cause of Death; Cohort Studies; Coronary Artery Disease; Female; Humans; Hyperthyroidism; Male; Middle Aged; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Analysis; Switzerland; Thyroid Function Tests; Thyrotropin; Young Adult

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Total and high-molecular-weight adiponectin and risk of incident diabetes in older people. - Kizer, Jorge R; Arnold, Alice M; Benkeser, David; Ix, Joachim H; Djoussé, Luc; Zieman, Susan J; Barzilay, Joshua I; Tracy, Russell P; Mantzoros, Christos S; Siscovick, David S; Mukamal, Kenneth J (Diabetes Care, 2012)
OBJECTIVE: To delineate the associations of total adiponectin, high-molecular-weight (HMW) adiponectin, and the HMW-to-total adiponectin ratio with diabetes in older adults. RESEARCH DESIGN AND METHODS: Total and HMW adiponectin were measured in a population-based study of older adults. The relations of total adiponectin, HMW adiponectin, and their ratio with incident diabetes (n = 309) were assessed in 3,802 individuals. RESULTS: Total and HMW adiponectin were highly correlated (r = 0.94). Analysis using cubic splines revealed that the associations between total and HMW adiponectin and new-onset diabetes were not linear. Specifically, after adjustment for confounders, there were similar inverse relationships for total (hazard ratio per SD 0.49 [95% CI 0.39-0.63]) and HMW adiponectin (0.42 [0.32-0.56]) with diabetes up to values of 20 and 10 mg/L, respectively, above which the associations plateaued. These associations persisted after adjustment for potential mediators (blood pressure, lipids, C-reactive protein, and homeostasis model assessment of insulin resistance [HOMA-IR]). There was, however, evidence of interaction by HOMA-IR in the lower range of adiponectin, with stronger inverse associations among insulin-sensitive than insulin-resistant participants. HMW-to-total adiponectin ratio showed a linear adjusted association with outcome, but this was abolished by inclusion of mediating variables. CONCLUSIONS: In this older cohort, increasing concentrations of total and HMW adiponectin were associated with comparably lower risks of diabetes, but these associations leveled off with further increases above concentrations of 20 and 10 mg/L, respectively. The more pronounced risk decreases at the lower range among participants without insulin resistance support a role for adiponectin that is independent of baseline hyperinsulinemia, but this will require further investigation.
Keywords: Adiponectin; Aged; Diabetes Mellitus; Female; Humans; Male; Risk Factors

Trans-fatty acid consumption and heart rate variability in 2 separate cohorts of older and younger adults. - Soares-Miranda, Luisa; Stein, Phyllis K; Imamura, Fumiaki; Sattelmair, Jacob; Lemaitre, Rozenn N; Siscovick, David S; Mota, Jorge; Mozaffarian, Dariush (Circ Arrhythm Electrophysiol, 2012)
BACKGROUND: Trans-fatty acid (TFA) consumption is associated with risk of coronary heart disease, and trans-18:2, but not trans-18:1, in red blood cell membranes has been associated with sudden cardiac arrest. Abnormal heart rate variability (HRV) reflects autonomic dysfunction and predicts cardiac death. Relationships between TFA consumption and HRV remain understudied. We determined whether total TFA consumption, as well as trans-18:1 and trans-18:2 TFA consumption, was independently associated with HRV in 2 independent cohorts in the United States and Portugal. METHODS AND RESULTS: In 2 independent cohorts of older US adults (Cardiovascular Health Study [CHS], age 72±5 years, 1989/1995) and young Portuguese adults (Porto, age 19±2 years, 2008/2010), we assessed habitual TFA intake by food frequency questionnaires in CHS (separately estimating trans-18:1 and trans-18:2) and multiple 24-hour recalls in Porto (estimating total TFA only, which in a subset correlated with circulating trans-18:2 but not trans-18:1, suggesting that we captured the former). HRV was assessed using 24-hour Holters in CHS (n=1076) and repeated short-term (5-minute) ECGs in Porto (n=160). We used multivariate-adjusted linear regression to relate TFA consumption to HRV cross-sectionally (CHS, Porto) and longitudinally (CHS). In CHS, higher trans-18:2 consumption was associated with lower 24-hour SD of all normal-to-normal intervals both cross-sectionally (-12%; 95% CI, -19% to -6%; P=0.001) and longitudinally (-15%; 95% CI, -25% to -4%; P= 0.009) and lower 24-hour SD of 5-minute average N-N intervals and mean of the 5-minute SD of N-N intervals calculated over 24 hours (P<0.05 each). Higher trans-18:1 consumption in CHS was associated with more favorable 24-hour HRV in particular time-domain indices (24-hour SD of all normal-to-normal intervals, SD of 5-minute average N-N intervals, mean of the 5-minute SD of N-N intervals calculated over 24 hours; P<0.05 each). In Porto, each higher SD TFA consumption was associated with 4% lower 5-minute 24-hour SD of all normal-to-normal intervals (95% CI, -8% to -1%; P=0.04) and 7% lower 5-minute square root of the mean of the squares of successive N-N differences (95% CI, -13% to -1%; P=0.04). CONCLUSIONS: Trans-18:2 consumption is associated with specific, less favorable indices of HRV in both older and young adults. Trans-18:1 consumption is associated with more favorable HRV indices in older adults. Our results support the need to investigate potential HRV-related mechanisms, whereby trans-18:2 may increase arrhythmic risk.
Keywords: Adolescent; Age Factors; Aged; Aging; Arrhythmias, Cardiac; Cohort Studies; Cross-Sectional Studies; Dietary Fats; Electrocardiography, Ambulatory; Feeding Behavior; Female; Heart Rate; Humans; Linear Models; Longitudinal Studies; Male; Multivariate Analysis; Portugal; Predictive Value of Tests; Prospective Studies; Risk Assessment; Risk Factors; Surveys and Questionnaires; Trans Fatty Acids; United States; Young Adult

Variation in the lysyl oxidase (LOX) gene is associated with keratoconus in family-based and case-control studies. - Bykhovskaya, Yelena; Li, Xiaohui; Epifantseva, Irina; Haritunians, Talin; Siscovick, David; Aldave, Anthony; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Taylor, Kent D; Rotter, Jerome I; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2012)
PURPOSE: Keratoconus is a bilateral noninflammatory progressive corneal disorder with complex genetic inheritance and a common cause for cornea transplantation in young adults. A genomewide linkage scan in keratoconus families identified a locus at 5q23.2, overlapping the gene coding for the lysyl oxidase (LOX). LOX encodes an enzyme responsible for collagen cross-linking in a variety of tissues including the cornea. Corneal collagen cross-linking with long-wave ultraviolet light and riboflavin is a promising new treatment for keratoconus. To determine whether LOX is a genetic determinant of the pathogenesis of keratoconus, we analyzed association results of LOX polymorphisms in two independent case-control samples and in keratoconus families. METHODS: Association results were analyzed of single-nucleotide polymorphisms (SNPs) in the LOX gene from a Genome-Wide Association Study (GWAS) investigation in two independent panels of patients with keratoconus and controls and in keratoconus families. RESULTS: Evidence of association was found at SNPs rs10519694 and rs2956540 located in intron 4 of LOX in the GWAS discovery case-control panel with P values of 2.3×10(-3) and 7×10(-3), respectively. The same two SNPs were found to be associated with keratoconus by family-based association testing with P values of 2.7×10(-3) and 7.7×10(-4), respectively. Meta P values of 4.0×10(-5) and 4.0×10(-7) were calculated for SNPs rs10519694 and rs2956540 by analyzing case-control and family samples simultaneously. Sequencing of LOX exons in a subset of keratoconus patients identified two polymorphisms, rs1800449 and rs2288393, located in LOX transcripts I and II, associated with keratoconus in case-control and family samples with a meta P value of 0.02. CONCLUSIONS: Results provided strong genetic evidence that LOX variants lead to increased susceptibility to developing of keratoconus.
Keywords: Case-Control Studies; Cornea; Corneal Topography; DNA; Family; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Polymorphism, Genetic; Protein-Lysine 6-Oxidase

Circulating 25-hydroxyvitamin D is associated with insulin resistance cross-sectionally but not longitudinally in older adults: The Cardiovascular Health Study. - Danziger, John; Biggs, Mary L; Niemi, Matt; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; de Boer, Ian H; Siscovick, David S; Kestenbaum, Bryan; Mukamal, Kenneth J (Metabolism, 2013)
BACKGROUND: Despite extensive study, the role of vitamin D in insulin resistance and secretion remains unclear. OBJECTIVE: To examine the cross-sectional and longitudinal relationships between 25-hydroxyvitamin D (25(OH)D) concentrations and indices of insulin resistance and secretion in older adults. METHODS AND RESULTS: Among 2134 participants of the Cardiovascular Health Study who were free from cardiovascular disease, we measured serum 25(OH)D concentrations in samples collected in 1992-1993. We examined insulin resistance and secretion using Homeostasis Model Assessment (HOMA) estimates cross-sectionally and among 1469 participants who had repeated HOMA measures four years later (1996-1997). In cross-sectional analysis, each 10 ng/mL increment in 25(OH)D concentration was associated with a 0.09 lower adjusted HOMA-IR [95% CI (-0.17, -0.02), p=0.01]. However, baseline 25(OH)D concentrations were not associated with change in HOMA-IR over 4 years of follow up (p=0.48). 25(OH)D concentrations were not associated with insulin secretion, as determined by HOMA-β, in either cross-sectional or longitudinal analysis. CONCLUSIONS: Circulating 25(OH)D concentrations are associated with lower insulin resistance in cross-sectional but not longitudinal analyses. Whether this reflects residual confounding in cross-sectional analyses or the short-term nature of the relationship between vitamin D and insulin sensitivity will require trials with repeated measures of these factors.
Keywords: Adiposity; Aged; Anthropometry; Cardiovascular Diseases; Cross-Sectional Studies; Exercise; Female; Humans; Hydroxycholecalciferols; Inflammation; Insulin; Insulin Resistance; Longitudinal Studies; Male; Middle Aged; Obesity; Risk Factors; Surveys and Questionnaires

Common carotid intima-media thickness does not add to Framingham risk score in individuals with diabetes mellitus: the USE-IMT initiative. - den Ruijter, H M; Peters, S A E; Groenewegen, K A; Anderson, T J; Britton, A R; Dekker, J M; Engstrom, G; Eijkemans, M J; Evans, G W; de Graaf, J; Grobbee, D E; Hedblad, B; et al. (Diabetologia, 2013)
AIMS/HYPOTHESIS: The aim of this work was to investigate whether measurement of the mean common carotid intima-media thickness (CIMT) improves cardiovascular risk prediction in individuals with diabetes. METHODS: We performed a subanalysis among 4,220 individuals with diabetes in a large ongoing individual participant data meta-analysis involving 56,194 subjects from 17 population-based cohorts worldwide. We first refitted the risk factors of the Framingham heart risk score on the individuals without previous cardiovascular disease (baseline model) and then expanded this model with the mean common CIMT (CIMT model). The absolute 10 year risk for developing a myocardial infarction or stroke was estimated from both models. In individuals with diabetes we compared discrimination and calibration of the two models. Reclassification of individuals with diabetes was based on allocation to another cardiovascular risk category when mean common CIMT was added. RESULTS: During a median follow-up of 8.7 years, 684 first-time cardiovascular events occurred among the population with diabetes. The C statistic was 0.67 for the Framingham model and 0.68 for the CIMT model. The absolute 10 year risk for developing a myocardial infarction or stroke was 16% in both models. There was no net reclassification improvement with the addition of mean common CIMT (1.7%; 95% CI -1.8, 3.8). There were no differences in the results between men and women. CONCLUSIONS/INTERPRETATION: There is no improvement in risk prediction in individuals with diabetes when measurement of the mean common CIMT is added to the Framingham risk score. Therefore, this measurement is not recommended for improving individual cardiovascular risk stratification in individuals with diabetes.
Keywords: Cardiovascular Diseases; Carotid Intima-Media Thickness; Diabetes Mellitus; Humans; Myocardial Infarction; Risk Factors; Stroke

Common FABP4 genetic variants and plasma levels of fatty acid binding protein 4 in older adults. - Mukamal, Kenneth J; Wilk, Jemma B; Biggs, Mary L; Jensen, Majken K; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Mozaffarian, Dariush; Psaty, Bruce M; Siscovick, David S; Djoussé, Luc (Lipids, 2013)
We examined common variants in the fatty acid binding protein 4 gene (FABP4) and plasma levels of FABP4 in adults aged 65 and older from the Cardiovascular Health Study. We genotyped rs16909187, rs1054135, rs16909192, rs10808846, rs7018409, rs2290201, and rs6992708 and measured circulating FABP4 levels among 3190 European Americans and 660 African Americans. Among European Americans, the minor alleles of six single nucleotide polymorphisms (SNP) were associated with lower FABP4 levels (all p ≤ 0.01). Among African Americans, the SNP with the lowest minor allele frequency was associated with lower FABP4 levels (p = 0.015). The C-A haplotype of rs16909192 and rs2290201 was associated with lower FABP4 levels in both European Americans (frequency = 16 %; p = 0.001) and African Americans (frequency = 8 %; p = 0.04). The haplotype combined a SNP in the first intron with one in the 3'untranslated region. However, the alleles associated with lower FABP4 levels were associated with higher fasting glucose in meta-analyses from the MAGIC consortium. These results demonstrate associations of common SNP and haplotypes in the FABP4 gene with lower plasma FABP4 but higher fasting glucose levels.
Keywords: African Americans; Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Fatty Acid-Binding Proteins; Female; Gene Frequency; Genetic Association Studies; Haplotypes; Humans; Insulin; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Cystatin C versus creatinine in determining risk based on kidney function. - Shlipak, Michael G; Matsushita, Kunihiro; Arnlöv, Johan; Inker, Lesley A; Katz, Ronit; Polkinghorne, Kevan R; Rothenbacher, Dietrich; Sarnak, Mark J; Astor, Brad C; Coresh, Josef; Levey, Andrew S; Gansevoort, Ron T (N Engl J Med, 2013)
BACKGROUND: Adding the measurement of cystatin C to that of serum creatinine to determine the estimated glomerular filtration rate (eGFR) improves accuracy, but the effect on detection, staging, and risk classification of chronic kidney disease across diverse populations has not been determined. METHODS: We performed a meta-analysis of 11 general-population studies (with 90,750 participants) and 5 studies of cohorts with chronic kidney disease (2960 participants) for whom standardized measurements of serum creatinine and cystatin C were available. We compared the association of the eGFR, as calculated by the measurement of creatinine or cystatin C alone or in combination with creatinine, with the rates of death (13,202 deaths in 15 cohorts), death from cardiovascular causes (3471 in 12 cohorts), and end-stage renal disease (1654 cases in 7 cohorts) and assessed improvement in reclassification with the use of cystatin C. RESULTS: In the general-population cohorts, the prevalence of an eGFR of less than 60 ml per minute per 1.73 m(2) of body-surface area was higher with the cystatin C-based eGFR than with the creatinine-based eGFR (13.7% vs. 9.7%). Across all eGFR categories, the reclassification of the eGFR to a higher value with the measurement of cystatin C, as compared with creatinine, was associated with a reduced risk of all three study outcomes, and reclassification to a lower eGFR was associated with an increased risk. The net reclassification improvement with the measurement of cystatin C, as compared with creatinine, was 0.23 (95% confidence interval [CI], 0.18 to 0.28) for death and 0.10 (95% CI, 0.00 to 0.21) for end-stage renal disease. Results were generally similar for the five cohorts with chronic kidney disease and when both creatinine and cystatin C were used to calculate the eGFR. CONCLUSIONS: The use of cystatin C alone or in combination with creatinine strengthens the association between the eGFR and the risks of death and end-stage renal disease across diverse populations. (Funded by the National Kidney Foundation and others.).
Keywords: Creatinine; Cystatin C; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Kidney Function Tests; Reference Standards; Renal Insufficiency, Chronic; Risk; Risk Assessment

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Fatty acid-binding protein 4 and incident heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Bartz, Traci M; Ix, Joachim H; Kochar, Jinesh; Kizer, Jorge R; Gottdiener, John S; Tracy, Russell P; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Zieman, Susan J (Eur J Heart Fail, 2013)
AIM: To examine the association of plasma fatty acid-binding protein 4 (FABP4) with incident heart failure. METHODS AND RESULTS: In a prospective study of 4179 participants from the Cardiovascular Health Study, we measured plasma FABP4 on blood specimens collected between 1992 and 1993. Incident heart failure was adjudicated by an endpoint committee and we used a Cox proportional hazards model to calculate hazard ratios (HRs) of heart failure. The average age at baseline was 75 years. During a median follow-up of 10.7 years, 1182 cases of incident heart failure occurred. We observed a positive association between FABP4 and heart failure in the minimally adjusted models [HR 1.32, 95% confidence interval (CI) 1.25-1.38 per 1 SD higher FABP4] that was attenuated upon adjustment for potential confounders, mostly kidney function and body mass index (corresponding HR 1.09, 95% CI 1.01-1.17). In a subsample of heart failure cases with available data on LV systolic function, FABP4 was not associated with heart failure with or without preserved LV systolic function. Exclusion of people with unintentional weight loss and self-reported fair/poor health status did not alter the conclusion. CONCLUSION: An elevated plasma concentration of FABP4 was associated with a modestly higher risk of heart failure in older adults in the USA after adjustment for confounding factors.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Fatty Acid-Binding Proteins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Male; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Ventricular Function, Left

Fetuin-A, type 2 diabetes, and risk of cardiovascular disease in older adults: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Shlipak, Michael; Ix, Joachim H (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A, a hepatic secretory protein that simultaneously inhibits arterial calcification and insulin action, is associated with type 2 diabetes, but its association with cardiovascular disease (CVD) is uncertain. Preliminary studies suggest that the association of fetuin-A with CVD might differ among individuals with or without type 2 diabetes. RESEARCH DESIGN AND METHODS: This was a prospective study of 3,810 community-living individuals older than 65 years (511 with type 2 diabetes) and free of CVD in 1992 when fetuin-A levels were measured. Participants were followed-up for incident CVD through June 2008. RESULTS: Mean age was 75 years, and 61% were women; 1,456 participants had an incident CVD event (248 among individuals with type 2 diabetes). The association of fetuin-A with CVD was modified by type 2 diabetes (P interaction = 0.02). Higher fetuin-A was associated with lower CVD risk among persons without type 2 diabetes [hazard ratio per SD 0.1 g/L higher fetuin-A, 0.93 (95% CI, 0.88-0.99)], whereas a trend in the opposite direction was observed among individuals with type 2 diabetes, although it was not statistically significant [1.07 (0.93-1.22)]. Among individuals without type 2 diabetes, similar effect modification was observed by obesity and insulin resistance. Consistently, higher fetuin-A was associated with lower CVD risk only in the subgroups without obesity or with HOMA-IR below the median [0.91 (0.85-0.97) and 0.87 (0.79-0.95), respectively]. CONCLUSIONS: The association of fetuin-A with risk of CVD differs among elderly individuals with and without insulin resistance or type 2 diabetes.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Fetuins; Humans; Incidence; Longitudinal Studies; Male; Risk Factors

Fibroblast growth factor 23, bone mineral density, and risk of hip fracture among older adults: the cardiovascular health study. - Jovanovich, Anna; Bůzková, Petra; Chonchol, Michel; Robbins, John; Fink, Howard A; de Boer, Ian H; Kestenbaum, Bryan; Katz, Ronit; Carbone, Laura; Lee, Jennifer; Laughlin, Gail A; Mukamal, Kenneth J; et al. (J Clin Endocrinol Metab, 2013)
CONTEXT: Fibroblast growth factor 23 (FGF23) is a phosphaturic hormone that also inhibits calcitriol synthesis. OBJECTIVE: Our objective was to evaluate the relationships of plasma FGF23 concentrations with bone mineral density (BMD) and hip fracture in community-dwelling older adults. DESIGN AND SETTING: Linear regression and Cox proportional hazard models were used to examine the associations of plasma FGF23 concentrations with BMD and incident hip fracture, respectively. Analyses were also stratified by chronic kidney disease. PARTICIPANTS: Participants included 2008 women and 1329 men ≥65 years from the 1996 to 1997 Cardiovascular Health Study visit. MAIN OUTCOME MEASURES: Dual x-ray absorptiometry measured total hip (TH) and lumbar spine (LS) BMD in 1291 participants. Hip fracture incidence was assessed prospectively through June 30, 2008 by hospitalization records in all participants. RESULTS: Women had higher plasma FGF23 concentrations than men (75 [56-107] vs 66 [interquartile range = 52-92] relative units/mL; P < .001). After adjustment, higher FGF23 concentrations were associated with greater total hip and lumbar spine BMD in men only (β per doubling of FGF23 = 0.02, with 95% confidence interval [CI] = 0.001-0.04 g/cm(2), and 0.03 with 95% CI = 0.01-0.06 g/cm(2)). During 9.6 ± 5.1-11.0 years of follow-up, 328 hip fractures occurred. Higher FGF23 concentrations were not associated with hip fracture risk in women or men (adjusted hazard ratio = 0.95, with 95% CI = 0.78-1.15, and 1.09 with 95% CI = 0.82-1.46 per doubling of FGF23). Results did not differ by chronic kidney disease status (P > .4 for interactions). CONCLUSIONS: In this large prospective cohort of community-dwelling older adults, higher FGF23 concentrations were weakly associated with greater lumbar spine and total hip BMD but not with hip fracture risk.
Keywords: Aged; Aged, 80 and over; Bone Density; Female; Fibroblast Growth Factors; Hip Fractures; Humans; Longitudinal Studies; Male; Middle Aged; Prospective Studies; Risk; Spinal Fractures

Fibroblast growth factor 23, left ventricular mass, and left ventricular hypertrophy in community-dwelling older adults. - Jovanovich, Anna; Ix, Joachim H; Gottdiener, John; McFann, Kim; Katz, Ronit; Kestenbaum, Bryan; de Boer, Ian H; Sarnak, Mark; Shlipak, Michael G; Mukamal, Kenneth J; Siscovick, David; Chonchol, Michel (Atherosclerosis, 2013)
OBJECTIVES: In chronic kidney disease (CKD), high FGF23 concentrations are associated with left ventricular hypertrophy (LVH), cardiovascular events, and death. The associations of FGF23 with left ventricular mass (LVM) and LVH in the general population and the influence of CKD remains uncertain. METHODS: C-terminal plasma FGF23 concentrations were measured, and LVM and LVH evaluated by echocardiogram among 2255 individuals ≥65 years in the Cardiovascular Health Study. Linear regression analysis adjusting for demographics, cardiovascular, and kidney related risk factors examined the associations of FGF23 concentrations with LVM. Analyses were stratified by CKD status and adjusted linear and logistic regression analysis explored the associations of FGF23 with LVM and LVH. RESULTS: Among the entire cohort, higher FGF23 concentrations were associated with greater LVM in adjusted analyses (β = 6.71 [95% CI 4.35-9.01] g per doubling of FGF23). 32% (n = 624) had CKD (eGFR <60 mL/min/1.73 m(2) and/or urine albumin-to-creatinine ratio >30 mg/g). Associations were stronger among participants with CKD (p interaction = 0.006): LVM β = 9.71 [95% CI 5.86-13.56] g per doubling of FGF23 compared to those without CKD (β = 3.44 [95% CI 0.77, 6.11] g per doubling of FGF23). While there was no significant interaction between FGF23 and CKD for LVH (p interaction = 0.25), the OR (1.46 95% CI [1.20-1.77]) in the CKD group was statistically significant and of larger magnitude than the OR for in the no CKD group (1.12 [95% CI 0.97-1.48]). CONCLUSION: In a large cohort of older community-dwelling adults, higher FGF23 concentrations were associated with greater LVM and LVH with stronger relationships in participants with CKD.
Keywords: Aged; Female; Fibroblast Growth Factors; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Longitudinal Studies; Male; Renal Insufficiency, Chronic; Risk Factors; Ultrasonography

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Gene-centric meta-analyses of 108 912 individuals confirm known body mass index loci and reveal three novel signals. - Guo, Yiran; Lanktree, Matthew B; Taylor, Kira C; Hakonarson, Hakon; Lange, Leslie A; Keating, Brendan J (Hum Mol Genet, 2013)
Recent genetic association studies have made progress in uncovering components of the genetic architecture of the body mass index (BMI). We used the ITMAT-Broad-Candidate Gene Association Resource (CARe) (IBC) array comprising up to 49 320 single nucleotide polymorphisms (SNPs) across ~2100 metabolic and cardiovascular-related loci to genotype up to 108 912 individuals of European ancestry (EA), African-Americans, Hispanics and East Asians, from 46 studies, to provide additional insight into SNPs underpinning BMI. We used a five-phase study design: Phase I focused on meta-analysis of EA studies providing individual level genotype data; Phase II performed a replication of cohorts providing summary level EA data; Phase III meta-analyzed results from the first two phases; associated SNPs from Phase III were used for replication in Phase IV; finally in Phase V, a multi-ethnic meta-analysis of all samples from four ethnicities was performed. At an array-wide significance (P < 2.40E-06), we identify novel BMI associations in loci translocase of outer mitochondrial membrane 40 homolog (yeast) - apolipoprotein E - apolipoprotein C-I (TOMM40-APOE-APOC1) (rs2075650, P = 2.95E-10), sterol regulatory element binding transcription factor 2 (SREBF2, rs5996074, P = 9.43E-07) and neurotrophic tyrosine kinase, receptor, type 2 [NTRK2, a brain-derived neurotrophic factor (BDNF) receptor gene, rs1211166, P = 1.04E-06] in the Phase IV meta-analysis. Of 10 loci with previous evidence for BMI association represented on the IBC array, eight were replicated, with the remaining two showing nominal significance. Conditional analyses revealed two independent BMI-associated signals in BDNF and melanocortin 4 receptor (MC4R) regions. Of the 11 array-wide significant SNPs, three are associated with gene expression levels in both primary B-cells and monocytes; with rs4788099 in SH2B adaptor protein 1 (SH2B1) notably being associated with the expression of multiple genes in cis. These multi-ethnic meta-analyses expand our knowledge of BMI genetics.
Keywords: Body Mass Index; Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide

Genetic association of COL5A1 variants in keratoconus patients suggests a complex connection between corneal thinning and keratoconus. - Li, Xiaohui; Bykhovskaya, Yelena; Canedo, Ana Laura Caiado; Haritunians, Talin; Siscovick, David; Aldave, Anthony J; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2013)
PURPOSE: Single nucleotide polymorphisms (SNPs) located near or within the COL5A1 gene, at 9q34.2-q34.3 chromosomal region have been reported in association with central corneal thickness (CCT). Using family linkage analysis, we identified a keratoconus susceptibility locus at 9q34. These findings led us to perform an association study between COL5A1 variation and keratoconus susceptibility. METHODS: A Caucasian case-control cohort of 222 keratoconus patients and 3324 controls was selected as the discovery panel. An independent case-control panel of 304 cases and 518 controls and a family panel of 186 subjects were replicated for genotyping and association. Forty-four SNPs (21 for discovery and 23 for fine-mapping) spanning 300 kilobases in and around COL5A1 were genotyped and tested for genetic association. Logistic regression models implemented in PLINK were used to test for association in case controls. Generalized estimating equation models accounting for familial correlations implemented in genome-wide interaction analyses with family data were used for association testing in families. RESULTS: Two CCT associated SNPs (rs1536482 and rs7044529 near and within COL5A1) were identified in the keratoconus discovery cohort (P values of 6.5 × 10(-3) and 7.4 × 10(-3)). SNP rs1536482 was replicated in the second case-control sample (P = 0.02), and SNP rs7044529 was replicated in a keratoconus family panel (P = 0.03). Meta P values of rs1536482 and rs7044529 in the keratoconus cohorts were 1.5 × 10(-4) (odds ratio [OR] = 1.30) and 2.9 × 10(-3) (OR = 1.39). After Bonferroni correction, the association of SNP rs1536482 remained significant (P = 6.5 × 10(-3)). CONCLUSIONS: SNPs in the COL5A1 region, which regulate normal variation in CCT, may play a role in the thinning associated with keratoconus.
Keywords: Adult; Aged; Collagen Type V; Cornea; Corneal Topography; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Male; Microscopy, Acoustic; Middle Aged; Polymorphism, Single Nucleotide; Tomography, Optical Coherence

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genetically elevated fetuin-A levels, fasting glucose levels, and risk of type 2 diabetes: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Psaty, Bruce M; Ix, Joachim H; Mukamal, Kenneth J (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A levels are associated with higher risk of type 2 diabetes, but it is unknown if the association is causal. We investigated common (>5%) genetic variants in the fetuin-A gene (AHSG) fetuin-A levels, fasting glucose, and risk of type 2 diabetes. RESEARCH DESIGN AND METHODS: Genetic variation, fetuin-A levels, and fasting glucose were assessed in 2,893 Caucasian and 542 African American community-living individuals 65 years of age or older in 1992-1993. RESULTS: Common AHSG variants (rs4917 and rs2248690) were strongly associated with fetuin-A concentrations (P<0.0001). In analyses of 259 incident cases of type 2 diabetes, the single nucleotide polymorphisms (SNPs) were not associated with diabetes risk during follow-up and similar null associations were observed when 579 prevalent cases were included. As expected, higher fetuin-A levels were associated with higher fasting glucose concentrations (1.9 mg/dL [95% CI, 1.2-2.7] higher per SD in Caucasians), but Mendelian randomization analyses using both SNPs as unbiased proxies for measured fetuin-A did not support an association between genetically predicted fetuin-A levels and fasting glucose (-0.3 mg/dL [95% CI, -1.9 to 1.3] lower per SD in Caucasians). The difference between the associations of fasting glucose with actual and genetically predicted fetuin-A level was statistically significant (P=0.001). Results among the smaller sample of African Americans trended in similar directions but were statistically insignificant. CONCLUSIONS: Common variants in the AHSG gene are strongly associated with plasma fetuin-A concentrations, but not with risk of type 2 diabetes or glucose concentrations, raising the possibility that the association between fetuin-A and type 2 diabetes may not be causal.
Keywords: alpha-2-HS-Glycoprotein; Blood Glucose; Diabetes Mellitus, Type 2; Fasting; Female; Genotype; Humans; Male; Polymorphism, Single Nucleotide

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

Long-chain monounsaturated Fatty acids and incidence of congestive heart failure in 2 prospective cohorts. - Imamura, Fumiaki; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Steffen, Lyn M; Folsom, Aaron R; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2013)
BACKGROUND: Decades-old animal experiments suggested that dietary long-chain monounsaturated fatty acids (LCMUFAs) caused cardiotoxicity, leading, for example, development of Canola oil (Canadian oil low in erucic acid) from rapeseed. However, potential cardiotoxicity in humans and contemporary dietary sources of LCMUFAs are unknown. METHODS AND RESULTS: We prospectively investigated the associations of plasma phospholipid LCMUFAs (20:1, 22:1, and 24:1), assessed as objective biomarkers of exposure, with incidence congestive heart failure in 2 independent cohorts: 3694 older adults (mean age, 75.2±5.2 years) in the Cardiovascular Health Study (CHS; 1992-2006) and 3577 middle-aged adults (mean age, 54.1±5.8 years) in the Atherosclerosis Risk in Communities Study, Minnesota subcohort (ARIC; 1987-2008). We further examined dietary correlates of circulating LCMUFAs in CHS and ARIC and US dietary sources of LCMUFAs in the 2003-2010 National Health and Nutrition Examination Survey (NHANES). In CHS, 997 congestive heart failure events occurred during 39 238 person-years; in ARIC, 330 events congestive heart failure events occurred during 64 438 person-years. After multivariable adjustment, higher levels of 22:1 and 24:1 were positively associated with greater incident congestive heart failure in both CHS and ARIC; hazard ratios were 1.34 (95% confidence interval, 1.02-1.76) and 1.57 (95% confidence interval, 1.11-2.23) for highest versus lowest quintiles of 22:1, respectively, and 1.75 (95% confidence interval, 1.23-2.50) and 1.92 (95% confidence interval, 1.22-3.03) for 24:1, respectively (P for trend ≤0.03 each). A variety of foods were related to circulating LCMUFAs in CHS and ARIC, consistent with food sources of LCMUFAs in NHANES, including fish, poultry, meats, whole grains, and mustard. CONCLUSIONS: Higher circulating levels of 22:1 and 24:1, with apparently diverse dietary sources, were associated with incident congestive heart failure in 2 independent cohorts, suggesting possible cardiotoxicity of LCMUFAs in humans.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Dietary Fats; Fatty Acids, Monounsaturated; Feeding Behavior; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Nutrition Surveys; Prospective Studies; Risk Factors; Stroke

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Plasma Fatty Acid binding protein 4 and risk of sudden cardiac death in older adults. - Djoussé, Luc; Maziarz, Marlena; Biggs, Mary L; Ix, Joachim H; Zieman, Susan J; Kizer, Jorge R; Lemaitre, Rozenn N; Mozaffarian, Dariush; Tracy, Russell P; Mukamal, Kenneth J; Siscovick, David S; Sotoodehnia, Nona (Cardiol Res Pract, 2013)
Although fatty acid binding protein 4 (FABP4) may increase risk of diabetes and exert negative cardiac inotropy, it is unknown whether plasma concentrations of FABP4 are associated with incidence of sudden cardiac death (SCD). We prospectively analyzed data on 4,560 participants of the Cardiovascular Health Study. FABP4 was measured at baseline using ELISA, and SCD events were adjudicated through review of medical records. We used Cox proportional hazards to estimate effect measures. During a median followup of 11.8 years, 146 SCD cases occurred. In a multivariable model adjusting for demographic, lifestyle, and metabolic factors, relative risk of SCD associated with each higher standard deviation (SD) of plasma FABP4 was 1.15 (95% CI: 0.95-1.38), P = 0.15. In a secondary analysis stratified by prevalent diabetes status, FABP4 was associated with higher risk of SCD in nondiabetic participants, (RR per SD higher FABP4: 1.33 (95% CI: 1.07-1.65), P = 0.009) but not in diabetic participants (RR per SD higher FABP4: 0.88 (95% CI: 0.62-1.27), P = 0.50), P for diabetes-FABP4 interaction 0.049. In summary, a single measure of plasma FABP4 obtained later in life was not associated with the risk of SCD in older adults overall. Confirmation of our post-hoc results in nondiabetic people in other studies is warranted.

Plasma free fatty acids and risk of heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Benkeser, David; Arnold, Alice; Kizer, Jorge R; Zieman, Susan J; Lemaitre, Rozenn N; Tracy, Russell P; Gottdiener, John S; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Ix, Joachim H (Circ Heart Fail, 2013)
BACKGROUND: Although plasma free fatty acid (FFA) concentrations have been associated with lipotoxicity, apoptosis, and risk of diabetes mellitus and coronary heart disease, it is unclear whether FFA levels are associated with heart failure (HF). METHODS AND RESULTS: To test the hypothesis that plasma concentration of FFAs is positively associated with incident HF, we prospectively analyzed data on 4248 men and women free of HF at baseline and >65 years old from the Cardiovascular Health Study. FFA concentration was measured in duplicate by the Wako enzymatic method. Incident HF was validated by a centralized Events Committee. We used Cox proportional hazards to estimate the hazard ratio of HF per SD of FFAs. During a median follow-up of 10.5 years, a total of 1286 new cases of HF occurred. In a multivariable model adjusting for clinic site, comorbidity, demographic, anthropometric, and lifestyle factors, each SD (0.2 mEq/L) higher plasma FFA was associated with 12% (95% confidence interval, 6%-19%) higher risk of HF. Controlling for time-varying diabetes mellitus and coronary heart disease did not change the results (hazard ratio per SD, 1.16 [95% confidence interval, 1.09-1.23]). CONCLUSIONS: A single measure of plasma FFA obtained later in life is associated with a higher risk of HF in older adults. Additional studies are needed to explore biological mechanisms by which FFAs may influence the risk of HF and determine whether FFAs could serve as a novel pharmacological target for HF prevention.
Keywords: Aged; Aged, 80 and over; Biomarkers; Comorbidity; Fatty Acids, Nonesterified; Female; Heart Failure; Humans; Incidence; Kaplan-Meier Estimate; Linear Models; Male; Multivariate Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States

Prediction and classification of cardiovascular disease risk in older adults with diabetes. - Mukamal, K J; Kizer, J R; Djoussé, L; Ix, J H; Zieman, S; Siscovick, D S; Sibley, C T; Tracy, R P; Arnold, A M (Diabetologia, 2013)
AIMS/HYPOTHESIS: We sought to derive and validate a cardiovascular disease (CVD) prediction algorithm for older adults with diabetes, and evaluate the incremental benefit of adding novel circulating biomarkers and measures of subclinical atherosclerosis. METHODS: As part of the Cardiovascular Health Study (CHS), a population-based cohort of adults aged ≥65 years, we examined the 10 year risk of myocardial infarction, stroke and cardiovascular death in 782 older adults with diabetes, in whom 265 events occurred. We validated predictive models in 843 adults with diabetes, who were followed for 7 years in a second cohort, the Multi-Ethnic Study of Atherosclerosis (MESA); here 71 events occurred. RESULTS: The best fitting standard model included age, smoking, systolic blood pressure, total and HDL-cholesterol, creatinine and the use of glucose-lowering agents; however, this model had a C statistic of 0.64 and poorly classified risk in men. Novel biomarkers did not improve discrimination or classification. The addition of ankle-brachial index, electrocardiographic left ventricular hypertrophy and internal carotid intima-media thickness modestly improved discrimination (C statistic 0.68; p = 0.002) and classification (net reclassification improvement [NRI] 0.12; p = 0.01), mainly in those remaining free of CVD. Results were qualitatively similar in the MESA, with a change in C statistic from 0.65 to 0.68 and an NRI of 0.09 upon inclusion of subclinical disease measures. CONCLUSIONS/INTERPRETATION: Standard clinical risk factors and novel biomarkers poorly discriminate and classify CVD risk in older adults with diabetes. The inclusion of subclinical atherosclerotic measures modestly improves these features, but to develop more robust risk prediction, a better understanding of the pathophysiology and determinants of CVD in this patient group is needed.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Myocardial Infarction; Regression Analysis; Risk Factors; Stroke

Risk factors for type 2 diabetes mellitus preceded by β-cell dysfunction, insulin resistance, or both in older adults: the Cardiovascular Health Study. - Imamura, Fumiaki; Mukamal, Kenneth J; Meigs, James B; Luchsinger, José A; Ix, Joachim H; Siscovick, David S; Mozaffarian, Dariush (Am J Epidemiol, 2013)
Insulin resistance (IR) and pancreatic β-cell dysfunction lead to type 2 diabetes mellitus (DM). We tested whether risk factors would differ for DM that was preceded predominantly by IR, β-cell dysfunction, or both among 4,384 older adults (mean age, 72.7 (standard deviation, 5.6) years) in the Cardiovascular Health Study, which was conducted in North Carolina, California, Maryland, and Pennsylvania (1989-2007). When evaluating established risk factors, we found older age, greater adiposity, higher systolic blood pressure, a lower high-density lipoprotein cholesterol level, a higher triglyceride level, and a lower alcohol intake to be independently associated with greater IR but, conversely, with better β-cell function (P < 0.001). The prospective associations between some risk factors and incident DM varied significantly depending on whether DM was preceded predominantly by IR, β-cell dysfunction, or both. For example, obesity and lower high-density lipoprotein cholesterol levels were positively associated with DM preceded predominantly by IR (hazard ratio (HR) = 5.02, 95% confidence interval (CI): 2.81, 9.00; and HR = 1.97, 95% CI: 1.32, 2.93, respectively), with a significant association with and an insignificant trend toward a lower risk of DM preceded predominantly by β-cell dysfunction (HR = 0.33, 95% CI: 0.14, 0.80; and HR = 0.78, 95% CI: 0.43, 1.39, respectively). In conclusion, among older adults, DM risk factors were differentially associated with DM preceded predominantly by IR or β-cell dysfunction. Biologic and clinical implications of putative subtypes of DM require further investigation.
Keywords: Adiposity; Age Factors; Aged; Aged, 80 and over; Aging; Alcohol Drinking; Blood Pressure; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Insulin Resistance; Insulin-Secreting Cells; Lipids; Male; Prospective Studies; Risk Factors; Socioeconomic Factors; United States

Risk of venous thromboembolism associated with single and combined effects of Factor V Leiden, Prothrombin 20210A and Methylenetethraydrofolate reductase C677T: a meta-analysis involving over 11,000 cases and 21,000 controls. - Simone, Benedetto; De Stefano, Valerio; Leoncini, Emanuele; Zacho, Jeppe; Martinelli, Ida; Emmerich, Joseph; Rossi, Elena; Folsom, Aaron R; Almawi, Wassim Y; Scarabin, Pierre Y; den Heijer, Martin; Cushman, Mary; et al. (Eur J Epidemiol, 2013)
Genetic and environmental factors interact in determining the risk of venous thromboembolism (VTE). The risk associated with the polymorphic variants G1691A of factor V (Factor V Leiden, FVL), G20210A of prothrombin (PT20210A) and C677T of methylentetrahydrofolate reductase (C677T MTHFR) genes has been investigated in many studies. We performed a pooled analysis of case-control and cohort studies investigating in adults the association between each variant and VTE, published on Pubmed, Embase or Google through January 2010. Authors of eligible papers, were invited to provide all available individual data for the pooling. The Odds Ratio (OR) for first VTE associated with each variant, individually and combined with the others, were calculated with a random effect model, in heterozygotes and homozygotes (dominant model for FVL and PT20210A; recessive for C677T MTHFR). We analysed 31 databases, including 11,239 cases and 21,521 controls. No significant association with VTE was found for homozygous C677T MTHFR (OR: 1.38; 95 % confidence intervals [CI]: 0.98-1.93), whereas the risk was increased in carriers of either heterozygous FVL or PT20210 (OR = 4.22; 95 % CI: 3.35-5.32; and OR = 2.79;95 % CI: 2.25-3.46, respectively), in double heterozygotes (OR = 3.42; 95 %CI 1.64-7.13), and in homozygous FVL or PT20210A (OR = 11.45; 95 %CI: 6.79-19.29; and OR: 6.74 (CI 95 % 2.19-20.72), respectively). The stratified analyses showed a stronger effect of FVL on individuals ≤ 45 years (p value for interaction = 0.036) and of PT20210A in women using oral contraceptives (p-value for interaction = 0.045). In this large pooled analysis, inclusive of large studies like MEGA, no effect was found for C677T MTHFR on VTE; FVL and PT20210A were confirmed to be moderate risk factors. Notably, double carriers of the two genetic variants produced an impact on VTE risk significantly increased but weaker than previously thought.
Keywords: Case-Control Studies; Factor V; Genetic Predisposition to Disease; Humans; Methylenetetrahydrofolate Reductase (NADPH2); Prothrombin; Risk Factors; Venous Thromboembolism

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

A systematic mapping approach of 16q12.2/FTO and BMI in more than 20,000 African Americans narrows in on the underlying functional variation: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Peters, Ulrike; North, Kari E; Sethupathy, Praveen; Buyske, Steve; Haessler, Jeff; Jiao, Shuo; Fesinmeyer, Megan D; Jackson, Rebecca D; Kuller, Lew H; Rajkovic, Aleksandar; Lim, Unhee; Cheng, Iona; et al. (PLoS Genet, 2013)
Genetic variants in intron 1 of the fat mass- and obesity-associated (FTO) gene have been consistently associated with body mass index (BMI) in Europeans. However, follow-up studies in African Americans (AA) have shown no support for some of the most consistently BMI-associated FTO index single nucleotide polymorphisms (SNPs). This is most likely explained by different race-specific linkage disequilibrium (LD) patterns and lower correlation overall in AA, which provides the opportunity to fine-map this region and narrow in on the functional variant. To comprehensively explore the 16q12.2/FTO locus and to search for second independent signals in the broader region, we fine-mapped a 646-kb region, encompassing the large FTO gene and the flanking gene RPGRIP1L by investigating a total of 3,756 variants (1,529 genotyped and 2,227 imputed variants) in 20,488 AAs across five studies. We observed associations between BMI and variants in the known FTO intron 1 locus: the SNP with the most significant p-value, rs56137030 (8.3 × 10(-6)) had not been highlighted in previous studies. While rs56137030was correlated at r(2)>0.5 with 103 SNPs in Europeans (including the GWAS index SNPs), this number was reduced to 28 SNPs in AA. Among rs56137030 and the 28 correlated SNPs, six were located within candidate intronic regulatory elements, including rs1421085, for which we predicted allele-specific binding affinity for the transcription factor CUX1, which has recently been implicated in the regulation of FTO. We did not find strong evidence for a second independent signal in the broader region. In summary, this large fine-mapping study in AA has substantially reduced the number of common alleles that are likely to be functional candidates of the known FTO locus. Importantly our study demonstrated that comprehensive fine-mapping in AA provides a powerful approach to narrow in on the functional candidate(s) underlying the initial GWAS findings in European populations.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Aged, 80 and over; Alleles; Body Mass Index; Chromosome Mapping; Continental Population Groups; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Obesity; Proteins

Total and high-molecular-weight adiponectin and risk of coronary heart disease and ischemic stroke in older adults. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Djoussé, Luc; Zieman, Susan J; Mukamal, Kenneth J; Tracy, Russell P; Mantzoros, Christos S; Siscovick, David S; Gottdiener, John S; Ix, Joachim H (J Clin Endocrinol Metab, 2013)
CONTEXT: Adiponectin is atheroprotective in the laboratory, but prospective studies have shown opposite associations with cardiovascular disease (CVD) in healthy middle-aged populations (protective) and older cohorts (adverse). Whether this relates to different proportions of high-molecular-weight (HMW) adiponectin is unknown. OBJECTIVE: The aim of the study was to test the hypothesis that total adiponectin is directly associated, but HMW adiponectin is inversely related, with CVD in older adults. DESIGN, SETTING, AND PARTICIPANTS: We evaluated 3290 participants free of prevalent CVD in a longitudinal cohort study of U.S. adults aged 65 yr and older. MAIN OUTCOME MEASURES: We measured incident CVD (n = 1291), comprising coronary heart disease and ischemic stroke. RESULTS: Total and HMW adiponectin were tightly correlated (r = 0.94). Cubic splines adjusted for potential confounders revealed that the associations of total and HMW adiponectin with CVD were U-shaped, with inflection points of 20 and 10 mg/liter, respectively. After controlling for potential confounding, levels of total and HMW adiponectin below these cutpoints tended to be inversely associated with incident CVD, driven by their significant or near-significant relations with coronary heart disease [hazard ratio (HR), 0.85 per sd increase; 95% confidence interval (CI), 0.75-96; and HR, 0.87; 95% CI, 0.75-1.01, respectively]. These associations were abrogated by additional inclusion of putative metabolic intermediates. Above these cutpoints, however, both total and HMW adiponectin were significantly directly associated with CVD after adjustment for confounders and, particularly, mediators (HR, 1.20 per sd increase; 95% CI, 1.06-1.35; and HR, 1.12; 95% CI, 1.02-1.24, respectively). CONCLUSION: In community-living elders, total and HMW adiponectin showed similar U-shaped relationships with CVD. The inverse relation in the lower range, but not the direct association at the higher end, disappeared after inclusion of putative intermediates, suggesting that high levels may reflect adverse processes separate from adiponectin's beneficial glycometabolic properties.
Keywords: Adiponectin; Adult; Aged; Aged, 80 and over; Brain Ischemia; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Humans; Male; Molecular Weight; Residence Characteristics; Risk Factors; Stroke

Advanced glycation/glycoxidation endproduct carboxymethyl-lysine and incidence of coronary heart disease and stroke in older adults. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Ix, Joachim H; Mukamal, Kenneth J; Djoussé, Luc; Tracy, Russell P; Siscovick, David S; Psaty, Bruce M; Zieman, Susan J (Atherosclerosis, 2014)
BACKGROUND: Advanced glycation/glycoxidation endproducts (AGEs) accumulate in settings of increased oxidative stress--such as diabetes, chronic kidney disease and aging--where they promote vascular stiffness and atherogenesis, but the prospective association between AGEs and cardiovascular events in elders has not been previously examined. METHODS: To test the hypothesis that circulating levels of N(ɛ)-carboxymethyl-lysine (CML), a major AGE, increase the risk of incident coronary heart disease and stroke in older adults, we measured serum CML by immunoassay in 2111 individuals free of prevalent cardiovascular disease participating in a population-based study of U.S. adults ages 65 and older. RESULTS: During median follow-up of 9.1 years, 625 cardiovascular events occurred. CML was positively associated with incident cardiovascular events after adjustment for age, sex, race, systolic blood pressure, anti-hypertensive treatment, diabetes, smoking status, triglycerides, albumin, and self-reported health status (hazard ratio [HR] per SD [0.99 pmol/l] increase=1.11, 95% confidence interval [CI]=1.03-1.19). This association was not materially attenuated by additional adjustment for C-reactive protein, estimated glomerular filtration rate (eGFR), and urine albumin/creatinine ratio. Findings were similar for the component endpoints of coronary heart disease and stroke. CONCLUSIONS: In this large older cohort, CML was associated with an increased risk of cardiovascular events independent of a wide array of potential confounders and mediators. Although the moderate association limits CML's value for risk prediction, these community-based findings provide support for clinical trials to test AGE-lowering therapies for cardiovascular prevention in this population.
Keywords: Aged; Albumins; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Creatinine; Female; Glomerular Filtration Rate; Glycation End Products, Advanced; Humans; Immunoassay; Incidence; Lysine; Male; Oxidative Stress; Proportional Hazards Models; Stroke; Treatment Outcome

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Muzny, Donna; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

The challenges of genome-wide interaction studies: lessons to learn from the analysis of HDL blood levels. - van Leeuwen, Elisabeth M; Smouter, Françoise A S; Kam-Thong, Tony; Karbalai, Nazanin; Smith, Albert V; Harris, Tamara B; Launer, Lenore J; Sitlani, Colleen M; Li, Guo; Brody, Jennifer A; Bis, Joshua C; White, Charles C; et al. (PLoS One, 2014)
Genome-wide association studies (GWAS) have revealed 74 single nucleotide polymorphisms (SNPs) associated with high-density lipoprotein cholesterol (HDL) blood levels. This study is, to our knowledge, the first genome-wide interaction study (GWIS) to identify SNP×SNP interactions associated with HDL levels. We performed a GWIS in the Rotterdam Study (RS) cohort I (RS-I) using the GLIDE tool which leverages the massively parallel computing power of Graphics Processing Units (GPUs) to perform linear regression on all genome-wide pairs of SNPs. By performing a meta-analysis together with Rotterdam Study cohorts II and III (RS-II and RS-III), we were able to filter 181 interaction terms with a p-value<1 · 10-8 that replicated in the two independent cohorts. We were not able to replicate any of these interaction term in the AGES, ARIC, CHS, ERF, FHS and NFBC-66 cohorts (Ntotal = 30,011) when adjusting for multiple testing. Our GWIS resulted in the consistent finding of a possible interaction between rs774801 in ARMC8 (ENSG00000114098) and rs12442098 in SPATA8 (ENSG00000185594) being associated with HDL levels. However, p-values do not reach the preset Bonferroni correction of the p-values. Our study suggest that even for highly genetically determined traits such as HDL the sample sizes needed to detect SNP×SNP interactions are large and the 2-step filtering approaches do not yield a solution. Here we present our analysis plan and our reservations concerning GWIS.
Keywords: Cholesterol, HDL; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Circulating fibrosis biomarkers and risk of atrial fibrillation: The Cardiovascular Health Study (CHS). - Rosenberg, Michael A; Maziarz, Marlena; Tan, Alex Y; Glazer, Nicole L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Djoussé, Luc; Siscovick, David S; Heckbert, Susan R; Mukamal, Kenneth J (Am Heart J, 2014)
BACKGROUND: Cardiac fibrosis is thought to play a central role in the pathogenesis of atrial fibrillation (AF). Retrospective studies have suggested that circulating fibrosis biomarkers are associated with AF, but prospective studies are limited. METHODS: We measured circulating levels of 2 fibrosis biomarkers, procollagen type III, N-terminal propeptide (PIIINP) and transforming growth factor β1 among participants of the CHS, a population-based study of older Americans. We used Cox proportional hazards and competing risks models to examine adjusted risk of incident AF over a median follow-up of 8.8 years. RESULTS: Levels of PIIINP were assessed in 2,935 participants, of whom 767 developed AF. Compared with the median PIIINP level (4.45 μg/L), adjusted hazard ratios (95% CIs) were 0.85 (0.72-1.00) at the 10th percentile, 0.93 (0.88-0.99) at the 25th percentile, 1.04 (0.95-1.04) at the 75th percentile, and 1.07 (0.90-1.26) at the 90th. Transforming growth factor β1 levels, assessed in 1,538 participants with 408 cases of incident AF, were not associated with AF risk. CONCLUSION: In older adults, PIIINP levels were associated with risk of incident AF in a complex manner, with an association that appeared to be positive up to median levels but with little relationship beyond that. Further studies are required to confirm and possibly delineate the mechanism for this relationship.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Cardiomyopathies; Electrocardiography; Enzyme-Linked Immunosorbent Assay; Female; Fibrosis; Follow-Up Studies; Humans; Incidence; Male; Peptide Fragments; Procollagen; Prospective Studies; Risk Factors; Time Factors; Transforming Growth Factor beta1; United States

Circulating levels of carboxy‐methyl‐lysine (CML) are associated with hip fracture risk: the Cardiovascular Health Study. - Barzilay, Joshua I; Bůzková, Petra; Zieman, Susan J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Tracy, Russell P; Siscovick, David S; Cauley, Jane A; Mukamal, Kenneth J (J Bone Miner Res, 2014)
Advanced glycation end products (AGE) in bone tissue are associated with impaired biomechanical properties and increased fracture risk. Here we examine whether serum levels of the AGE carboxy‐methyl‐lysine (CML) are associated with risk of hip fracture.We followed 3373 participants from the Cardiovascular Health Study (age 78 years; range, 68–102 years; 39.8% male) for a median of 9.22 years (range, 0.01–12.07 years). Rates of incident hip fracture were calculated by quartiles of baseline CML levels, and hazard ratios were adjusted for covariates associated with hip fracture risk. A subcohort of 1315 participants had bone mineral density (BMD)measurement. There were 348 hip fractures during follow‐up, with incidence rates of hip fracture by CML quartiles of 0.94, 1.34, 1.18, and 1.69 per 100 participant‐years. The unadjusted hazard ratio of hip fracture increased with each 1 SD increase (189 ng/mL) of CML level (hazard ratio, 1.27; 95% confidence interval [CI], 1.16–1.40]; p<0.001). Sequential adjustment for age, gender, race/ethnicity,body mass index (BMI), smoking, alcohol consumption, prevalent coronary heart disease (CHD), energy expenditure, and estimated glomerular filtration rate (based on cystatin C), moderately attenuated the hazard ratio for fracture (1.17; 95% CI, 1.05–1.31; p=0.006).In the cohort with BMD testing, total hip BMD was not significantly associated with CML levels. We conclude that increasing levels of CML are associated with hip fracture risk in older adults, independent of hip BMD. These results implicate AGE in the pathogenesis of hip fractures.
Keywords: Age Factors; Aged; Female; Follow-Up Studies; Glycation End Products, Advanced; Hip Fractures; Humans; Incidence; Lysine; Male; Prospective Studies; Retrospective Studies; Risk Factors

Common carotid intima-media thickness measurements do not improve cardiovascular risk prediction in individuals with elevated blood pressure: the USE-IMT collaboration. - Bots, Michiel L; Groenewegen, Karlijn A; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; Hedblad, Bo; Hofman, Albert; Holewijn, Suzanne; et al. (Hypertension, 2014)
Carotid intima-media thickness (CIMT) is a marker of cardiovascular risk. It is unclear whether measurement of mean common CIMT improves 10-year risk prediction of first-time myocardial infarction or stroke in individuals with elevated blood pressure. We performed an analysis among individuals with elevated blood pressure (i.e., a systolic blood pressure ≥140 mm Hg and a diastolic blood pressure ≥ 90 mm Hg) in USE-IMT, a large ongoing individual participant data meta-analysis. We refitted the risk factors of the Framingham Risk Score on asymptomatic individuals (baseline model) and expanded this model with mean common CIMT (CIMT model) measurements. From both models, 10-year risks to develop a myocardial infarction or stroke were estimated. In individuals with elevated blood pressure, we compared discrimination and calibration of the 2 models and calculated the net reclassification improvement (NRI). We included 17 254 individuals with elevated blood pressure from 16 studies. During a median follow-up of 9.9 years, 2014 first-time myocardial infarctions or strokes occurred. The C-statistics of the baseline and CIMT models were similar (0.73). NRI with the addition of mean common CIMT was small and not significant (1.4%; 95% confidence intervals, -1.1 to 3.7). In those at intermediate risk (n=5008, 10-year absolute risk of 10% to 20%), the NRI was 5.6% (95% confidence intervals, 1.6-10.4). There is no added value of measurement of mean common CIMT in individuals with elevated blood pressure for improving cardiovascular risk prediction. For those at intermediate risk, the addition of mean common CIMT to an existing cardiovascular risk score is small but statistically significant.
Keywords: Adult; Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Carotid Artery, Common; Carotid Intima-Media Thickness; Cohort Studies; Female; Humans; Hypertension; Male; Meta-Analysis as Topic; Middle Aged; Risk Assessment; Risk Factors

A common SCN5A variant is associated with PR interval and atrial fibrillation among African Americans. - Ilkhanoff, Leonard; Arking, Dan E; Lemaitre, Rozenn N; Alonso, Alvaro; Chen, Lin Y; Durda, Peter; Hesselson, Stephanie E; Kerr, Kathleen F; Magnani, Jared W; Marcus, Gregory M; Schnabel, Renate B; Smith, J Gustav; et al. (J Cardiovasc Electrophysiol, 2014)
OBJECTIVE: We examined the association of rs7626962 (S1103Y) or rs7629265, a variant in high linkage disequilibrium with S1103Y (r(2) = 0.87 - 1), with sudden cardiac death (SCD) and atrial fibrillation (AF) among African Americans. BACKGROUND: The SCN5A missense variant S1103Y has been associated with SCD among African Americans in small case-control studies, but larger population-based studies are needed to validate these findings. The association of this variant with AF has not been fully explored. METHODS: Using genotyping data on over 7,000 African Americans from 5 cohorts (Atherosclerosis Risk in Communities [ARIC], Cleveland Family Study [CFS], Jackson Heart Study [JHS], Multi-Ethnic Study of Atherosclerosis [MESA], Cardiovascular Health Study [CHS]), we examined the association of rs7629265 with electrocardiographic PR, QRS, and QT intervals, and with incident AF and SCD. We examined association of S1103Y (rs7626962) with SCD using a population-based case-control study of SCD Cardiac Arrest Blood Study (CABS). RESULTS: Meta-analyses across 5 cohorts demonstrated that rs7629265 was significantly associated with PR duration (β = -4.1 milliseconds; P = 2.2×10(-6) ), but not significantly associated with QRS or QT intervals. In meta-analyses of prospectively followed ARIC and CHS participants (n = 3,656), rs7629265 was associated with increased AF risk (n = 299 AF cases; HR = 1.74, P = 1.9 × 10(-4) ). By contrast, rs7629265 was not significantly associated with SCD risk in ARIC (n = 83 SCD cases; P = 0.30) or CHS (n = 54 SCD cases; P = 0.47). Similarly, S1103Y was not significantly associated with SCD risk in CABS (n = 225 SCD cases; P = 0.29). CONCLUSION: The common SCN5A variant, rs7629265, is associated with increased AF risk and shorter PR interval among African Americans. In contrast to prior reports, we found no evidence of association of rs7629265 or rs7626962 (S1103Y) with SCD risk in the general population.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Female; Genetic Variation; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Prospective Studies; Risk Factors; Single-Blind Method

Decline in estimated glomerular filtration rate and subsequent risk of end-stage renal disease and mortality. - Coresh, Josef; Turin, Tanvir Chowdhury; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Appel, Lawrence J; Arima, Hisatomi; Chadban, Steven J; Cirillo, Massimo; Djurdjev, Ognjenka; Green, Jamie A; Heine, Gunnar H; et al. (JAMA, 2014)
IMPORTANCE: The established chronic kidney disease (CKD) progression end point of end-stage renal disease (ESRD) or a doubling of serum creatinine concentration (corresponding to a change in estimated glomerular filtration rate [GFR] of −57% or greater) is a late event. OBJECTIVE: To characterize the association of decline in estimated GFR with subsequent progression to ESRD with implications for using lesser declines in estimated GFR as potential alternative end points for CKD progression. Because most people with CKD die before reaching ESRD, mortality risk also was investigated. DATA SOURCES AND STUDY SELECTION: Individual meta-analysis of 1.7 million participants with 12,344 ESRD events and 223,944 deaths from 35 cohorts in the CKD Prognosis Consortium with a repeated measure of serum creatinine concentration over 1 to 3 years and outcome data. DATA EXTRACTION AND SYNTHESIS: Transfer of individual participant data or standardized analysis of outputs for random-effects meta-analysis conducted between July 2012 and September 2013, with baseline estimated GFR values collected from 1975 through 2012. MAIN OUTCOMES AND MEASURES: End-stage renal disease (initiation of dialysis or transplantation) or all-cause mortality risk related to percentage change in estimated GFR over 2 years, adjusted for potential confounders and first estimated GFR. RESULTS: The adjusted hazard ratios (HRs) of ESRD and mortality were higher with larger estimated GFR decline. Among participants with baseline estimated GFR of less than 60 mL/min/1.73 m2, the adjusted HRs for ESRD were 32.1 (95% CI, 22.3-46.3) for changes of −57% in estimated GFR and 5.4 (95% CI, 4.5-6.4) for changes of −30%. However, changes of −30% or greater (6.9% [95% CI, 6.4%-7.4%] of the entire consortium) were more common than changes of −57% (0.79% [95% CI, 0.52%-1.06%]). This association was strong and consistent across the length of the baseline period (1 to 3 years), baseline estimated GFR, age, diabetes status, or albuminuria. Average adjusted 10-year risk of ESRD (in patients with a baseline estimated GFR of 35 mL/min/1.73 m2) was 99% (95% CI, 95%-100%) for estimated GFR change of −57%, was 83% (95% CI, 71%-93%) for estimated GFR change of −40%, and was 64% (95% CI, 52%-77%) for estimated GFR change of −30% vs 18% (95% CI, 15%-22%) for estimated GFR change of 0%. Corresponding mortality risks were 77% (95% CI, 71%-82%), 60% (95% CI, 56%-63%), and 50% (95% CI, 47%-52%) vs 32% (95% CI, 31%-33%), showing a similar but weaker pattern. CONCLUSIONS AND RELEVANCE: Declines in estimated GFR smaller than a doubling of serum creatinine concentration occurred more commonly and were strongly and consistently associated with the risk of ESRD and mortality, supporting consideration of lesser declines in estimated GFR (such as a 30% reduction over 2 years) as an alternative end point for CKD progression.
Keywords: Adult; Aged; Aged, 80 and over; Cohort Studies; Creatinine; Disease Progression; Endpoint Determination; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Reference Values; Risk

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Effect of genetic variants associated with plasma homocysteine levels on stroke risk. - Cotlarciuc, Ioana; Malik, Rainer; Holliday, Elizabeth G; Ahmadi, Kourosh R; Paré, Guillaume; Psaty, Bruce M; Fornage, Myriam; Hasan, Nazeeha; Rinne, Paul E; Ikram, M Arfan; Markus, Hugh S; Rosand, Jonathan; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Elevated total plasma homocysteine (tHcy) levels are known to be associated with increased risk of ischemic stroke (IS). Given that both tHcy and IS are heritable traits, we investigated a potential genetic relationship between homocysteine levels and stroke risk by assessing 18 polymorphisms previously associated with tHcy levels for their association with IS and its subtypes. METHODS: Previous meta-analysis results from an international stroke collaborative network, METASTROKE, were used to assess association of the 18 tHcy-associated single-nucleotide polymorphisms (SNPs) in 12 389 IS cases and 62 004 controls. We also investigated the associations in regions located within 50 kb from the 18 tHcy-related SNPs and the association of a genetic risk score, including the 18 SNPs. RESULTS: One SNP located in the RASIP1 gene and a cluster of 3 SNPs located at and near SLC17A3 were significantly associated with IS (P<0.0003) after correcting for multiple testing. For stroke subtypes, the sentinel SNP located upstream of MUT was significantly associated with small-vessel disease (P=0.0022), whereas 1 SNP located in MTHFR was significantly associated with large-vessel disease (P=0.00019). A genetic risk score, including the 18 SNPs, did not show significant association with IS or its subtypes. CONCLUSIONS: This study found several potential associations with IS and its subtypes: an association of an MUT variant with small-vessel disease, an MTHFR variant with large-vessel disease, and associations of RASIP1 and SLC17A3 variants with overall IS.
Keywords: Brain Ischemia; Cohort Studies; Europe; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome; Homocysteine; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Estimated GFR and circulating 24,25-dihydroxyvitamin D3 concentration: a participant-level analysis of 5 cohort studies and clinical trials. - de Boer, Ian H; Sachs, Michael C; Chonchol, Michel; Himmelfarb, Jonathan; Hoofnagle, Andrew N; Ix, Joachim H; Kremsdorf, Robin A; Lin, Yvonne S; Mehrotra, Rajnish; Robinson-Cohen, Cassianne; Siscovick, David S; Steffes, Michael W; et al. (Am J Kidney Dis, 2014)
BACKGROUND: Decreased glomerular filtration rate (GFR) leads to reduced production of 1,25-dihydroxyvitamin D3 from 25-hydroxyvitamin D3 (25[OH]D3). Effects of low GFR on vitamin D catabolism are less well understood. We tested associations of estimated GFR (eGFR) with the circulating concentration of 24,25-dihydroxyvitamin D3 (24,25[OH]2D3), the most abundant product of 25(OH)D3 catabolism, across populations with a wide range of GFRs. STUDY DESIGN: Cross-sectional study. SETTING & PARTICIPANTS: 9,596 participants in 5 cohort studies and clinical trials: the Diabetes Control and Complications Trial (N=1,193), Multi-Ethnic Study of Atherosclerosis (N=6,470), Cardiovascular Health Study (N=932), Seattle Kidney Study (N=289), and Hemodialysis Study (N=712). PREDICTOR: eGFR. OUTCOME: Circulating 24,25(OH)2D3 concentration. MEASUREMENTS: GFR was estimated from serum creatinine using the Chronic Kidney Disease Epidemiology Collaboration equation. Vitamin D metabolites were measured by mass spectrometry. RESULTS: Circulating 24,25(OH)2D3 concentration was correlated with circulating 25(OH)D3 concentration (Pearson r range, 0.64-0.88). This correlation was weaker with lower eGFRs. Moreover, the increment in 24,25(OH)2D3 concentration associated with higher 25(OH)D3 concentration (slope) was lower with lower eGFRs: 2.06 (95% CI, 2.01-2.10), 1.77 (95% CI, 1.74-1.81), 1.55 (95% CI, 1.48-1.62), 1.17 (95% CI, 1.05-1.29), 0.92 (95% CI, 0.74-1.10), 0.61 (95% CI, 0.22-1.00), and 0.37 (95% CI, 0.35-0.39) ng/mL of 24,25(OH)2D3 per 10 ng/mL of 25(OH)D3 for eGFRs≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m2 and end-stage renal disease treated with hemodialysis, respectively. As a result, at a 25(OH)D3 concentration of 20 ng/mL, mean 24,25(OH)2D3 concentrations were 2.92 (95% CI, 2.87-2.96), 2.68 (95% CI, 2.64-2.72), 2.35 (95% CI, 2.26-2.45), 1.92 (95% CI, 1.74-2.10), 1.69 (95% CI, 1.43-1.95), 1.14 (95% CI, 0.62-1.66), and 1.04 (95% CI,1.02-1.07) ng/mL for each category, respectively. This interaction was independent of other relevant clinical characteristics. Race, diabetes, urine albumin excretion, and circulating parathyroid hormone and fibroblast growth factor 23 concentrations more modestly modified the association of 24,25(OH)2D3 with 25(OH)D3. LIMITATIONS: Lack of direct pharmacokinetic measurements of vitamin D catabolism. CONCLUSIONS: Lower eGFR is associated strongly with reduced vitamin D catabolism, as measured by circulating 24,25(OH)2D3 concentration.
Keywords: 24,25-Dihydroxyvitamin D 3; Adult; Aged; Aged, 80 and over; Biomarkers; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Observational Studies as Topic; Randomized Controlled Trials as Topic; Young Adult

Fibroblast growth factor 23, the ankle-brachial index, and incident peripheral artery disease in the Cardiovascular Health Study. - Garimella, Pranav S; Ix, Joachim H; Katz, Ronit; Chonchol, Michel B; Kestenbaum, Bryan R; de Boer, Ian H; Siscovick, David S; Shastri, Shani; Hiramoto, Jade S; Shlipak, Michael G; Sarnak, Mark J (Atherosclerosis, 2014)
BACKGROUND: Fibroblast growth factor 23 (FGF23) has emerged as a novel risk factor for mortality and cardiovascular events. Its association with the ankle-brachial index (ABI) and clinical peripheral artery disease (PAD) is less known. METHODS: Using data (N = 3143) from the Cardiovascular Health Study (CHS), a cohort of community dwelling adults >65 years of age, we analyzed the cross-sectional association of FGF23 with ABI and its association with incident clinical PAD events during 9.8 years of follow up using multinomial logistic regression and Cox proportional hazards models respectively. RESULTS: The prevalence of cardiovascular disease (CVD) and traditional risk factors like diabetes, coronary artery disease, and heart failure increased across higher quartiles of FGF23. Compared to those with ABI of 1.1-1.4, FGF23 per doubling at baseline was associated with prevalent PAD (ABI < 0.9) although this association was attenuated after adjusting for CVD risk factors, and kidney function (OR 0.91, 95% CI 0.76-1.08). FGF23 was not associated with high ABI (>1.4) (OR 1.06, 95% CI 0.75-1.51). Higher FGF23 was associated with incidence of PAD events in unadjusted, demographic adjusted, and CVD risk factor adjusted models (HR 2.26, 95% CI 1.28-3.98; highest versus lowest quartile). The addition of estimated glomerular filtration and urine albumin to creatinine ratio to the model however, attenuated these findings (HR 1.46, 95% CI, 0.79-2.70). CONCLUSIONS: In community dwelling older adults, FGF23 was not associated with baseline low or high ABI or incident PAD events after adjusting for confounding variables. These results suggest that FGF23 may primarily be associated with adverse cardiovascular outcomes through non atherosclerotic mechanisms.
Keywords: Aged; Ankle Brachial Index; Cardiovascular Diseases; Cross-Sectional Studies; Fibroblast Growth Factors; Humans; Incidence; Peripheral Arterial Disease; Risk Factors

Fibroblast growth factor-23 and incident atrial fibrillation: the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS). - Mathew, Jehu S; Sachs, Michael C; Katz, Ronit; Patton, Kristen K; Heckbert, Susan R; Hoofnagle, Andrew N; Alonso, Alvaro; Chonchol, Michel; Deo, Rajat; Ix, Joachim H; Siscovick, David S; Kestenbaum, Bryan; et al. (Circulation, 2014)
BACKGROUND: Fibroblast growth factor-23 (FGF-23) is a hormone that promotes urinary phosphate excretion and regulates vitamin D metabolism. Circulating FGF-23 concentrations increase markedly in chronic kidney disease and are associated with increased risk of clinical cardiovascular events. FGF-23 may promote atrial fibrillation (AF) by inducing left ventricular hypertrophy and diastolic and left atrial dysfunction. METHODS AND RESULTS: We tested the associations of circulating FGF-23 concentration with incident AF among 6398 participants in the Multi-Ethnic Study of Atherosclerosis (MESA) and 1350 participants in the Cardiovascular Health Study (CHS), all free of clinical cardiovascular disease at baseline. Over a median of 7.7 and 8.0 years of follow-up, we observed 291 and 229 incident AF events in MESA and CHS, respectively. In multivariable Cox proportional hazards models, each 2-fold-higher FGF-23 concentration was associated with a 41% higher risk of incident AF in MESA (hazard ratio, 1.41; 95% confidence interval, 1.13-1.76; P=0.003) and a 30% higher risk of incident AF in CHS (hazard ratio, 1.30; 95% confidence interval, 1.05-1.61; P=0.016) after adjustment for potential confounding characteristics, including kidney disease. Serum phosphate concentration was significantly associated with incident AF in MESA (hazard ratio, 1.15 per 0.5 mg/dL; 95% confidence interval, 1.02-1.31; P=0.023) but not CHS. In MESA, an association of low estimated glomerular filtration rate with incident AF was partially attenuated by adjustment for FGF-23. CONCLUSION: Higher circulating FGF-23 concentration is associated with incident AF and may, in part, explain the link between chronic kidney disease and AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Comorbidity; Ethnic Groups; Female; Fibroblast Growth Factor 3; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Middle Aged; Phosphates; Proportional Hazards Models; Renal Insufficiency, Chronic; Risk Factors; United States; Ventricular Dysfunction, Left; Ventricular Remodeling; Vitamin D

Fibroblast growth factor-23 and the long-term risk of hospital-associated AKI among community-dwelling older individuals. - Brown, Jeremiah R; Katz, Ronit; Ix, Joachim H; de Boer, Ian H; Siscovick, David S; Grams, Morgan E; Shlipak, Michael; Sarnak, Mark J (Clin J Am Soc Nephrol, 2014)
BACKGROUND AND OBJECTIVES: AKI occurs frequently in older persons. Elevated circulating fibroblast growth factor-23 (FGF-23), a known marker of impaired mineral metabolism, may also reflect tubular dysfunction and risk of AKI. This study evaluated FGF-23 as well as traditional markers of kidney disease, namely urine albumin-to-creatinine ratio (UACR) and creatinine-cystatin C estimated GFR (eGFRCrCyC), as risk factors for AKI in elderly individuals. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Plasma FGF-23, UACR, and eGFRCrCyC were measured in 3241 community-dwelling elderly individuals in the Cardiovascular Health Study. Hospitalization for AKI was defined by International Classification of Diseases, Ninth Revision, Clinical Modification codes. Associations of each biomarker with AKI were evaluated using Cox proportional hazards models adjusted for demographics, cardiovascular risk factors, and biomarkers of kidney function. RESULTS: The mean participant age was 78 years; 60% of participants were women and 16% were African American. The median (interquartile range) values of biomarkers were as follows: FGF-23, 70 RU/ml (53, 99); UACR, 8.88 mg/g (4.71, 20.47); and eGFRCrCyC, 71 ml/min per 1.73 m(2) (59, 83). Hospitalized AKI occurred in 119 participants over 10.0 years of median follow-up. In fully adjusted analyses, compared with the lowest quartiles, the highest quartiles of FGF-23 (≥100 RU/ml) and UACR (≥20.9 mg/g) were associated with AKI (FGF-23: hazard ratio [HR], 1.99; 95% confidence interval [95% CI], 1.04 to 3.80; and UACR: HR, 3.35; 95% CI, 1.83 to 6.13). Compared with the highest quartile, the lowest quartile of eGFRCrCyC (<57 ml/min per 1.73 m(2)) was associated with AKI with an HR of 2.15 (95% CI, 1.21 to 3.82). CONCLUSIONS: FGF-23 adjusted for albuminuria, cardiovascular disease risk factors, and baseline eGFR is independently associated with a higher risk of AKI hospitalizations in community-dwelling elderly individuals. Further studies to understand the nature of this association are warranted.
Keywords: Acute Kidney Injury; Age Factors; Aged; Aged, 80 and over; Albuminuria; Biomarkers; Creatinine; Cystatin C; Female; Fibroblast Growth Factors; Glomerular Filtration Rate; Hospitalization; Humans; Independent Living; Kidney; Longitudinal Studies; Male; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors

Fibrosis-related biomarkers and incident cardiovascular disease in older adults: the cardiovascular health study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Biggs, Mary L; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Sicovick, David S; Tracy, Russell P; et al. (Circ Arrhythm Electrophysiol, 2014)
BACKGROUND: Fibrotic changes in the heart and arteries have been implicated in a diverse range of cardiovascular diseases (CVD), but whether circulating biomarkers that reflect fibrosis are associated with CVD is unknown. METHODS AND RESULTS: We determined the associations of 2 biomarkers of fibrosis, transforming growth factor- β (TGF-β), and procollagen type III N-terminal propeptide (PIIINP), with incident heart failure, myocardial infarction, and stroke among community-living older adults in the Cardiovascular Health Study. We measured circulating TGF-β (n=1371) and PIIINP (n=2568) from plasma samples collected in 1996 and ascertained events through 2010. Given TGF-β's pleiotropic effects on inflammation and fibrogenesis, we investigated potential effect modification by C-reactive protein in secondary analyses. After adjustment for sociodemographic, clinical, and biochemical risk factors, PIIINP was associated with total CVD (hazard ratio [HR] per SD=1.07; 95% confidence interval [CI], 1.01-1.14) and heart failure (HR per SD=1.08; CI, 1.01-1.16) but not myocardial infarction or stroke. TGF-β was not associated with any CVD outcomes in the full cohort but was associated with total CVD (HR per SD=1.16; CI, 1.02-1.31), heart failure (HR per SD=1.16; CI, 1.01-1.34), and stroke (HR per SD=1.20; CI, 1.01-1.42) among individuals with C-reactive protein above the median, 2.3 mg/L (P interaction <0.05). CONCLUSIONS: Our findings provide large-scale, prospective evidence that circulating biomarkers of fibrosis, measured in community-living individuals late in life, are associated with CVD. Further research on whether TGF-β has a stronger fibrogenic effect in the setting of inflammation is warranted.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Female; Fibrosis; Heart Failure; Humans; Incidence; Male; Myocardial Infarction; Peptide Fragments; Procollagen; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Time Factors; Transforming Growth Factor beta; United States

Fibrosis-related biomarkers and risk of total and cause-specific mortality: the cardiovascular health study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Biggs, Mary L; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; Tracy, Russell P; et al. (Am J Epidemiol, 2014)
Fibrosis has been implicated in diverse diseases of the liver, kidney, lungs, and heart, but its importance as a risk factor for mortality remains unconfirmed. We determined the prospective associations of 2 complementary biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with total and cause-specific mortality risks among community-living older adults in the Cardiovascular Health Study (1996-2010). We measured circulating TGF-β and PIIINP levels in plasma samples collected in 1996 and ascertained the number of deaths through 2010. Both TGF-β and PIIINP were associated with elevated risks of total and pulmonary mortality after adjustment for sociodemographic, clinical, and biochemical risk factors. For total mortality, the hazard ratios per doubling of TGF-β and PIIINP were 1.09 (95% confidence interval (CI): 1.01, 1.17; P = 0.02) and 1.14 (CI: 1.03, 1.27; P = 0.01), respectively. The corresponding hazard ratios for pulmonary mortality were 1.27 (CI: 1.01, 1.60; P = 0.04) for TGF-β and 1.52 (CI: 1.11, 2.10; P = 0.01) for PIIINP. Associations of TGF-β and PIIINP with total and pulmonary mortality were strongest among individuals with higher C-reactive protein concentrations (P for interaction < 0.05). Our findings provide some of the first large-scale prospective evidence that circulating biomarkers of fibrosis measured late in life are associated with death.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cause of Death; Female; Fibrosis; Follow-Up Studies; Humans; Likelihood Functions; Male; Multivariate Analysis; Peptide Fragments; Procollagen; Proportional Hazards Models; Prospective Studies; Risk Factors; Transforming Growth Factor beta

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Large-scale meta-analysis of genome-wide association data identifies six new risk loci for Parkinson's disease. - Nalls, Mike A; Pankratz, Nathan; Lill, Christina M; Do, Chuong B; Hernandez, Dena G; Saad, Mohamad; DeStefano, Anita L; Kara, Eleanna; Bras, Jose; Sharma, Manu; Schulte, Claudia; Keller, Margaux F; et al. (Nat Genet, 2014)
We conducted a meta-analysis of Parkinson's disease genome-wide association studies using a common set of 7,893,274 variants across 13,708 cases and 95,282 controls. Twenty-six loci were identified as having genome-wide significant association; these and 6 additional previously reported loci were then tested in an independent set of 5,353 cases and 5,551 controls. Of the 32 tested SNPs, 24 replicated, including 6 newly identified loci. Conditional analyses within loci showed that four loci, including GBA, GAK-DGKQ, SNCA and the HLA region, contain a secondary independent risk variant. In total, we identified and replicated 28 independent risk variants for Parkinson's disease across 24 loci. Although the effect of each individual locus was small, risk profile analysis showed substantial cumulative risk in a comparison of the highest and lowest quintiles of genetic risk (odds ratio (OR) = 3.31, 95% confidence interval (CI) = 2.55-4.30; P = 2 × 10(-16)). We also show six risk loci associated with proximal gene expression or DNA methylation.
Keywords: Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Polymorphism, Single Nucleotide; Risk Factors

Lipoprotein-associated phospholipase A2 and risk of dementia in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Irizarry, Michael C; Cushman, Mary; Jenny, Nancy S; Chi, Gloria C; Koro, Carol (Atherosclerosis, 2014)
OBJECTIVE: To evaluate associations between Lipoprotein-associated phospholipase A2 (Lp-PLA2) mass and activity with risk of dementia and its subtypes. METHODS: Analysis were completed on 3320 participants of the Cardiovascular Health Study (CHS), a population-based longitudinal study of community-dwelling adults age ≥65 years followed for an average of 5.4 years. Baseline serum Lp-PLA2 mass was measured using a sandwich enzyme immunoassay and Lp-PLA2 activity utilized a tritiated-platelet activating factor activity assay. Cox proportional hazards regression assessed the relative risk of incident dementia with higher baseline Lp-PLA2 adjusting for demographics, cardiovascular disease (CVD) and risk factors, inflammation markers and apolipoprotein E (APOE) genotype. RESULTS: Each standard deviation higher Lp-PLA2 mass and activity were related to increased risk of dementia (fully adjusted HR: 1.11 per SD, 95% CI: 1.00-1.24 for mass; HR: 1.12 per SD, 95% CI: 1.00-1.26 for activity). Persons in the highest quartile of Lp-PLA2 mass were 50% more likely to develop dementia than those in the lowest quartile in adjusted models (HR: 1.49; 95% CI: 1.08-2.06). Among dementia subtypes, the risk of AD was increased two-fold in the highest compared to lowest quartile of Lp-PLA2 mass (adjusted HR: 1.98, 95% CI: 1.22-3.21). Results were attenuated in models of mixed dementia and VaD. Lp-PLA2 activity also doubled the risk of mixed dementia in the highest compared to lowest quartile (HR: 2.21, 95% CI: 1.12-4.373). INTERPRETATION: These data support Lp-PLA2 as a risk factor for dementia independent of CVD and its risk factors. Further study is required to clarify the role of Lp-PLA2-related mechanisms in dementia subtypes.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Alzheimer Disease; Dementia; Female; Humans; Male; Risk; Risk Factors

Meta-analysis in more than 17,900 cases of ischemic stroke reveals a novel association at 12q24.12. - Kilarski, Laura L; Achterberg, Sefanja; Devan, William J; Traylor, Matthew; Malik, Rainer; Lindgren, Arne; Pare, Guillame; Sharma, Pankaj; Slowik, Agniesczka; Thijs, Vincent; Walters, Matthew; Worrall, Bradford B; et al. (Neurology, 2014)
OBJECTIVES: To perform a genome-wide association study (GWAS) using the Immunochip array in 3,420 cases of ischemic stroke and 6,821 controls, followed by a meta-analysis with data from more than 14,000 additional ischemic stroke cases. METHODS: Using the Immunochip, we genotyped 3,420 ischemic stroke cases and 6,821 controls. After imputation we meta-analyzed the results with imputed GWAS data from 3,548 cases and 5,972 controls recruited from the ischemic stroke WTCCC2 study, and with summary statistics from a further 8,480 cases and 56,032 controls in the METASTROKE consortium. A final in silico "look-up" of 2 single nucleotide polymorphisms in 2,522 cases and 1,899 controls was performed. Associations were also examined in 1,088 cases with intracerebral hemorrhage and 1,102 controls. RESULTS: In an overall analysis of 17,970 cases of ischemic stroke and 70,764 controls, we identified a novel association on chromosome 12q24 (rs10744777, odds ratio [OR] 1.10 [1.07-1.13], p = 7.12 × 10(-11)) with ischemic stroke. The association was with all ischemic stroke rather than an individual stroke subtype, with similar effect sizes seen in different stroke subtypes. There was no association with intracerebral hemorrhage (OR 1.03 [0.90-1.17], p = 0.695). CONCLUSION: Our results show, for the first time, a genetic risk locus associated with ischemic stroke as a whole, rather than in a subtype-specific manner. This finding was not associated with intracerebral hemorrhage.
Keywords: Brain Ischemia; Cerebral Hemorrhage; Chromosomes, Human, Pair 12; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Metabolic syndrome and risk of incident peripheral artery disease: the cardiovascular health study. - Garg, Parveen K; Biggs, Mary L; Carnethon, Mercedes; Ix, Joachim H; Criqui, Michael H; Britton, Kathryn A; Djoussé, Luc; Sutton-Tyrrell, Kim; Newman, Anne B; Cushman, Mary; Mukamal, Kenneth J (Hypertension, 2014)
Prior studies evaluating metabolic syndrome (MetS) and incident peripheral artery disease (PAD) have been limited by use of modified MetS criteria and restriction to clinical PAD end points. We investigated MetS and risk of developing a low ankle-brachial index (ABI) and clinical PAD in the Cardiovascular Health Study, a population-based cohort of adults aged ≥65 years. Participants with MetS met at least 3 of 5 Adult Treatment Panel III criteria. Baseline C-reactive protein-MetS or fibrinogen-MetS were defined as presence of 3 of 6 components, with elevated C-reactive protein (>3 mg/L) or fibrinogen (>341 mg/dL) as a sixth component. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among a subset of 1899 individuals with 2 ABI measurements 6 years apart. Over a median follow-up of 13.7 years, 4632 individuals were followed up for clinical PAD, defined as revascularization or diagnosed claudication. Adult Treatment Panel III MetS was associated with both incident low ABI (risk ratio, 1.26; 95% confidence interval [CI], 1.00-1.58) and clinical PAD (hazard ratio, 1.47; 95% CI, 1.11-1.94). Incorporating C-reactive protein or fibrinogen into Adult Treatment Panel III criteria identified an additional 16% to 20% of individuals as having MetS, and both C-reactive protein-MetS and fibrinogen-MetS were associated with incident low ABI (risk ratio, 1.36; 95% CI, 1.07-1.72 and risk ratio, 1.43; 95% CI, 1.13-1.81, respectively) and clinical PAD (hazard ratio, 1.56; 95% CI, 1.17-2.08 and hazard ratio, 1.55; 95% CI, 1.17-2.07, respectively). Among Adult Treatment Panel III MetS criteria, risk of PAD was most strongly associated with hypertension.
Keywords: Aged; Ankle Brachial Index; C-Reactive Protein; Female; Fibrinogen; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Metabolic Syndrome; Peripheral Arterial Disease; Prevalence; Risk Factors; Vasculitis

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Plasma free fatty acids and risk of stroke in the Cardiovascular Health Study. - Khawaja, Owais; Maziarz, Marlena; Biggs, Mary L; Longstreth, William T; Ix, Joachim H; Kizer, Jorge R; Zieman, Susan; Tracy, Russell P; Mozaffarian, Dariush; Mukamal, Kenneth J; Siscovick, David S; Djoussé, Luc (Int J Stroke, 2014)
BACKGROUND: Although free fatty acids have been positively associated with risk factors for stroke, the role of plasma free fatty acids in the development of stroke has not been elucidated in older adults. AIMS: We sought to examine the association between plasma free fatty acids and incident stroke. METHODS: Prospective cohort of 4369 men and women≥65 years of age in the Cardiovascular Health Study. Plasma levels of free fatty acids were measured at the 1992-1993 examination and stroke events were adjudicated by a committee of experts including neurologists and neuroradiologists. Cox regression was used to estimate the relative risk of stroke associated with free fatty acids concentrations. RESULTS: The average age among participants was 75±5·2 years. During a median follow-up of 11·4 years, 732 incident strokes occurred. The crude incidence rates of stroke were 14·5, 14·9, and 17·6 per 1000 person-years across increasing tertiles of plasma free fatty acids. The adjusted hazard ratio (95% confidence interval) for incident stroke was 1·05 (0·97-1·14) per standard deviation increase in plasma free fatty acids. Restriction to ischemic stroke did not alter the results [hazard ratio (95% confidence interval): 1·04 (0·96-1·14) per standard deviation higher free fatty acids], and there was no effect modification by adiposity (P interaction=0·18) or by diabetes (P interaction=0·15). CONCLUSION: Our data did not show an association of plasma free fatty acids with incident stroke among community dwelling older adults.
Keywords: Aged; Biomarkers; Brain Ischemia; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Male; Prospective Studies; Risk; Stroke

Plasma phospholipid trans-fatty acids levels, cardiovascular diseases, and total mortality: the cardiovascular health study. - Wang, Qianyi; Imamura, Fumiaki; Lemaitre, Rozenn N; Rimm, Eric B; Wang, Molin; King, Irena B; Song, Xiaoling; Siscovick, David; Mozaffarian, Dariush (J Am Heart Assoc, 2014)
BACKGROUND: While self-reported trans-fatty acid (TFA) consumption is linked to coronary heart disease (CHD), relationships between objective biomarkers of TFA subtypes (t-16:1n9, total t-18:1, and cis/trans-(c/t-), t/c- and t/t-18:2) and cardiovascular disease (CVD) or total mortality are not well established. METHODS AND RESULTS: We evaluated 2742 adults in the Cardiovascular Health Study, aged 74±5 years and free of prevalent CVD, with plasma phospholipid TFA measures in 1992. Incident fatal and nonfatal CHD events, CVD and non-CVD mortality, and total mortality were centrally adjudicated through 2010. Risks were assessed using Cox proportional hazards. During 31 494 person-years, 1735 total deaths and 639 total CHD events occurred. In the multivariate model including mutual adjustment for the 5 TFA subtypes, circulating t/t-18:2 was associated with higher total mortality (extreme quintile hazard ratio (HR)=1.23, 95% CI=1.04 to 1.44, P-trend=0.01), CVD mortality (HR=1.40, 95% CI=1.05 to 1.86, P-trend=0.02), and total CHD (HR=1.39, 95% CI=1.06 to 1.83, P-trend=0.01). t/c-18:2 was positively related to total mortality (HR=1.19, P-trend=0.05), total CHD (HR=1.67, P-trend=0.002), and nonfatal CHD (HR=2.06, P-trend=0.002) after mutual adjustment; these associations were insignificant without mutual adjustment. Neither t-16:1n9 nor t-18:1 was significantly associated with total mortality or CVD, nor was c/t-18:2 if we excluded early cases. CONCLUSIONS: Among circulating TFAs, t/t-18:2 was most adversely associated with total mortality, mainly due to the increased risk of CVD. t/c-18:2 was also positively associated with total mortality and CHD, but only after adjustment for other TFAs. These results highlight the need for further investigation of dietary sources, nondietary determinants, and health effects of specific TFA subtypes, especially t-18:2 isomers.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cohort Studies; Dietary Fats; Female; Follow-Up Studies; Humans; Incidence; Male; Mortality; Phospholipids; Prognosis; Proportional Hazards Models; Prospective Studies; Trans Fatty Acids

Plasma-free fatty acids, fatty acid-binding protein 4, and mortality in older adults (from the Cardiovascular Health Study). - Miedema, Michael D; Maziarz, Marlena; Biggs, Mary L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Mozaffarian, Dariush; Tracy, Russell P; Psaty, Bruce M; Siscovick, David S; Mukamal, Kenneth J; Djoussé, Luc (Am J Cardiol, 2014)
Plasma-free fatty acids (FFAs) are largely derived from adipose tissue. Elevated levels of FFA and fatty acid-binding protein 4 (FABP4), a key cytoplasmic chaperone of fatty acids, have been associated with adverse cardiovascular outcomes, but limited data are available on the relation of these biomarkers with cardiovascular and total mortality. We studied 4,707 participants with a mean age of 75 years who had plasma FFA and FABP4 measured in 1992 to 1993 as part of the Cardiovascular Health Study, an observational cohort of community-dwelling older adults. Over a median follow-up of 11.8 years, 3,555 participants died. Cox proportional hazard regression was used to determine the association between FFA, FABP4, and mortality. In fully adjusted models, FFA were associated with dose-dependent significantly higher total mortality (hazard ratio [HR] per SD: 1.14, 95% confidence interval [CI] 1.09 to 1.18), but FABP4 levels were not (HR 1.04, 95% CI 0.98 to 1.09). In a cause-specific mortality analysis, higher concentrations of FFA were associated with significantly higher risk of death because of cardiovascular disease, dementia, infection, and respiratory causes but not cancer or trauma. We did not find evidence of an interaction between FFA and FABP4 (p = 0.45), but FABP4 appeared to be associated with total mortality differentially in men and women (HR 1.17, 95% CI 1.08 to 1.26 for men; HR 1.02, 95% CI 0.96 to 1.07 for women, interaction p value <0.001). In conclusion, in a cohort of community-dwelling older subjects, elevated plasma concentrations of FFA, but not FABP4, were associated with cardiovascular and noncardiovascular mortality.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cause of Death; Fatty Acid-Binding Proteins; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Health Status; Humans; Male; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors; United States

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Quantifying rare, deleterious variation in 12 human cytochrome P450 drug-metabolism genes in a large-scale exome dataset. - Gordon, Adam S; Tabor, Holly K; Johnson, Andrew D; Snively, Beverly M; Assimes, Themistocles L; Auer, Paul L; Ioannidis, John P A; Peters, Ulrike; Robinson, Jennifer G; Sucheston, Lara E; Wang, Danxin; Sotoodehnia, Nona; et al. (Hum Mol Genet, 2014)
The study of genetic influences on drug response and efficacy ('pharmacogenetics') has existed for over 50 years. Yet, we still lack a complete picture of how genetic variation, both common and rare, affects each individual's responses to medications. Exome sequencing is a promising alternative method for pharmacogenetic discovery as it provides information on both common and rare variation in large numbers of individuals. Using exome data from 2203 AA and 4300 Caucasian individuals through the NHLBI Exome Sequencing Project, we conducted a survey of coding variation within 12 Cytochrome P450 (CYP) genes that are collectively responsible for catalyzing nearly 75% of all known Phase I drug oxidation reactions. In addition to identifying many polymorphisms with known pharmacogenetic effects, we discovered over 730 novel nonsynonymous alleles across the 12 CYP genes of interest. These alleles include many with diverse functional effects such as premature stop codons, aberrant splicesites and mutations at conserved active site residues. Our analysis considering both novel, predicted functional alleles as well as known, actionable CYP alleles reveals that rare, deleterious variation contributes markedly to the overall burden of pharmacogenetic alleles within the populations considered, and that the contribution of rare variation to this burden is over three times greater in AA individuals as compared with Caucasians. While most of these impactful alleles are individually rare, 7.6-11.7% of individuals interrogated in the study carry at least one newly described potentially deleterious alleles in a major drug-metabolizing CYP.
Keywords: Cytochrome P-450 Enzyme System; Databases, Genetic; European Continental Ancestry Group; Exome; Humans; Pharmaceutical Preparations; Pharmacogenetics; Polymorphism, Genetic

Relations of plasma total and high-molecular-weight adiponectin to new-onset heart failure in adults ≥65 years of age (from the Cardiovascular Health study). - Karas, Maria G; Benkeser, David; Arnold, Alice M; Bartz, Traci M; Djoussé, Luc; Mukamal, Kenneth J; Ix, Joachim H; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Mantzoros, Christos S; Gottdiener, John S; et al. (Am J Cardiol, 2014)
Adiponectin exhibits cardioprotective properties in experimental studies, but elevated levels have been linked to increased mortality in older adults and patients with chronic heart failure (HF). The adipokine's association with new-onset HF remains less well defined. The aim of this study was to investigate the associations of total and high-molecular weight (HMW) adiponectin with incident HF (n = 780) and, in a subset, echocardiographic parameters in a community-based cohort of adults aged ≥65 years. Total and HMW adiponectin were measured in 3,228 subjects without prevalent HF, atrial fibrillation or CVD. The relations of total and HMW adiponectin with HF were nonlinear, with significant associations observed only for concentrations greater than the median (12.4 and 6.2 mg/L, respectively). After adjustment for potential confounders, the hazard ratios per SD increment in total adiponectin were 0.93 (95% confidence interval 0.72 to 1.21) for concentrations less than the median and 1.25 (95% confidence interval 1.14 to 1.38) higher than the median. There was a suggestion of effect modification by body mass index, whereby the association appeared strongest in participants with lower body mass indexes. Consistent with the HF findings, higher adiponectin tended to be associated with left ventricular systolic dysfunction and left atrial enlargement. Results were similar for HMW adiponectin. In conclusion, total and HMW adiponectin showed comparable relations with incident HF in this older cohort, with a threshold effect of increasing risk occurring at their median concentrations. High levels of adiponectin may mark or mediate age-related processes that lead to HF in older adults.
Keywords: Adiponectin; Age of Onset; Aged; Biomarkers; Cross-Sectional Studies; Echocardiography, Doppler; Enzyme-Linked Immunosorbent Assay; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Prognosis; Prospective Studies; Recurrence; Severity of Illness Index; United States; Ventricular Function, Left

Relative risks of chronic kidney disease for mortality and end-stage renal disease across races are similar. - Wen, Chi Pang; Matsushita, Kunihiro; Coresh, Josef; Iseki, Kunitoshi; Islam, Muhammad; Katz, Ronit; McClellan, William; Peralta, Carmen A; Wang, Haiyan; de Zeeuw, Dick; Astor, Brad C; Gansevoort, Ron T; et al. (Kidney Int, 2014)
Some suggest race-specific cutpoints for kidney measures to define and stage chronic kidney disease (CKD), but evidence for race-specific clinical impact is limited. To address this issue, we compared hazard ratios of estimated glomerular filtration rates (eGFR) and albuminuria across races using meta-regression in 1.1 million adults (75% Asians, 21% Whites, and 4% Blacks) from 45 cohorts. Results came mainly from 25 general population cohorts comprising 0.9 million individuals. The associations of lower eGFR and higher albuminuria with mortality and end-stage renal disease (ESRD) were largely similar across races. For example, in Asians, Whites, and Blacks, the adjusted hazard ratios (95% confidence interval) for eGFR 45-59 versus 90-104 ml/min per 1.73 m(2) were 1.3 (1.2-1.3), 1.1 (1.0-1.2), and 1.3 (1.1-1.7) for all-cause mortality, 1.6 (1.5-1.7), 1.4 (1.2-1.7), and 1.4 (0.7-2.9) for cardiovascular mortality, and 27.6 (11.1-68.7), 11.2 (6.0-20.9), and 4.1 (2.2-7.5) for ESRD, respectively. The corresponding hazard ratios for urine albumin-to-creatinine ratio 30-299 mg/g or dipstick 1+ versus an albumin-to-creatinine ratio under 10 or dipstick negative were 1.6 (1.4-1.8), 1.7 (1.5-1.9), and 1.8 (1.7-2.1) for all-cause mortality, 1.7 (1.4-2.0), 1.8 (1.5-2.1), and 2.8 (2.2-3.6) for cardiovascular mortality, and 7.4 (2.0-27.6), 4.0 (2.8-5.9), and 5.6 (3.4-9.2) for ESRD, respectively. Thus, the relative mortality or ESRD risks of lower eGFR and higher albuminuria were largely similar among three major races, supporting similar clinical approach to CKD definition and staging, across races.
Keywords: Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Albuminuria; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Creatinine; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Renal Insufficiency, Chronic; Risk Factors

Separate prediction of intracerebral hemorrhage and ischemic stroke. - Ferket, Bart S; van Kempen, Bob J H; Wieberdink, Renske G; Steyerberg, Ewout W; Koudstaal, Peter J; Hofman, Albert; Shahar, Eyal; Gottesman, Rebecca F; Rosamond, Wayne; Kizer, Jorge R; Kronmal, Richard A; Psaty, Bruce M; et al. (Neurology, 2014)
OBJECTIVES: To develop and validate 10-year cumulative incidence functions of intracerebral hemorrhage (ICH) and ischemic stroke (IS). METHODS: We used data on 27,493 participants from 3 population-based cohort studies: the Atherosclerosis Risk in Communities Study, median age 54 years, 45% male, median follow-up 20.7 years; the Rotterdam Study, median age 68 years, 38% male, median follow-up 14.3 years; and the Cardiovascular Health Study, median age 71 years, 41% male, median follow-up 12.8 years. Among these participants, 325 ICH events, 2,559 IS events, and 9,909 nonstroke deaths occurred. We developed 10-year cumulative incidence functions for ICH and IS using stratified Cox regression and competing risks analysis. Basic models including only established nonlaboratory risk factors were extended with diastolic blood pressure, total cholesterol/high-density lipoprotein cholesterol ratio, body mass index, waist-to-hip ratio, and glomerular filtration rate. The cumulative incidence functions' performances were cross-validated in each cohort separately by Harrell C-statistic and calibration plots. RESULTS: High total cholesterol/high-density lipoprotein cholesterol ratio decreased the ICH rates but increased IS rates (p for difference across stroke types <0.001). For both the ICH and IS models, C statistics increased more by model extension in the Atherosclerosis Risk in Communities and Cardiovascular Health Study cohorts. Improvements in C statistics were reproduced by cross-validation. Models were well calibrated in all cohorts. Correlations between 10-year ICH and IS risks were moderate in each cohort. CONCLUSIONS: We developed and cross-validated cumulative incidence functions for separate prediction of 10-year ICH and IS risk. These functions can be useful to further specify an individual's stroke risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Body Mass Index; Brain Ischemia; Cholesterol; Female; Humans; Incidence; Intracranial Hemorrhages; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Risk Assessment; Risk Factors; Stroke

Serum carboxymethyl-lysine, disability, and frailty in older persons: the Cardiovascular Health Study. - Whitson, Heather E; Arnold, Alice M; Yee, Laura M; Mukamal, Kenneth J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Siscovick, David; Tracy, Russell P; Thielke, Stephen M; Hirsch, Calvin; Newman, Anne B; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Advanced glycation endproducts are biologically active compounds that accumulate in disordered metabolism and normal aging. Carboxymethyl-lysine (CML), a ubiquitous human advanced glycation endproduct, has been associated with age-related conditions and mortality. Our objective was to ascertain the relationship between CML and geriatric outcomes (disability and frailty) in a large cohort of older men and women. METHODS: In 1996-1997, serum CML was measured in 3,373 Cardiovascular Health Study participants (mean age 78.1 ± 4.8 years). Disability, defined as difficulty in any of six activities of daily living, was assessed every 6-12 months for 14 years. Frailty was defined according to five standard criteria at the 1996-1997 visit. Cox proportional hazard models estimated the relationship between CML and incident disability (N = 2,643). Logistic regression models estimated the relationship between CML and prevalent frailty. RESULTS: Adjusting for multiple potential confounders, higher CML was associated with incident disability (hazard ratio per standard deviation [225 ng/mL] increase: 1.05, 95% CI 1.01-1.11). In men, odds of frailty increased with higher CML values (odds ratio = 1.30 per standard deviation, 95% CI 1.14-1.48), but the relationship was attenuated by adjustment for cognitive status, kidney function, and arthritis. CML was not associated with frailty in women. CONCLUSIONS: Higher serum CML levels in late life are associated with incident disability and prevalent frailty. Further work is needed to understand CML's value as a risk stratifier, biomarker, or target for interventions that promote healthy aging.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Biomarkers; Cardiac Rehabilitation; Cardiovascular Diseases; Disabled Persons; Female; Follow-Up Studies; Frail Elderly; Health Status; Humans; Incidence; Lysine; Male; Prevalence; Prognosis; Retrospective Studies; United States

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Subclinical vascular disease burden and longer survival. - Odden, Michelle C; Yee, Laura M; Arnold, Alice M; Sanders, Jason L; Hirsch, Calvin; DeFilippi, Christopher; Kizer, Jorge R; Inzitari, Marco; Newman, Anne B (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the contribution of gradations of subclinical vascular disease (SVD) to the likelihood of longer survival and to determine what allows some individuals with SVD to live longer. DESIGN: Cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals born between June 30, 1918, and June 30, 1921 (N = 2,082; aged 70-75 at baseline (1992-93)). MEASUREMENTS: A SVD index was scored as 0 for no abnormalities, 1 for mild abnormalities, and 2 for severe abnormalities on ankle-arm index, electrocardiogram, and common carotid intima-media thickness measured at baseline. Survival groups were categorized as 80 and younger, 81 to 84, 85 to 89, and 90 and older. RESULTS: A 1-point lower SVD score was associated with 1.22 greater odds (95% confidence interval = 1.14-1.31) of longer survival, independent of potential confounders. This association was unchanged after adjustment for intermediate incident cardiovascular events. There was suggestion of an interaction between kidney function, smoking, and C-reactive protein and SVD; the association between SVD and longer survival appeared to be modestly greater in persons with poor kidney function, inflammation, or a history of smoking. CONCLUSION: A lower burden of SVD is associated with longer survival, independent of intermediate cardiovascular events. Abstinence from smoking, better kidney function, and lower inflammation may attenuate the effects of higher SVD and promote longer survival.
Keywords: Aged; Aged, 80 and over; C-Reactive Protein; Carotid Intima-Media Thickness; Cohort Studies; Cystatin C; Depression; Diabetes Mellitus; Electrocardiography; Female; Humans; Inflammation; Kidney Diseases; Male; Smoking; Survival Analysis; United States; Vascular Diseases

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of Fetuin-A With Incident Fractures in Community-Dwelling Older Adults: The Cardiovascular Health Study. - Fink, Howard A; Bůzková, Petra; Garimella, Pranav S; Mukamal, Kenneth J; Cauley, Jane A; Kizer, Jorge R; Barzilay, Joshua I; Jalal, Diana I; Ix, Joachim H (J Bone Miner Res, 2015)
Fetuin-A, a serum protein that regulates calcium mineralization, has been associated with bone mineral density (BMD) in several cross-sectional human studies, suggesting a possible beneficial effect on clinically important measures of bone health. Fetuin-A and incidence of subsequent fracture was assessed in 4714 men and women ≥65 years of age. Proportional hazards models were used to estimate risk of incident hip (hospital discharge ICD-9 codes) and composite fracture (hip, pelvis, humerus, or proximal forearm; hospital discharge ICD-9 codes and Medicare claims data). A total of 576 participants had an incident hip fracture (median follow-up 11.2 years) and 768 had an incident composite fracture (median follow-up 6.9 years). In unadjusted analyses, there was no association between fetuin-A (per SD increase) and risk of hip fracture (hazard ratio [HR], 0.96; 95% CI, 0.88 to 1.05) or composite fracture (HR, 0.99; 95% CI, 0.92 to 1.06). Results were not significantly changed after adjustment for potential confounding variables. Analyses modeling fetuin-A in quartiles or within a subset with available BMD measures also showed no statistically significant association with risk of hip or composite fracture. Though fetuin-A was positively associated with areal BMD in partially adjusted models (total hip: β, 0.013 g/cm(2) ; 95% CI, 0.005 to 0.021; femoral neck: β, 0.011 g/cm(2) ; 95% CI, 0.004 to 0.018; and lumbar spine: β, 0.007 g/cm(2) ; 95% CI, 0.001 to 0.028), these associations were no longer significant after further adjustment for BMI and in final multivariate models. In this large sample of community-dwelling older adults, a small positive association between fetuin-A and areal BMD appeared attributable to confounding variables and we found no evidence of an association between fetuin-A and risk of clinical fracture.
Keywords: Adult; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Bone Density; Cross-Sectional Studies; Female; Follow-Up Studies; Fractures, Bone; Humans; Incidence; Male; Models, Biological

Associations between metabolic dysregulation and circulating biomarkers of fibrosis: the Cardiovascular Health Study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; King, George L; Mukamal, Ken J (Metabolism, 2015)
AIM: Fibrosis is one postulated pathway by which diabetes produces cardiac and other systemic complications. Our aim was to determine which metabolic parameters are associated with circulating fibrosis-related biomarkers transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP). METHODS: We used linear regression to determine the cross-sectional associations of diverse metabolic parameters, including fasting glucose, fasting insulin, body mass index, fatty acid binding protein 4, and non-esterified fatty acids, with circulating levels of TGF-β (n = 1559) and PIIINP (n = 3024) among community-living older adults in the Cardiovascular Health Study. RESULTS: Among the main metabolic parameters we examined, only fasting glucose was associated with TGF-β (P = 0.03). In contrast, multiple metabolic parameters were associated with PIIINP, including fasting insulin, body mass index, and non-esterified fatty acids (P<0.001, P<0.001, P=0.001, respectively). These associations remained statistically significant after mutual adjustment, except the association between BMI and PIIINP. CONCLUSIONS: Isolated hyperglycemia is associated with higher serum concentrations of TGF-β, while a broader phenotype of insulin resistance is associated with higher serum PIIINP. Whether simultaneous pharmacologic targeting of these two metabolic phenotypes can synergistically reduce the risk of cardiac and other manifestations of fibrosis remains to be determined.
Keywords: Aged; Aged, 80 and over; Biomarkers; Blood Glucose; Cardiovascular System; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Fatty Acids, Nonesterified; Female; Fibrosis; Health; Humans; Insulin; Insulin Resistance; Male; Metabolic Diseases; Peptide Fragments; Procollagen; Transforming Growth Factor beta

Circulating and dietary trans fatty acids and incident type 2 diabetes in older adults: the Cardiovascular Health Study. - Wang, Qianyi; Imamura, Fumiaki; Ma, Wenjie; Wang, Molin; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Biggs, Mary L; Delaney, Joseph A; Mukamal, Kenneth J; Djoussé, Luc; Siscovick, David S; et al. (Diabetes Care, 2015)
OBJECTIVE: To investigate the effects of trans fatty acids (TFAs) on type 2 diabetes mellitus (DM) by specific TFA subtype or method of assessment. RESEARCH DESIGN AND METHODS: In the Cardiovascular Health Study, plasma phospholipid trans (t)-16:1n9, t-18:1, and cis (c)/t-, t/c-, and t/t-18:2 were measured in blood drawn from 2,919 adults aged 74 ± 5 years and free of prevalent DM in 1992. Dietary TFA was estimated among 4,207 adults free of prevalent DM when dietary questionnaires were initially administered in 1989 or 1996. Incident DM was defined through 2010 by medication use or blood glucose levels. Risks were assessed by Cox proportional hazards. RESULTS: In biomarker analyses, 287 DM cases occurred during 30,825 person-years. Both t-16:1n9 (extreme quartile hazard ratio 1.59 [95% CI 1.04-2.42], P-trend = 0.04) and t-18:1 (1.91 [1.20-3.03], P-trend = 0.01) levels were associated with higher incident DM after adjustment for de novo lipogenesis fatty acids. In dietary analyses, 407 DM cases occurred during 50,105 person-years. Incident DM was positively associated with consumption of total TFAs (1.38 [1.03-1.86], P-trend = 0.02), t-18:1 (1.32 [1.00-1.76], P-trend = 0.04), and t-18:2 (1.41 [1.05-1.89], P-trend = 0.02). After further adjustment for other dietary habits, however, the associations of estimated dietary TFA with DM were attenuated, and only nonsignificant positive trends remained. CONCLUSIONS: Among older adults, plasma phospholipid t-16:1n9 and t-18:1 levels were positively related to DM after adjustment for de novo lipogenesis fatty acids. Estimated dietary TFA was not significantly associated with DM. These findings highlight the need for further observational, interventional, and experimental studies of the effects TFA on DM.
Keywords: Aged; Biomarkers; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Dietary Fats, Unsaturated; Epidemiologic Methods; Female; Food Habits; Humans; Male; Phospholipids; Trans Fatty Acids

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease. - Rannikmae, Kristiina; Davies, Gail; Thomson, Pippa A; Bevan, Steve; Devan, William J; Falcone, Guido J; Traylor, Matthew; Anderson, Christopher D; Battey, Thomas W K; Radmanesh, Farid; Deka, Ranjan; Woo, Jessica G; et al. (Neurology, 2015)
OBJECTIVES: We hypothesized that common variants in the collagen genes COL4A1/COL4A2 are associated with sporadic forms of cerebral small vessel disease. METHODS: We conducted meta-analyses of existing genotype data among individuals of European ancestry to determine associations of 1,070 common single nucleotide polymorphisms (SNPs) in the COL4A1/COL4A2 genomic region with the following: intracerebral hemorrhage and its subtypes (deep, lobar) (1,545 cases, 1,485 controls); ischemic stroke and its subtypes (cardioembolic, large vessel disease, lacunar) (12,389 cases, 62,004 controls); and white matter hyperintensities (2,733 individuals with ischemic stroke and 9,361 from population-based cohorts with brain MRI data). We calculated a statistical significance threshold that accounted for multiple testing and linkage disequilibrium between SNPs (p < 0.000084). RESULTS: Three intronic SNPs in COL4A2 were significantly associated with deep intracerebral hemorrhage (lead SNP odds ratio [OR] 1.29, 95% confidence interval [CI] 1.14-1.46, p = 0.00003; r(2) > 0.9 between SNPs). Although SNPs associated with deep intracerebral hemorrhage did not reach our significance threshold for association with lacunar ischemic stroke (lead SNP OR 1.10, 95% CI 1.03-1.18, p = 0.0073), and with white matter hyperintensity volume in symptomatic ischemic stroke patients (lead SNP OR 1.07, 95% CI 1.01-1.13, p = 0.016), the direction of association was the same. There was no convincing evidence of association with white matter hyperintensities in population-based studies or with non-small vessel disease cerebrovascular phenotypes. CONCLUSIONS: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.
Keywords: Cerebral Small Vessel Diseases; Collagen Type IV; Genetic Association Studies; Genetic Variation; Humans; Polymorphism, Single Nucleotide

Contribution of Major Lifestyle Risk Factors for Incident Heart Failure in Older Adults: The Cardiovascular Health Study. - Del Gobbo, Liana C; Kalantarian, Shadi; Imamura, Fumiaki; Lemaitre, Rozenn; Siscovick, David S; Psaty, Bruce M; Mozaffarian, Dariush (JACC Heart Fail, 2015)
OBJECTIVES: The goal of this study was to determine the relative contribution of major lifestyle factors on the development of heart failure (HF) in older adults. BACKGROUND: HF incurs high morbidity, mortality, and health care costs among adults ≥65 years of age, which is the most rapidly growing segment of the U.S. METHODS: We prospectively investigated separate and combined associations of lifestyle risk factors with incident HF (1,380 cases) over 21.5 years among 4,490 men and women in the Cardiovascular Health Study, which is a community-based cohort of older adults. Lifestyle factors included 4 dietary patterns (Alternative Healthy Eating Index, Dietary Approaches to Stop Hypertension, an American Heart Association 2020 dietary goals score, and a Biologic pattern, which was constructed using previous knowledge of cardiovascular disease dietary risk factors), 4 physical activity metrics (exercise intensity, walking pace, energy expended in leisure activity, and walking distance), alcohol intake, smoking, and obesity. RESULTS: No dietary pattern was associated with developing HF (p > 0.05). Walking pace and leisure activity were associated with a 26% and 22% lower risk of HF, respectively (pace >3 mph vs. <2 mph; hazard ratio [HR]: 0.74; 95% confidence interval [CI]: 0.63 to 0.86; leisure activity ≥845 kcal/week vs. <845 kcal/week; HR: 0.78; 95% CI: 0.69 to 0.87). Modest alcohol intake, maintaining a body mass index <30 kg/m(2), and not smoking were also independently associated with a lower risk of HF. Participants with ≥4 healthy lifestyle factors had a 45% (HR: 0.55; 95% CI: 0.42 to 0.74) lower risk of HF. Heterogeneity by age, sex, cardiovascular disease, hypertension medication use, and diabetes was not observed. CONCLUSIONS: Among older U.S. adults, physical activity, modest alcohol intake, avoiding obesity, and not smoking, but not dietary patterns, were associated with a lower risk of HF.
Keywords: Aged; Alcohol Drinking; Cohort Studies; Diet; Female; Heart Failure; Humans; Incidence; Male; Motor Activity; Obesity; Proportional Hazards Models; Prospective Studies; Risk Factors; Sedentary Lifestyle; Smoking; United States

Convergent genetic and expression data implicate immunity in Alzheimer's disease. (Alzheimers Dement, 2015)
BACKGROUND: Late-onset Alzheimer's disease (AD) is heritable with 20 genes showing genome-wide association in the International Genomics of Alzheimer's Project (IGAP). To identify the biology underlying the disease, we extended these genetic data in a pathway analysis. METHODS: The ALIGATOR and GSEA algorithms were used in the IGAP data to identify associated functional pathways and correlated gene expression networks in human brain. RESULTS: ALIGATOR identified an excess of curated biological pathways showing enrichment of association. Enriched areas of biology included the immune response (P = 3.27 × 10(-12) after multiple testing correction for pathways), regulation of endocytosis (P = 1.31 × 10(-11)), cholesterol transport (P = 2.96 × 10(-9)), and proteasome-ubiquitin activity (P = 1.34 × 10(-6)). Correlated gene expression analysis identified four significant network modules, all related to the immune response (corrected P = .002-.05). CONCLUSIONS: The immune response, regulation of endocytosis, cholesterol transport, and protein ubiquitination represent prime targets for AD therapeutics.
Keywords: Algorithms; Alzheimer Disease; Brain; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide

Development and validation of a model to predict 5-year risk of death without ESRD among older adults with CKD. - Bansal, Nisha; Katz, Ronit; de Boer, Ian H; Peralta, Carmen A; Fried, Linda F; Siscovick, David S; Rifkin, Dena E; Hirsch, Calvin; Cummings, Steven R; Harris, Tamara B; Kritchevsky, Stephen B; Sarnak, Mark J; et al. (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: CKD is associated with mortality. Accurate prediction tools for mortality may guide clinical decision-making, particularly among elderly persons with CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: A prediction equation was developed for 5-year risk of mortality among participants with CKD in the Cardiovascular Health Study. Sixteen candidate predictor variables were explored, which included demographics, physical examination measures, comorbidity, medication use, and kidney function measures (eGFR calculated from serum creatinine and the CKD Epidemiology Collaboration equation and the urine albumin-to-creatinine ratio). Models were developed using Cox regression and evaluated using c statistics. A final parsimonious model was externally validated in an independent cohort of community-living elders with CKD in the Health, Aging, and Body Composition Study. RESULTS: The development cohort included 828 participants who had a mean age of 80 (±5.6) years and an eGFR of 47 (±11) ml/min per 1.73 m(2), and median albumin-to-creatinine ratio of 13 (interquartile range 6-51) mg/g. The validation cohort included 789 participants who had a mean age of 74 (±2.8) years and an eGFR of 50 (±9) ml/min per 1.73 m(2), and median albumin-to-creatinine ratio of 13 (interquartile range 6-42) mg/g. The final model for 5-year mortality risk included age, sex, race, eGFR, urine albumin-to-creatinine ratio, smoking, diabetes mellitus, and history of heart failure and stroke (c statistic=0.72; 95% confidence interval, 0.68 to 0.74). When a point-based system was assigned for each of nine variables in the equation, the estimated risk of death within 5 years ranged from 3.8% among participants with the lowest scores to 83.6% among participants with nine points. The model performed fair in external validation (c statistic=0.69; 95% confidence interval, 0.64 to 0.74). CONCLUSIONS: A simple prediction tool using nine readily available clinical variables can assist in predicting 5-year mortality risk in elderly patients with CKD, which may be useful in counseling patients and guiding clinical decision making.
Keywords: Age Factors; Aged; Aged, 80 and over; Albuminuria; Continental Population Groups; Creatinine; Diabetes Mellitus; Female; Glomerular Filtration Rate; Heart Failure; Humans; Male; Proportional Hazards Models; Regression Analysis; Renal Insufficiency, Chronic; Risk Factors; Sex Factors; Smoking; Stroke

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Fetuin-A and risk of coronary heart disease: A Mendelian randomization analysis and a pooled analysis of AHSG genetic variants in 7 prospective studies. - Laugsand, Lars E; Ix, Joachim H; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Dehghan, Abbas; Rexrode, Kathryn; Lopez, Oscar L; Rimm, Eric B; Siscovick, David S; O'Donnell, Christopher J; et al. (Atherosclerosis, 2015)
BACKGROUND AND AIMS: Fetuin-A has a plausible role in the inhibition of arterial calcification, but its association with risk of coronary heart disease (CHD) in the general population is unclear. We used two common genetic variants in the fetuin-A gene (AHSG) that are strongly associated with circulating fetuin-A levels to investigate the associations with risk of CHD and subclinical cardiovascular measures (intima-media thickness, ankle-arm index, and coronary artery calcification). METHODS: Genetic variation and fetuin-A levels were assessed in 3299 community-living individuals (2733 Caucasians and 566 African Americans) 65 years of age or older, free of previous cardiovascular disease, who participated in the Cardiovascular Health Study (CHS) in 1992-1993. RESULTS: Among Caucasians, both rs2248690 and rs4917 were associated with 12% lower fetuin-A concentrations per minor allele (P < 0.0001). The hazard ratios (HRs) per minor allele for incident CHD were 1.12 (95% CI: 1.00-1.26) for rs2248690 and 1.02 (0.91-1.14) for rs4917. Using both genotypes as an instrumental variable for measured fetuin-A, the HRs for one standard deviation increase in genetically determined fetuin-A levels on CHD risk were 0.84 (95% CI: 0.70-1.00) for rs2248690 and 0.97 (95% CI: 0.82-1.14) for rs4917, respectively. However, in CHS neither of the genotypes were associated with subclinical cardiovascular measures and when CHS data were meta-analyzed with data from six other prospective studies (totaling 26,702 Caucasian participants and 3295 CHD cases), the meta-analyzed HRs for incident CHD were 1.12 (0.93-1.34) and 1.06 (0.93-1.20) for rs2248690 and rs4917, respectively (p heterogeneity 0.005 and 0.0048). CONCLUSION: Common variants in the AHSG gene are strongly associated with fetuin-A levels, but their concurrent association with CHD risk in current prospective studies is inconsistent. Further investigation in studies with measured fetuin-A and AHSG variants is needed to clarify the potential causal association of fetuin-A with CHD risk.
Keywords: Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Carotid Intima-Media Thickness; Coronary Vessels; Female; Genetic Variation; Genotype; Heart Diseases; Humans; Insulin Resistance; Longitudinal Studies; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Vascular Calcification

Fibroblast growth factor 23 and sudden versus non-sudden cardiac death: the Cardiovascular Health Study. - Deo, Rajat; Katz, Ronit; de Boer, Ian H; Sotoodehnia, Nona; Kestenbaum, Bryan; Mukamal, Kenneth J; Chonchol, Michel; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G; Ix, Joachim H (Am J Kidney Dis, 2015)
BACKGROUND: Elevated fibroblast growth factor 23 (FGF-23) concentrations are associated with greater risk of cardiovascular events and mortality, especially among people with chronic kidney disease (CKD). Because individuals with CKD are at an increased risk of sudden cardiac death (SCD), we sought to understand whether FGF-23 level is a stronger risk factor for SCD versus non-SCD. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 3,244 participants 65 years or older in the community-based Cardiovascular Health Study. PREDICTOR: Plasma FGF-23 concentrations. OUTCOMES: We assessed SCD and non-SCD in these analyses. SCD was adjudicated rigorously and was defined as a sudden pulseless condition of cardiac origin in a previously stable person occurring out of hospital or in the emergency department. MEASUREMENTS: We estimated associations of baseline FGF-23 concentrations with SCD and non-SCD using Cox proportional hazards models after adjustment for demographics, cardiovascular risk factors, comorbid conditions, and kidney function. We also tested whether associations differed by CKD status. RESULTS: During a median follow-up of 8.1 years, there were 118 adjudicated SCD and 570 non-SCD events. After multivariable adjustment for demographics, cardiovascular risk factors, comorbid conditions, and parameters of kidney function, higher FGF-23 concentrations were an independent risk factor for non-SCD (HR [per doubling], 1.17; 95% CI, 1.06-1.30). However, elevated FGF-23 concentrations were not associated independently with SCD (HR [per doubling], 1.07; 95% CI, 0.85-1.35). In stratified analysis by CKD status (36.5% of cohort), doubling of FGF-23 concentrations was associated independently with non-SCD (adjusted HR, 1.26; 95% CI, 1.10-1.45). A similar magnitude of association was observed between FGF-23 level and SCD in the CKD subgroup; however, it was not significant (HR, 1.20; 95% CI, 0.89-1.62). LIMITATIONS: Limited power to detect moderate-sized effects between FGF-23 level and SCD in both the primary and stratified analyses. CONCLUSIONS: In this population-based study, FGF-23 level elevations were associated independently with non-SCD. Among individuals with CKD, the associations between FGF-23 level and SCD and non-SCD were similar.
Keywords: Aged; Aged, 80 and over; Biomarkers; Comorbidity; Death, Sudden, Cardiac; Electrocardiography; Female; Fibroblast Growth Factors; Follow-Up Studies; Heart Arrest; Heart Diseases; Humans; Kaplan-Meier Estimate; Male; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors; Sympathetic Nervous System; United States

Fibrosis-related biomarkers and large and small vessel disease: the Cardiovascular Health Study. - Agarwal, Isha; Arnold, Alice; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Jensen, Richard A; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; et al. (Atherosclerosis, 2015)
OBJECTIVE: Fibrosis has been implicated in a number of pathological, organ-based conditions of the liver, kidney, heart, and lungs. The objective of this study was to determine whether biomarkers of fibrosis are associated with vascular disease in the large and/or small vessels. METHODS: We evaluated the associations of two circulating biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident peripheral artery disease (PAD) and subclinical macrovascular (carotid intima-media thickness, flow-mediated vasodilation, ankle-brachial index, retinal vein diameter), and microvascular (retinal artery diameter and retinopathy) disease among older adults in the Cardiovascular Health Study. We measured TGF-β and PIIINP from samples collected in 1996 and ascertained clinical PAD through 2011. Measurements of large and small vessels were collected between 1996 and 1998. RESULTS: After adjustment for sociodemographic, clinical, and biochemical risk factors, TGF-β was associated with incident PAD (hazard ratio [HR] = 1.36 per doubling of TGF-β, 95% confidence interval [CI] = 1.04, 1.78) and retinal venular diameter (1.63 μm per doubling of TGF-β, CI = 0.23, 3.02). PIIINP was not associated with incident PAD, but was associated with carotid intima-media thickness (0.102 mm per doubling of PIIINP, CI = 0.029, 0.174) and impaired brachial artery reactivity (-0.20% change per doubling of PIIINP, CI = -0.39, -0.02). Neither TGF-β nor PIIINP were associated with retinal arteriolar diameter or retinopathy. CONCLUSIONS: Serum concentrations of fibrosis-related biomarkers were associated with several measures of large vessel disease, including incident PAD, but not with small vessel disease. Fibrosis may contribute to large vessel atherosclerosis in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Brachial Artery; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cross-Sectional Studies; Female; Fibrosis; Humans; Incidence; Male; Peptide Fragments; Peripheral Arterial Disease; Predictive Value of Tests; Procollagen; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Transforming Growth Factor beta; United States; Vasodilation

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Genes from a translational analysis support a multifactorial nature of white matter hyperintensities. - Lopez, Lorna M; Hill, W David; Harris, Sarah E; Valdes Hernandez, Maria; Munoz Maniega, Susana; Bastin, Mark E; Bailey, Emma; Smith, Colin; McBride, Martin; McClure, John; Graham, Delyth; Dominiczak, Anna; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) of presumed vascular origin increase the risk of stroke and dementia. Despite strong WMH heritability, few gene associations have been identified. Relevant experimental models may be informative. METHODS: We tested the associations between genes that were differentially expressed in brains of young spontaneously hypertensive stroke-prone rats and human WMH (using volume and visual score) in 621 subjects from the Lothian Birth Cohort 1936 (LBC1936). We then attempted replication in 9361 subjects from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE). We also tested the subjects from LBC1936 for previous genome-wide WMH associations found in subjects from CHARGE. RESULTS: Of 126 spontaneously hypertensive stroke-prone rat genes, 10 were nominally associated with WMH volume or score in subjects from LBC1936, of which 5 (AFP, ALB, GNAI1, RBM8a, and MRPL18) were associated with both WMH volume and score (P<0.05); 2 of the 10 (XPNPEP1, P=6.7×10(-5); FARP1, P=0.024) plus another spontaneously hypertensive stroke-prone rat gene (USMG5, P=0.00014), on chromosomes 10, 13, and 10 respectively, were associated with WMH in subjects from CHARGE. Gene set enrichment showed significant associations for downregulated spontaneously hypertensive stroke-prone rat genes with WMH in humans. In subjects from LBC1936, we replicated CHARGE's genome-wide WMH associations on chromosomes 17 (TRIM65 and TRIM47) and, for the first time, 1 (PMF1). CONCLUSIONS: Despite not passing multiple testing thresholds individually, these genes collectively are relevant to known WMH associations, proposed WMH mechanisms, or dementia: associations with Alzheimer's disease, late-life depression, ATP production, osmotic regulation, neurodevelopmental abnormalities, and cognitive impairment. If replicated further, they suggest a multifactorial nature for WMH and argue for more consideration of vascular contributions to dementia.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Causality; Dementia; Female; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Wistar; Risk Factors; Translational Medical Research; White Matter

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome of The Netherlands population-specific imputations identify an ABCA6 variant associated with cholesterol levels. - van Leeuwen, Elisabeth M; Karssen, Lennart C; Deelen, Joris; Isaacs, Aaron; Medina-Gómez, Carolina; Mbarek, Hamdi; Kanterakis, Alexandros; Trompet, Stella; Postmus, Iris; Verweij, Niek; van Enckevort, David J; Huffman, Jennifer E; et al. (Nat Commun, 2015)
Variants associated with blood lipid levels may be population-specific. To identify low-frequency variants associated with this phenotype, population-specific reference panels may be used. Here we impute nine large Dutch biobanks (~35,000 samples) with the population-specific reference panel created by the Genome of The Netherlands Project and perform association testing with blood lipid levels. We report the discovery of five novel associations at four loci (P value <6.61 × 10(-4)), including a rare missense variant in ABCA6 (rs77542162, p.Cys1359Arg, frequency 0.034), which is predicted to be deleterious. The frequency of this ABCA6 variant is 3.65-fold increased in the Dutch and its effect (βLDL-C=0.135, βTC=0.140) is estimated to be very similar to those observed for single variants in well-known lipid genes, such as LDLR.
Keywords: ATP-Binding Cassette Transporters; Cholesterol; Gene Frequency; Genetic Association Studies; Humans; Mutation, Missense; Netherlands

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

Higher circulating adiponectin levels are associated with increased risk of atrial fibrillation in older adults. - Macheret, Fima; Bartz, Traci M; Djoussé, Luc; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Heckbert, Susan R; Psaty, Bruce M; Kizer, Jorge R (Heart, 2015)
BACKGROUND: Adiponectin has cardioprotective properties, suggesting that lower levels seen in obesity and diabetes could heighten risk of atrial fibrillation (AF). Among older adults, however, higher adiponectin has been linked to greater incidence of adverse outcomes associated with AF, although recent reports have shown this association to be U-shaped. We postulated that higher adiponectin would be linked to increased risk for AF in older adults in a U-shaped manner. METHODS: We examined the associations of total and high-molecular-weight (HMW) adiponectin with incident AF among individuals free of prevalent cardiovascular disease (CVD) participating in a population-based cohort study of older adults (n=3190; age=74±5 years). RESULTS: During median follow-up of 11.4 years, there were 886 incident AF events. Adjusted cubic splines showed a positive and linear association between adiponectin and incident AF. After adjusting for potential confounders, including amino-terminal pro-B-type natriuretic peptide 1-76, the HR (95% CI) for AF per SD increase in total adiponectin was 1.14 (1.05 to 1.24), while that for HMW adiponectin was 1.17 (1.08 to 1.27). Additional adjustment for putative mediators, including subclinical CVD, diabetes, lipids and inflammation, did not significantly affect these estimates. CONCLUSIONS: The present findings demonstrate that higher, not lower, levels of adiponectin are independently associated with increased risk of AF in older adults despite its documented cardiometabolic benefits. Additional work is necessary to determine if adiponectin is a marker of failed counter-regulatory pathways or whether this hormone is directly harmful in the setting of or as a result of advanced age.
Keywords: Adiponectin; Age Factors; Aged; Aged, 80 and over; Aging; Atrial Fibrillation; Biomarkers; Female; Humans; Incidence; Linear Models; Male; Multivariate Analysis; Natriuretic Peptide, Brain; Peptide Fragments; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Physical Activity, Physical Fitness, and Leukocyte Telomere Length: The Cardiovascular Health Study. - Soares-Miranda, Luisa; Imamura, Fumiaki; Siscovick, David; Jenny, Nancy Swords; Fitzpatrick, Annette L; Mozaffarian, Dariush (Med Sci Sports Exerc, 2015)
INTRODUCTION: The influence of physical activity (PA) and physical fitness (PF) at older ages on changes in telomere length (TL)--repetitive DNA sequences that may mark biologic aging--is not well-established. Few prior studies (mainly cross-sectional) have been conducted in older adults, and few studies have evaluated PF. METHODS: We investigated cross-sectional and prospective associations of PA and PF with leukocyte TL among 582 older adults (mean ± SD age, 73 ± 5 yr at baseline) in the Cardiovascular Health Study, with serial TL measures and PA and PF assessed multiple times. Cross-sectional associations were assessed using multivariable repeated-measures regression, in which cumulatively averaged PA and PF measures were related to TL. Longitudinal analyses assessed cumulatively averaged PA and PF against later changes in TL, and changes in cumulatively averaged PA and PF against changes in TL. RESULTS: Cross-sectionally, greater walking distance and chair test performance, but not other PA and PF measures, were each associated with longer TL (P trend = 0.007 and 0.04, respectively). In longitudinal analyses, no significant associations of baseline PA and PF with change in TL were observed. In contrast, changes in leisure-time activity and chair test performance were each inversely associated with changes in TL. CONCLUSIONS: Cross-sectional analyses suggest that greater PA and PF are associated with longer TL. Prospective analyses show that changes in PA and PF are associated with differences in changes in TL. Even later in life, changes in certain PA and PF measures are associated with changes in TL, suggesting that leisure-time activity and fitness could reduce leukocyte telomere attrition among older adults.
Keywords: Aged; Aging; Cross-Sectional Studies; Exercise Test; Female; Hand Strength; Humans; Leukocytes; Male; Motor Activity; Physical Fitness; Prospective Studies; Telomere Homeostasis; Walking

Potassium and glucose measures in older adults: the Cardiovascular Health Study. - Chatterjee, Ranee; Biggs, Mary L; de Boer, Ian H; Brancati, Frederick L; Svetkey, Laura P; Barzilay, Joshua; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Siscovick, David S; Mozaffarian, Dariush; Edelman, David; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: We sought to determine the impacts of serum and dietary potassium measures on glucose metabolism and diabetes risk in older adults. METHODS: Among participants of the Cardiovascular Health Study, a community-based cohort of older American adults, we examined a) cross-sectional associations between potassium and measures of insulin sensitivity and secretion estimated from oral glucose tolerance tests and b) longitudinal associations of serum and dietary potassium with diabetes risk. RESULTS: Among 4,754 participants aged ≥65 years at baseline, there were 445 cases of incident diabetes during a median follow-up of 12 years. In multivariate models, baseline serum and dietary potassium were both associated with lower insulin sensitivity and greater insulin secretion. Compared with those with a serum potassium ≥4.5 mEq/L, participants with a serum potassium <4.0mEq/L had an adjusted mean difference in Matsuda insulin sensitivity index of -0.18 (-0.39, 0.02). Compared with those in the highest quartile, participants in the lowest quartile of dietary potassium intake had a corresponding adjusted mean difference in Matsuda insulin sensitivity index of -0.61 (-0.94, -0.29). In multivariate models, neither serum nor dietary potassium intake was associated with long-term diabetes risk. CONCLUSIONS: Although we did not identify serum and dietary potassium as risk factors for incident diabetes in older adults, results from cross-sectional analyses suggest that both may be associated with increased insulin resistance. This relationship with insulin resistance needs to be confirmed, and its importance on diabetes risk, cardiovascular risk, and conditions specific to older adults should be determined as well.
Keywords: Aged; Blood Glucose; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Insulin; Insulin Resistance; Longitudinal Studies; Male; Multivariate Analysis; Potassium; Potassium, Dietary; Risk Factors; United States

Race/Ethnic Differences in the Associations of the Framingham Risk Factors with Carotid IMT and Cardiovascular Events. - Gijsberts, Crystel M; Groenewegen, Karlijn A; Hoefer, Imo E; Eijkemans, Marinus J C; Asselbergs, Folkert W; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; et al. (PLoS One, 2015)
BACKGROUND: Clinical manifestations and outcomes of atherosclerotic disease differ between ethnic groups. In addition, the prevalence of risk factors is substantially different. Primary prevention programs are based on data derived from almost exclusively White people. We investigated how race/ethnic differences modify the associations of established risk factors with atherosclerosis and cardiovascular events. METHODS: We used data from an ongoing individual participant meta-analysis involving 17 population-based cohorts worldwide. We selected 60,211 participants without cardiovascular disease at baseline with available data on ethnicity (White, Black, Asian or Hispanic). We generated a multivariable linear regression model containing risk factors and ethnicity predicting mean common carotid intima-media thickness (CIMT) and a multivariable Cox regression model predicting myocardial infarction or stroke. For each risk factor we assessed how the association with the preclinical and clinical measures of cardiovascular atherosclerotic disease was affected by ethnicity. RESULTS: Ethnicity appeared to significantly modify the associations between risk factors and CIMT and cardiovascular events. The association between age and CIMT was weaker in Blacks and Hispanics. Systolic blood pressure associated more strongly with CIMT in Asians. HDL cholesterol and smoking associated less with CIMT in Blacks. Furthermore, the association of age and total cholesterol levels with the occurrence of cardiovascular events differed between Blacks and Whites. CONCLUSION: The magnitude of associations between risk factors and the presence of atherosclerotic disease differs between race/ethnic groups. These subtle, yet significant differences provide insight in the etiology of cardiovascular disease among race/ethnic groups. These insights aid the race/ethnic-specific implementation of primary prevention.
Keywords: Adult; Age Distribution; Aged; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Cholesterol, LDL; Comorbidity; Continental Population Groups; Diabetes Mellitus; Dyslipidemias; Ethnic Groups; Female; Follow-Up Studies; Global Health; Humans; Hypertension; Incidence; Linear Models; Male; Middle Aged; Myocardial Infarction; Prevalence; Proportional Hazards Models; Risk Factors; Smoking; Stroke

Shared genetic basis for migraine and ischemic stroke: A genome-wide analysis of common variants. - Malik, Rainer; Freilinger, Tobias; Winsvold, Bendik S; Anttila, Verneri; Vander Heiden, Jason; Traylor, Matthew; de Vries, Boukje; Holliday, Elizabeth G; Terwindt, Gisela M; Sturm, Jonathan; Bis, Joshua C; Hopewell, Jemma C; et al. (Neurology, 2015)
OBJECTIVE: To quantify genetic overlap between migraine and ischemic stroke (IS) with respect to common genetic variation. METHODS: We applied 4 different approaches to large-scale meta-analyses of genome-wide data on migraine (23,285 cases and 95,425 controls) and IS (12,389 cases and 62,004 controls). First, we queried known genome-wide significant loci for both disorders, looking for potential overlap of signals. We then analyzed the overall shared genetic load using polygenic scores and estimated the genetic correlation between disease subtypes using data derived from these models. We further interrogated genomic regions of shared risk using analysis of covariance patterns between the 2 phenotypes using cross-phenotype spatial mapping. RESULTS: We found substantial genetic overlap between migraine and IS using all 4 approaches. Migraine without aura (MO) showed much stronger overlap with IS and its subtypes than migraine with aura (MA). The strongest overlap existed between MO and large artery stroke (LAS; p = 6.4 × 10(-28) for the LAS polygenic score in MO) and between MO and cardioembolic stroke (CE; p = 2.7 × 10(-20) for the CE score in MO). CONCLUSIONS: Our findings indicate shared genetic susceptibility to migraine and IS, with a particularly strong overlap between MO and both LAS and CE pointing towards shared mechanisms. Our observations on MA are consistent with a limited role of common genetic variants in this subtype.
Keywords: Brain Ischemia; Genome-Wide Association Study; Humans; Migraine with Aura; Migraine without Aura; Stroke

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

Thyroid function within the normal range and risk of coronary heart disease: an individual participant data analysis of 14 cohorts. - Asvold, Bjørn O; Vatten, Lars J; Bjøro, Trine; Bauer, Douglas C; Bremner, Alexandra; Cappola, Anne R; Ceresini, Graziano; den Elzen, Wendy P J; Ferrucci, Luigi; Franco, Oscar H; Franklyn, Jayne A; Gussekloo, Jacobijn; et al. (JAMA Intern Med, 2015)
IMPORTANCE: Some experts suggest that serum thyrotropin levels in the upper part of the current reference range should be considered abnormal, an approach that would reclassify many individuals as having mild hypothyroidism. Health hazards associated with such thyrotropin levels are poorly documented, but conflicting evidence suggests that thyrotropin levels in the upper part of the reference range may be associated with an increased risk of coronary heart disease (CHD). OBJECTIVE: To assess the association between differences in thyroid function within the reference range and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data analysis of 14 cohorts with baseline examinations between July 1972 and April 2002 and with median follow-up ranging from 3.3 to 20.0 years. Participants included 55,412 individuals with serum thyrotropin levels of 0.45 to 4.49 mIU/L and no previously known thyroid or cardiovascular disease at baseline. EXPOSURES: Thyroid function as expressed by serum thyrotropin levels at baseline. MAIN OUTCOMES AND MEASURES: Hazard ratios (HRs) of CHD mortality and CHD events according to thyrotropin levels after adjustment for age, sex, and smoking status. RESULTS: Among 55,412 individuals, 1813 people (3.3%) died of CHD during 643,183 person-years of follow-up. In 10 cohorts with information on both nonfatal and fatal CHD events, 4666 of 48,875 individuals (9.5%) experienced a first-time CHD event during 533,408 person-years of follow-up. For each 1-mIU/L higher thyrotropin level, the HR was 0.97 (95% CI, 0.90-1.04) for CHD mortality and 1.00 (95% CI, 0.97-1.03) for a first-time CHD event. Similarly, in analyses by categories of thyrotropin, the HRs of CHD mortality (0.94 [95% CI, 0.74-1.20]) and CHD events (0.97 [95% CI, 0.83-1.13]) were similar among participants with the highest (3.50-4.49 mIU/L) compared with the lowest (0.45-1.49 mIU/L) thyrotropin levels. Subgroup analyses by sex and age group yielded similar results. CONCLUSIONS AND RELEVANCE: Thyrotropin levels within the reference range are not associated with risk of CHD events or CHD mortality. This finding suggests that differences in thyroid function within the population reference range do not influence the risk of CHD. Increased CHD risk does not appear to be a reason for lowering the upper thyrotropin reference limit.
Keywords: Cohort Studies; Coronary Disease; Humans; Hypothyroidism; Thyrotropin

Urinary uromodulin, kidney function, and cardiovascular disease in elderly adults. - Garimella, Pranav S; Biggs, Mary L; Katz, Ronit; Ix, Joachim H; Bennett, Michael R; Devarajan, Prasad; Kestenbaum, Bryan R; Siscovick, David S; Jensen, Majken K; Shlipak, Michael G; Chaves, Paulo H M; Sarnak, Mark J (Kidney Int, 2015)
Urinary uromodulin (uUMOD) is the most common secreted tubular protein in healthy adults. However, the relationship between uUMOD and clinical outcomes is still unclear. Here we measured uUMOD in 192 participants of the Cardiovascular Health Study with over a 30% decline in estimated glomerular filtration rate (eGFR) over 9 years, 54 with incident end-stage renal disease (ESRD), and in a random subcohort of 958 participants. The association of uUMOD with eGFR decline was evaluated using logistic regression and with incident ESRD, cardiovascular disease, heart failure, and mortality using Cox proportional regression. Mean age was 78 years and median uUMOD was 25.8 μg/ml. In a case-control study evaluating eGFR decline (192 cases and 231 controls), each 1-s.d. higher uUMOD was associated with a 23% lower odds of eGFR decline (odds ratio 0.77 (95% CI 0.62-0.96)) and a 10% lower risk of mortality (hazard ratio 0.90 (95% CI 0.83-0.98)) after adjusting for demographics, eGFR, albumin/creatinine ratio, and other risk factors. There was no risk association of uUMOD with ESRD, cardiovascular disease, or heart failure after multivariable adjustment. Thus, low uUMOD levels may identify persons at risk of progressive kidney disease and mortality above and beyond established markers of kidney disease, namely eGFR and the albumin/creatinine ratio. Future studies need to confirm these results and evaluate whether uUMOD is a marker of tubular health and/or whether it plays a causal role in preserving kidney function.
Keywords: Aged; Aged, 80 and over; Albuminuria; Biomarkers; Cardiovascular Diseases; Case-Control Studies; Creatinine; Disease Progression; Female; Glomerular Filtration Rate; Heart Failure; Humans; Incidence; Kidney Failure, Chronic; Male; Proportional Hazards Models; Uromodulin

Urine Collagen Fragments and CKD Progression-The Cardiovascular Health Study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth; Djoussé, Luc; Siscovick, David; Tracy, Russell; Katz, Ronit; Delaney, Joseph A; Chaves, Paulo; Rifkin, Dena E; Hughes-Austin, Jan M; Garimella, Pranav S; et al. (J Am Soc Nephrol, 2015)
Tubulointerstitial fibrosis is common with ageing and strongly prognostic for ESRD but is poorly captured by eGFR or urine albumin to creatinine ratio (ACR). Higher urine levels of procollagen type III N-terminal propeptide (PIIINP) mark the severity of tubulointerstitial fibrosis in biopsy studies, but the association of urine PIIINP with CKD progression is unknown. Among community-living persons aged ≥65 years, we measured PIIINP in spot urine specimens from the 1996 to 1997 Cardiovascular Health Study visit among individuals with CKD progression (30% decline in eGFR over 9 years, n=192) or incident ESRD (n=54) during follow-up, and in 958 randomly selected participants. We evaluated associations of urine PIIINP with CKD progression and incident ESRD. Associations of urine PIIINP with cardiovascular disease, heart failure, and death were evaluated as secondary end points. At baseline, mean age (±SD) was 78±5 years, mean eGFR was 63±18 ml/min per 1.73 m(2), and median urine PIIINP was 2.6 (interquartile range, 1.4-4.2) μg/L. In a case-control study (192 participants, 231 controls), each doubling of urine PIIINP associated with 22% higher odds of CKD progression (adjusted odds ratio, 1.22; 95% confidence interval, 1.00 to 1.49). Higher urine PIIINP level was also associated with incident ESRD, but results were not significant in fully adjusted models. In a prospective study among the 958 randomly selected participants, higher urine PIIINP was significantly associated with death, but not with incident cardiovascular disease or heart failure. These data suggest higher urine PIIINP levels associate with CKD progression independently of eGFR and ACR in older individuals.
Keywords: Aged; Cardiovascular Diseases; Case-Control Studies; Disease Progression; Female; Heart Failure; Humans; Kidney Failure, Chronic; Male; Peptide Fragments; Procollagen; Prospective Studies; Renal Insufficiency, Chronic

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

-3 Polyunsaturated Fatty Acid Biomarkers and Coronary Heart Disease: Pooling Project of 19 Cohort Studies - Del Gobbo, L. C.; Imamura, F.; Aslibekyan, S.; Marklund, M.; Virtanen, J. K.; Wennberg, M.; Yakoob, M. Y.; Chiuve, S. E.; Dela Cruz, L.; Frazier-Wood, A. C.; Fretts, A. M.; Guallar, E.; et al. (JAMA Intern Med, 2016)
-3 polyunsaturated fatty acids for primary prevention of coronary heart disease (CHD) remains controversial. Most prior longitudinal studies evaluated self-reported consumption rather than biomarkers.\ -3) for incident CHD.\ A global consortium of 19 studies identified by November 2014.\ -3 biomarkers and ascertained CHD.\ -6 levels, and FADS desaturase genes.\ Incident total CHD, fatal CHD, and nonfatal myocardial infarction (MI).\ -3 biomarkers ALA, DPA, and DHA were associated with a lower risk of fatal CHD, with relative risks (RRs) of 0.91 (95% CI, 0.84-0.98) for ALA, 0.90 (95% CI, 0.85-0.96) for DPA, and 0.90 (95% CI, 0.84-0.96) for DHA. Although DPA was associated with a lower risk of total CHD (RR, 0.94; 95% CI, 0.90-0.99), ALA (RR, 1.00; 95% CI, 0.95-1.05), EPA (RR, 0.94; 95% CI, 0.87-1.02), and DHA (RR, 0.95; 95% CI, 0.91-1.00) were not. Significant associations with nonfatal MI were not evident. Associations appeared generally stronger in phospholipids and total plasma. Restricted cubic splines did not identify evidence of nonlinearity in dose responses.\ -3 fatty acids are associated with a modestly lower incidence of fatal CHD.

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

APOL1 Genotype, Kidney and Cardiovascular Disease, and Death in Older Adults. - Mukamal, Kenneth J; Tremaglio, Joseph; Friedman, David J; Ix, Joachim H; Kuller, Lewis H; Tracy, Russell P; Pollak, Martin R (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: We sought to evaluate the cardiovascular impact of coding variants in the apolipoprotein L1 gene APOL1 that protect against trypanosome infection but have been associated with kidney disease among African Americans. APPROACH AND RESULTS: As part of the Cardiovascular Health Study, a population-based cohort of Americans aged ≥65 years, we genotyped APOL1 polymorphisms rs73885319 and rs71785153 and examined kidney function, subclinical atherosclerosis, and incident cardiovascular disease and death over 13 years of follow-up among 91 African Americans with 2 risk alleles, 707 other African Americans, and 4964 white participants. The high-risk genotype with 2 risk alleles was associated with 2-fold higher levels of albuminuria and lower ankle-brachial indices but similar carotid intima-media thickness among African Americans. Median survival among high-risk African Americans was 9.9 years (95% confidence interval [CI], 8.7-11.9), compared with 13.6 years (95% CI, 12.5-14.3) among other African Americans and 13.3 years (95% CI, 13.0-13.6) among whites (P=0.03). The high-risk genotype was also associated with increased risk for incident myocardial infarction (adjusted hazard ratio 1.8; 95% CI, 1.1-3.0) and mortality (adjusted hazard ratio 1.3; 95% CI 1.0-1.7). Albuminuria and risk for myocardial infarction and mortality were nearly identical between African Americans with 0 to 1 risk alleles and whites. CONCLUSIONS: APOL1 genotype is associated with albuminuria, subclinical atherosclerosis, incident myocardial infarction, and mortality in older African Americans. African Americans without 2 risk alleles do not differ significantly in risk of myocardial infarction or mortality from whites. APOL1 trypanolytic variants may account for a substantial proportion of the excess risk of chronic disease in African Americans.
Keywords: African Americans; Age Factors; Aged; Albuminuria; Apolipoproteins; Atherosclerosis; Cardiovascular Diseases; Cause of Death; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Health Status Disparities; Heterozygote; Homozygote; Humans; Incidence; Kaplan-Meier Estimate; Kidney Diseases; Lipoproteins, HDL; Male; Myocardial Infarction; Phenotype; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Association of inflammatory, lipid and mineral markers with cardiac calcification in older adults. - Bortnick, Anna E; Bartz, Traci M; Ix, Joachim H; Chonchol, Michel; Reiner, Alexander; Cushman, Mary; Owens, David; Barasch, Eddy; Siscovick, David S; Gottdiener, John S; Kizer, Jorge R (Heart, 2016)
OBJECTIVE: Calcification of the aortic valve and adjacent structures involves inflammatory, lipid and mineral metabolism pathways. We hypothesised that circulating biomarkers reflecting these pathways are associated with cardiac calcification in older adults. METHODS: We investigated the associations of various biomarkers with valvular and annular calcification in the Cardiovascular Health Study. Of the 5888 participants, up to 3585 were eligible after exclusions for missing biomarker, covariate or echocardiographic data. We evaluated analytes reflecting lipid (lipoprotein (Lp) (a), Lp-associated phospholipase A2 (LpPLA2) mass and activity), inflammatory (interleukin-6, soluble (s) CD14) and mineral metabolism (fetuin-A, fibroblast growth factor (FGF)-23) pathways that were measured within 5 years of echocardiography. The relationships of plasma biomarkers with aortic valve calcification (AVC), aortic annular calcification (AAC) and mitral annular calcification (MAC) were assessed with relative risk (RR) regression. RESULTS: Calcification was prevalent: AVC 59%, AAC 45% and MAC 41%. After adjustment, Lp(a), LpPLA2 mass and activity and sCD14 were positively associated with AVC. RRs for AVC per SD (95% CI) were as follows: Lp(a), 1.051 (1.022 to 1.081); LpPLA2 mass, 1.036 (1.006 to 1.066) and LpPLA2 activity, 1.037 (1.004 to 1.071); sCD14, 1.039 (1.005 to 1.073). FGF-23 was positively associated with MAC, 1.040 (1.004 to 1.078) and fetuin-A was negatively associated, 0.949 (0.911 to 0.989). No biomarkers were significantly associated with AAC. CONCLUSION: This study shows novel associations of circulating FGF-23 and fetuin-A with MAC, and LpPLA2 and sCD14 with AVC, confirming that previously reported for Lp(a). Further investigation of Lp and inflammatory pathways may provide added insight into the aetiology of AVC, while study of phosphate regulation may illuminate the pathogenesis of MAC.

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Gibbs, Richard A; Muzny, Donna; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.

Digit Symbol Substitution test and future clinical and subclinical disorders of cognition, mobility and mood in older adults. - Rosano, Caterina; Perera, Subashan; Inzitari, Marco; Newman, Anne B; Longstreth, William T; Studenski, Stephanie (Age Ageing, 2016)
OBJECTIVE: to examine whether psychomotor speed predicts individual and combined disorders in cognition, mobility and mood and if white matter hyperintensities explain these associations. DESIGN AND SETTING: longitudinal; Cardiovascular Health Study. SUBJECTS: 5,888 participants (57.6% women, 15.7% black, 75.1 (5.5), mean years (SD)). METHODS: psychomotor speed (Digit Symbol Substitution Test (DSST)) and small vessel disease (white matter hyperintensities (WMH)) were measured in 1992-94. Global cognition (Modified Mini-Mental State (3MS) examination), mobility (gait speed (GS)) and mood (Center for Epidemiologic Studies Depression (CES-D) scale) were measured annually over 5 years and classified as clinical, subclinical or no disorders based on established values (3MS: 80 and 85 points; GS: 0.6 and 1.0 m/s; CES-D: 10 and 5 points). Analyses were adjusted for demographics, baseline status, education, diabetes, hypertension, ankle-arm index. RESULTS: among those with no disorder in cognition, mobility and mood (N = 619) in 1992-94, being in the lowest DSST quartile compared to the highest was associated with nearly twice the odds of developing 1+ clinical or subclinical disorders (N = 413) during follow-up. Associations were stronger for incident clinical disorders in cognition (OR: 8.44, p < 0.01) or mobility (OR: 9.09, p < 0.05) than for mood (OR: 1.88, p < 0.10). Results were similar after adjustment for WMH. CONCLUSIONS: slower psychomotor speed may serve as a biomarker of risk of clinical disorders of cognition, mobility and mood. While in part attributable to vascular brain disease, other potentially modifiable contributors may be present. Further studying the causes of psychomotor slowing with ageing might provide novel insights into age-related brain disorders.

A DNA methylation biomarker of alcohol consumption. - Liu, C; Marioni, R E; Hedman, Å K; Pfeiffer, L; Tsai, P-C; Reynolds, L M; Just, A C; Duan, Q; Boer, C G; Tanaka, T; Elks, C E; Aslibekyan, S; et al. (Mol Psychiatry, 2016)
The lack of reliable measures of alcohol intake is a major obstacle to the diagnosis and treatment of alcohol-related diseases. Epigenetic modifications such as DNA methylation may provide novel biomarkers of alcohol use. To examine this possibility, we performed an epigenome-wide association study of methylation of cytosine-phosphate-guanine dinucleotide (CpG) sites in relation to alcohol intake in 13 population-based cohorts (ntotal=13 317; 54% women; mean age across cohorts 42-76 years) using whole blood (9643 European and 2423 African ancestries) or monocyte-derived DNA (588 European, 263 African and 400 Hispanic ancestry) samples. We performed meta-analysis and variable selection in whole-blood samples of people of European ancestry (n=6926) and identified 144 CpGs that provided substantial discrimination (area under the curve=0.90-0.99) for current heavy alcohol intake (⩾42 g per day in men and ⩾28 g per day in women) in four replication cohorts. The ancestry-stratified meta-analysis in whole blood identified 328 (9643 European ancestry samples) and 165 (2423 African ancestry samples) alcohol-related CpGs at Bonferroni-adjusted P<1 × 10(-7). Analysis of the monocyte-derived DNA (n=1251) identified 62 alcohol-related CpGs at P<1 × 10(-7). In whole-blood samples of people of European ancestry, we detected differential methylation in two neurotransmitter receptor genes, the γ-Aminobutyric acid-A receptor delta and γ-aminobutyric acid B receptor subunit 1; their differential methylation was associated with expression levels of a number of genes involved in immune function. In conclusion, we have identified a robust alcohol-related DNA methylation signature and shown the potential utility of DNA methylation as a clinically useful diagnostic test to detect current heavy alcohol consumption.Molecular Psychiatry advance online publication, 15 November 2016; doi:10.1038/mp.2016.192.

Effects of Disease Burden and Functional Adaptation on Morbidity and Mortality on Older Adults. - Sanders, Jason L; Arnold, Alice M; Hirsch, Calvin H; Thielke, Stephen M; Kim, Dae; Mukamal, Kenneth J; Kizer, Jorge R; Ix, Joachim H; Kaplan, Robert C; Kritchevsky, Stephen B; Newman, Anne B (J Am Geriatr Soc, 2016)
OBJECTIVES: To ascertain whether older adults with extensive disease but relative vigor (adapters) shorten the period at the end of life in which they live with morbidity (compress morbidity). DESIGN: Prospective, community-based cohort study in four U.S. cities. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals aged 65 and older. MEASUREMENTS: Participants were categorized into three groups according to extent of disease (assessed noninvasively), vigor, and frailty (expected agers (n = 3,528, extent of disease similar to vigor and frailty-reference group), adapters (n = 882, higher disease but vigorous), and prematurely frail (n = 855, lower disease but frail)) and compared according to years of able life (YAL), years of self-reported healthy life (YHL), and mortality using multivariable regression and survival analysis. RESULTS: After adjustment, adapters had 0.97 (95% confidence interval (CI) = 0.60-1.33) more YAL and 0.54 (95% CI = 0.19-0.90) more YHL than expected agers, and those who were prematurely frail had -0.99 (95% CI = -1.36 to -0.62) fewer YAL and -0.53 (95% CI = -0.89 to -0.17) fewer YHL than expected agers. Adapters had 0.9 more and prematurely frail had 1.5 fewer years of total life than expected agers (P < .001). Adapters spent 55% of their remaining life able and healthy, those who were prematurely frail spent 37%, and of expected agers spent 47% (P < .001). CONCLUSION: Despite similar levels of disease burden, older adults who were more vigorous appeared to compress morbidity and live longer. Older adults with higher frailty lengthened morbidity and had greater mortality. Adaptive factors may compress morbidity and decrease mortality.

Epigenetic Signatures of Cigarette Smoking. - Joehanes, Roby; Just, Allan C; Marioni, Riccardo E; Pilling, Luke C; Reynolds, Lindsay M; Mandaviya, Pooja R; Guan, Weihua; Xu, Tao; Elks, Cathy E; Aslibekyan, Stella; Moreno-Macias, Hortensia; Smith, Jennifer A; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: DNA methylation leaves a long-term signature of smoking exposure and is one potential mechanism by which tobacco exposure predisposes to adverse health outcomes, such as cancers, osteoporosis, lung, and cardiovascular disorders. METHODS AND RESULTS: To comprehensively determine the association between cigarette smoking and DNA methylation, we conducted a meta-analysis of genome-wide DNA methylation assessed using the Illumina BeadChip 450K array on 15 907 blood-derived DNA samples from participants in 16 cohorts (including 2433 current, 6518 former, and 6956 never smokers). Comparing current versus never smokers, 2623 cytosine-phosphate-guanine sites (CpGs), annotated to 1405 genes, were statistically significantly differentially methylated at Bonferroni threshold of P<1×10(-7) (18 760 CpGs at false discovery rate <0.05). Genes annotated to these CpGs were enriched for associations with several smoking-related traits in genome-wide studies including pulmonary function, cancers, inflammatory diseases, and heart disease. Comparing former versus never smokers, 185 of the CpGs that differed between current and never smokers were significant P<1×10(-7) (2623 CpGs at false discovery rate <0.05), indicating a pattern of persistent altered methylation, with attenuation, after smoking cessation. Transcriptomic integration identified effects on gene expression at many differentially methylated CpGs. CONCLUSIONS: Cigarette smoking has a broad impact on genome-wide methylation that, at many loci, persists many years after smoking cessation. Many of the differentially methylated genes were novel genes with respect to biological effects of smoking and might represent therapeutic targets for prevention or treatment of tobacco-related diseases. Methylation at these sites could also serve as sensitive and stable biomarkers of lifetime exposure to tobacco smoke.

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Céline; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fibroblast Growth Factor-23 and Frailty in Elderly Community-Dwelling Individuals: The Cardiovascular Health Study. - Beben, Tomasz; Ix, Joachim H; Shlipak, Michael G; Sarnak, Mark J; Fried, Linda F; Hoofnagle, Andrew N; Chonchol, Michel; Kestenbaum, Bryan R; de Boer, Ian H; Rifkin, Dena E (J Am Geriatr Soc, 2016)
OBJECTIVES: To evaluate whether fibroblast growth factor 23 (FGF-23) is related to frailty and to characterize the nature of their joint association with mortality. DESIGN: Cross-sectional analysis for frailty and longitudinal cohort analysis for mortality. SETTING: Cardiovascular Health Study. PARTICIPANTS: Community-dwelling individuals (N = 2,977; mean age 77.9 ± 4.7, 40% male, 83% white). MEASUREMENTS: The predictor was serum FGF-23 concentration (C-terminal enzyme-linked immunosorbent assay), and the outcomes were frailty status (determined according to frailty phenotype criteria of weight loss, weakness, exhaustion, slowness, and low physical activity) and mortality. Multinomial logistic regression was used to assess the cross-sectional association between FGF-23 and frailty and prefrailty, adjusting for demographic characteristics, cardiovascular disease and risk factors, and kidney markers. Proportional hazards Cox proportional hazards regression was used to assess the association between FGF-23, frailty, and all-cause mortality. RESULTS: Mean estimated glomerular filtration rate (eGFR) was 64 ± 17 mL/min per 1.73 m(2) . Median FGF-23 was 70.3 RU/mL (interquartile range 53.4-99.2); 52% were prefrail, and 13% were frail. After multivariate adjustment, each doubling in FGF-23 concentration was associated with 38% (95% confidence interval (CI) = 17-62%) higher odds of frailty than of nonfrailty and 16% (95% CI = 3-30%) higher odds of prefrailty. FGF-23 (hazard ratio (HR) = 1.16, 95% CI = 1.10-1.23) and frailty (HR = 1.82, 95% CI = 1.57-2.12) were independently associated with mortality, but neither association was meaningfully attenuated when adjusted for the other. CONCLUSION: In a large cohort of older adults, higher FGF-23 was independently associated with prevalent frailty and prefrailty. FGF-23 and frailty were independent and additive risk factors for mortality. FGF-23 may be a marker for functional outcomes.
Keywords: Aged; Anthropometry; Biomarkers; Cardiovascular Diseases; Cross-Sectional Studies; Enzyme-Linked Immunosorbent Assay; Female; Fibroblast Growth Factors; Frail Elderly; Glomerular Filtration Rate; Humans; Independent Living; Longitudinal Studies; Male; Phenotype; Risk Factors; Surveys and Questionnaires

Fibrosis markers, hip fracture risk, and bone density in older adults. - Barzilay, J I; Bůžková, P; Kizer, J R; Djoussé, L; Ix, J H; Fink, H A; Siscovick, D S; Cauley, J A; Mukamal, K J (Osteoporos Int, 2016)
UNLABELLED: We examined whether blood levels of two markers of fibrosis (transforming growth factor beta one (TGF-β1) and procollagen type III N-terminal propeptide (PIIINP)) are related to hip fracture risk and to bone mineral density (BMD). TGF-β1 levels were associated with lower hip fracture risk in women and with lower BMD in men. PIIINP levels were not associated with either outcome. INTRODUCTION: TGF-β1 serves several roles in bone formation and resorption. A consequence of TGF-β1 activation is the production of PIIINP, a marker of collagen III deposition. Here, we explore whether these two biomarkers are related to incident hip fracture and bone mineral density (BMD) and whether their associations are modified by systemic inflammation, as measured by C-reactive protein (CRP) levels. METHODS: Participants were from the Cardiovascular Health Study (mean age 78 years; mean follow-up 8.3 years). We included 1681 persons with measured levels of TGF-β1 (149 hip fractures) and 3226 persons with measured levels of PIIINP (310 hip fractures). RESULTS: Among women, higher TGF-β1 levels were associated with lower hip fracture risk (HR, per doubling, 0.78 [95 % CI 0.61, 0.91]). Among men, TGF-β1 levels were associated with hip fracture risk in a non-linear manner, but among those with elevated CRP levels, doubling was associated with increased risk of fracture (HR 2.22 [1.20, 4.08]) (p = 0.02, interaction between low and high CRP and TGF-β1 on fracture risk). TGF-β1 levels had no significant association with total hip or total body BMD in women but were significantly associated with lower BMD in men. There were no associations of PIIINP levels with hip fracture risk or BMD in men or women. CONCLUSIONS: TGF-β1 levels appear to be associated with bone-related phenotypes in a sex-specific manner. The reasons for these differences between men and women regarding TGF-β1 levels and hip fracture risk and bone density require further investigation.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

Galectin-3 and Soluble ST2 and Kidney Function Decline in Older Adults: The Cardiovascular Health Study (CHS). - Bansal, Nisha; Katz, Ronit; Seliger, Stephen; DeFilippi, Christopher; Sarnak, Mark J; Delaney, Joseph A; Christenson, Robert; de Boer, Ian H; Kestenbaum, Bryan; Robinson-Cohen, Cassianne; Ix, Joachim H; Shlipak, Michael G (Am J Kidney Dis, 2016)
Keywords: Aged; Cohort Studies; Creatinine; Cystatin C; Female; Galectin 3; Glomerular Filtration Rate; Humans; Interleukin-1 Receptor-Like 1 Protein; Logistic Models; Longitudinal Studies; Male; Prognosis; Renal Insufficiency, Chronic

{Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Pattaro, C.; Teumer, A.; Gorski, M.; Chu, A. Y.; Li, M.; Mijatovic, V.; Garnaas, M.; Tin, A.; Sorice, R.; Li, Y.; Taliun, D.; Olden, M.; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.

Genetic variants in RBFOX3 are associated with sleep latency. - Amin, Najaf; Allebrandt, Karla V; van der Spek, Ashley; Müller-Myhsok, Bertram; Hek, Karin; Teder-Laving, Maris; Hayward, Caroline; Esko, Tõnu; van Mill, Josine G; Mbarek, Hamdi; Watson, Nathaniel F; Melville, Scott A; et al. (Eur J Hum Genet, 2016)
Time to fall asleep (sleep latency) is a major determinant of sleep quality. Chronic, long sleep latency is a major characteristic of sleep-onset insomnia and/or delayed sleep phase syndrome. In this study we aimed to discover common polymorphisms that contribute to the genetics of sleep latency. We performed a meta-analysis of genome-wide association studies (GWAS) including 2 572 737 single nucleotide polymorphisms (SNPs) established in seven European cohorts including 4242 individuals. We found a cluster of three highly correlated variants (rs9900428, rs9907432 and rs7211029) in the RNA-binding protein fox-1 homolog 3 gene (RBFOX3) associated with sleep latency (P-values=5.77 × 10(-08), 6.59 × 10(-)(08) and 9.17 × 10(-)(08)). These SNPs were replicated in up to 12 independent populations including 30 377 individuals (P-values=1.5 × 10(-)(02), 7.0 × 10(-)(03) and 2.5 × 10(-)(03); combined meta-analysis P-values=5.5 × 10(-07), 5.4 × 10(-07) and 1.0 × 10(-07)). A functional prediction of RBFOX3 based on co-expression with other genes shows that this gene is predominantly expressed in brain (P-value=1.4 × 10(-316)) and the central nervous system (P-value=7.5 × 10(-)(321)). The predicted function of RBFOX3 based on co-expression analysis with other genes shows that this gene is significantly involved in the release cycle of neurotransmitters including gamma-aminobutyric acid and various monoamines (P-values<2.9 × 10(-11)) that are crucial in triggering the onset of sleep. To conclude, in this first large-scale GWAS of sleep latency we report a novel association of variants in RBFOX3 gene. Further, a functional prediction of RBFOX3 supports the involvement of RBFOX3 with sleep latency.

{The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G. B.; Ferreira, T.; Chasman, D. I.; Jackson, A. U.; Schmidt, E. M.; Johnson, T.; Thorleifsson, G.; Luan, J.; Donnelly, L. A.; Kanoni, S.; Petersen, A. K.; Pihur, V.; et al. (Nat Genet, 2016)
To dissect the genetic architecture of blood pressure and assess effects on target organ damage, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry, and genotypes from an additional 140,886 individuals were used for validation. We identified 66 blood pressure-associated loci, of which 17 were new; 15 harbored multiple distinct association signals. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in blood pressure control through modulation of vascular tone across multiple tissues. The 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent. The 66-SNP blood pressure risk score was significantly associated with target organ damage in multiple tissues but with minor effects in the kidney. Our findings expand current knowledge of blood pressure-related pathways and highlight tissues beyond the classical renal system in blood pressure regulation.

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study of the Modified Stumvoll Insulin Sensitivity Index Identifies BCL2 and FAM19A2 as Novel Insulin Sensitivity Loci. - Walford, Geoffrey A; Gustafsson, Stefan; Rybin, Denis; Stančáková, Alena; Chen, Han; Liu, Ching-Ti; Hong, Jaeyoung; Jensen, Richard A; Rice, Ken; Morris, Andrew P; Mägi, Reedik; Tönjes, Anke; et al. (Diabetes, 2016)
Genome-wide association studies (GWAS) have found few common variants that influence fasting measures of insulin sensitivity. We hypothesized that a GWAS of an integrated assessment of fasting and dynamic measures of insulin sensitivity would detect novel common variants. We performed a GWAS of the modified Stumvoll Insulin Sensitivity Index (ISI) within the Meta-Analyses of Glucose and Insulin-Related Traits Consortium. Discovery for genetic association was performed in 16,753 individuals, and replication was attempted for the 23 most significant novel loci in 13,354 independent individuals. Association with ISI was tested in models adjusted for age, sex, and BMI and in a model analyzing the combined influence of the genotype effect adjusted for BMI and the interaction effect between the genotype and BMI on ISI (model 3). In model 3, three variants reached genome-wide significance: rs13422522 (NYAP2; P = 8.87 × 10(-11)), rs12454712 (BCL2; P = 2.7 × 10(-8)), and rs10506418 (FAM19A2; P = 1.9 × 10(-8)). The association at NYAP2 was eliminated by conditioning on the known IRS1 insulin sensitivity locus; the BCL2 and FAM19A2 associations were independent of known cardiometabolic loci. In conclusion, we identified two novel loci and replicated known variants associated with insulin sensitivity. Further studies are needed to clarify the causal variant and function at the BCL2 and FAM19A2 loci.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

GWAS for executive function and processing speed suggests involvement of the CADM2 gene. - Ibrahim-Verbaas, C A; Bressler, J; Debette, S; Schuur, M; Smith, A V; Bis, J C; Davies, G; Trompet, S; Smith, J A; Wolf, C; Chibnik, L B; Liu, Y; et al. (Mol Psychiatry, 2016)
To identify common variants contributing to normal variation in two specific domains of cognitive functioning, we conducted a genome-wide association study (GWAS) of executive functioning and information processing speed in non-demented older adults from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium. Neuropsychological testing was available for 5429-32,070 subjects of European ancestry aged 45 years or older, free of dementia and clinical stroke at the time of cognitive testing from 20 cohorts in the discovery phase. We analyzed performance on the Trail Making Test parts A and B, the Letter Digit Substitution Test (LDST), the Digit Symbol Substitution Task (DSST), semantic and phonemic fluency tests, and the Stroop Color and Word Test. Replication was sought in 1311-21860 subjects from 20 independent cohorts. A significant association was observed in the discovery cohorts for the single-nucleotide polymorphism (SNP) rs17518584 (discovery P-value=3.12 × 10(-8)) and in the joint discovery and replication meta-analysis (P-value=3.28 × 10(-9) after adjustment for age, gender and education) in an intron of the gene cell adhesion molecule 2 (CADM2) for performance on the LDST/DSST. Rs17518584 is located about 170 kb upstream of the transcription start site of the major transcript for the CADM2 gene, but is within an intron of a variant transcript that includes an alternative first exon. The variant is associated with expression of CADM2 in the cingulate cortex (P-value=4 × 10(-4)). The protein encoded by CADM2 is involved in glutamate signaling (P-value=7.22 × 10(-15)), gamma-aminobutyric acid (GABA) transport (P-value=1.36 × 10(-11)) and neuron cell-cell adhesion (P-value=1.48 × 10(-13)). Our findings suggest that genetic variation in the CADM2 gene is associated with individual differences in information processing speed.

Inflammatory markers and extent and progression of early atherosclerosis: Meta-analysis of individual-participant-data from 20 prospective studies of the PROG-IMT collaboration. - Willeit, Peter; Thompson, Simon G; Agewall, Stefan; Bergström, Göran; Bickel, Horst; Catapano, Alberico L; Chien, Kuo-Liong; de Groot, Eric; Empana, Jean-Philippe; Etgen, Thorleif; Franco, Oscar H; Iglseder, Bernhard; et al. (Eur J Prev Cardiol, 2016)
BACKGROUND: Large-scale epidemiological evidence on the role of inflammation in early atherosclerosis, assessed by carotid ultrasound, is lacking. We aimed to quantify cross-sectional and longitudinal associations of inflammatory markers with common-carotid-artery intima-media thickness (CCA-IMT) in the general population. METHODS: Information on high-sensitivity C-reactive protein, fibrinogen, leucocyte count and CCA-IMT was available in 20 prospective cohort studies of the PROG-IMT collaboration involving 49,097 participants free of pre-existing cardiovascular disease. Estimates of associations were calculated within each study and then combined using random-effects meta-analyses. RESULTS: Mean baseline CCA-IMT amounted to 0.74 mm (SD = 0.18) and mean CCA-IMT progression over a mean of 3.9 years to 0.011 mm/year (SD = 0.039). Cross-sectional analyses showed positive linear associations between inflammatory markers and baseline CCA-IMT. After adjustment for traditional cardiovascular risk factors, mean differences in baseline CCA-IMT per one-SD higher inflammatory marker were: 0.0082 mm for high-sensitivity C-reactive protein (p < 0.001); 0.0072 mm for fibrinogen (p < 0.001); and 0.0025 mm for leucocyte count (p = 0.033). 'Inflammatory load', defined as the number of elevated inflammatory markers (i.e. in upper two quintiles), showed a positive linear association with baseline CCA-IMT (p < 0.001). Longitudinal associations of baseline inflammatory markers and changes therein with CCA-IMT progression were null or at most weak. Participants with the highest 'inflammatory load' had a greater CCA-IMT progression (p = 0.015). CONCLUSION: Inflammation was independently associated with CCA-IMT cross-sectionally. The lack of clear associations with CCA-IMT progression may be explained by imprecision in its assessment within a limited time period. Our findings for 'inflammatory load' suggest important combined effects of the three inflammatory markers on early atherosclerosis.

Interaction of methylation-related genetic variants with circulating fatty acids on plasma lipids: a meta-analysis of 7 studies and methylation analysis of 3 studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Ma, Yiyi; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Manichaikul, Ani W; Chu, Audrey Y; Samieri, Cecilia; Zhou, Xia; Guan, Weihua; Wang, Lu; Biggs, Mary L; Chen, Yii-der I; et al. (Am J Clin Nutr, 2016)
BACKGROUND: DNA methylation is influenced by diet and single nucleotide polymorphisms (SNPs), and methylation modulates gene expression. OBJECTIVE: We aimed to explore whether the gene-by-diet interactions on blood lipids act through DNA methylation. DESIGN: We selected 7 SNPs on the basis of predicted relations in fatty acids, methylation, and lipids. We conducted a meta-analysis and a methylation and mediation analysis with the use of data from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium and the ENCODE (Encyclopedia of DNA Elements) consortium. RESULTS: On the basis of the meta-analysis of 7 cohorts in the CHARGE consortium, higher plasma HDL cholesterol was associated with fewer C alleles at ATP-binding cassette subfamily A member 1 (ABCA1) rs2246293 (β = -0.6 mg/dL, P = 0.015) and higher circulating eicosapentaenoic acid (EPA) (β = 3.87 mg/dL, P = 5.62 × 10(21)). The difference in HDL cholesterol associated with higher circulating EPA was dependent on genotypes at rs2246293, and it was greater for each additional C allele (β = 1.69 mg/dL, P = 0.006). In the GOLDN (Genetics of Lipid Lowering Drugs and Diet Network) study, higher ABCA1 promoter cg14019050 methylation was associated with more C alleles at rs2246293 (β = 8.84%, P = 3.51 × 10(18)) and lower circulating EPA (β = -1.46%, P = 0.009), and the mean difference in methylation of cg14019050 that was associated with higher EPA was smaller with each additional C allele of rs2246293 (β = -2.83%, P = 0.007). Higher ABCA1 cg14019050 methylation was correlated with lower ABCA1 expression (r = -0.61, P = 0.009) in the ENCODE consortium and lower plasma HDL cholesterol in the GOLDN study (r = -0.12, P = 0.0002). An additional mediation analysis was meta-analyzed across the GOLDN study, Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. Compared with the model without the adjustment of cg14019050 methylation, the model with such adjustment provided smaller estimates of the mean plasma HDL cholesterol concentration in association with both the rs2246293 C allele and EPA and a smaller difference by rs2246293 genotypes in the EPA-associated HDL cholesterol. However, the differences between 2 nested models were NS (P > 0.05). CONCLUSION: We obtained little evidence that the gene-by-fatty acid interactions on blood lipids act through DNA methylation.
Keywords: Apolipoproteins E; ATP Binding Cassette Transporter 1; Cholesterol, HDL; Cohort Studies; Diet; DNA Methylation; Eicosapentaenoic Acid; Epigenesis, Genetic; Fatty Acids; Gene Expression Regulation; Humans; Lipids; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Triglycerides

Longitudinal assessment of N-terminal pro-B-type natriuretic peptide and risk of diabetes in older adults: The cardiovascular health study. - Brutsaert, Erika F; Biggs, Mary L; Delaney, Joseph A; Djoussé, Luc; Gottdiener, John S; Ix, Joachim H; Kim, Francis; Mukamal, Kenneth J; Siscovick, David S; Tracy, Russell P; de Boer, Ian H; deFilippi, Christopher R; et al. (Metabolism, 2016)
INTRODUCTION: Natriuretic peptides have a well-recognized role in cardiovascular homeostasis. Recently, higher levels of B-type natriuretic peptide (BNP) have also been associated with decreased risk of diabetes in middle-aged adults. Whether this association persists into older age, where the pathophysiology of diabetes changes, has not been established, nor has its intermediate pathways. METHODS: We investigated the relationship between N-terminal (NT)-proBNP and incident diabetes in 2359 older adults free of cardiovascular disease or chronic kidney disease in the Cardiovascular Health Study. RESULTS: We documented 348 incident cases of diabetes over 12.6years of median follow-up. After adjusting for age, sex, race, body mass index, systolic blood pressure, anti-hypertensive treatment, smoking, alcohol use, and LDL, each doubling of NT-proBNP was associated with a 9% lower risk of incident diabetes (HR=0.91 [95% CI: 0.84-0.99]). Additional adjustment for waist circumference, physical activity, estimated glomerular filtration rate or C-reactive protein did not influence the association. Among putative mediators, HDL and triglycerides, adiponectin, and especially homeostasis model assessment of insulin resistance, all appeared to account for a portion of the lower risk associated with NT-proBNP. CONCLUSION: In older adults without prevalent cardiovascular or kidney disease, higher NT-proBNP is associated with decreased risk of incident diabetes even after adjustment for traditional risk factors. These findings suggest that the metabolic effects of natriuretic peptides persist late in life and offer a potential therapeutic target for prevention of diabetes in older people.

Measures of Body Size and Composition and Risk of Incident Atrial Fibrillation in Older People: The Cardiovascular Health Study. - Karas, Maria G; Yee, Laura M; Biggs, Mary L; Djoussé, Luc; Mukamal, Kenneth J; Ix, Joachim H; Zieman, Susan J; Siscovick, David S; Gottdiener, John S; Rosenberg, Michael A; Kronmal, Richard A; Heckbert, Susan R; et al. (Am J Epidemiol, 2016)
Various anthropometric measures, including height, have been associated with atrial fibrillation (AF). This raises questions about the appropriateness of using ratio measures such as body mass index (BMI), which contains height squared in its denominator, in the evaluation of AF risk. Among older adults, the optimal anthropometric approach to risk stratification of AF remains uncertain. Anthropometric and bioelectrical impedance measures were obtained from 4,276 participants (mean age = 72.4 years) free of cardiovascular disease in the Cardiovascular Health Study. During follow-up (1989-2008), 1,050 cases of AF occurred. BMI showed a U-shaped association, whereas height, weight, waist circumference, hip circumference, fat mass, and fat-free mass were linearly related to incident AF. The strongest adjusted association occurred for height (per each 1-standard-deviation increment, hazard ratio = 1.38, 95% confidence interval: 1.25, 1.51), which exceeded all other measures, including weight (hazard ratio = 1.21, 95% confidence interval: 1.13, 1.29). Combined assessment of log-transformed weight and height showed regression coefficients that departed from the 1 to -2 ratio inherent in BMI, indicating a loss of predictive information. Risk estimates for AF tended to be stronger for hip circumference than for waist circumference and for fat-free mass than for fat mass, which was explained largely by height. These findings highlight the prominent role of body size and the inadequacy of BMI as determinants of AF in older adults.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. - Natarajan, Pradeep; Bis, Joshua C; Bielak, Lawrence F; Cox, Amanda J; Dörr, Marcus; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: -The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease (CHD). We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent CHD. METHODS AND RESULTS: -We studied a total of 25,109 European ancestry and African-American participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52,869 with common carotid intima media thickness (CIMT) measured by ultrasonography within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Participants were genotyped for 247,870 DNA sequence variants (231,539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and CIMT. APOB p.Arg3527Gln was associated with four-fold excess CAC (P = 3×10(-10)). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC (P = 1×10(-12)) and 1.4% reduced CIMT (P = 4×10(-14)) in carriers compared with non-carriers. In secondary analyses conditioning on LDL cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for CHD (OR 0.77; P = 1×10(-11)). CONCLUSIONS: -Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities as well as clinical CHD.

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

Novel Genetic Loci Associated With Retinal Microvascular Diameter. - Jensen, Richard A; Sim, Xueling; Smith, Albert Vernon; Li, Xiaohui; Jakobsdottir, Johanna; Cheng, Ching-Yu; Brody, Jennifer A; Cotch, Mary Frances; McKnight, Barbara; Klein, Ronald; Wang, Jie Jin; Kifley, Annette; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: There is increasing evidence that retinal microvascular diameters are associated with cardiovascular and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. METHODS AND RESULTS: This study extends previous genome-wide association study results using 24 000+ multiethnic participants from 7 discovery cohorts and 5000+ subjects of European ancestry from 2 replication cohorts. Using the Illumina HumanExome BeadChip, we investigate the association of single-nucleotide polymorphisms and variants collectively across genes with summary measures of retinal vessel diameters, referred to as the central retinal venule equivalent and the central retinal arteriole equivalent. We report 4 new loci associated with central retinal venule equivalent, one of which is also associated with central retinal arteriole equivalent. The 4 single-nucleotide polymorphisms are rs7926971 in TEAD1 (P=3.1×10(-) (11); minor allele frequency=0.43), rs201259422 in TSPAN10 (P=4.4×10(-9); minor allele frequency=0.27), rs5442 in GNB3 (P=7.0×10(-10); minor allele frequency=0.05), and rs1800407 in OCA2 (P=3.4×10(-8); minor allele frequency=0.05). The latter single-nucleotide polymorphism, rs1800407, was also associated with central retinal arteriole equivalent (P=6.5×10(-12)). Results from the gene-based burden tests were null. In phenotype look-ups, single-nucleotide polymorphism rs201255422 was associated with both systolic (P=0.001) and diastolic blood pressures (P=8.3×10(-04)). CONCLUSIONS: Our study expands the understanding of genetic factors influencing the size of the retinal microvasculature. These findings may also provide insight into the relationship between retinal and systemic microvascular disease.

{Novel genetic loci underlying human intracranial volume identified through genome-wide association - Adams, H. H.; Hibar, D. P.; Chouraki, V.; Stein, J. L.; Nyquist, P. A.; Renter?a, M. E.; Trompet, S.; Arias-Vasquez, A.; Seshadri, S.; Desrivi?res, S.; Beecham, A. H.; Jahanshad, N.; et al. (Nat Neurosci, 2016)
Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five previously unknown loci for intracranial volume and confirmed two known signals. Four of the loci were also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high genetic correlation with child head circumference (Ïgenetic = 0.748), which indicates a similar genetic background and allowed us to identify four additional loci through meta-analysis (Ncombined = 37,345). Variants for intracranial volume were also related to childhood and adult cognitive function, and Parkinson's disease, and were enriched near genes involved in growth pathways, including PI3K-AKT signaling. These findings identify the biological underpinnings of intracranial volume and their link to physiological and pathological traits.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.

Relations of Postload and Fasting Glucose With Incident Cardiovascular Disease and Mortality Late in Life: The Cardiovascular Health Study. - Brutsaert, Erika F; Shitole, Sanyog; Biggs, Mary Lou; Mukamal, Kenneth J; deBoer, Ian H; Thacker, Evan L; Barzilay, Joshua I; Djoussé, Luc; Ix, Joachim H; Smith, Nicholas L; Kaplan, Robert C; Siscovick, David S; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Older adults have a high prevalence of postload hyperglycemia. Postload glucose has shown more robust associations with cardiovascular disease (CVD) and death than fasting glucose, but data in the oldest old are sparse. METHODS: Fasting and 2-hour postload glucose were measured in community-dwelling older adults, mean age 78, at the 1996-1997 follow-up visit of the Cardiovascular Health Study. We evaluated their associations with atherosclerotic CVD (ASCVD) and mortality using standard Cox regression and competing-risks analyses and assessed improvement in prediction-model discrimination with the c-statistic. RESULTS: Among 2,394 participants without treated diabetes and available data on glycemic measures, there were 579 ASCVD events and 1,698 deaths during median follow-up of 11.2 years. In fully adjusted models, both fasting and 2-hour glucose were associated with ASCVD (HR per SD, 1.13 [1.03-1.25] and 1.17 [1.07-1.28], respectively) and all-cause mortality (HR 1.12 [1.07-1.18] and 1.14 [1.08-1.20]). After mutual adjustment, however, the associations for fasting glucose with both outcomes were abolished, but those for postload glucose were largely unchanged. Consistent findings were observed for ASCVD in competing-risks models. CONCLUSION: In adults surviving to advanced old age, postload glucose was associated with ASCVD and mortality independently of fasting glucose, but fasting glucose was not associated with these outcomes independently of postload glucose. These findings affirm the robust association of postload glucose with ASCVD and death late in life.
Keywords: Aged; Aging; Blood Glucose; Cardiovascular Diseases; Fasting; Female; Follow-Up Studies; Glucose; Glucose Tolerance Test; Health Surveys; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; United States

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Study of Cardiovascular Health Outcomes in the Era of Claims Data: The Cardiovascular Health Study. - Psaty, Bruce M; Delaney, Joseph A; Arnold, Alice M; Curtis, Lesley H; Fitzpatrick, Annette L; Heckbert, Susan R; McKnight, Barbara; Ives, Diane; Gottdiener, John S; Kuller, Lewis H; Longstreth, W T (Circulation, 2016)
BACKGROUND: Increasingly, the diagnostic codes from administrative claims data are being used as clinical outcomes. METHODS AND RESULTS: Data from the Cardiovascular Health Study (CHS) were used to compare event rates and risk factor associations between adjudicated hospitalized cardiovascular events and claims-based methods of defining events. The outcomes of myocardial infarction (MI), stroke, and heart failure were defined in 3 ways: the CHS adjudicated event (CHS[adj]), selected International Classification of Diseases, Ninth Edition diagnostic codes only in the primary position for Medicare claims data from the Center for Medicare & Medicaid Services (CMS[1st]), and the same selected diagnostic codes in any position (CMS[any]). Conventional claims-based methods of defining events had high positive predictive values but low sensitivities. For instance, the positive predictive value of International Classification of Diseases, Ninth Edition code 410.x1 for a new acute MI in the first position was 90.6%, but this code identified only 53.8% of incident MIs. The observed event rates for CMS[1st] were low. For MI, the incidence was 14.9 events per 1000 person-years for CHS[adj] MI, 8.6 for CMS[1st] MI, and 12.2 for CMS[any] MI. In general, cardiovascular disease risk factor associations were similar across the 3 methods of defining events. Indeed, traditional cardiovascular disease risk factors were also associated with all first hospitalizations not resulting from an MI. CONCLUSIONS: The use of diagnostic codes from claims data as clinical events, especially when restricted to primary diagnoses, leads to an underestimation of event rates. Additionally, claims-based events data represent a composite end point that includes the outcome of interest and selected (misclassified) nonevent hospitalizations.
Keywords: Blood Glucose; Cardiovascular Diseases; Female; Follow-Up Studies; Health Surveys; Hospitalization; Hospitals, Veterans; Humans; Insurance Claim Review; International Classification of Diseases; Lipids; Male; Managed Care Programs; Medicare; Risk Factors; Sampling Studies; Treatment Outcome; United States

Testosterone, Dihydrotestosterone, Sex Hormone Binding Globulin and Incident Diabetes among Older Men: the Cardiovascular Health Study. - Joyce, Katherine E; Biggs, Mary L; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Siscovick, David S; Shores, Molly M; Matsumoto, Alvin M; Mukamal, Kenneth J (J Clin Endocrinol Metab, 2016)
CONTEXT: Although sex hormone binding globulin (SHBG) and testosterone (T) have been inversely associated with risk of diabetes, few studies have examined dihydrotestosterone (DHT), a more potent androgen than T, or older adults, whose glycemic pathophysiology differs from younger adults. OBJECTIVE: To determine the associations of SHBG, T, and DHT with insulin resistance and incident diabetes in older adult men. DESIGN: In a prospective cohort study, we evaluated baseline levels of SHBG, T, and DHT using liquid chromatography-tandem mass spectrometry among 852 men in the Cardiovascular Health Study free of diabetes and cardiovascular disease in 1994. MAIN OUTCOME: Insulin resistance estimated by HOMA-IR and insulin sensitivity estimated by the Gutt index in 1996, and incident diabetes (n=112) ascertained over a mean follow-up of 9.8 years. RESULTS: In linear regression models adjusted for demographics, alcohol consumption, current smoking, body-mass index, and other androgens, SHBG (HOMA-IR 0.30 units lower per doubling; 95% confidence interval [CI], 0.08-0.52; p=0.01) and total DHT (HOMA-IR 0.18 units lower per doubling; 95% CI 0.06-0.30; p=0.01), but not free T (p=0.33) were inversely associated with insulin resistance. In corresponding Cox proportional hazards models, total DHT was again inversely associated with risk of diabetes (adjusted hazard ratio per doubling 0.69; 95% CI, 0.52-0.92; p=0.01), but SHBG (hazard ratio 1.09; 95% CI, 0.74-1.59; p=0.66) and free T (hazard ratio 1.15; 95% CI, 0.92-1.43; p=0.23) were not. CONCLUSIONS: Among older men, higher levels of DHT are inversely associated with insulin resistance and risk of diabetes over the ensuing 10 years, while levels of T are not. Future studies are still needed to clarify the role of SHBG in risk of diabetes in this population.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

Twenty-eight genetic loci associated with ST-T-wave amplitudes of the electrocardiogram. - Verweij, Niek; Mateo Leach, Irene; Isaacs, Aaron; Arking, Dan E; Bis, Joshua C; Pers, Tune H; van den Berg, Marten E; Lyytikäinen, Leo-Pekka; Barnett, Phil; Wang, Xinchen; Soliman, Elsayed Z; van Duijn, Cornelia M; et al. (Hum Mol Genet, 2016)
The ST-segment and adjacent T-wave (ST-T wave) amplitudes of the electrocardiogram are quantitative characteristics of cardiac repolarization. Repolarization abnormalities have been linked to ventricular arrhythmias and sudden cardiac death. We performed the first genome-wide association meta-analysis of ST-T-wave amplitudes in up to 37 977 individuals identifying 71 robust genotype-phenotype associations clustered within 28 independent loci. Fifty-four genes were prioritized as candidates underlying the phenotypes, including genes with established roles in the cardiac repolarization phase (SCN5A/SCN10A, KCND3, KCNB1, NOS1AP and HEY2) and others with as yet undefined cardiac function. These associations may provide insights in the spatiotemporal contribution of genetic variation influencing cardiac repolarization and provide novel leads for future functional follow-up.
Keywords: Adaptor Proteins, Signal Transducing; Arrhythmias, Cardiac; Basic Helix-Loop-Helix Transcription Factors; Brugada Syndrome; Cardiac Conduction System Disease; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Repressor Proteins; Shab Potassium Channels; Shal Potassium Channels

Urinary Uromodulin and Risk of Urinary Tract Infections: The Cardiovascular Health Study. - Garimella, Pranav S; Bartz, Traci M; Ix, Joachim H; Chonchol, Michel; Shlipak, Michael G; Devarajan, Prasad; Bennett, Michael R; Sarnak, Mark J (Am J Kidney Dis, 2016)
BACKGROUND: Laboratory studies suggest that urinary uromodulin, the most common protein in the urine of healthy adults, may protect against urinary tract infection (UTI). Epidemiologic studies evaluating this relationship in humans are lacking. STUDY DESIGN: Prospective longitudinal cohort study. SETTING & PARTICIPANTS: 953 participants enrolled in the Cardiovascular Health Study. PREDICTOR: Uromodulin assayed using enzyme-linked immunosorbent assay in spot urine samples. OUTCOMES: Composite of outpatient UTI events or UTI-related hospitalizations and each of them individually identified using International Classification of Diseases, Ninth Revision (ICD-9) codes using negative binomial regression with robust standard errors adjusted for age, race, sex, body mass index, diabetes, estimated glomerular filtration rate, and urinary albumin and urinary creatinine excretion. RESULTS: Median uromodulin level was 25.9 (IQR, 17.3-38.9) μg/mL, mean age of participants was 78 years, 61% were women, and 15% were black. There were 331 outpatient UTI events and 87 UTI-related hospitalizations among 186 participants during a median 9.9 years of follow-up. Persons in the highest quartile (>38.93μg/mL) of uromodulin concentration had a significantly lower risk for the composite outcome (incidence rate ratio [IRR], 0.47; 95% CI, 0.29-0.79) compared with those in the lowest quartile (≤17.26μg/mL). This association remained significant for outpatient UTI events (highest vs lowest quartile even after excluding those with prior UTI: IRR, 0.42; 95% CI, 0.23-0.77). The direction of association with UTI hospitalization was similar, but not statistically significant (IRR, 0.78; 95% CI, 0.39-1.58). LIMITATIONS: Use of ICD-9 codes to identify outcomes and lack of generalizability to younger populations. CONCLUSIONS: High urinary uromodulin levels are associated with lower risk for UTI in older community-dwelling adults independent of traditional UTI risk factors. This finding supports prior laboratory data indicating a protective role of uromodulin against UTI. Further research is needed to understand if this may lead to new treatments to prevent or treat UTI.

740 adults from 20 prospective cohort studies - Wu, J. H. Y.; Marklund, M.; Imamura, F.; Tintle, N.; Ardisson Korat, A. V.; de Goede, J.; Zhou, X.; Yang, W. S.; de Oliveira Otto, M. C.; ger, J.; Qureshi, W.; Virtanen, J. K.; et al. (Lancet Diabetes Endocrinol, 2017)
The metabolic effects of omega-6 polyunsaturated fatty acids (PUFAs) remain contentious, and little evidence is available regarding their potential role in primary prevention of type 2 diabetes. We aimed to assess the associations of linoleic acid and arachidonic acid biomarkers with incident type 2 diabetes.\ We did a pooled analysis of new, harmonised, individual-level analyses for the biomarkers linoleic acid and its metabolite arachidonic acid and incident type 2 diabetes. We analysed data from 20 prospective cohort studies from ten countries (Iceland, the Netherlands, the USA, Taiwan, the UK, Germany, Finland, Australia, Sweden, and France), with biomarkers sampled between 1970 and 2010. Participants included in the analyses were aged 18 years or older and had data available for linoleic acid and arachidonic acid biomarkers at baseline. We excluded participants with type 2 diabetes at baseline. The main outcome was the association between omega-6 PUFA biomarkers and incident type 2 diabetes. We assessed the relative risk of type 2 diabetes prospectively for each cohort and lipid compartment separately using a prespecified analytic plan for exposures, covariates, effect modifiers, and analysis, and the findings were then pooled using inverse-variance weighted meta-analysis.\ 13).\ Findings suggest that linoleic acid has long-term benefits for the prevention of type 2 diabetes and that arachidonic acid is not harmful.\ Funders are shown in the appendix.

Assessing the causal relationship between obesity and venous thromboembolism through a Mendelian Randomization study. - Lindström, Sara; Germain, Marine; Crous-Bou, Marta; Smith, Erin N; Morange, Pierre-Emmanuel; van Hylckama Vlieg, Astrid; de Haan, Hugoline G; Chasman, Daniel; Ridker, Paul; Brody, Jennifer; de Andrade, Mariza; Heit, John A; et al. (Hum Genet, 2017)
Observational studies have shown an association between obesity and venous thromboembolism (VTE) but it is not known if observed associations are causal, due to reverse causation or confounding bias. We conducted a Mendelian Randomization study of body mass index (BMI) and VTE. We identified 95 single nucleotide polymorphisms (SNPs) that have been previously associated with BMI and assessed the association between genetically predicted high BMI and VTE leveraging data from a previously conducted GWAS within the INVENT consortium comprising a total of 7507 VTE cases and 52,632 controls of European ancestry. Five BMI SNPs were associated with VTE at P < 0.05, with the strongest association seen for the FTO SNP rs1558902 (OR 1.07, 95% CI 1.02-1.12, P = 0.005). In addition, we observed a significant association between genetically predicted BMI and VTE (OR = 1.59, 95% CI 1.30-1.93 per standard deviation increase in BMI, P = 5.8 × 10). Our study provides evidence for a causal relationship between high BMI and risk of VTE. Reducing obesity levels will likely result in lower incidence in VTE.
Keywords: Adult; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Incidence; Logistic Models; Male; Mendelian Randomization Analysis; Obesity; Polymorphism, Single Nucleotide; Proportional Hazards Models; Venous Thromboembolism

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Association of Coronary Artery Calcium Score vs Age With Cardiovascular Risk in Older Adults: An Analysis of Pooled Population-Based Studies. - Yano, Yuichiro; O'Donnell, Christopher J; Kuller, Lewis; Kavousi, Maryam; Erbel, Raimund; Ning, Hongyan; D'Agostino, Ralph; Newman, Anne B; Nasir, Khurram; Hofman, Albert; Lehmann, Nils; Dhana, Klodian; et al. (JAMA Cardiol, 2017)
Importance: Besides age, other discriminators of atherosclerotic cardiovascular disease (ASCVD) risk are needed in older adults. Objectives: To examine the predictive ability of coronary artery calcium (CAC) score vs age for incident ASCVD and how risk prediction changes by adding CAC score and removing only age from prediction models. Design, Setting, and Participants: We conducted an analysis of pooled US population-based studies, including the Framingham Heart Study, the Multi-Ethnic Study of Atherosclerosis, and the Cardiovascular Health Study. Results were compared with 2 European cohorts, the Rotterdam Study and the Heinz Nixdorf Recall Study. Participants underwent CAC scoring between 1998 and 2006 using cardiac computed tomography. The participants included adults older than 60 years without known ASCVD at baseline. Exposures: Coronary artery calcium scores. Main Outcomes and Measures: Incident ASCVD events including coronary heart disease (CHD) and stroke. Results: The study included 4778 participants from 3 US cohorts, with a mean age of 70.1 years; 2582 (54.0%) were women, and 2431 (50.9%) were nonwhite. Over 11 years of follow-up (44 152 person-years), 405 CHD and 228 stroke events occurred. Coronary artery calcium score (vs age) had a greater association with incident CHD (C statistic, 0.733 vs 0.690; C statistics difference, 0.043; 95% CI of difference, 0.009-0.075) and modestly improved prediction of incident stroke (C statistic, 0.695 vs 0.670; C statistics difference, 0.025; 95% CI of difference, -0.015 to 0.064). Adding CAC score to models including traditional cardiovascular risk factors, with only age being removed, provided improved discrimination for incident CHD (C statistic, 0.735 vs 0.703; C statistics difference, 0.032; 95% CI of difference, 0.002-0.062) but not for stroke. Coronary artery calcium score was more likely than age to provide higher category-free net reclassification improvement among participants who experienced an ASCVD event (0.390; 95% CI, 0.312-0.467 vs 0.08; 95% CI -0.001 to 0.181) and to result in more accurate reclassification of risk for ASCVD events among these individuals. The findings were similar in the 2 European cohorts (n = 4990). Conclusions and Relevance: Coronary artery calcium may be an alternative marker besides age to better discriminate between lower and higher CHD risk in older adults. Whether CAC score can assist in guiding the decision to initiate statin treatment for primary prevention in older adults requires further investigation.

Association of Diabetic Macular Edema and Proliferative Diabetic Retinopathy With Cardiovascular Disease: A Systematic Review and Meta-analysis. - Xie, Jing; Ikram, M Kamran; Cotch, Mary Frances; Klein, Barbara; Varma, Rohit; Shaw, Jonathan E; Klein, Ronald; Mitchell, Paul; Lamoureux, Ecosse L; Wong, Tien Yin (JAMA Ophthalmol, 2017)
Importance: Previous studies on the relationship between diabetic retinopathy (DR) and cardiovascular disease (CVD) focused on the early stages of DR. Understanding whether patients with type 2 diabetes and severe stages of DR (diabetic macular edema [DME] and proliferative diabetic retinopathy [PDR]) have a higher risk of CVD will allow physicians to more effectively counsel patients. Objective: To examine the association of severe stages of DR (DME and PDR) with incident CVD in patients with type 2 diabetes. Data Sources: English-language publications were reviewed for articles evaluating the relationship of DR and CVD in MEDLINE, EMBASE, Current Contents, and the Cochrane Library from inception (January 1, 1950) to December 31, 2014, using the search terms diabetic retinopathy OR macular edema AND stroke OR cerebrovascular disease OR coronary artery disease OR heart failure OR myocardial infarction OR angina pectoris OR acute coronary syndrome OR coronary artery disease OR cardiomyopathy. Study Selection: Among 656 studies screened for eligibility, 7604 individuals were included from 8 prospective population-based studies with data on photographic-based DR grading, follow-up visits, and well-defined incident CVD end point. Data Extraction and Synthesis: Two independent reviewers conducted a systematic search of the 4 databases, and a single pooled database was developed. Incidence rate ratios (IRRs) were estimated for patients with DME, PDR, and vision-threatening DR, compared with persons without these conditions, by using individual participant data followed by a standard inverse-variance meta-analysis (2-step analysis). The review and analyses were performed from January 1, 2009, to January 1, 2017. Main Outcome and Measures: Incident CVD, including coronary heart disease, stroke, or death from cardiovascular causes. Results: Among 7604 patients with type 2 diabetes, the prevalence of DME was 4.6% and PDR, 7.4%. After a mean follow-up of 5.9 years (range, 3.2-10.1 years), 1203 incident CVD events, including 916 coronary heart disease cases, were reported. Persons with DME or PDR were more likely to have incident CVD (IRR, 1.39; 95% CI, 1.16-1.67) and fatal CVD (IRR, 2.33; 95% CI, 1.49-3.67) compared with those without DME or PDR. Conclusions and Relevance: Patients with type 2 diabetes and DME or PDR have an increased risk of incident CVD, which suggests that these persons should be followed up more closely to prevent CVD.
Keywords: Cardiovascular Diseases; Diabetic Retinopathy; Global Health; Humans; Incidence; Macular Edema; Risk Factors

Association of DPP-4 activity with BMD, body composition, and incident hip fracture: the Cardiovascular Health Study. - Carbone, L D; Bůžková, P; Fink, H A; Robbins, J A; Bethel, M; Isales, C M; Hill, W D (Osteoporos Int, 2017)
There was no association of plasma DPP-4 activity levels with bone mineral density (BMD), body composition, or incident hip fractures in a cohort of elderly community-dwelling adults. INTRODUCTION: Dipeptidyl peptidase IV (DPP-4) inactivates several key hormones including those that stimulate postprandial insulin secretion, and DPP-4 inhibitors (gliptins) are approved to treat diabetes. While DPP-4 is known to modulate osteogenesis, the relationship between DPP-4 activity and skeletal health is uncertain. The purpose of the present study was to examine possible associations between DPP-4 activity in elderly subjects enrolled in the Cardiovascular Health Study (CHS) and BMD, body composition measurements, and incident hip fractures. METHODS: All 1536 male and female CHS participants who had evaluable DXA scans and plasma for DPP-4 activity were included in the analyses. The association between (1) BMD of the total hip, femoral neck, lumbar spine, and total body; (2) body composition measurements (% lean, % fat, and total body mass); and (3) incident hip fractures and plasma levels of DPP-4 activity were determined. RESULTS: Mean plasma levels of DPP-4 activity were significantly higher in blacks (227 ± 78) compared with whites (216 ± 89) (p = 0.04). However, there was no significant association of DPP-4 activity with age or gender (p ≥ 0.14 for both). In multivariable adjusted models, there was no association of plasma DPP-4 activity with BMD overall (p ≥ 0.55 for all) or in gender stratified analyses (p ≥ 0.23). There was also no association of DPP-4 levels and incident hip fractures overall (p ≥ 0.24) or in gender stratified analyses (p ≥ 0.39). CONCLUSION: Plasma DPP-4 activity, within the endogenous physiological range, was significantly associated with race, but not with BMD, body composition, or incident hip fractures in elderly community-dwelling subjects.

Association of Holter-Derived Heart Rate Variability Parameters With the Development of Congestive Heart Failure in the Cardiovascular Health Study. - Patel, Vaiibhav N; Pierce, Brian R; Bodapati, Rohan K; Brown, David L; Ives, Diane G; Stein, Phyllis K (JACC Heart Fail, 2017)
OBJECTIVES: This study sought to determine whether Holter-based parameters of heart rate variability (HRV) are independently associated with incident heart failure among older adults in the CHS (Cardiovascular Health Study) as evidenced by an improvement in the predictive power of the Health Aging and Body Composition Heart Failure (Health ABC) score. BACKGROUND: Abnormal HRV, a marker of autonomic dysfunction, has been associated with multiple adverse cardiovascular outcomes but not the development of congestive heart failure (CHF). METHODS: Asymptomatic CHS participants with interpretable 24-h baseline Holter recordings were included (n = 1,401). HRV measures and premature ventricular contraction (PVC) counts were compared between participants with (n = 260) and without (n = 1,141) incident CHF on follow-up. Significantly different parameters between groups were added to the components of the Health ABC score, a validated CHF prediction tool, using stepwise Cox regression. RESULTS: The final model included components of the Health ABC score, In PVC counts (adjusted hazard ratio [aHR]: 1.12; 95% confidence interval [CI]: 1.07 to 1.19; p < 0.001) and the following HRV measures: abnormal heart rate turbulence onset (aHR: 1.52; 95% CI: 1.11 to 2.08; p = 0.009), short-term fractal scaling exponent (aHR: 0.27; 95% CI: 0.14 to 0.53; p < 0.001), in very low frequency power (aHR: 1.28; 95% CI: 1.02 to 1.60; p = 0.037), and coefficient of variance of N-N intervals (aHR: 0.94; 95% CI: 0.90 to 0.99; p = 0.009). The C-statistic for the final model was significantly improved over the Health ABC model alone (0.77 vs. 0.73; p = 0.0002). CONCLUSIONS: Abnormal HRV parameters were significantly and independently associated with incident CHF in asymptomatic, older adults. When combined with increased PVCs, HRV improved the predictive power of the Health ABC score.

The complex genetics of gait speed: genome-wide meta-analysis approach. - Ben-Avraham, Dan; Karasik, David; Verghese, Joe; Lunetta, Kathryn L; Smith, Jennifer A; Eicher, John D; Vered, Rotem; Deelen, Joris; Arnold, Alice M; Buchman, Aron S; Tanaka, Toshiko; Faul, Jessica D; et al. (Aging (Albany NY), 2017)
Emerging evidence suggests that the basis for variation in late-life mobility is attributable, in part, to genetic factors, which may become increasingly important with age. Our objective was to systematically assess the contribution of genetic variation to gait speed in older individuals. We conducted a meta-analysis of gait speed GWASs in 31,478 older adults from 17 cohorts of the CHARGE consortium, and validated our results in 2,588 older adults from 4 independent studies. We followed our initial discoveries with network and eQTL analysis of candidate signals in tissues. The meta-analysis resulted in a list of 536 suggestive genome wide significant SNPs in or near 69 genes. Further interrogation with Pathway Analysis placed gait speed as a polygenic complex trait in five major networks. Subsequent eQTL analysis revealed several SNPs significantly associated with the expression of PRSS16, WDSUB1 and PTPRT, which in addition to the meta-analysis and pathway suggested that genetic effects on gait speed may occur through synaptic function and neuronal development pathways. No genome-wide significant signals for gait speed were identified from this moderately large sample of older adults, suggesting that more refined physical function phenotypes will be needed to identify the genetic basis of gait speed in aging.

Detection of genetic loci associated with plasma fetuin-A: A meta-analysis of genome-wide association studies from the CHARGE Consortium. - Jensen, Majken K; Jensen, Richard A; Mukamal, Kenneth J; Guo, Xiuqing; Yao, Jie; Sun, Qi; Cornelis, Marilyn; Liu, Yongmei; Chen, Ming-Huei; Kizer, Jorge R; Djoussé, Luc; Siscovick, David S; et al. (Hum Mol Genet, 2017)
Plasma fetuin-A is associated with type 2 diabetes, and AHSG, the gene encoding fetuin-A, has been identified as a susceptibility locus for diabetes and metabolic syndrome. Thus far, unbiased investigations of the genetic determinants of plasma fetuin-A concentrations have not been conducted. We searched for single nucleotide polymorphisms (SNPs) related to fetuin-A concentrations by a genome-wide association study in six population-based studies.We examined the association of fetuin-A levels with ∼ 2.5 million genotyped and imputed SNPs in 9,055 participants of European descent and 2,119 African Americans. In both ethnicities, strongest associations were centered in a region with a high degree of LD near the AHSG locus. Among 136 genome-wide significant (p < 0.05x10-8) SNPs near the AHSG locus, the top SNP was rs4917 (p = 1.27x10-303), a known coding SNP in exon 6 that is associated with a 0.06 g/L (∼13%) lower fetuin-A level. This variant alone explained 14% of the variation in fetuin-A levels. Analyses conditioned on rs4917 indicated that the strong association with the AHSG locus stems from additional independent associations of multiple variants among European Americans. In conclusion, levels of fetuin-A in plasma are strongly associated with SNPs in its encoding gene, AHSG, but not elsewhere in the genome. Given the strength of the associations observed for multiple independent SNPs, the AHSG gene is an example of a candidate locus suitable for additional investigations including fine mapping to elucidate the biological basis of the findings and further functional experiments to clarify AHSG as a potential therapeutic target.

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10-7; replication: N = 7,182, p < 1.6 × 10-3). The replicated methylation sites are heritable (h2 > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Fibroblast Growth Factor 23 and the Risk of Infection-Related Hospitalization in Older Adults. - Nowak, Kristen L; Bartz, Traci M; Dalrymple, Lorien; de Boer, Ian H; Kestenbaum, Bryan; Shlipak, Michael G; Garimella, Pranav S; Ix, Joachim H; Chonchol, Michel (J Am Soc Nephrol, 2017)
Within monocytes, 1,25-dihydroxyvitamin D [1,25(OH)2D] is important for production of cathelicidins, which in turn, are critical for antibacterial action. Fibroblast growth factor 23 (FGF23) decreases 1,25(OH)2D production and thus, could increase infection risk. We examined this possibility in 3141 community-dwelling adults ages ≥65 years old at baseline in the Cardiovascular Health Study using Cox proportional hazards models to examine the association between FGF23 concentrations and first infection-related hospitalizations and determine whether associations differed by the presence of CKD (eGFR<60 ml/min per 1.73 m(2) [n=832] or urine albumin-to-creatinine ratio >30 mg/g [n=577]). Mean±SD age of participants was 78±5 years old, 60% of participants were women, and the median plasma FGF23 concentration was 70 (interquartile range, 53-99) relative units per milliliter. In fully adjusted models, higher FGF23 concentrations associated with higher risk of first infection-related hospitalization (hazard ratio [HR], 1.11; 95% confidence interval [95% CI], 1.03 to 1.20 per doubling of FGF23) during a median follow-up of 8.6 years. In participants with or without CKD (defined by eGFR), FGF23 concentration associated with first infection-related hospitalization with HRs of 1.24 (95% CI, 1.08 to 1.42) and 1.06 (95% CI, 0.97 to 1.17) per doubling of FGF23, respectively (P=0.13 for interaction). Associations did not differ between groups when stratified by urine albumin-to-creatinine ratio. In sensitivity analyses, the addition of serum calcium, phosphorus, 25-hydroxyvitamin D, intact parathyroid hormone, and 24,25-dihydroxyvitamin D did not meaningfully change the estimates. In conclusion, in community-dwelling older adults, higher plasma FGF23 concentrations independently associated with the risk of first infection-related hospitalization.

Fibroblast Growth Factor 23, Mineral Metabolism, and Adiposity in Normal Kidney Function. - Zaheer, Sarah; de Boer, Ian H; Allison, Matthew; Brown, Jenifer M; Psaty, Bruce M; Robinson-Cohen, Cassianne; Michos, Erin D; Ix, Joachim H; Kestenbaum, Bryan; Siscovick, David; Vaidya, Anand (J Clin Endocrinol Metab, 2017)
Context: Obesity is associated with poor bone mineralization and quality. Fibroblast growth factor 23 (FGF23) plays an important role in skeletal physiology. Objective: To test hypothesis that greater adiposity results in higher FGF23 levels among individuals with normal estimated glomerular filtration rate (eGFR). Design, Setting, Participants: Cross-sectional analyses among participants with eGFR ≥60 mL/min/1.73m2. We assessed the association between crude [body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR); n = 5610] and refined (abdominal adipose tissue area by computed tomography; n = 1313) measures of adiposity and FGF23 using multivariable linear regression. Main Outcome Measure: Serum FGF23. Results: FGF23 was higher across BMI categories (BMI <25: 37.7; BMI 25 to 29.99: 38.7; BMI 30 to 39.99: 39.8; BMI ≥40: 40.9 pg/mL, unadjusted P trend < 0.0001). The association between BMI and FGF23 was independent of known confounders of FGF23 (adjusted β = +7.2% higher FGF23 per 10 kg/m2; P < 0.0001). Similar results were observed using WC and WHR. Abdominal adipose tissue area was also independently associated with higher FGF23 (P < 0.01). Notably, the positive associations between FGF23 and adiposity were observed despite the fact that eGFR did not decline and serum phosphate levels did not increase with adiposity. Conclusion: In a large cohort with normal kidney function, adiposity was associated with higher FGF23 levels independent of known confounders, including eGFR and phosphate. Further studies are needed to evaluate the causes of higher FGF23 in settings of greater adiposity and the potential impact on skeletal health.
Keywords: Adiposity; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Fibroblast Growth Factors; Glomerular Filtration Rate; Humans; Kidney; Male; Middle Aged; Minerals; Renal Insufficiency, Chronic; Risk Factors

Fifteen Genetic Loci Associated With the Electrocardiographic P Wave. - Christophersen, Ingrid E; Magnani, Jared W; Yin, Xiaoyan; Barnard, John; Weng, Lu-Chen; Arking, Dan E; Niemeijer, Maartje N; Lubitz, Steven A; Avery, Christy L; Duan, Qing; Felix, Stephan B; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: The P wave on an ECG is a measure of atrial electric function, and its characteristics may serve as predictors for atrial arrhythmias. Increased mean P-wave duration and P-wave terminal force traditionally have been used as markers for left atrial enlargement, and both have been associated with increased risk of atrial fibrillation. Here, we explore the genetic basis of P-wave morphology through meta-analysis of genome-wide association study results for P-wave duration and P-wave terminal force from 12 cohort studies. METHODS AND RESULTS: We included 44 456 individuals, of which 6778 (16%) were of African ancestry. Genotyping, imputation, and genome-wide association study were performed at each study site. Summary-level results were meta-analyzed centrally using inverse-variance weighting. In meta-analyses of P-wave duration, we identified 6 significant (P<5×10-8) novel loci and replicated a prior association with SCN10A. We identified 3 loci at SCN5A, TBX5, and CAV1/CAV2 that were jointly associated with the PR interval, PR segment, and P-wave duration. We identified 6 novel loci in meta-analysis of P-wave terminal force. Four of the identified genetic loci were significantly associated with gene expression in 329 left atrial samples. Finally, we observed that some of the loci associated with the P wave were linked to overall atrial conduction, whereas others identified distinct phases of atrial conduction. CONCLUSIONS: We have identified 6 novel genetic loci associated with P-wave duration and 6 novel loci associated with P-wave terminal force. Future studies of these loci may aid in identifying new targets for drugs that may modify atrial conduction or treat atrial arrhythmias.
Keywords: Arrhythmias, Cardiac; Caveolin 1; Caveolin 2; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Genotype; Heart Atria; Humans; NAV1.5 Voltage-Gated Sodium Channel; NAV1.8 Voltage-Gated Sodium Channel; T-Box Domain Proteins

Generalization and fine mapping of European ancestry-based central adiposity variants in African ancestry populations. - Yoneyama, S; Yao, J; Guo, X; Fernandez-Rhodes, L; Lim, U; Boston, J; Bůžková, P; Carlson, C S; Cheng, I; Cochran, B; Cooper, R; Ehret, G; et al. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Central adiposity measures such as waist circumference (WC) and waist-to-hip ratio (WHR) are associated with cardiometabolic disorders independently of body mass index (BMI) and are gaining clinically utility. Several studies report genetic variants associated with central adiposity, but most utilize only European ancestry populations. Understanding whether the genetic associations discovered among mainly European descendants are shared with African ancestry populations will help elucidate the biological underpinnings of abdominal fat deposition. SUBJECTS/METHODS: To identify the underlying functional genetic determinants of body fat distribution, we conducted an array-wide association meta-analysis among persons of African ancestry across seven studies/consortia participating in the Population Architecture using Genomics and Epidemiology (PAGE) consortium. We used the Metabochip array, designed for fine-mapping cardiovascular-associated loci, to explore novel array-wide associations with WC and WHR among 15 945 African descendants using all and sex-stratified groups. We further interrogated 17 known WHR regions for African ancestry-specific variants. RESULTS: Of the 17 WHR loci, eight single-nucleotide polymorphisms (SNPs) located in four loci were replicated in the sex-combined or sex-stratified meta-analyses. Two of these eight independently associated with WHR after conditioning on the known variant in European descendants (rs12096179 in TBX15-WARS2 and rs2059092 in ADAMTS9). In the fine-mapping assessment, the putative functional region was reduced across all four loci but to varying degrees (average 40% drop in number of putative SNPs and 20% drop in genomic region). Similar to previous studies, the significant SNPs in the female-stratified analysis were stronger than the significant SNPs from the sex-combined analysis. No novel associations were detected in the array-wide analyses. CONCLUSIONS: Of 17 previously identified loci, four loci replicated in the African ancestry populations of this study. Utilizing different linkage disequilibrium patterns observed between European and African ancestries, we narrowed the suggestive region containing causative variants for all four loci.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

{Genome-wide meta-analysis of 241,258 adults accounting for smoking behaviour identifies novel loci for obesity traits - Justice, A. E.; Winkler, T. W.; Feitosa, M. F.; Graff, M.; Fisher, V. A.; Young, K.; Barata, L.; Deng, X.; Czajkowski, J.; Hadley, D.; Ngwa, J. S.; Ahluwalia, T. S.; et al. (Nat Commun, 2017)
Few genome-wide association studies (GWAS) account for environmental exposures, like smoking, potentially impacting the overall trait variance when investigating the genetic contribution to obesity-related traits. Here, we use GWAS data from 51,080 current smokers and 190,178 nonsmokers (87% European descent) to identify loci influencing BMI and central adiposity, measured as waist circumference and waist-to-hip ratio both adjusted for BMI. We identify 23 novel genetic loci, and 9 loci with convincing evidence of gene-smoking interaction (GxSMK) on obesity-related traits. We show consistent direction of effect for all identified loci and significance for 18 novel and for 5 interaction loci in an independent study sample. These loci highlight novel biological functions, including response to oxidative stress, addictive behaviour, and regulatory functions emphasizing the importance of accounting for environment in genetic analyses. Our results suggest that tobacco smoking may alter the genetic susceptibility to overall adiposity and body fat distribution.

Higher plasma transforming growth factor (TGF)-β is associated with kidney disease in older community dwelling adults. - Mehta, Tapan; Bůzková, Petra; Kizer, Jorge R; Djoussé, Luc; Chonchol, Michel; Mukamal, Kenneth J; Shlipak, Michael; Ix, Joachim H; Jalal, Diana (BMC Nephrol, 2017)
BACKGROUND: TGF-β is induced in the vasculature with aging suggesting that high plasma TGF-β levels may be a risk factor for chronic kidney disease (CKD) in older adults. METHODS: We conducted a cross-sectional analysis of the association between plasma TGF-β levels and CKD including data for 1722 older adults who had participated in the 1996/97 visit of the Cardiovascular Health Study (CHS). Prevalent CKD was defined as eGFR < 60 mL/min/1.73 m(2) or urinary albumin/creatinine ratio (ACR) ≥30 mg/g. We also evaluated whether baseline TGF-β levels predicted change in eGFR, cardiovascular (CV) events, or mortality in longitudinal analysis. RESULTS: Plasma TGF-β levels were significantly and independently associated with lower eGFR in cross-sectional analysis. Doubling of TGF-β was significantly associated with lower eGFR (β estimate after adjusting for CV risk factors = -1.18, 95% CI -2.03, -0.32). We observed no association with albuminuria. There was no association between baseline TGF-β and change in eGFR, but each doubling of TGF-β at baseline was associated with increased risk of a composite outcome of CV events and mortality, adjusted HR 1.10 (95% C.I. 1.02- 1.20, p = 0.006). CONCLUSION: In this large cohort of community-dwelling older individuals, high plasma TGF-β levels are modestly, but independently associated with lower eGFR but not with albuminuria in cross-sectional analysis. In addition, TGF-β levels are associated with increased risk of CV events and mortality. Further research is needed to determine the direction of association between plasma TGF-β and the risk of CKD and CKD-associated morbidities in older adults.

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

{Novel genetic loci associated with hippocampal volume - Hibar, D. P.; Adams, H. H. H.; Jahanshad, N.; Chauhan, G.; Stein, J. L.; Hofer, E.; Renteria, M. E.; Bis, J. C.; Arias-Vasquez, A.; Ikram, M. K.; Desrivi?res, S.; Vernooij, M. W.; et al. (Nat Commun, 2017)
The hippocampal formation is a brain structure integrally involved in episodic memory, spatial navigation, cognition and stress responsiveness. Structural abnormalities in hippocampal volume and shape are found in several common neuropsychiatric disorders. To identify the genetic underpinnings of hippocampal structure here we perform a genome-wide association study (GWAS) of 33,536 individuals and discover six independent loci significantly associated with hippocampal volume, four of them novel. Of the novel loci, three lie within genes (ASTN2, DPP4 and MAST4) and one is found 200 kb upstream of SHH. A hippocampal subfield analysis shows that a locus within the MSRB3 gene shows evidence of a localized effect along the dentate gyrus, subiculum, CA1 and fissure. Further, we show that genetic variants associated with decreased hippocampal volume are also associated with increased risk for Alzheimer's disease (rg=-0.155). Our findings suggest novel biological pathways through which human genetic variation influences hippocampal volume and risk for neuropsychiatric illness.

PCSK9 Loss-of-Function Variants, Low-Density Lipoprotein Cholesterol, and Risk of Coronary Heart Disease and Stroke: Data From 9 Studies of Blacks and Whites. - Kent, Shia T; Rosenson, Robert S; Avery, Christy L; Chen, Yii-der I; Correa, Adolfo; Cummings, Steven R; Cupples, L Adrienne; Cushman, Mary; Evans, Daniel S; Gudnason, Vilmundur; Harris, Tamara B; Howard, George; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: PCSK9 loss-of-function (LOF) variants allow for the examination of the effects of lifetime reduced low-density lipoprotein cholesterol (LDL-C) on cardiovascular events. We examined the association of PCSK9 LOF variants with LDL-C and incident coronary heart disease and stroke through a meta-analysis of data from 8 observational cohorts and 1 randomized trial of statin therapy. METHODS AND RESULTS: These 9 studies together included 17 459 blacks with 403 (2.3%) having at least 1 Y142X or C679X variant and 31 306 whites with 955 (3.1%) having at least 1 R46L variant. Unadjusted odds ratios for associations between PCSK9 LOF variants and incident coronary heart disease (851 events in blacks and 2662 events in whites) and stroke (523 events in blacks and 1660 events in whites) were calculated using pooled Mantel-Haenszel estimates with continuity correction factors. Pooling results across studies using fixed-effects inverse-variance-weighted models, PCSK9 LOF variants were associated with 35 mg/dL (95% confidence interval [CI], 32-39) lower LDL-C in blacks and 13 mg/dL (95% CI, 11-16) lower LDL-C in whites. PCSK9 LOF variants were associated with a pooled odds ratio for coronary heart disease of 0.51 (95% CI, 0.28-0.92) in blacks and 0.82 (95% CI, 0.63-1.06) in whites. PCSK9 LOF variants were not associated with incident stroke (odds ratio, 0.84; 95% CI, 0.48-1.47 in blacks and odds ratio, 1.06; 95% CI, 0.80-1.41 in whites). CONCLUSIONS: PCSK9 LOF variants were associated with lower LDL-C and coronary heart disease incidence. PCSK9 LOF variants were not associated with stroke risk.

Pharmacogenomics study of thiazide diuretics and QT interval in multi-ethnic populations: the cohorts for heart and aging research in genomic epidemiology. - Seyerle, A A; Sitlani, C M; Noordam, R; Gogarten, S M; Li, J; Li, X; Evans, D S; Sun, F; Laaksonen, M A; Isaacs, A; Kristiansson, K; Highland, H M; et al. (Pharmacogenomics J, 2017)
Thiazide diuretics, commonly used antihypertensives, may cause QT interval (QT) prolongation, a risk factor for highly fatal and difficult to predict ventricular arrhythmias. We examined whether common single-nucleotide polymorphisms (SNPs) modified the association between thiazide use and QT or its component parts (QRS interval, JT interval) by performing ancestry-specific, trans-ethnic and cross-phenotype genome-wide analyses of European (66%), African American (15%) and Hispanic (19%) populations (N=78 199), leveraging longitudinal data, incorporating corrected standard errors to account for underestimation of interaction estimate variances and evaluating evidence for pathway enrichment. Although no loci achieved genome-wide significance (P<5 × 10(-8)), we found suggestive evidence (P<5 × 10(-6)) for SNPs modifying the thiazide-QT association at 22 loci, including ion transport loci (for example, NELL1, KCNQ3). The biologic plausibility of our suggestive results and simulations demonstrating modest power to detect interaction effects at genome-wide significant levels indicate that larger studies and innovative statistical methods are warranted in future efforts evaluating thiazide-SNP interactions.The Pharmacogenomics Journal advance online publication, 18 July 2017; doi:10.1038/tpj.2017.10.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

The Relation of Serum Potassium Concentration with Cardiovascular Events and Mortality in Community-Living Individuals. - Hughes-Austin, Jan M; Rifkin, Dena E; Beben, Tomasz; Katz, Ronit; Sarnak, Mark J; Deo, Rajat; Hoofnagle, Andrew N; Homma, Shunichi; Siscovick, David S; Sotoodehnia, Nona; Psaty, Bruce M; de Boer, Ian H; et al. (Clin J Am Soc Nephrol, 2017)
BACKGROUND AND OBJECTIVES: Hyperkalemia is associated with adverse outcomes in patients with CKD and in hospitalized patients with acute medical conditions. Little is known regarding hyperkalemia, cardiovascular disease (CVD), and mortality in community-living populations. In a pooled analysis of two large observational cohorts, we investigated associations between serum potassium concentrations and CVD events and mortality, and whether potassium-altering medications and eGFR<60 ml/min per 1.73 m(2) modified these associations. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Among 9651 individuals from the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS), who were free of CVD at baseline (2000-2002 in the MESA and 1989-1993 in the CHS), we investigated associations between serum potassium categories (<3.5, 3.5-3.9, 4.0-4.4, 4.5-4.9, and ≥5.0 mEq/L) and CVD events, mortality, and mortality subtypes (CVD versus non-CVD) using Cox proportional hazards models, adjusting for demographics, time-varying eGFR, traditional CVD risk factors, and use of potassium-altering medications. RESULTS: Compared with serum potassium concentrations between 4.0 and 4.4 mEq/L, those with concentrations ≥5.0 mEq/L were at higher risk for all-cause mortality (hazard ratio, 1.41; 95% confidence interval, 1.12 to 1.76), CVD death (hazard ratio, 1.50; 95% confidence interval, 1.00 to 2.26), and non-CVD death (hazard ratio, 1.40; 95% confidence interval, 1.07 to 1.83) in fully adjusted models. Associations of serum potassium with these end points differed among diuretic users (Pinteraction<0.02 for all), such that participants who had serum potassium ≥5.0 mEq/L and were concurrently using diuretics were at higher risk of each end point compared with those not using diuretics. CONCLUSIONS: Serum potassium concentration ≥5.0 mEq/L was associated with all-cause mortality, CVD death, and non-CVD death in community-living individuals; associations were stronger in diuretic users. Whether maintenance of potassium within the normal range may improve clinical outcomes requires future study.

Relationship of bone mineral density with valvular and annular calcification in community-dwelling older people: The Cardiovascular Health Study. - Massera, Daniele; Xu, Shuo; Bartz, Traci M; Bortnick, Anna E; Ix, Joachim H; Chonchol, Michel; Owens, David S; Barasch, Eddy; Gardin, Julius M; Gottdiener, John S; Robbins, John R; Siscovick, David S; et al. (Arch Osteoporos, 2017)
Associations between bone mineral density and aortic valvular, aortic annular, and mitral annular calcification were investigated in a cross-sectional analysis of a population-based cohort of 1497 older adults. Although there was no association between continuous bone mineral density and outcomes, a significant association between osteoporosis and aortic valvular calcification in men was found. INTRODUCTION: The process of cardiac calcification bears a resemblance to skeletal bone metabolism and its regulation. Experimental studies suggest that bone mineral density (BMD) and valvular calcification may be reciprocally related, but epidemiologic data are sparse. METHODS: We tested the hypothesis that BMD of the total hip and femoral neck measured by dual-energy X-ray absorptiometry (DXA) is inversely associated with prevalence of three echocardiographic measures of cardiac calcification in a cross-sectional analysis of 1497 older adults from the Cardiovascular Health Study. The adjusted association of BMD with aortic valve calcification (AVC), aortic annular calcification (AAC), and mitral annular calcification (MAC) was assessed with relative risk (RR) regression. RESULTS: Mean (SD) age was 76.2 (4.8) years; 58% were women. Cardiac calcification was highly prevalent in women and men: AVC, 59.5 and 71.0%; AAC 45.1 and 46.7%; MAC 42.8 and 39.5%, respectively. After limited and full adjustment for potential confounders, no statistically significant associations were detected between continuous BMD at either site and the three measures of calcification. Assessment of WHO BMD categories revealed a significant association between osteoporosis at the total hip and AVC in men (adjusted RR compared with normal BMD = 1.24 (1.01-1.53)). In graded sensitivity analyses, there were apparent inverse associations between femoral neck BMD and AVC with stenosis in men, and femoral neck BMD and moderate/severe MAC in women, but these were not significant. CONCLUSION: These findings support further investigation of the sex-specific relationships between low BMD and cardiac calcification, and whether processes linking the two could be targeted for therapeutic ends.

REPEATED MEASUREMENTS OF BLOOD PRESSURE AND CHOLESTEROL IMPROVES CARDIOVASCULAR DISEASE RISK PREDICTION: AN INDIVIDUAL-PARTICIPANT-DATA META-ANALYSIS. - Paige, Ellie; Barrett, Jessica; Pennells, Lisa; Sweeting, Michael; Willeit, Peter; Di Angelantonio, Emanuele; Gudnason, Vilmundur; Nordestgaard, Børge G; Psaty, Bruce M; Goldbourt, Uri; Best, Lyle G; Assmann, Gerd; et al. (Am J Epidemiol, 2017)
The added value of incorporating information from repeated measurements of blood pressure and cholesterol for cardiovascular disease (CVD) risk prediction has not been rigorously assessed. We used data from the Emerging Risk Factors Collaboration on 191,445 adults (38 cohorts from across 17 countries with data from 1962-2014) with > 1 million measurements of systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol; over a median 12 years of follow-up, 21,170 CVD events occurred. Risk prediction models using cumulative means of repeated measurements and summary measures from longitudinal modelling of the repeated measurements were compared to models using measurements from a single time point. Risk discrimination (C-index) and net reclassification were calculated, and changes in C-indices were meta-analysed across studies. Compared to the single time point model, the cumulative means and the longitudinal models increased the C-index by 0.0040 (95% CI: 0.0023, 0.0057) and 0.0023 (0.0005, 0.0042), respectively. Reclassification was also improved in both models; compared to the single time point model, overall net reclassification improvements were 0.0369 (0.0303, 0.0436) for the cumulative means model and 0.0177 (0.0110, 0.0243) for the longitudinal model. In conclusion, incorporating repeated measurements of blood pressure and cholesterol into CVD risk prediction models slightly improves risk prediction.

Sleep-disordered breathing is associated with higher carboxymethyllysine level in elderly women but not elderly men in the cardiovascular health study. - Ahiawodzi, Peter D; Kerber, Richard A; Taylor, Kira C; Groves, Frank D; O'Brien, Elizabeth; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Robbins, John; et al. (Biomarkers, 2017)
CONTEXT: Carboxymethyl-lysine (CML) results from oxidative stress and has been linked to cardiovascular disease. OBJECTIVE: The objective of this study is to investigate the association between sleep-disordered breathing (SDB) - a source of oxidative stress - and CML. MATERIALS AND METHODS: About 1002 participants in the Cardiovascular Health Study (CHS) were studied. RESULTS: Women with SDB had significantly higher CML concentration compared with those without SDB (OR = 1.63, 95%CI = 1.03-2.58, p = 0.04). The association was not significant among men. DISCUSSION: SDB was associated with CML concentration among elderly women but not men in the Cardiovascular Health Study. CONCLUSION: Accumulation of CML may be an adverse health consequence of SDB.

Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. - Baumgartner, Christine; da Costa, Bruno R; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C; Cappola, Anne R; Heckbert, Susan R; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P J; Peeters, Robin P; et al. (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. METHODS: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. RESULTS: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26-1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ≤0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. CONCLUSIONS: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF.
Keywords: Adult; Aged; Aged, 80 and over; Asymptomatic Diseases; Atrial Fibrillation; Biomarkers; Chi-Square Distribution; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Time Factors; Young Adult

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci. - Fernandez-Rhodes, Lindsay; Gong, Jian; Haessler, Jeffrey; Franceschini, Nora; Graff, Mariaelisa; Nishimura, Katherine K; Wang, Yujie; Highland, Heather M; Yoneyama, Sachiko; Bush, William S; Goodloe, Robert; Ritchie, Marylyn D; et al. (Hum Genet, 2017)
Most body mass index (BMI) genetic loci have been identified in studies of primarily European ancestries. The effect of these loci in other racial/ethnic groups is less clear. Thus, we aimed to characterize the generalizability of 170 established BMI variants, or their proxies, to diverse US populations and trans-ethnically fine-map 36 BMI loci using a sample of >102,000 adults of African, Hispanic/Latino, Asian, European and American Indian/Alaskan Native descent from the Population Architecture using Genomics and Epidemiology Study. We performed linear regression of the natural log of BMI (18.5-70 kg/m(2)) on the additive single nucleotide polymorphisms (SNPs) at BMI loci on the MetaboChip (Illumina, Inc.), adjusting for age, sex, population stratification, study site, or relatedness. We then performed fixed-effect meta-analyses and a Bayesian trans-ethnic meta-analysis to empirically cluster by allele frequency differences. Finally, we approximated conditional and joint associations to test for the presence of secondary signals. We noted directional consistency with the previously reported risk alleles beyond what would have been expected by chance (binomial p < 0.05). Nearly, a quarter of the previously described BMI index SNPs and 29 of 36 densely-genotyped BMI loci on the MetaboChip replicated/generalized in trans-ethnic analyses. We observed multiple signals at nine loci, including the description of seven loci with novel multiple signals. This study supports the generalization of most common genetic loci to diverse ancestral populations and emphasizes the importance of dense multiethnic genomic data in refining the functional variation at genetic loci of interest and describing several loci with multiple underlying genetic variants.
Keywords: Body Mass Index; Ethnic Groups; Genetics, Population; Humans; Obesity

Trends in the incidence of dementia: design and methods in the Alzheimer Cohorts Consortium. - Chibnik, Lori B; Wolters, Frank J; Bäckman, Kristoffer; Beiser, Alexa; Berr, Claudine; Bis, Joshua C; Boerwinkle, Eric; Bos, Daniel; Brayne, Carol; Dartigues, Jean-François; Darweesh, Sirwan K L; Debette, Stephanie; et al. (Eur J Epidemiol, 2017)
Several studies have reported a decline in incidence of dementia which may have large implications for the projected burden of disease, and provide important guidance to preventive efforts. However, reports are conflicting or inconclusive with regard to the impact of gender and education with underlying causes of a presumed declining trend remaining largely unidentified. The Alzheimer Cohorts Consortium aggregates data from nine international population-based cohorts to determine changes in the incidence of dementia since 1990. We will employ Poisson regression models to calculate incidence rates in each cohort and Cox proportional hazard regression to compare 5-year cumulative hazards across study-specific epochs. Finally, we will meta-analyse changes per decade across cohorts, and repeat all analysis stratified by sex, education and APOE genotype. In all cohorts combined, there are data on almost 69,000 people at risk of dementia with the range of follow-up years between 2 and 27. The average age at baseline is similar across cohorts ranging between 72 and 77. Uniting a wide range of disease-specific and methodological expertise in research teams, the first analyses within the Alzheimer Cohorts Consortium are underway to tackle outstanding challenges in the assessment of time-trends in dementia occurrence.

The 24,25 to 25-hydroxyvitamin D ratio and fracture risk in older adults: The cardiovascular health study. - Ginsberg, Charles; Katz, Ronit; de Boer, Ian H; Kestenbaum, Bryan R; Chonchol, Michel; Shlipak, Michael G; Sarnak, Mark J; Hoofnagle, Andrew N; Rifkin, Dena E; Garimella, Pranav S; Ix, Joachim H (Bone, 2018)
25-hydroxyvitamin D [25(OH)D] may not optimally indicate vitamin D receptor activity. Higher concentrations of its catabolic product 24,25-dihydroxyvitmin D [24,25(OH)2D] and a higher ratio of 24,25(OH)2D to 25(OH)D (the vitamin D metabolite ratio [VMR]) may provide additional information on receptor activity. We compared the strength of associations of these markers with serum PTH concentrations, hip bone mineral density (BMD), and risk of incident hip fracture in community-living older participants in the Cardiovascular Health Study. Among 890 participants, the mean age was 78years, 60% were women, and the mean 25(OH)D was 28±11ng/ml. In cross-sectional analysis, the strength of association of each vitamin D measure with PTH was similar; a 1% higher 25(OH)D, 24,25(OH)2D, and VMR were associated with 0.32%, 0.25%, and 0.26% lower PTH, respectively (p<0.05 for all). Among 358 participants with available BMD data, we found no associations of 25(OH)D or VMR with BMD, whereas higher 24,25(OH)2D was modestly associated with greater hip BMD (1% higher 24,25(OH)2D associated with 0.04% [95% CI 0.01-0.08%] higher BMD). Risk of incident hip fracture risk was evaluated using a case-cohort design. There were 289 hip fractures during a mean follow up time of 8.4years. Both higher 24,25(OH)2D and VMR were associated with lower risk of hip fracture (HR per SD higher, 0.73 [0.61, 0.87] and 0.74 [0.61, 0.88], respectively) whereas 25(OH)D was not associated with hip fracture (HR 0.93 [0.79, 1.10]). We conclude that evaluating vitamin D status by incorporating assessment of 24,25(OH)D and the VMR provides information on bone health above and beyond 25(OH)D alone.

Biochemical Markers of Bone Turnover and Risk of Incident Diabetes in Older Women: The Cardiovascular Health Study. - Massera, Daniele; Biggs, Mary L; Walker, Marcella D; Mukamal, Kenneth J; Ix, Joachim H; Djoussé, Luc; Valderrábano, Rodrigo J; Siscovick, David S; Tracy, Russell P; Xue, XiaoNan; Kizer, Jorge R (Diabetes Care, 2018)
OBJECTIVE: To investigate the relationship of osteocalcin (OC), a marker of bone formation, and C-terminal cross-linked telopeptide of type I collagen (CTX), a marker of bone resorption, with incident diabetes in older women. RESEARCH DESIGN AND METHODS: The analysis included 1,455 female participants from the population-based Cardiovascular Health Study (CHS) (mean [SD] age 74.6 [5.0] years). The cross-sectional association of serum total OC and CTX levels with insulin resistance (HOMA-IR) was examined using multiple linear regression. The longitudinal association of both markers with incident diabetes, defined by follow-up glucose measurements, medications, and ICD-9 codes, was examined using multivariable Cox proportional hazards models. RESULTS: OC and CTX were strongly correlated ( = 0.80). In cross-sectional analyses, significant or near-significant inverse associations with HOMA-IR were observed for continuous levels of OC (β = -0.12 per SD increment; = 0.004) and CTX (β = -0.08 per SD; = 0.051) after full adjustment for demographic, lifestyle, and clinical covariates. During a median follow-up of 11.5 years, 196 cases of incident diabetes occurred. After full adjustment, both biomarkers exhibited inverse associations with incident diabetes (OC: hazard ratio 0.85 per SD [95% CI 0.71-1.02; = 0.075]; CTX: 0.82 per SD [0.69-0.98; = 0.031]), associations that were comparable in magnitude and approached or achieved statistical significance. CONCLUSIONS: In late postmenopausal women, lower OC and CTX levels were associated with similarly increased risks of insulin resistance at baseline and incident diabetes over long-term follow-up. Further research to delineate the mechanisms linking abnormal bone homeostasis and energy metabolism could uncover new approaches for the prevention of these age-related disorders.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Fatty acid biomarkers of dairy fat consumption and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies. - Imamura, Fumiaki; Fretts, Amanda; Marklund, Matti; Ardisson Korat, Andres V; Yang, Wei-Sin; Lankinen, Maria; Qureshi, Waqas; Helmer, Catherine; Chen, Tzu-An; Wong, Kerry; Bassett, Julie K; Murphy, Rachel; et al. (PLoS Med, 2018)
BACKGROUND: We aimed to investigate prospective associations of circulating or adipose tissue odd-chain fatty acids 15:0 and 17:0 and trans-palmitoleic acid, t16:1n-7, as potential biomarkers of dairy fat intake, with incident type 2 diabetes (T2D). METHODS AND FINDINGS: Sixteen prospective cohorts from 12 countries (7 from the United States, 7 from Europe, 1 from Australia, 1 from Taiwan) performed new harmonised individual-level analysis for the prospective associations according to a standardised plan. In total, 63,682 participants with a broad range of baseline ages and BMIs and 15,180 incident cases of T2D over the average of 9 years of follow-up were evaluated. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Prespecified interactions by age, sex, BMI, and race/ethnicity were explored in each cohort and were meta-analysed. Potential heterogeneity by cohort-specific characteristics (regions, lipid compartments used for fatty acid assays) was assessed with metaregression. After adjustment for potential confounders, including measures of adiposity (BMI, waist circumference) and lipogenesis (levels of palmitate, triglycerides), higher levels of 15:0, 17:0, and t16:1n-7 were associated with lower incidence of T2D. In the most adjusted model, the hazard ratio (95% CI) for incident T2D per cohort-specific 10th to 90th percentile range of 15:0 was 0.80 (0.73-0.87); of 17:0, 0.65 (0.59-0.72); of t16:1n7, 0.82 (0.70-0.96); and of their sum, 0.71 (0.63-0.79). In exploratory analyses, similar associations for 15:0, 17:0, and the sum of all three fatty acids were present in both genders but stronger in women than in men (pinteraction < 0.001). Whereas studying associations with biomarkers has several advantages, as limitations, the biomarkers do not distinguish between different food sources of dairy fat (e.g., cheese, yogurt, milk), and residual confounding by unmeasured or imprecisely measured confounders may exist. CONCLUSIONS: In a large meta-analysis that pooled the findings from 16 prospective cohort studies, higher levels of 15:0, 17:0, and t16:1n-7 were associated with a lower risk of T2D.
Keywords: Aged; Australia; Biomarkers; Dairy Products; Diabetes Mellitus, Type 2; Dietary Fats; Europe; Fatty Acids; Fatty Acids, Monounsaturated; Female; Humans; Incidence; Male; Middle Aged; Prospective Studies; Sex Factors; Taiwan; United States

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genetically elevated high-density lipoprotein cholesterol through the cholesteryl ester transfer protein gene does not associate with risk of Alzheimer's disease. - Peloso, Gina M; van der Lee, Sven J; DeStefano, Anita L; Seshardi, Sudha (Alzheimers Dement (Amst), 2018)
Introduction: There is conflicting evidence whether high-density lipoprotein cholesterol (HDL-C) is a risk factor for Alzheimer's disease (AD) and dementia. Genetic variation in the cholesteryl ester transfer protein () locus is associated with altered HDL-C. We aimed to assess AD risk by genetically predicted HDL-C. Methods: Ten single nucleotide polymorphisms within the locus predicting HDL-C were applied to the International Genomics of Alzheimer's Project (IGAP) exome chip stage 1 results in up 16,097 late onset AD cases and 18,077 cognitively normal elderly controls. We performed instrumental variables analysis using inverse variance weighting, weighted median, and MR-Egger. Results: Based on 10 single nucleotide polymorphisms distinctly predicting HDL-C in the locus, we found that HDL-C was not associated with risk of AD ( > .7). Discussion: Our study does not support the role of HDL-C on risk of AD through HDL-C altered by . This study does not rule out other mechanisms by which HDL-C affects risk of AD.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium. - de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Sun, Qi; King, Irena B; Wu, Jason H Y; Manichaikul, Ani; Rich, Stephen S; Tsai, Michael Y; Chen, Y D; Fornage, Myriam; Weihua, Guan; Aslibekyan, Stella; et al. (PLoS One, 2018)
BACKGROUND: Odd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established. OBJECTIVE: To elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between genetic variation and OCSFA. DESIGN: We performed a meta-analysis of genome-wide association studies (GWAS) of plasma phospholipid/erythrocyte levels of C15:0, C17:0, C19:0, and C23:0 among 11,494 individuals of European descent. We also investigated relationships between specific single nucleotide polymorphisms (SNPs) in the lactase (LCT) gene, associated with adult-onset lactase intolerance, with circulating levels of dairy-derived OCSFA, and evaluated associations of candidate sphingolipid genes with C23:0 levels. RESULTS: We found no genome-wide significant evidence that common genetic variation is associated with circulating levels of C15:0 or C23:0. In two cohorts with available data, we identified one intronic SNP (rs13361131) in myosin X gene (MYO10) associated with C17:0 level (P = 1.37×10-8), and two intronic SNP (rs12874278 and rs17363566) in deleted in lymphocytic leukemia 1 (DLEU1) region associated with C19:0 level (P = 7.07×10-9). In contrast, when using a candidate-gene approach, we found evidence that three SNPs in LCT (rs11884924, rs16832067, and rs3816088) are associated with circulating C17:0 level (adjusted P = 4×10-2). In addition, nine SNPs in the ceramide synthase 4 (CERS4) region were associated with circulating C23:0 levels (adjusted P<5×10-2). CONCLUSIONS: Our findings suggest that circulating levels of OCSFA may be predominantly influenced by non-genetic factors. SNPs associated with C17:0 level in the LCT gene may reflect genetic influence in dairy consumption or in metabolism of dairy foods. SNPs associated with C23:0 may reflect a role of genetic factors in the synthesis of sphingomyelin.
Keywords: Fatty Acids; Genome-Wide Association Study; Humans; Introns; Lactase; Myosins; Polymorphism, Single Nucleotide; Sphingomyelins; Sphingosine N-Acyltransferase; Tumor Suppressor Proteins

Genome-wide association study in 79,366 European-ancestry individuals informs the genetic architecture of 25-hydroxyvitamin D levels. - Jiang, Xia; O'Reilly, Paul F; Aschard, Hugues; Hsu, Yi-Hsiang; Richards, J Brent; Dupuis, Josée; Ingelsson, Erik; Karasik, David; Pilz, Stefan; Berry, Diane; Kestenbaum, Bryan; Zheng, Jusheng; et al. (Nat Commun, 2018)
Vitamin D is a steroid hormone precursor that is associated with a range of human traits and diseases. Previous GWAS of serum 25-hydroxyvitamin D concentrations have identified four genome-wide significant loci (GC, NADSYN1/DHCR7, CYP2R1, CYP24A1). In this study, we expand the previous SUNLIGHT Consortium GWAS discovery sample size from 16,125 to 79,366 (all European descent). This larger GWAS yields two additional loci harboring genome-wide significant variants (P = 4.7×10 at rs8018720 in SEC23A, and P = 1.9×10 at rs10745742 in AMDHD1). The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to GWAS common SNPs is 7.5%, with statistically significant loci explaining 38% of this total. Further investigation identifies signal enrichment in immune and hematopoietic tissues, and clustering with autoimmune diseases in cell-type-specific analysis. Larger studies are required to identify additional common SNPs, and to explore the role of rare or structural variants and gene-gene interactions in the heritability of circulating 25-hydroxyvitamin D levels.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of SNP-by9-ACEI/ARB and SNP-by-thiazide diuretic and effect on serum potassium in cohorts of European and African ancestry. - Irvin, Marguerite R; Sitlani, Colleen M; Noordam, Raymond; Avery, Christie L; Bis, Joshua C; Floyd, James S; Li, Jin; Limdi, Nita A; Srinivasasainagendra, Vinodh; Stewart, James; de Mutsert, Renée; Mook-Kanamori, Dennis O; et al. (Pharmacogenomics J, 2018)
We evaluated interactions of SNP-by-ACE-I/ARB and SNP-by-TD on serum potassium (K+) among users of antihypertensive treatments (anti-HTN). Our study included seven European-ancestry (EA) (N = 4835) and four African-ancestry (AA) cohorts (N = 2016). We performed race-stratified, fixed-effect, inverse-variance-weighted meta-analyses of 2.5 million SNP-by-drug interaction estimates; race-combined meta-analysis; and trans-ethnic fine-mapping. Among EAs, we identified 11 significant SNPs (P < 5 × 10) for SNP-ACE-I/ARB interactions on serum K+ that were located between NR2F1-AS1 and ARRDC3-AS1 on chromosome 5 (top SNP rs6878413 P = 1.7 × 10; ratio of serum K+ in ACE-I/ARB exposed compared to unexposed is 1.0476, 1.0280, 1.0088 for the TT, AT, and AA genotypes, respectively). Trans-ethnic fine mapping identified the same group of SNPs on chromosome 5 as genome-wide significant for the ACE-I/ARB analysis. In conclusion, SNP-by-ACE-I /ARB interaction analyses uncovered loci that, if replicated, could have future implications for the prevention of arrhythmias due to anti-HTN treatment-related hyperkalemia. Before these loci can be identified as clinically relevant, future validation studies of equal or greater size in comparison to our discovery effort are needed.

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

Low thyroid function is not associated with an accelerated deterioration in renal function. - Meuwese, Christiaan L; van Diepen, Merel; Cappola, Anne R; Sarnak, Mark J; Shlipak, Michael G; Bauer, Douglas C; Fried, Linda P; Iacoviello, Massimo; Vaes, Bert; Degryse, Jean; Khaw, Kay-Tee; Luben, Robert N; et al. (Nephrol Dial Transplant, 2018)
Background: Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups. Methods: Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models. Results: A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function. Conclusions: Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Metabolic Clusters and Outcomes in Older Adults: The Cardiovascular Health Study. - Mukamal, Kenneth J; Siscovick, David S; de Boer, Ian H; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Fitzpatrick, Annette L; Tracy, Russell P; Boyko, Edward J; Kahn, Steven E; Arnold, Alice M (J Am Geriatr Soc, 2018)
BACKGROUND/OBJECTIVES: Few studies have the requisite phenotypic information to define metabolic patterns that may inform our understanding of the pathophysiology and consequences of diabetes in older adults. We sought to characterize clusters of older adults on the basis of shared metabolic features. DESIGN: Population-based prospective cohort study. SETTING: Four U.S. Cardiovascular Health Study field centers. PARTICIPANTS: Individuals aged 65 and older taking no glucose-lowering agents (N = 2,231). MEASUREMENTS: K-means cluster analysis of 11 metabolic parameters (fasting and postload serum glucose and plasma insulin, fasting C-peptide, body mass index, C-reactive protein (CRP), estimated glomerular filtration rate (eGFR), albuminuria, carboxymethyl lysine (an advanced glycation end-product), procollagen III N-terminal propeptide (a fibrotic marker)) and their associations with incident cardiovascular disease, diabetes, disability, and mortality over 8 to 14.5 years of follow-up and with measures of subclinical cardiovascular disease. RESULTS: A 6-cluster solution provided robust differentiation into distinct, identifiable clusters. Cluster A (n = 739) had the lowest glucose and insulin and highest eGFR and the lowest rates of all outcomes. Cluster B (n = 419) had high glucose and insulin and intermediate rates of most outcomes. Cluster C (n = 118) had the highest insulin. Cluster D (n = 129) had the highest glucose with much lower insulin. Cluster E (n = 314) had the lowest eGFR and highest albuminuria. Cluster F (n = 512) had the highest CRP. Rates of CVD, mortality, and subclinical atherosclerosis were highest in clusters C, D, and E and were similar to rates in participants with treated diabetes. Incidence of disability was highest in Cluster C. CONCLUSION: Clustering according to metabolic parameters identifies distinct phenotypes that are strongly associated with clinical and functional outcomes, even at advanced age.
Keywords: Aged; Aged, 80 and over; Blood Glucose; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Incidence; Insulin; Longitudinal Studies; Male; Prospective Studies; Risk Factors; United States

Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen C; Cookson, William O C; Altmüller, Janine; Ang, Wei; Barr, R Graham; Beaty, Terri H; Becker, Allan B; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur Steina; et al. (Nat Genet, 2018)
We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23,948 asthma cases, 118,538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function. - Wyss, Annah B; Sofer, Tamar; Lee, Mi Kyeong; Terzikhan, Natalie; Nguyen, Jennifer N; Lahousse, Lies; Latourelle, Jeanne C; Smith, Albert Vernon; Bartz, Traci M; Feitosa, Mary F; Gao, Wei; Ahluwalia, Tarunveer S; et al. (Nat Commun, 2018)
Nearly 100 loci have been identified for pulmonary function, almost exclusively in studies of European ancestry populations. We extend previous research by meta-analyzing genome-wide association studies of 1000 Genomes imputed variants in relation to pulmonary function in a multiethnic population of 90,715 individuals of European (N = 60,552), African (N = 8429), Asian (N = 9959), and Hispanic/Latino (N = 11,775) ethnicities. We identify over 50 additional loci at genome-wide significance in ancestry-specific or multiethnic meta-analyses. Using recent fine-mapping methods incorporating functional annotation, gene expression, and differences in linkage disequilibrium between ethnicities, we further shed light on potential causal variants and genes at known and newly identified loci. Several of the novel genes encode proteins with predicted or established drug targets, including KCNK2 and CDK12. Our study highlights the utility of multiethnic and integrative genomics approaches to extend existing knowledge of the genetics of lung function and clinical relevance of implicated loci.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium. - Inker, Lesley A; Grams, Morgan E; Levey, Andrew S; Coresh, Josef; Cirillo, Massimo; Collins, John F; Gansevoort, Ron T; Gutierrez, Orlando M; Hamano, Takayuki; Heine, Gunnar H; Ishikawa, Shizukiyo; Jee, Sun Ha; et al. (Am J Kidney Dis, 2018)
RATIONALE & OBJECTIVE: Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework. STUDY DESIGN: Cross-sectional individual participant-level analyses in a global consortium. SETTING & STUDY POPULATIONS: 17 CKD and 38 general population and high-risk cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension. DATA EXTRACTION: Data were obtained and analyzed between July 2015 and January 2018. ANALYTICAL APPROACH: We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses. RESULTS: The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g). LIMITATIONS: Variations in study era, health care delivery system, typical diet, and laboratory assays. CONCLUSIONS: Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Targeted sequencing to identify novel genetic risk factors for deep vein thrombosis: a study of 734 genes. - de Haan, H G; van Hylckama Vlieg, A; Lotta, L A; Gorski, Marcin M; Bucciarelli, P; Martinelli, I; Baglin, T P; Peyvandi, F; Rosendaal, F R (J Thromb Haemost, 2018)
BACKGROUND: Although several genetic risk factors for deep vein thrombosis (DVT) are known, almost all related to hemostasis, a large genetic component remains unexplained. OBJECTIVES: We aimed to identify novel genetic determinants using targeted DNA sequencing. PATIENTS/METHODS: We included 899 DVT patients and 599 controls from three case-control studies (DVT-Milan, MEGA, and THE-VTE) for sequencing of the coding regions of 734 genes involved in hemostasis or related pathways. We performed single-variant association tests for common variants (minor allele frequency [MAF]≥1%) and gene-based tests for rare variants (MAF≤1%), accounting for multiple testing by the false discovery rate (FDR). RESULTS: Sixty-two out of 3,617 common variants were associated with DVT risk (FDR<0.10). Most of these mapped to F5, ABO, FGA-FGG, and CYP4V2-KLKB1-F11. Lead variant at F5 was rs6672595 (odds ratio [OR] 1.58, 95% confidence interval [CI] 1.29-1.92), in moderate linkage with known variant rs4524. Reciprocal conditional analyses suggested that intronic variation might drive this association. We also observed a secondary association at the F11 region: missense KLKB1 variant rs3733402 remained associated conditional on known variants rs2039614 and rs2289252 (OR 1.36, 95% CI 1.10-1.69). Two novel variant associations were observed, in CBS and MASP1, but these did not replicate in the meta-analysis data from the INVENT consortium. There was no support for a burden of rare variants contributing to DVT risk (FDR>0.2). CONCLUSIONS: We confirmed associations between DVT and common variants in F5, ABO, FGA-FGG, and CYP4V2-KLKB1-F11 and observed secondary signals in F5 and CYP4V2-KLKB1-F11 that warrant replication and fine-mapping in larger studies. This article is protected by copyright. All rights reserved.

Time-varying social support and time to death in the cardiovascular health study. - MacNeil-Vroomen, Janet; Schulz, Richard; Doyle, Margaret; Murphy, Terrence E; Ives, Diane G; Monin, Joan K (Health Psychol, 2018)
OBJECTIVES: There is a consensus that social connectedness is integral for a long, healthy life. However, studies of social support and survival have primarily relied on baseline social support measures, potentially missing the effects of fluctuations of perceived support over time. This is especially important for older adults who experience increased changes in disability. This study examined whether among older adults time-varying perceived social support was associated with time to death (main effect model of support) and whether time-varying disability was a modifier (stress-buffering model of support). Gender and marital status were also examined as modifiers. METHODS: Older adults in the Cardiovascular Health Study ( = 5,201) completed self- report measures of demographics and psychological health and clinical risk factors for mortality at baseline (1989-1990). Perceived social support and disability were measured from baseline through Wave 11 (1998-1999). Cox regression of time to death with time-varying covariates was performed. RESULTS: Time-varying as well as baseline-only perceived social support was associated with greater survival in the unadjusted models but not after adjustment. Gender, marital status, and time-varying disability were not significant modifiers. CONCLUSIONS: In contrast with the previously reported association between baseline individual differences in perceived social support and time to death, older adults' baseline-only and fluctuating perceptions of perceived support over time were not associated with time to death after adjustment for other clinical physical and psychological risk factors. Research is needed to identify other relationship factors that may be more informative as time-varying predictors of health and longevity in large longitudinal data sets. (PsycINFO Database Record

Trans-ethnic analysis of metabochip data identifies two new loci associated with BMI. - Gong, J; Nishimura, K K; Fernandez-Rhodes, L; Haessler, J; Bien, S; Graff, M; Lim, U; Lu, Y; Gross, M; Fornage, M; Yoneyama, S; Isasi, C R; et al. (Int J Obes (Lond), 2018)
OBJECTIVE: Body mass index (BMI) is commonly used to assess obesity, which is associated with numerous diseases and negative health outcomes. BMI has been shown to be a heritable, polygenic trait, with close to 100 loci previously identified and replicated in multiple populations. We aim to replicate known BMI loci and identify novel associations in a trans-ethnic study population. SUBJECTS: Using eligible participants from the Population Architecture using Genomics and Epidemiology consortium, we conducted a trans-ethnic meta-analysis of 102 514 African Americans, Hispanics, Asian/Native Hawaiian, Native Americans and European Americans. Participants were genotyped on over 200 000 SNPs on the Illumina Metabochip custom array, or imputed into the 1000 Genomes Project (Phase I). Linear regression of the natural log of BMI, adjusting for age, sex, study site (if applicable), and ancestry principal components, was conducted for each race/ethnicity within each study cohort. Race/ethnicity-specific, and combined meta-analyses used fixed-effects models. RESULTS: We replicated 15 of 21 BMI loci included on the Metabochip, and identified two novel BMI loci at 1q41 (rs2820436) and 2q31.1 (rs10930502) at the Metabochip-wide significance threshold (P<2.5 × 10). Bioinformatic functional investigation of SNPs at these loci suggests a possible impact on pathways that regulate metabolism and adipose tissue. CONCLUSION: Conducting studies in genetically diverse populations continues to be a valuable strategy for replicating known loci and uncovering novel BMI associations.

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2018)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.

Advanced glycation end product carboxymethyl-lysine and risk of incident peripheral artery disease in older adults: The Cardiovascular Health Study. - Garg, Parveen K; Biggs, Mary L; Barzilay, Joshua; Djoussé, Luc; Hirsch, Calvin; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Mukamal, Kenneth J (Diab Vasc Dis Res, 2019)
Carboxymethyl-lysine is an advanced glycation end product that is detectable in the serum. Higher carboxymethyl-lysine levels have been associated with increased risk of coronary heart disease, stroke and cardiovascular mortality. We determined whether high carboxymethyl-lysine levels are also associated with the risk of peripheral artery disease in Cardiovascular Health Study participants who were all aged 65 years and older at baseline. Multivariate Cox proportional hazards models were used to determine the association of baseline carboxymethyl-lysine levels with incident peripheral artery disease in 3267 individuals followed for a median length of 10.0 years. A total of 157 cases of incident peripheral artery disease occurred during follow-up. No significant relationship between carboxymethyl-lysine and risk of peripheral artery disease was found (hazard ratio per standard deviation increment = 1.03; 95% confidence interval = 0.87, 1.23).

APOL1 gene variants and kidney disease in whites: the cardiovascular health study. - Drury, Erika R; Friedman, David J; Pollak, Martin R; Ix, Joachim H; Kuller, Lewis H; Tracy, Russell P; Mukamal, Kenneth J (Nephrol Dial Transplant, 2019)

The Association of Aromatic Amino Acids with Incident Hip Fracture, aBMD, and Body Composition from the Cardiovascular Health Study. - Le, Brian; Bůzková, Petra; Robbins, John A; Fink, Howard A; Raiford, Mattie; Isales, Carlos M; Shikany, James M; Coughlin, Steven S; Carbone, Laura D (Calcif Tissue Int, 2019)
In 5187 persons from the Cardiovascular Health Study, there was no significant association of dietary intakes of aromatic amino acids (AAA) with areal BMD of the hip or body composition. However, those who had the lowest dietary intakes of AAA were at increased risk for incident hip fractures. Prior studies of the association of protein intake with osteoporosis are conflicting and have not directly examined the relationship of aromatic amino acids (AAA) with fractures, areal bone mineral density (aBMD), and body composition. We sought to determine the relationship of dietary intakes of AAA with osteoporosis parameters in elderly men and women. 5187 men and women aged ≥ 65 years from the Cardiovascular Health Study (CHS) with dietary intakes of AAA (tryptophan, phenylalanine, tyrosine) estimated by food frequency questionnaire (FFQ) were included. We examined the relationship between a one-time estimate of daily dietary AAA intake with risk of incident hip fractures over a median of 13.2 years of fracture follow-up. A subset (n = 1336) who had dual energy X-ray absorptiometry (DXA) performed were included in a cross-sectional analysis of the association of dietary AAA intake with aBMD of the total hip and measurements of body composition. In multivariable models adjusted for demographic and clinical variables, medication use, and diet, higher dietary AAA intake was not significantly associated with incident hip fractures. All hazard ratios (HR) were less than one (tryptophan, HR 0.14, 95% CI 0.01 to 1.89; phenylalanine, HR 0.60, 95% CI 0.23 to 1.55; tyrosine, HR 0.59, 95% CI 0.27 to 1.32), but confidence intervals were wide and included no difference. However, in post hoc analyses, the lowest quartile of intake for each AAA was associated with an increased risk for hip fracture compared to higher quartiles (p ≤ 0.047 for all). Dietary AAA intakes were not significantly associated with total hip aBMD or any measurements of body composition. Overall, there was no significant association of dietary AAA intake with hip fractures, aBMD of the hip, or body composition. However, there may be a subset of elderly individuals with low dietary intakes of AAA who are at increased for hip fractures.

{Association of dietary folate and vitamin B-12 intake with genome-wide DNA methylation in blood: a large-scale epigenome-wide association analysis in 5841 individuals - Mandaviya, P. R.; Joehanes, R.; Brody, J.; Castillo-Fernandez, J. E.; Dekkers, K. F.; Do, A. N.; Graff, M.; H?nninen, I. K.; Tanaka, T.; de Jonge, E. A. L.; Kiefte-de Jong, J. C.; Absher, D. M.; et al. (Am J Clin Nutr, 2019)
Folate and vitamin B-12 are essential micronutrients involved in the donation of methyl groups in cellular metabolism. However, associations between intake of these nutrients and genome-wide DNA methylation levels have not been studied comprehensively in humans.\ The aim of this study was to assess whether folate and/or vitamin B-12 intake are asssociated with genome-wide changes in DNA methylation in leukocytes.\ A large-scale epigenome-wide association study of folate and vitamin B-12 intake was performed on DNA from 5841 participants from 10 cohorts using Illumina 450k arrays. Folate and vitamin B-12 intakes were calculated from food-frequency questionnaires (FFQs). Continuous and categorical (low compared with high intake) linear regression mixed models were applied per cohort, controlling for confounders. A meta-analysis was performed to identify significant differentially methylated positions (DMPs) and regions (DMRs), and a pathway analysis was performed on the DMR annotated genes.\ The categorical model resulted in 6 DMPs, which are all negatively associated with folate intake, annotated to FAM64A, WRAP73, FRMD8, CUX1, and LCN8 genes, which have a role in cellular processes including centrosome localization, cell proliferation, and tumorigenesis. Regional analysis showed 74 folate-associated DMRs, of which 73 were negatively associated with folate intake. The most significant folate-associated DMR was a 400-base pair (bp) spanning region annotated to the LGALS3BP gene. In the categorical model, vitamin B-12 intake was associated with 29 DMRs annotated to 48 genes, of which the most significant was a 1100-bp spanning region annotated to the calcium-binding tyrosine phosphorylation-regulated gene (CABYR). Vitamin B-12 intake was not associated with DMPs.\ We identified novel epigenetic loci that are associated with folate and vitamin B-12 intake. Interestingly, we found a negative association between folate and DNA methylation. Replication of these methylation loci is necessary in future studies.

Association of Dietary Niacin Intake With Incident Hip Fracture, BMD, and Body Composition: The Cardiovascular Health Study. - Carbone, Laura D; Bůzková, Petra; Fink, Howard A; Raiford, Mattie; Le, Brian; Isales, Carlos M; Shikany, James M; Coughlin, Steven S; Robbins, John A (J Bone Miner Res, 2019)
Interest in niacin has increased in the setting of reports suggesting that niacin plays a role in diseases of aging. No study to date has examined the association of dietary niacin intake with multiple skeletal health parameters including bone mineral density (BMD), hip fractures, and body composition, and none have included both African American and white men and women. Participants included 5187 men and women ≥65 years from the Cardiovascular Health Study (CHS). Mean daily dietary niacin intake was 32.6 mg, with quartiles 1 through 4 defined as 3.6 to 21.8 mg/day, 21.9 to 30.2 mg/day, 30.3 to 40.9 mg/day, and 41.0 to 102.4 mg/day, respectively. Risk of incident hip fracture per 10 mg increment of daily dietary niacin intake was estimated using proportional hazards models. During a median follow-up of 13 years, 725 participants had an incident hip fracture. In models adjusted for demographic and clinical characteristics and diet, dietary niacin intake was significantly associated with an increased risk of hip fractures (hazard ratio [HR] 1.12; 95% CI, 1.01 to 1.24) with spline models suggesting a U-shaped association. In post hoc analyses, both the lowest (HR 1.31; 95% CI, 1.04 to 1.66) and highest (HR 1.53; 95% CI, 1.20 to 1.95) quartiles of niacin intake were associated with an increased risk of incident hip fracture versus quartiles 2 and 3. There was a trend for a significant inverse association of dietary niacin intake with hip BMD (p = 0.06), but no significant association with total body BMD or any body composition measures. In this cohort of elderly, community-dwelling African American and white men and women, both high and low dietary niacin intakes were associated with a significantly increased risk of subsequent hip fracture, suggesting a possible U-shaped association. By comparison, dietary niacin may have an inverse linear association with hip BMD. © 2018 American Society for Bone and Mineral Research.

Association of serum and urinary uromodulin and their correlates in older adults-The Cardiovascular Health Study. - Steubl, Dominik; Bůzková, Petra; Ix, Joachim H; Devarajan, Prasad; Bennett, Michael R; Chaves, Paolo H M; Shlipak, Michael G; Bansal, Nisha; Sarnak, Mark J; Garimella, Pranav S (Nephrology (Carlton), 2019)
Uromodulin is released into serum (sUMOD) and urine (uUMOD) exclusively by renal tubular cells. Both sUMOD and uUMOD are correlated with estimated glomerular filtration rate (eGFR), and associated with mortality and cardiovascular disease (CVD). However, no study to our knowledge has measured both sUMOD and uUMOD in the same population, thus the relationship of sUMOD with uUMOD with one another, and their respective correlates have not been evaluated simultaneously. We evaluated the correlations of sUMOD, uUMOD with eGFR in a random sub-cohort (n = 933) of the Cardiovascular Health Study and their associations with demographic and laboratory parameters and CVD risk factors using multi-variable linear regression analysis. The mean age of the cohort was 78 years, 40% were male and 15% were Black. The mean sUMOD level was 127 ng/mL, uUMOD was 30 500 ng/mL and eGFR was 63 mL/min/1.73 m . Correlation between sUMOD and uUMOD, adjusted for eGFR was moderate (r = 0.27 [95% confidence interval = 0.21-0.33]). The correlation of eGFR with sUMOD (r = 0.44 [0.39-0.49]) was stronger than with uUMOD (r = 0.21 [0.15-0.27]). In multi-variable analysis adjusting sUMOD for uUMOD and vice versa, sUMOD was independently associated with eGFR (β = 1.3 [1.1-1.6]), log2 C-reactive protein (β = -4.2 [-6.8 to -1.6]) and male sex (β = -13.6 [-22.7 to -4.5]). In contrast, male sex was associated with higher uUMOD (β = 3700 [400-7000]), while diabetes (β = -6400 [-10 600 to -2100]) and hypertension (-4300 [-7500 to -1100]) were associated with lower uUMOD levels. We conclude that sUMOD is more strongly associated with eGFR compared with uUMOD. Correlates of sUMOD and uUMOD differ substantially, suggesting that apical and basolateral secretion may be differentially regulated.

Association of serum uromodulin with mortality and cardiovascular disease in the elderly-the Cardiovascular Health Study. - Steubl, Dominik; Bůzková, Petra; Garimella, Pranav S; Ix, Joachim H; Devarajan, Prasad; Bennett, Michael R; Chaves, Paulo H M; Shlipak, Michael G; Bansal, Nisha; Sarnak, Mark J (Nephrol Dial Transplant, 2019)
BACKGROUND: Uromodulin (UMOD) is released by renal tubular cells into the serum (sUMOD) and urine. Lower urine UMOD has been linked to mortality and cardiovascular disease but much less is known about sUMOD. We evaluated the association of sUMOD with these outcomes in community-dwelling older adults. METHODS: We measured sUMOD in a random subcohort of 933 participants enrolled in the Cardiovascular Health Study. The associations of sUMOD with all-cause mortality, incident heart failure (HF) and incident cardiovascular disease (CVD; myocardial infarction, stroke and mortality due to coronary disease or stroke) were evaluated using multivariable Cox regression, adjusting for study participants' demographics, estimated glomerular filtration rate (eGFR), albuminuria and CVD risk factors. Generalized additive models with splines were used to address the functional form of sUMOD with outcomes. Due to nonlinear associations of sUMOD with all outcomes, 2.5% of the values on either end of the sUMOD distribution were excluded from the analyses, limiting the range of sUMOD to 34.3-267.1 ng/mL. RESULTS: The mean age was 78 ± 5 years, 40% were male, sUMOD level was 127 ± 64 ng/mL, eGFR was 63 mL/min/1.73 m2 and 42% had CKD defined as eGFR <60 mL/min/1.73 m2. Patients in the lower sUMOD quartiles had lower eGFR and higher albuminuria (P < 0.01, respectively). During a median follow-up of 9.9 years, 805 patients died, 283 developed HF and 274 developed CVD. In multivariable analysis, higher sUMOD was significantly associated with a lower hazard for mortality {hazard ratio [HR] 0.89 [95% confidence interval (CI) 0.80-0.99] per 1 standard deviation (SD) higher sUMOD}, CVD [HR 0.80 (95% CI 0.67-0.96)] and the composite endpoint [HR 0.88 (95% CI 0.78-0.99)]; the association with HF was not statistically significant [HR 0.84 (95% CI 0.70-1.01)]. CONCLUSION: Higher sUMOD is independently associated with a lower risk for mortality and CVD in older adults.

Association of variants in HTRA1 and NOTCH3 with MRI-defined extremes of cerebral small vessel disease in older subjects. - Mishra, Aniket; Chauhan, Ganesh; Violleau, Marie-Helene; Vojinovic, Dina; Jian, Xueqiu; Bis, Joshua C; Li, Shuo; Saba, Yasaman; Grenier-Boley, Benjamin; Yang, Qiong; Bartz, Traci M; Hofer, Edith; et al. (Brain, 2019)
We report a composite extreme phenotype design using distribution of white matter hyperintensities and brain infarcts in a population-based cohort of older persons for gene-mapping of cerebral small vessel disease. We demonstrate its application in the 3C-Dijon whole exome sequencing (WES) study (n = 1924, nWESextremes = 512), with both single variant and gene-based association tests. We used other population-based cohort studies participating in the CHARGE consortium for replication, using whole exome sequencing (nWES = 2,868, nWESextremes = 956) and genome-wide genotypes (nGW = 9924, nGWextremes = 3308). We restricted our study to candidate genes known to harbour mutations for Mendelian small vessel disease: NOTCH3, HTRA1, COL4A1, COL4A2 and TREX1. We identified significant associations of a common intronic variant in HTRA1, rs2293871 using single variant association testing (Pdiscovery = 8.21 × 10-5, Preplication = 5.25 × 10-3, Pcombined = 4.72 × 10-5) and of NOTCH3 using gene-based tests (Pdiscovery = 1.61 × 10-2, Preplication = 3.99 × 10-2, Pcombined = 5.31 × 10-3). Follow-up analysis identified significant association of rs2293871 with small vessel ischaemic stroke, and two blood expression quantitative trait loci of HTRA1 in linkage disequilibrium. Additionally, we identified two participants in the 3C-Dijon cohort (0.4%) carrying heterozygote genotypes at known pathogenic variants for familial small vessel disease within NOTCH3 and HTRA1. In conclusion, our proof-of-concept study provides strong evidence that using a novel composite MRI-derived phenotype for extremes of small vessel disease can facilitate the identification of genetic variants underlying small vessel disease, both common variants and those with rare and low frequency. The findings demonstrate shared mechanisms and a continuum between genes underlying Mendelian small vessel disease and those contributing to the common, multifactorial form of the disease.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

{Associations of circulating very-long-chain saturated fatty acids and incident type 2 diabetes: a pooled analysis of prospective cohort studies - Fretts, A. M.; Imamura, F.; Marklund, M.; Micha, R.; Wu, J. H. Y.; Murphy, R. A.; Chien, K. L.; McKnight, B.; Tintle, N.; Forouhi, N. G.; Qureshi, W. T.; Virtanen, J. K.; et al. (Am. J. Clin. Nutr., 2019)
Saturated fatty acids (SFAs) of different chain lengths have unique metabolic and biological effects, and a small number of recent studies suggest that higher circulating concentrations of the very-long-chain SFAs (VLSFAs) arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) are associated with a lower risk of diabetes. Confirmation of these findings in a large and diverse population is needed.\ We investigated the associations of circulating VLSFAs 20:0, 22:0, and 24:0 with incident type 2 diabetes in prospective studies.\ Twelve studies that are part of the Fatty Acids and Outcomes Research Consortium participated in the analysis. Using Cox or logistic regression within studies and an inverse-variance-weighted meta-analysis across studies, we examined the associations of VLSFAs 20:0, 22:0, and 24:0 with incident diabetes among 51,431 participants.\ There were 14,276 cases of incident diabetes across participating studies. Higher circulating concentrations of 20:0, 22:0, and 24:0 were each associated with a lower risk of incident diabetes. Pooling across cohorts, the RR (95% CI) for incident diabetes comparing the 90th percentile to the 10th percentile was 0.78 (0.70, 0.87) for 20:0, 0.84 (0.77, 0.91) for 22:0, and 0.75 (0.69, 0.83) for 24:0 after adjustment for demographic, lifestyle, adiposity, and other health factors. Results were fully attenuated in exploratory models that adjusted for circulating 16:0 and triglycerides.\ Results from this pooled analysis indicate that higher concentrations of circulating VLSFAs 20:0, 22:0, and 24:0 are each associated with a lower risk of diabetes.

Biochemical markers of bone turnover and risk of incident hip fracture in older women: the Cardiovascular Health Study. - Massera, D; Xu, S; Walker, M D; Valderrábano, R J; Mukamal, K J; Ix, J H; Siscovick, D S; Tracy, R P; Robbins, J A; Biggs, M L; Xue, X; Kizer, J R (Osteoporos Int, 2019)
The relationships of osteocalcin (OC) and C-telopeptide of type I collagen (CTX) with long-term incidence of hip fracture were examined in 1680 post-menopausal women from a population-based study. CTX, but not OC, levels were associated with incident hip fracture in these participants, a relationship characterized by an inverted U-shape. INTRODUCTION: We sought to investigate the relationships of OC, a marker of bone formation, and CTX, a marker of bone resorption, with long-term incidence of hip fracture in older women. METHODS: We included 1680 women from the population-based Cardiovascular Health Study (mean [SD] age 74.5 [5.0] years). The longitudinal association of both markers with incidence of hip fracture was examined using multivariable Cox models. RESULTS: During a median follow-up of 12.3 years, 288 incident hip fractures occurred. Linear spline analysis did not demonstrate an association between OC levels and incident hip fracture. By contrast, increasing levels of CTX up to the middle-upper range were associated with a significantly greater risk of hip fracture (HR = 1.52 per SD increment, 95% CI = 1.10-2.09), while further increases were associated with a marginally non-significant lower risk (HR = 0.80 per SD increment, 95% CI = 0.63-1.01), after full adjustment for potential confounders. In analyses of quartiles, CTX exhibited a similar inverted U-shaped relationship with incident fracture after adjustment, with a significant association observed only for the comparison of quartile 3 to quartile 1 (HR = 1.63, 95% CI = 1.10-2.43). In a subset with available measures, both OC and CTX were inversely associated with bone mineral density of the hip. CONCLUSION: CTX, but not OC, levels were associated with incident hip fracture in post-menopausal women, a relationship characterized by an inverted U-shape. These findings highlight the complex relationship of bone turnover markers with hip fracture risk.

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Common Genetic Variation in Relation to Brachial Vascular Dimensions and Flow-Mediated Vasodilation. - Dörr, Marcus; Hamburg, Naomi M; Müller, Christian; Smith, Nicholas L; Gustafsson, Stefan; Lehtimäki, Terho; Teumer, Alexander; Zeller, Tanja; Li, Xiaohui; Lind, Lars; Raitakari, Olli T; Völker, Uwe; et al. (Circ Genom Precis Med, 2019)

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

{Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies - Pennells, L.; Kaptoge, S.; Wood, A.; Sweeting, M.; Zhao, X.; White, I.; Burgess, S.; Willeit, P.; Bolton, T.; Moons, K. G. M.; van der Schouw, Y. T.; Selmer, R.; et al. (Eur Heart J, 2019)
There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied.\ Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged â‰¥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms.\ Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)
) with at least one obesity or lipid trait. Candidate genes include PRKAR2A, PTH1R, and HDAC9, which have been suggested to play roles in adipocyte differentiation or bone marrow adipose tissue. Taken together, these findings provide further insights into the processes that influence circulating adiponectin levels.

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

{A genome-wide association study identifies genetic loci associated with specific lobar brain volumes - van der Lee, S. J.; Knol, M. J.; Chauhan, G.; Satizabal, C. L.; Smith, A. V.; Hofer, E.; Bis, J. C.; Hibar, D. P.; Hilal, S.; van den Akker, E. B.; Arfanakis, K.; Bernard, M.; et al. (Commun Biol, 2019)
Brain lobar volumes are heritable but genetic studies are limited. We performed genome-wide association studies of frontal, occipital, parietal and temporal lobe volumes in 16,016 individuals, and replicated our findings in 8,789 individuals. We identified six genetic loci associated with specific lobar volumes independent of intracranial volume. Two loci, associated with occipital (6q22.32) and temporal lobe volume (12q14.3), were previously reported to associate with intracranial and hippocampal volume, respectively. We identified four loci previously unknown to affect brain volumes: 3q24 for parietal lobe volume, and 1q22, 4p16.3 and 14q23.1 for occipital lobe volume. The associated variants were located in regions enriched for histone modifications (DAAM1 and THBS3), or close to genes causing Mendelian brain-related diseases (ZIC4 and FGFRL1). No genetic overlap between lobar volumes and neurological or psychiatric diseases was observed. Our findings reveal part of the complex genetics underlying brain development and suggest a role for regulatory regions in determining brain volumes.

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

Genome-wide meta-analysis of SNP and antihypertensive medication interactions on left ventricular traits in African Americans. - Do, Anh N; Zhao, Wei; Baldridge, Abigail S; Raffield, Laura M; Wiggins, Kerri L; Shah, Sanjiv J; Aslibekyan, Stella; Tiwari, Hemant K; Limdi, Nita; Zhi, Degui; Sitlani, Colleen M; Taylor, Kent D; et al. (Mol Genet Genomic Med, 2019)
BACKGROUND: Left ventricular (LV) hypertrophy affects up to 43% of African Americans (AAs). Antihypertensive treatment reduces LV mass (LVM). However, interindividual variation in LV traits in response to antihypertensive treatments exists. We hypothesized that genetic variants may modify the association of antihypertensive treatment class with LV traits measured by echocardiography. METHODS: We evaluated the main effects of the three most common antihypertensive treatments for AAs as well as the single nucleotide polymorphism (SNP)-by-drug interaction on LVM and relative wall thickness (RWT) in 2,068 participants across five community-based cohorts. Treatments included thiazide diuretics (TDs), angiotensin converting enzyme inhibitors (ACE-Is), and dihydropyridine calcium channel blockers (dCCBs) and were compared in a pairwise manner. We performed fixed effects inverse variance weighted meta-analyses of main effects of drugs and 2.5 million SNP-by-drug interaction estimates. RESULTS: We observed that dCCBs versus TDs were associated with higher LVM after adjusting for covariates (p = 0.001). We report three SNPs at a single locus on chromosome 20 that modified the association between RWT and treatment when comparing dCCBs to ACE-Is with consistent effects across cohorts (smallest p = 4.7 × 10 , minor allele frequency range 0.09-0.12). This locus has been linked to LV hypertrophy in a previous study. A marginally significant locus in BICD1 (rs326641) was validated in an external population. CONCLUSIONS: Our study identified one locus having genome-wide significant SNP-by-drug interaction effect on RWT among dCCB users in comparison to ACE-I users. Upon additional validation in future studies, our findings can enhance the precision of medical approaches in hypertension treatment.
Keywords: African Americans; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Humans; Observational Studies as Topic; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors; Ventricular Dysfunction, Left

Genome-wide meta-analysis of variant-by-diuretic interactions as modulators of lipid traits in persons of European and African ancestry. - de Las Fuentes, L; Sung, Y J; Sitlani, C M; Avery, C L; Bartz, T M; Keyser, C de; Evans, D S; Li, X; Musani, S K; Ruiter, R; Smith, A V; Sun, F; et al. (Pharmacogenomics J, 2019)
Hypertension (HTN) is a significant risk factor for cardiovascular morbidity and mortality. Metabolic abnormalities, including adverse cholesterol and triglycerides (TG) profiles, are frequent comorbid findings with HTN and contribute to cardiovascular disease. Diuretics, which are used to treat HTN and heart failure, have been associated with worsening of fasting lipid concentrations. Genome-wide meta-analyses with 39,710 European-ancestry (EA) individuals and 9925 African-ancestry (AA) individuals were performed to identify genetic variants that modify the effect of loop or thiazide diuretic use on blood lipid concentrations. Both longitudinal and cross sectional data were used to compute cohort-specific interaction results, which were then combined through meta-analysis in each ancestry. These ancestry-specific results were further combined through trans-ancestry meta-analysis. Analysis of EA data identified two genome-wide significant (p < 5 × 10) loci with single nucleotide variant (SNV)-loop diuretic interaction on TG concentrations (including COL11A1). Analysis of AA data identified one genome-wide significant locus adjacent to BMP2 with SNV-loop diuretic interaction on TG concentrations. Trans-ancestry analysis strengthened evidence of association for SNV-loop diuretic interaction at two loci (KIAA1217 and BAALC). There were few significant SNV-thiazide diuretic interaction associations on TG concentrations and for either diuretic on cholesterol concentrations. Several promising loci were identified that may implicate biologic pathways that contribute to adverse metabolic side effects from diuretic therapy.

Genomic and transcriptomic association studies identify 16 novel susceptibility loci for venous thromboembolism. - Lindström, Sara; Wang, Lu; Smith, Erin N; Gordon, William; van Hylckama Vlieg, Astrid; de Andrade, Mariza; Brody, Jennifer A; Pattee, Jack W; Haessler, Jeffrey; Brumpton, Ben M; Chasman, Daniel I; Suchon, Pierre; et al. (Blood, 2019)
Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality. To advance our understanding of the biology contributing to VTE, we conducted a genome-wide association study (GWAS) of VTE and a transcriptome-wide association study (TWAS) based on imputed gene expression from whole blood and liver. We meta-analyzed GWAS data from 18 studies for 30 234 VTE cases and 172 122 controls and assessed the association between 12 923 718 genetic variants and VTE. We generated variant prediction scores of gene expression from whole blood and liver tissue and assessed them for association with VTE. Mendelian randomization analyses were conducted for traits genetically associated with novel VTE loci. We identified 34 independent genetic signals for VTE risk from GWAS meta-analysis, of which 14 are newly reported associations. This included 11 newly associated genetic loci (C1orf198, PLEK, OSMR-AS1, NUGGC/SCARA5, GRK5, MPHOSPH9, ARID4A, PLCG2, SMG6, EIF5A, and STX10) of which 6 replicated, and 3 new independent signals in 3 known genes. Further, TWAS identified 5 additional genetic loci with imputed gene expression levels differing between cases and controls in whole blood (SH2B3, SPSB1, RP11-747H7.3, RP4-737E23.2) and in liver (ERAP1). At some GWAS loci, we found suggestive evidence that the VTE association signal for novel and previously known regions colocalized with expression quantitative trait locus signals. Mendelian randomization analyses suggested that blood traits may contribute to the underlying risk of VTE. To conclude, we identified 16 novel susceptibility loci for VTE; for some loci, the association signals are likely mediated through gene expression of nearby genes.

Higher albumin:creatinine ratio and lower estimated glomerular filtration rate are potential risk factors for decline of physical performance in the elderly: the Cardiovascular Health Study. - Bůzková, Petra; Barzilay, Joshua I; Fink, Howard A; Robbins, John A; Cauley, Jane A; Ix, Joachim H; Mukamal, Kenneth J (Clin Kidney J, 2019)
Introduction: Mildly reduced renal function and elevated urine protein levels are each prospectively associated with hip fracture risk in older adults. Here we determine whether these markers are associated with reduced appendicular muscle performance. Methods: We prospectively examined the associations of urine albumin:creatinine ratio (ACR) and reduced estimated glomerular filtration rate (eGFR) with longitudinal changes in grip strength and gait speed >2 years in 2317 older community-dwelling men and women (median age 77 years). The median ACR was 9.8 [interquartile range (IQR) 5.40-21.50] mg/g creatinine and the median eGFR was 71.6 (IQR 59.1-83.56) mL/min/1.73 m. Models were adjusted for demographic factors, clinical history and biochemical measures in four candidate pathways: diabetes, oxidative stress, inflammation and fibrosis. Results: In demographic- and covariate-adjusted models, a 2-fold higher baseline urine ACR was associated with longitudinal changes of -0.17 kg [95% confidence interval (CI) -0.29 to -0.06) in grip strength and -1.10 cm/s (95% CI -1.67 to -0.53) gait speed per year. Corresponding estimates for a 10 mL/min/1.73 m lower baseline eGFR were -0.13 kg (95% CI -0.23 to -0.04) and -0.89 cm/s (95% CI -1.37 to -0.40), respectively. The associations of a 2-fold higher baseline ACR and a 10 mL/min/1.73 m lower baseline eGFR using cystatin C with grip strength and gait speed were equivalent to ∼1.2-1.9 additional years of age. Adjustment for covariates in candidate pathways did not attenuate these estimates. Conclusions: In older adults, higher ACR and lower eGFR are potential risk factors for a decline of physical performance >2 years.

{The impact of APOE genotype on survival: Results of 38,537 participants from six population-based cohorts (E2-CHARGE) - Wolters, F. J.; Yang, Q.; Biggs, M. L.; Jakobsdottir, J.; Li, S.; Evans, D. S.; Bis, J. C.; Harris, T. B.; Vasan, R. S.; Zilhao, N. R.; Ghanbari, M.; Ikram, M. A.; et al. (PLoS One, 2019)
Apolipoprotein E is a glycoprotein best known as a mediator and regulator of lipid transport and uptake. The APOE-Îµ4 allele has long been associated with increased risks of Alzheimer's disease and mortality, but the effect of the less prevalent APOE-Îµ2 allele on diseases in the elderly and survival remains elusive.\ We aggregated data of 38,537 individuals of European ancestry (mean age 65.5 years; 55.6% women) from six population-based cohort studies (Rotterdam Study, AGES-Reykjavik Study, Cardiovascular Health Study, Health-ABC Study, and the family-based Framingham Heart Study and Long Life Family Study) to determine the association of APOE, and in particular APOE-Îµ2, with survival in the population.\ During a mean follow-up of 11.7 years, 17,021 individuals died. Compared with homozygous APOE-Îµ3 carriers, APOE-Îµ2 carriers were at lower risk of death (hazard ratio,95% confidence interval: 0.94,0.90-0.99; P = 1.1*10-2), whereas APOE-Îµ4 carriers were at increased risk of death (HR 1.17,1.12-1.21; P = 2.8*10-16). APOE was associated with mortality risk in a dose-dependent manner, with risk estimates lowest for homozygous APOE-Îµ2 (HR 0.89,0.74-1.08), and highest for homozygous APOE-Îµ4 (HR 1.52,1.37-1.70). After censoring for dementia, effect estimates remained similar for APOE-Îµ2 (HR 0.95,0.90-1.01), but attenuated for APOE-Îµ4 (HR 1.07,1.01-1.12). Results were broadly similar across cohorts, and did not differ by age or sex. APOE genotype was associated with baseline lipid fractions (e.g. mean difference(95%CI) in LDL(mg/dL) for Îµ2 versus Îµ33: -17.1(-18.1-16.0), and Îµ4 versus Îµ33: +5.7(4.8;6.5)), but the association between APOE and mortality was unaltered after adjustment for baseline LDL or cardiovascular disease. Given the European ancestry of the study population, results may not apply to other ethnicities.\ Compared with APOE-Îµ3, APOE-Îµ2 is associated with prolonged survival, whereas mortality risk is increased for APOE-Îµ4 carriers. Further collaborative efforts are needed to unravel the role of APOE and in particular APOE-Îµ2 in health and disease.

A large-scale exome array analysis of venous thromboembolism. - Lindström, Sara; Brody, Jennifer A; Turman, Constance; Germain, Marine; Bartz, Traci M; Smith, Erin N; Chen, Ming-Huei; Puurunen, Marja; Chasman, Daniel; Hassler, Jeffrey; Pankratz, Nathan; Basu, Saonli; et al. (Genet Epidemiol, 2019)
Although recent Genome-Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome-wide search for low-frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta-analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and gene-based rare variant tests. In the single variant analysis, we limited our analysis to the 64,794 variants with at least 40 minor alleles across studies (minor allele frequency [MAF] ~0.08%). We confirmed associations with previously identified VTE loci, including ABO, F5, F11, and FGA. After adjusting for multiple testing, we observed no novel significant findings in single variant or gene-based analysis. Given our sample size, we had greater than 80% power to detect minimum odds ratios greater than 1.5 and 1.8 for a single variant with MAF of 0.01 and 0.005, respectively. Larger studies and sequence data may be needed to identify novel low-frequency and rare variants associated with VTE risk.

{Low thyroid function is not associated with an accelerated deterioration in renal function - Meuwese, C. L.; van Diepen, M.; Cappola, A. R.; Sarnak, M. J.; Shlipak, M. G.; Bauer, D. C.; Fried, L. P.; Iacoviello, M.; Vaes, B.; Degryse, J.; Khaw, K. T.; Luben, R. N.; et al. (Nephrol Dial Transplant, 2019)
Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups.\ Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models.\ A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function.\ Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Multiethnic Genome-Wide Association Study of Diabetic Retinopathy Using Liability Threshold Modeling of Duration of Diabetes and Glycemic Control. - Pollack, Samuela; Igo, Robert P; Jensen, Richard A; Christiansen, Mark; Li, Xiaohui; Cheng, Ching-Yu; Ng, Maggie C Y; Smith, Albert V; Rossin, Elizabeth J; Segrè, Ayellet V; Davoudi, Samaneh; Tan, Gavin S; et al. (Diabetes, 2019)
To identify genetic variants associated with diabetic retinopathy (DR), we performed a large multiethnic genome-wide association study. Discovery included eight European cohorts ( = 3,246) and seven African American cohorts ( = 2,611). We meta-analyzed across cohorts using inverse-variance weighting, with and without liability threshold modeling of glycemic control and duration of diabetes. Variants with a value <1 × 10 were investigated in replication cohorts that included 18,545 European, 16,453 Asian, and 2,710 Hispanic subjects. After correction for multiple testing, the C allele of rs142293996 in an intron of nuclear VCP-like () was associated with DR in European discovery cohorts ( = 2.1 × 10), but did not reach genome-wide significance after meta-analysis with replication cohorts. We applied the Disease Association Protein-Protein Link Evaluator (DAPPLE) to our discovery results to test for evidence of risk being spread across underlying molecular pathways. One protein-protein interaction network built from genes in regions associated with proliferative DR was found to have significant connectivity ( = 0.0009) and corroborated with gene set enrichment analyses. These findings suggest that genetic variation in as well as variation within a protein-protein interaction network that includes genes implicated in inflammation, may influence risk for DR.

{Omega-3 Fatty Acids and Genome-Wide Interaction Analyses Reveal DPP10-Pulmonary Function Association - Xu, J.; Gaddis, N. C.; Bartz, T. M.; Hou, R.; Manichaikul, A. W.; Pankratz, N.; Smith, A. V.; Sun, F.; Terzikhan, N.; Markunas, C. A.; Patchen, B. K.; Schu, M.; et al. (Am J Respir Crit Care Med, 2019)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health.\ To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility.\ Associations of n-3 PUFA biomarkers (α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (FEV1, FVC, and FEV1/FVC) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N = 16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N = 11,962) and replicated in one cohort (N = 1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of SNP associations and their interactions with n-3 PUFAs.\ DPA and DHA were positively associated with FEV1 and FVC (P < 0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P2df = 9.4 × 10-9 across discovery and replication cohorts). The rs11693320-A allele (frequency, ∼80%) was associated with lower FVC (PSNP = 2.1 × 10-9; βSNP = -161.0 ml), and the association was attenuated by higher DHA levels (PSNP×DHA interaction = 2.1 × 10-7; βSNP×DHA interaction = 36.2 ml).\ We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

{Quality of dietary fat and genetic risk of type 2 diabetes: individual participant data meta-analysis - Merino, J.; Guasch-Ferr?, M.; Ellervik, C.; Dashti, H. S.; Sharp, S. J.; Wu, P.; Overvad, K.; Sarnowski, C.; Kuokkanen, M.; Lemaitre, R. N.; Justice, A. E.; Ericson, U.; et al. (BMJ, 2019)
{To investigate whether the genetic burden of type 2 diabetes modifies the association between the quality of dietary fat and the incidence of type 2 diabetes.\ Individual participant data meta-analysis.\ Eligible prospective cohort studies were systematically sourced from studies published between January 1970 and February 2017 through electronic searches in major medical databases (Medline, Embase, and Scopus) and discussion with investigators.\ Data from cohort studies or multicohort consortia with available genome-wide genetic data and information about the quality of dietary fat and the incidence of type 2 diabetes in participants of European descent was sought. Prospective cohorts that had accrued five or more years of follow-up were included. The type 2 diabetes genetic risk profile was characterized by a 68-variant polygenic risk score weighted by published effect sizes. Diet was recorded by using validated cohort-specific dietary assessment tools. Outcome measures were summary adjusted hazard ratios of incident type 2 diabetes for polygenic risk score, isocaloric replacement of carbohydrate (refined starch and sugars) with types of fat, and the interaction of types of fat with polygenic risk score.\ Of 102 305 participants from 15 prospective cohort studies, 20 015 type 2 diabetes cases were documented after a median follow-up of 12 years (interquartile range 9.4-14.2). The hazard ratio of type 2 diabetes per increment of 10 risk alleles in the polygenic risk score was 1.64 (95% confidence interval 1.54 to 1.75

{Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium - Inker, L. A.; Grams, M. E.; Levey, A. S.; Coresh, J.; Cirillo, M.; Collins, J. F.; Gansevoort, R. T.; Gutierrez, O. M.; Hamano, T.; Heine, G. H.; Ishikawa, S.; Jee, S. H.; et al. (Am J Kidney Dis, 2019)
Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework.\ Cross-sectional individual participant-level analyses in a global consortium.\ 17 CKD and 38 general population and high-risk cohorts.\ Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension.\ Data were obtained and analyzed between July 2015 and January 2018.\ We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses.\ The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m2), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g).\ Variations in study era, health care delivery system, typical diet, and laboratory assays.\ Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

{Soluble CD14 and CD14 Variants, Other Inflammatory Markers, and Glucose Dysregulation in Older Adults: The Cardiovascular Health Study - Shitole, S. G.; Biggs, M. L.; Reiner, A. P.; Mukamal, K. J.; Djouss?, L.; Ix, J. H.; Barzilay, J. I.; Tracy, R. P.; Siscovick, D.; Kizer, J. R. (Diabetes Care, 2019)
Experimental studies have implicated soluble (s)CD14, an effector of lipopolysaccharide-induced inflammation, in insulin resistance, but its role in human metabolic endotoxemia has not been studied. We evaluated sCD14 in relation to dysglycemia in older adults and how this compares to other markers of inflammation.\ We investigated associations of sCD14, interleukin-6 (IL-6), CRP, and white blood cell (WBC) count with insulin resistance (quantitative insulin-sensitivity check index and HOMA 2 of insulin resistance) and incident type 2 diabetes in a population-based cohort of older adults. We also assessed the causal role of sCD14 in insulin resistance using an instrumental variable approach by Mendelian randomization.\ After adjustment for conventional risk factors, each of the four biomarkers showed positive cross-sectional associations with both insulin resistance measures. These associations persisted after mutual adjustment for all markers except sCD14. Over a median follow-up of 11.6 years, 466 cases of diabetes occurred. All biomarkers except sCD14 were positively associated with diabetes, although only WBC count remained associated (hazard ratio 1.43 per doubling [95% CI 1.07, 1.90]) after mutual adjustment. Instrumental variable analysis did not support a causal role for sCD14 in insulin resistance.\ Among older adults, sCD14 was associated with insulin resistance, but this disappeared after adjustment for other biomarkers, showed no evidence of a causal basis, and was not accompanied by a similar association with diabetes. IL-6, CRP, and WBC count were each associated with insulin resistance and diabetes, WBC count most robustly. These findings do not support a central role for sCD14, but they highlight the preeminence of WBC count as an inflammatory measure of diabetes risk in this population.

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

{Cerebral small vessel disease genomics and its implications across the lifespan - Sargurupremraj, M.; Suzuki, H.; Jian, X.; Sarnowski, C.; Evans, T. E.; Bis, J. C.; Eiriksdottir, G.; Sakaue, S.; Terzikhan, N.; Habes, M.; Zhao, W.; Armstrong, N. J.; et al. (Nat Commun, 2020)
White matter hyperintensities (WMH) are the most common brain-imaging feature of cerebral small vessel disease (SVD), hypertension being the main known risk factor. Here, we identify 27 genome-wide loci for WMH-volume in a cohort of 50,970 older individuals, accounting for modification/confounding by hypertension. Aggregated WMH risk variants were associated with altered white matter integrity (p = 2.5Ã—10-7) in brain images from 1,738 young healthy adults, providing insight into the lifetime impact of SVD genetic risk. Mendelian randomization suggested causal association of increasing WMH-volume with stroke, Alzheimer-type dementia, and of increasing blood pressure (BP) with larger WMH-volume, notably also in persons without clinical hypertension. Transcriptome-wide colocalization analyses showed association of WMH-volume with expression of 39 genes, of which four encode known drug targets. Finally, we provide insight into BP-independent biological pathways underlying SVD and suggest potential for genetic stratification of high-risk individuals and for genetically-informed prioritization of drug targets for prevention trials.

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

The Difference Between Cystatin C and Creatinine-Based Estimated GFR and Incident Frailty: An Analysis of the Cardiovascular Health Study (CHS). - Potok, O Alison; Phil, Ronit Katz D; Bansal, Nisha; Siscovick, David S; Odden, Michelle; Ix, Joachim H; Shlipak, Michael G; Rifkin, Dena E (Am J Kidney Dis, 2020)

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

{Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale - Li, X.; Li, Z.; Zhou, H.; Gaynor, S. M.; Liu, Y.; Chen, H.; Sun, R.; Dey, R.; Arnett, D. K.; Aslibekyan, S.; Ballantyne, C. M.; Bielak, L. F.; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.

Fatty Acid Binding Protein-4 and Risk of Cardiovascular Disease: The Cardiovascular Health Study. - Egbuche, Obiora; Biggs, Mary L; Ix, Joachim H; Kizer, Jorge R; Lyles, Mary F; Siscovick, David S; Djoussé, Luc; Mukamal, Kenneth J (J Am Heart Assoc, 2020)
Background FABP-4 (fatty acid binding protein-4) is a lipid chaperone in adipocytes and has been associated with prognosis in selected clinical populations. We investigated the associations between circulating FABP-4, risk of incident cardiovascular disease (CVD), and risk of CVD mortality among older adults with and without established CVD. Methods and Results In the Cardiovascular Health Study, we measured FABP4 levels in stored specimens from the 1992-993 visit and followed participants for incident CVD if they were free of prevalent CVD at baseline and for CVD mortality through June 2015. We used Cox regression to estimate hazard ratios for incident CVD and CVD mortality per doubling in serum FABP-4 adjusted for age, sex, race, field center, waist circumference, blood pressure, lipids, fasting glucose, and C-reactive protein. Among 4026 participants free of CVD and 681 with prevalent CVD, we documented 1878 cases of incident CVD and 331 CVD deaths, respectively. In adjusted analyses, FABP-4 was modestly associated with risk of incident CVD (mean, 34.24; SD, 18.90; HR, 1.10 per doubling in FABP-4, 95% CI, 1.00-1.21). In contrast, FABP-4 was more clearly associated with risk of CVD mortality among participants without (HR hazard ratio 1.24, 95% CI, 1.10-1.40) or with prevalent CVD (HR hazard ratio 1.57, 95% CI, 1.24-1.98). These associations were not significantly modified by sex, age, and waist circumference. Conclusions Serum FABP-4 is modestly associated with risk of incident CVD even after adjustment for standard risk factors, but more strongly associated with CVD mortality among older adults with and without established CVD.

{Fatty acids in the de novo lipogenesis pathway and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies - Imamura, F.; Fretts, A. M.; Marklund, M.; Ardisson Korat, A. V.; Yang, W. S.; Lankinen, M.; Qureshi, W.; Helmer, C.; Chen, T. A.; Virtanen, J. K.; Wong, K.; Bassett, J. K.; et al. (PLoS Med, 2020)
De novo lipogenesis (DNL) is the primary metabolic pathway synthesizing fatty acids from carbohydrates, protein, or alcohol. Our aim was to examine associations of in vivo levels of selected fatty acids (16:0, 16:1n7, 18:0, 18:1n9) in DNL with incidence of type 2 diabetes (T2D).\ Seventeen cohorts from 12 countries (7 from Europe, 7 from the United States, 1 from Australia, 1 from Taiwan; baseline years = 1970-1973 to 2006-2010) conducted harmonized individual-level analyses of associations of DNL-related fatty acids with incident T2D. In total, we evaluated 65,225 participants (mean ages = 52.3-75.5 years; % women = 20.4%-62.3% in 12 cohorts recruiting both sexes) and 15,383 incident cases of T2D over the 9-year follow-up on average. Cohort-specific association of each of 16:0, 16:1n7, 18:0, and 18:1n9 with incident T2D was estimated, adjusted for demographic factors, socioeconomic characteristics, alcohol, smoking, physical activity, dyslipidemia, hypertension, menopausal status, and adiposity. Cohort-specific associations were meta-analyzed with an inverse-variance-weighted approach. Each of the 4 fatty acids positively related to incident T2D. Relative risks (RRs) per cohort-specific range between midpoints of the top and bottom quintiles of fatty acid concentrations were 1.53 (1.41-1.66; p < 0.001) for 16:0, 1.40 (1.33-1.48; p < 0.001) for 16:1n-7, 1.14 (1.05-1.22; p = 0.001) for 18:0, and 1.16 (1.07-1.25; p < 0.001) for 18:1n9. Heterogeneity was seen across cohorts (I2 = 51.1%-73.1% for each fatty acid) but not explained by lipid fractions and global geographical regions. Further adjusted for triglycerides (and 16:0 when appropriate) to evaluate associations independent of overall DNL, the associations remained significant for 16:0, 16:1n7, and 18:0 but were attenuated for 18:1n9 (RR = 1.03, 95% confidence interval (CI) = 0.94-1.13). These findings had limitations in potential reverse causation and residual confounding by imprecisely measured or unmeasured factors.\ Concentrations of fatty acids in the DNL were positively associated with T2D incidence. Our findings support further work to investigate a possible role of DNL and individual fatty acids in the development of T2D.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

The genetic architecture of the human cerebral cortex - Grasby, Katrina L.; Jahanshad, Neda; Painter, Jodie N.; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P.; Lind, Penelope A.; Pizzagalli, Fabrizio; Ching, Christopher R. K.; McMahon, Mary Agnes B.; Shatokhina, Natalia; Zsembik, Leo C. P.; et al. (Science, 2020)

{Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E.; Roshchupkin, G. V.; Adams, H. H. H.; Knol, M. J.; Lin, H.; Li, S.; Zare, H.; Ahmad, S.; Armstrong, N. J.; Satizabal, C. L.; Bernard, M.; Bis, J. C.; et al. (Nat Commun, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/Î²-catenin, TGF-Î² and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.

{Genetic Determinants of Electrocardiographic P-wave Duration and Relation to Atrial Fibrillation - Weng, L. C.; Hall, A. W.; Choi, S. H.; Jurgens, S. J.; Haessler, J.; Bihlmeyer, N. A.; Grarup, N.; Lin, H.; Teumer, A.; Li-Gao, R.; Yao, J.; Guo, X.; et al. (Circ Genom Precis Med, 2020)
Background - The P-wave duration (PWD) is an electrocardiographic (ECG) measurement that represents cardiac conduction in the atria. Shortened or prolonged PWD is associated with atrial fibrillation (AF). We used exome chip data to examine the associations between common and rare variants with PWD. Methods - Fifteen studies comprising 64,440 individuals (56,943 European, 5,681 African, 1,186 Hispanic, 630 Asian), and 230,000 variants were used to examine associations with maximum PWD across the 12-lead ECG. Meta-analyses summarized association results for common variants; gene-based burden and SKAT tests examined low-frequency variant-PWD associations. Additionally, we examined the associations between PWD loci and AF using previous AF GWAS. Results - We identified 21 common and low-frequency genetic loci (14 novel) associated with maximum PWD, including several AF loci (TTN, CAND2, SCN10A, PITX2, CAV1, SYNPO2L, SOX5, TBX5, MYH6, RPL3L). The top variants at known sarcomere genes (TTN, MYH6) were associated with longer PWD and increased AF risk. However, top variants at other loci (e.g., PITX2 and SCN10A) were associated with longer PWD but lower AF risk. Conclusions - Our results highlight multiple novel genetic loci associated with PWD, and underscore the shared mechanisms of atrial conduction and AF. Prolonged PWD may be an endophenotype for several different genetic mechanisms of AF.

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity. - Yaghootkar, Hanieh; Zhang, Yiying; Spracklen, Cassandra N; Karaderi, Tugce; Huang, Lam Opal; Bradfield, Jonathan; Schurmann, Claudia; Fine, Rebecca S; Preuss, Michael H; Kutalik, Zoltán; Wittemans, Laura Bl; Lu, Yingchang; et al. (Diabetes, 2020)
Leptin influences food intake by informing the brain about the status of body fat stores. Rare mutations associated with congenital leptin deficiency cause severe early-onset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify five novel variants, including four missense variants, in , and , and one intergenic variant near The missense variant Val94Met (rs17151919) in was common in individuals of African ancestry only and its association with lower leptin concentrations was specific to this ancestry (P=2x10, n=3,901). Using analyses, we show that the Met94 allele decreases leptin secretion. We also show that the Met94 allele is associated with higher BMI in young African-ancestry children but not in adults, suggesting leptin regulates early adiposity.

{Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Shah, S.; Henry, A.; Roselli, C.; Lin, H.; Sveinbj?rnsson, G.; Fatemifar, G.; Hedman, ?. K.; Wilk, J. B.; Morley, M. P.; Chaffin, M. D.; Helgadottir, A.; Verweij, N.; et al. (Nat Commun, 2020)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained. We report results from a GWAS meta-analysis of HF comprising 47,309 cases and 930,014 controls. Twelve independent variants at 11 genomic loci are associated with HF, all of which demonstrate one or more associations with coronary artery disease (CAD), atrial fibrillation, or reduced left ventricular function, suggesting shared genetic aetiology. Functional analysis of non-CAD-associated loci implicate genes involved in cardiac development (MYOZ1, SYNPO2L), protein homoeostasis (BAG3), and cellular senescence (CDKN1A). Mendelian randomisation analysis supports causal roles for several HF risk factors, and demonstrates CAD-independent effects for atrial fibrillation, body mass index, and hypertension. These findings extend our knowledge of the pathways underlying HF and may inform new therapeutic strategies.

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Intact and C-Terminal FGF23 Assays-Do Kidney Function, Inflammation, and Low Iron Influence Relationships With Outcomes? - Sharma, Shilpa; Katz, Ronit; Bullen, Alexander L; Chaves, Paulo H M; de Leeuw, Peter W; Kroon, Abraham A; Houben, Alfons J H M; Shlipak, Michael G; Ix, Joachim H (J Clin Endocrinol Metab, 2020)
CONTEXT: Higher fibroblast growth factor-23 (FGF23) concentrations are associated with heart failure and mortality in diverse populations, but the strengths of associations differ markedly depending up on which assay is used. OBJECTIVE: We sought to evaluate whether iron deficiency, inflammation, or kidney function account for differences in the strengths of associations between these 2 FGF23 assays with clinical outcomes. DESIGN: Case cohort study from the Cardiovascular Health Study. SETTING: A total of 844 community-dwelling individuals aged 65 years or older with and without chronic kidney disease were followed for 10 years. OUTCOMES: Outcomes included death, incident heart failure (HF), and incident myocardial infarction (MI). Exposure was baseline intact and C-terminal FGF23. Using modified Cox models, adjusting sequentially we tested whether observed associations of each assay with outcomes were attenuated by iron status, inflammation, kidney function, or their combinations. RESULTS: FGF23 measured by either assay was associated with mortality in unadjusted analysis (intact FGF23 hazard ratio [HR] per 2-fold higher 1.45; 95% CI, 1.25-1.68; C-terminal FGF23 HR 1.38; 95% CI, 1.26-1.50). Adjustment for kidney function completely attenuated associations of intact FGF23 with mortality (HR 1.00; 95% CI, 0.85-1.17), but had much less influence on the association of C-terminal FGF23, for which results remained significant after adjustment (HR 1.15; 95% CI, 1.04-1.28). Attenuation was much less with adjustment for iron status or inflammation. Results were similar for the HF end point. Neither C-terminal or intact FGF23 was associated with MI risk. CONCLUSIONS: The relationship of FGF23 with clinical end points is markedly different depending on the type of FGF23 assay used. The associations of biologically active FGF23 with clinical end points may be confounded by kidney disease, and thus much weaker than previously thought.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

Non-Esterified Fatty Acids and Hospitalizations among Older Adults: The Cardiovascular Health Study. - Ahiawodzi, Peter D; Bůzková, Petra; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Mukamal, Kenneth J (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: We sought to determine associations between total serum concentrations of non-esterified fatty acids (NEFAs) and incident total and cause-specific hospitalizations in a community-living cohort of elders. METHODS: We included 4715 participants in the Cardiovascular Health Study who had fasting total serum NEFA measured at the 1992/93 clinic visit and were followed for a median of 12 years. We identified all inpatient admissions requiring at least an overnight hospitalization and used primary diagnostic codes to categorize cause-specific hospitalizations. We used Cox proportional hazards regression models to determine associations with time-to-first hospitalization and Poisson regression for the rate ratios (RR) of hospitalizations and days hospitalized. RESULTS: We identified 21339 hospitalizations during follow-up. In fully adjusted models, higher total NEFAs were significantly associated with higher risk of incident hospitalization (Hazard Ratio (HR) per SD [0.2 mEq/L]=1.07, 95%CI=1.03-1.10, P&0.001), number of hospitalizations (RR per SD=1.04, 95%CI=1.01-1.07, P=0.01), and total number of days hospitalized (RR per SD=1.06, 95%CI=1.01-1.10, P=0.01). Among hospitalization subtypes, higher NEFA was associated with higher likelihood of mental, neurologic, respiratory, and musculoskeletal causes of hospitalization. Among specific causes of hospitalization, higher NEFA was associated with diabetes, pneumonia, and gastrointestinal hemorrhage. CONCLUSIONS: Higher fasting total serum NEFAs are associated with a broad array of causes of hospitalization among older adults. While some of these were expected, our results illustrate a possible utility of NEFAs as biomarkers for risk of hospitalization, and total days hospitalized, in older adults. Further research is needed to determine whether interventions based on NEFAs might be feasible.

Non-Esterified Fatty Acids and Risks of Frailty, Disability, and Mobility Limitation in Older Adults: The Cardiovascular Health Study. - Ahiawodzi, Peter; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Arnold, Alice; Newman, Anne; Mukamal, Kenneth J (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: Non-esterified fatty acids (NEFAs) play central roles in the relationship between adiposity and glucose metabolism, and they have been implicated in the pathogenesis of cardiovascular disease, but few studies have assessed their effects on complex geriatric syndromes like frailty that cross multiple organ systems. We sought to determine the relationships between NEFAs and incident frailty, disability, and mobility limitation in a population-based cohort of older persons. METHODS: We analyzed 4,710 Cardiovascular Health Study (CHS) participants who underwent measurement of circulating total fasting NEFAs in 1992-1993 and were assessed for frailty in 1996-1997 and for disability and mobility limitation annually. We used ordinal logistic regression to model incident frailty, linear regression to model components of frailty, and Cox regression to model disability and mobility limitation in relation to baseline NEFAs. To ensure proportional hazards, we truncated follow-up at 9 years for disability and 6.5 years for mobility limitation. RESULTS: A total of 42 participants became frail and 510 became pre-frail over a 4-year period, and we documented 1,720 cases of disability and 1,225 cases of mobility limitation during follow-up. NEFAs were positively associated in a dose-dependent manner with higher risks of incident frailty, disability, and mobility limitation. The adjusted odds ratios for frailty were 1.37 (95% confidence interval [CI] = 1.01-1.86; P = .04) across extreme tertiles and 1.17 (95% CI = 1.03-1.33; P = .01) per standard deviation increment. The corresponding hazard ratios for incident disability were 1.14 (95% CI = 1.01-1.30; P = .04) and 1.11 (95% CI = 1.06-1.17; P < .0001); those for incident mobility limitation were 1.23 (95% CI = 1.06-1.43; P = .006) and 1.15 (95% CI = 1.08-1.22; P < .0001). Results were largely consistent among both men and women. Among individual components of frailty, NEFAs were significantly associated with self-reported exhaustion (β = .07; standard error = .03; P = .02). CONCLUSION: Circulating NEFAs are significantly associated with frailty, disability, and mobility limitation among older adults. These results highlight the broad spectrum of adverse health issues associated with NEFA in older adults.

Non-esterified fatty acids and telomere length in older adults: The Cardiovascular Health Study. - Ahiawodzi, Peter; Fitzpatrick, Annette L; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Mukamal, Kenneth J (Metabol Open, 2020)
Background: Telomeres shorten as organisms age, placing limits on cell proliferation and serving as a marker of biological aging. Non-esterified fatty acids (NEFAs) are a key mediator of age-related metabolic abnormalities. We aimed to determine if NEFAs are associated with telomere length in community-living older adults. Material and methods: We cross-sectionally studied 1648 participants of the Cardiovascular Health Study (CHS) who underwent concomitant telomere length measurement from a sample of 4715 participants who underwent measurement of circulating total fasting NEFAs in stored specimens from their 1992-3 clinic visit. We used linear regression and inverse probability weighting to model telomere length as a function of NEFAs with adjustment for age, gender, race, clinic, BMI, marital status, smoking status, alcohol intake, diabetes status, years of education, hypertension status, prevalent cardiovascular disease, C-reactive protein, total adiponectin, albumin, fetuin-A, fasting insulin, eGFR, total cholesterol, HDL-cholesterol, triglycerides, and general health status. Results: Higher NEFAs were significantly associated with shorter telomere length, after adjusting for age, gender, race, and clinic site (β = -0.034; SE = 0.015;  = 0.02). Estimates remained similar in fully adjusted models where each SD of NEFA increment was associated with 0.042 kilobase (kb) pairs shorter telomere length (standard error = 0.016;  = 0.007); for comparison the coefficient for a single year of age in the same model was -0.017. These results were similar in strata of sex, and waist circumference although they tended to be strongest among participants in the youngest tertile of age (β = -0.079; SE = 0.029; P = 0.01). Conclusions: In this population-based cohort of community-living elders, we observed a significant inverse association between NEFAs and telomere length. If confirmed, NEFAs may represent a promising target for interventions to slow biological aging.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

A systematic review and participant-level meta-analysis found little association of retinal microvascular caliber and reduced kidney function. - Lye, Weng Kit; Paterson, Euan; Patterson, Christopher C; Maxwell, Alexander P; Binte Mohammed Abdul, Riswana Banu; Tai, E Shyong; Cheng, Ching Yu; Kayama, Takamasa; Yamashita, Hidetoshi; Sarnak, Mark; Shlipak, Michael; Matsushita, Kunihiro; et al. (Kidney Int, 2020)
Previously, variation in retinal vascular caliber has been reported in association with chronic kidney disease (CKD) but findings remain inconsistent. To help clarify this we conducted individual participant data meta-analysis and aggregate data meta-analysis on summary estimates to evaluate cross-sectional associations between retinal vascular caliber and CKD. A systematic review was performed using Medline and EMBASE for articles published until October 2018. The aggregate analysis used a two-stage approach combining summary estimates from eleven studies (44,803 patients) while the individual participant analysis used a one-stage approach combining raw data from nine studies (33,222 patients). CKD stages 3-5 was defined as an estimated glomerular filtration rate under 60 mL/min/1.73m. Retinal arteriolar and venular caliber (central retinal arteriolar and venular equivalent) were assessed from retinal photographs using computer-assisted methods. Logistic regression estimated relative risk of CKD stages 3-5 associated with a 20 μm decrease (approximately one standard deviation) in central retinal arteriolar and venular equivalent. Prevalence of CKD stages 3-5 was 11.2 % of 33,222 and 11.3 % of 44,803 patients in the individual participant and aggregate data analysis, respectively. No significant associations were detected in adjusted analyses between central retinal arteriolar and venular equivalent and CKD stages 3-5 in the aggregate analysis for central retinal arteriolar relative risk (0.98, 95% confidence interval 0.94-1.03); venular equivalent (0.99, 0.95- 1.04) or individual participant central retinal arteriolar (0.99, 0.95-1.04) or venular equivalent (1.01, 0.97-1.05). Thus, meta-analysis provided little evidence to suggest that cross sectional direct measurements of retinal vascular caliber was associated with CKD stages 3-5 in the general population. Hence, meta-analyses of longitudinal studies evaluating the association between retinal parameters and CKD stages 3-5 may be warranted.

{Association between ABO haplotypes and the risk of venous thrombosis: impact on disease risk estimation - Goumidi, L.; Thibord, F.; Wiggins, K. L.; Li-Gao, R.; Brown, M. R.; van Hylckama Vlieg, A.; Souto, J. C.; Soria, J. M.; Ibrahim-Kosta, M.; Saut, N.; Daian, D.; Olaso, R.; et al. (Blood, 2021)
10.1182/blood.2020008997Genetic risk score (GRS) analysis is a popular approach to derive individual risk prediction models for complex diseases. In venous thrombosis (VT), such type of analysis shall integrate information at the ABO blood group locus, which is one of the major susceptibility loci. However, there is no consensus about which single nucleotide polymorphisms (SNPs) must be investigated when properly assessing association between ABO locus and VT risk. Using comprehensive haplotype analyses of ABO blood group tagging SNPs in 5425 cases and 8445 controls from 6 studies, we demonstrate that using only rs8176719 (tagging O1) to correctly assess the impact of ABO locus on VT risk is suboptimal, because 5% of rs8176719-delG carriers do not have an increased risk of developing VT. Instead, we recommend the use of 4 SNPs, rs2519093 (tagging A1), rs1053878 (A2), rs8176743 (B), and rs41302905 (O2), when assessing the impact of ABO locus on VT risk to avoid any risk misestimation. Compared with the O1 haplotype, the A2 haplotype is associated with a modest increase in VT risk (odds ratio, ∼1.2), the A1 and B haplotypes are associated with an ∼1.8-fold increased risk, whereas the O2 haplotype tends to be slightly protective (odds ratio, ∼0.80). In addition, although the A1 and B blood groups are associated with increased von Willebrand factor and factor VIII plasma levels, only the A1 blood group is associated with ICAM levels, but in an opposite direction, leaving additional avenues to be explored to fully understand the spectrum of biological effects mediated by ABO locus on cardiovascular traits.

Association Between Intracerebral Hemorrhage and Subsequent Arterial Ischemic Events in Participants From 4 Population-Based Cohort Studies. - Murthy, Santosh B; Zhang, Cenai; Diaz, Ivan; Levitan, Emily B; Koton, Silvia; Bartz, Traci M; DeRosa, Janet T; Strobino, Kevin; Colantonio, Lisandro D; Iadecola, Costantino; Safford, Monika M; Howard, Virginia J; et al. (JAMA Neurol, 2021)
Importance: Intracerebral hemorrhage and arterial ischemic disease share risk factors, to our knowledge, but the association between the 2 conditions remains unknown. Objective: To evaluate whether intracerebral hemorrhage was associated with an increased risk of incident ischemic stroke and myocardial infarction. Design, Setting, and Participants: An analysis was conducted of pooled longitudinal participant-level data from 4 population-based cohort studies in the United States: the Atherosclerosis Risk in Communities (ARIC) study, the Cardiovascular Health Study (CHS), the Northern Manhattan Study (NOMAS), and the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study. Patients were enrolled from 1987 to 2007, and the last available follow-up was December 31, 2018. Data were analyzed from September 1, 2019, to March 31, 2020. Exposure: Intracerebral hemorrhage, as assessed by an adjudication committee based on predefined clinical and radiologic criteria. Main Outcomes and Measures: The primary outcome was an arterial ischemic event, defined as a composite of ischemic stroke or myocardial infarction, centrally adjudicated within each study. Secondary outcomes were ischemic stroke and myocardial infarction. Participants with prevalent intracerebral hemorrhage, ischemic stroke, or myocardial infarction at their baseline study visit were excluded. Cox proportional hazards regression was used to examine the association between intracerebral hemorrhage and subsequent arterial ischemic events after adjustment for baseline age, sex, race/ethnicity, vascular comorbidities, and antithrombotic medications. Results: Of 55 131 participants, 47 866 (27 639 women [57.7%]; mean [SD] age, 62.2 [10.2] years) were eligible for analysis. During a median follow-up of 12.7 years (interquartile range, 7.7-19.5 years), there were 318 intracerebral hemorrhages and 7648 arterial ischemic events. The incidence of an arterial ischemic event was 3.6 events per 100 person-years (95% CI, 2.7-5.0 events per 100 person-years) after intracerebral hemorrhage vs 1.1 events per 100 person-years (95% CI, 1.1-1.2 events per 100 person-years) among those without intracerebral hemorrhage. In adjusted models, intracerebral hemorrhage was associated with arterial ischemic events (hazard ratio [HR], 2.3; 95% CI, 1.7-3.1), ischemic stroke (HR, 3.1; 95% CI, 2.1-4.5), and myocardial infarction (HR, 1.9; 95% CI, 1.2-2.9). In sensitivity analyses, intracerebral hemorrhage was associated with arterial ischemic events when updating covariates in a time-varying manner (HR, 2.2; 95% CI, 1.6-3.0); when using incidence density matching (odds ratio, 2.3; 95% CI, 1.3-4.2); when including participants with prevalent intracerebral hemorrhage, ischemic stroke, or myocardial infarction (HR, 2.2; 95% CI, 1.6-2.9); and when using death as a competing risk (subdistribution HR, 1.6; 95% CI, 1.1-2.1). Conclusions and Relevance: This study found that intracerebral hemorrhage was associated with an increased risk of ischemic stroke and myocardial infarction. These findings suggest that intracerebral hemorrhage may be a novel risk marker for arterial ischemic events.

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of Midlife Cardiovascular Risk Factors With the Risk of Heart Failure Subtypes Later in Life. - Cohen, Laura P; Vittinghoff, Eric; Pletcher, Mark J; Allen, Norrina B; Shah, Sanjiv J; Wilkins, John T; Chang, Patricia P; Ndumele, Chiadi E; Newman, Anne B; Ives, Diane; Maurer, Mathew S; Oelsner, Elizabeth C; et al. (J Card Fail, 2021)
BACKGROUND: Independent associations between cardiovascular risk factor exposures during midlife and later life development of heart failure (HF) with preserved ejection fraction (HFpEF) versus reduced EF (HFrEF) have not been previously studied. METHODS: We pooled data from 4 US cohort studies (Atherosclerosis Risk in Communities, Cardiovascular Health, Health , Aging and Body Composition, and Multi-Ethnic Study of Atherosclerosis) and imputed annual risk factor trajectories for body mass index, systolic and diastolic blood pressure, low-density lipoprotein and high-density lipoprotein cholesterol, and glucose starting from age 40 years. Time-weighted average exposures to each risk factor during midlife and later life were calculated and analyzed for associations with the development of HFpEF or HFrEF. RESULTS: A total of 23,861 participants were included (mean age at first in-person visit, 61.8 ±1 0.2 years; 56.6% female). During a median follow-up of 12 years, there were 3666 incident HF events, of which 51% had EF measured, including 934 with HFpEF and 739 with HFrEF. A high midlife systolic blood pressure and low midlife high-density lipoprotein cholesterol were associated with HFrEF, and a high midlife body mass index, systolic blood pressure, pulse pressure, and glucose were associated with HFpEF. After adjusting for later life exposures, only midlife pulse pressure remained independently associated with HFpEF. CONCLUSIONS: Midlife exposure to cardiovascular risk factors are differentially associated with HFrEF and HFpEF later in life. Having a higher pulse pressure during midlife is associated with a greater risk for HFpEF but not HFrEF, independent of later life exposures.

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

{Epigenome-wide association meta-analysis of DNA methylation with coffee and tea consumption - Karabegović, I.; Portilla-Fernandez, E.; Li, Y.; Ma, J.; Maas, S. C. E.; Sun, D.; Hu, E. A.; Kühnel, B.; Zhang, Y.; Ambatipudi, S.; Fiorito, G.; Huang, J.; et al. (Nat Commun, 2021)
10.1038/s41467-021-22752-6Coffee and tea are extensively consumed beverages worldwide which have received considerable attention regarding health. Intake of these beverages is consistently linked to, among others, reduced risk of diabetes and liver diseases; however, the mechanisms of action remain elusive. Epigenetics is suggested as a mechanism mediating the effects of dietary and lifestyle factors on disease onset. Here we report the results from epigenome-wide association studies (EWAS) on coffee and tea consumption in 15,789 participants of European and African-American ancestries from 15 cohorts. EWAS meta-analysis of coffee consumption reveals 11 CpGs surpassing the epigenome-wide significance threshold (P-value <1.1×10-7), which annotated to the AHRR, F2RL3, FLJ43663, HDAC4, GFI1 and PHGDH genes. Among them, cg14476101 is significantly associated with expression of the PHGDH and risk of fatty liver disease. Knockdown of PHGDH expression in liver cells shows a correlation with expression levels of genes associated with circulating lipids, suggesting a role of PHGDH in hepatic-lipid metabolism. EWAS meta-analysis on tea consumption reveals no significant association, only two CpGs annotated to CACNA1A and PRDM16 genes show suggestive association (P-value <5.0×10-6). These findings indicate that coffee-associated changes in DNA methylation levels may explain the mechanism of action of coffee consumption in conferring risk of diseases.

Estimating Systolic Blood Pressure Intervention Trial Participant Posttrial Survival Using Pooled Epidemiologic Cohort Data. - Bellows, Brandon K; Zhang, Yiyi; Zhang, Zugui; Lloyd-Jones, Donald M; Bress, Adam P; King, Jordan B; Kolm, Paul; Cushman, William C; Johnson, Karen C; Tamariz, Leonardo; Oelsner, Elizabeth C; Shea, Steven; et al. (J Am Heart Assoc, 2021)
Background Intensive systolic blood pressure treatment (<120 mm Hg) in SPRINT (Systolic Blood Pressure Intervention Trial) improved survival compared with standard treatment (<140 mm Hg) over a median follow-up of 3.3 years. We projected life expectancy after observed follow-up in SPRINT using SPRINT-eligible participants in the NHLBI-PCS (National Heart, Lung, and Blood Institute Pooled Cohorts Study). Methods and Results We used propensity scores to weight SPRINT-eligible NHLBI-PCS participants to resemble SPRINT participants. In SPRINT participants, we estimated in-trial survival (<4 years) using a time-based flexible parametric survival model. In SPRINT-eligible NHLBI-PCS participants, we estimated posttrial survival (≥4 years) using an age-based flexible parametric survival model and applied the formula to SPRINT participants to predict posttrial survival. We projected overall life expectancy for each SPRINT participant and compared it to parametric regression (eg, Gompertz) projections based on SPRINT data alone. We included 8584 SPRINT and 10 593 SPRINT-eligible NHLBI-PCS participants. After propensity weighting, mean (SD) age was 67.9 (9.4) and 68.2 (8.8) years, and 35.5% and 37.6% were women in SPRINT and NHLBI-PCS, respectively. Using the NHLBI-PCS-based method, projected mean life expectancy from randomization was 21.0 (7.4) years with intensive and 19.1 (7.2) years with standard treatment. Using the Gompertz regression, life expectancy was 11.2 (2.3) years with intensive and 10.5 (2.2) years with standard treatment. Conclusions Combining SPRINT and NHLBI-PCS observed data likely offers a more realistic estimate of life expectancy than parametrically extrapolating SPRINT data alone. These results offer insight into the potential long-term effectiveness of intensive SBP goals.

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

Identification of novel and rare variants associated with handgrip strength using whole genome sequence data from the NHLBI Trans-Omics in Precision Medicine (TOPMed) Program. - Sarnowski, Chloe; Chen, Han; Biggs, Mary L; Wassertheil-Smoller, Sylvia; Bressler, Jan; Irvin, Marguerite R; Ryan, Kathleen A; Karasik, David; Arnett, Donna K; Cupples, L Adrienne; Fardo, David W; Gogarten, Stephanie M; et al. (PLoS One, 2021)
Handgrip strength is a widely used measure of muscle strength and a predictor of a range of morbidities including cardiovascular diseases and all-cause mortality. Previous genome-wide association studies of handgrip strength have focused on common variants primarily in persons of European descent. We aimed to identify rare and ancestry-specific genetic variants associated with handgrip strength by conducting whole-genome sequence association analyses using 13,552 participants from six studies representing diverse population groups from the Trans-Omics in Precision Medicine (TOPMed) Program. By leveraging multiple handgrip strength measures performed in study participants over time, we increased our effective sample size by 7-12%. Single-variant analyses identified ten handgrip strength loci among African-Americans: four rare variants, five low-frequency variants, and one common variant. One significant and four suggestive genes were identified associated with handgrip strength when aggregating rare and functional variants; all associations were ancestry-specific. We additionally leveraged the different ancestries available in the UK Biobank to further explore the ancestry-specific association signals from the single-variant association analyses. In conclusion, our study identified 11 new loci associated with handgrip strength with rare and/or ancestry-specific genetic variations, highlighting the added value of whole-genome sequencing in diverse samples. Several of the associations identified using single-variant or aggregate analyses lie in genes with a function relevant to the brain or muscle or were reported to be associated with muscle or age-related traits. Further studies in samples with sequence data and diverse ancestries are needed to confirm these findings.

Identification of putative causal loci in whole-genome sequencing data via knockoff statistics. - He, Zihuai; Liu, Linxi; Wang, Chen; Le Guen, Yann; Lee, Justin; Gogarten, Stephanie; Lu, Fred; Montgomery, Stephen; Tang, Hua; Silverman, Edwin K; Cho, Michael H; Greicius, Michael; et al. (Nat Commun, 2021)
The analysis of whole-genome sequencing studies is challenging due to the large number of rare variants in noncoding regions and the lack of natural units for testing. We propose a statistical method to detect and localize rare and common risk variants in whole-genome sequencing studies based on a recently developed knockoff framework. It can (1) prioritize causal variants over associations due to linkage disequilibrium thereby improving interpretability; (2) help distinguish the signal due to rare variants from shadow effects of significant common variants nearby; (3) integrate multiple knockoffs for improved power, stability, and reproducibility; and (4) flexibly incorporate state-of-the-art and future association tests to achieve the benefits proposed here. In applications to whole-genome sequencing data from the Alzheimer's Disease Sequencing Project (ADSP) and COPDGene samples from NHLBI Trans-Omics for Precision Medicine (TOPMed) Program we show that our method compared with conventional association tests can lead to substantially more discoveries.
Keywords: Algorithms; Causality; Computer Simulation; Data Interpretation, Statistical; Datasets as Topic; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Markov Chains; Models, Genetic; Polymorphism, Single Nucleotide; Reproducibility of Results; Whole Genome Sequencing

Individual non-esterified fatty acids and incident atrial fibrillation late in life. - Pellegrini, Cara N; Bůzková, Petra; Lichtenstein, Alice H; Matthan, Nirupa R; Ix, Joachim H; Siscovick, David S; Heckbert, Susan R; Tracy, Russell P; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R (Heart, 2021)
OBJECTIVE: Obesity and dysmetabolism are major risk factors for atrial fibrillation (AF). Expansion of fat depots is associated with increased circulating total non-esterified fatty acids (NEFAs), elevated levels of which are associated with incident AF. We undertook comprehensive serum measurement of individual NEFA to identify specific associations with new-onset AF late in life. METHODS: The present study focused on participants with available serum and free of AF selected from the Cardiovascular Health Study, a community-based longitudinal investigation of older US adults. Thirty-five individual NEFAs were measured by gas chromatography. Cox regression was used to evaluate the association of individual NEFAs with incident AF. RESULTS: The study sample included 1872 participants (age 77.7±4.4). During median follow-up of 11.3 years, 715 cases of incident AF occurred. After concurrent adjustment of all NEFAs and full adjustment for potential confounders, higher serum concentration of nervonic acid (24:1 n-9), a long-chain monounsaturated fatty acid, was associated with higher risk of AF (HR per SD: 1.18, 95% CI 1.08 to 1.29; p<0.001). Conversely, higher serum concentration of gamma-linolenic acid (GLA) (18:3 n-6), a polyunsaturated n-6 fatty acid, was associated with lower risk of AF (HR per SD: 0.81, 95% CI 0.71 to 0.94; p=0.004). None of the remaining NEFAs was significantly associated with AF. CONCLUSIONS: Among older adults, serum levels of non-esterified nervonic acid were positively associated, while serum levels of non-esterified GLA were inversely associated, with incident AF. If confirmed, these results could offer new strategies for AF prevention and early intervention in this segment of the population at highest risk.

Meta-analysis of epigenome-wide association studies of carotid intima-media thickness. - Portilla-Fernández, Eliana; Hwang, Shih-Jen; Wilson, Rory; Maddock, Jane; Hill, W David; Teumer, Alexander; Mishra, Pashupati P; Brody, Jennifer A; Joehanes, Roby; Ligthart, Symen; Ghanbari, Mohsen; Kavousi, Maryam; et al. (Eur J Epidemiol, 2021)
Common carotid intima-media thickness (cIMT) is an index of subclinical atherosclerosis that is associated with ischemic stroke and coronary artery disease (CAD). We undertook a cross-sectional epigenome-wide association study (EWAS) of measures of cIMT in 6400 individuals. Mendelian randomization analysis was applied to investigate the potential causal role of DNA methylation in the link between atherosclerotic cardiovascular risk factors and cIMT or clinical cardiovascular disease. The CpG site cg05575921 was associated with cIMT (beta = -0.0264, p value = 3.5 × 10) in the discovery panel and was replicated in replication panel (beta = -0.07, p value = 0.005). This CpG is located at chr5:81649347 in the intron 3 of the aryl hydrocarbon receptor repressor gene (AHRR). Our results indicate that DNA methylation at cg05575921 might be in the pathway between smoking, cIMT and stroke. Moreover, in a region-based analysis, 34 differentially methylated regions (DMRs) were identified of which a DMR upstream of ALOX12 showed the strongest association with cIMT (p value = 1.4 × 10). In conclusion, our study suggests that DNA methylation may play a role in the link between cardiovascular risk factors, cIMT and clinical cardiovascular disease.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.

{A multi-ethnic epigenome-wide association study of leukocyte DNA methylation and blood lipids - Jhun, M. A.; Mendelson, M.; Wilson, R.; Gondalia, R.; Joehanes, R.; Salfati, E.; Zhao, X.; Braun, K. V. E.; Do, A. N.; Hedman, Å. K.; Zhang, T.; Carnero-Montoro, E.; et al. (Nat Commun, 2021)
10.1038/s41467-021-23899-yHere we examine the association between DNA methylation in circulating leukocytes and blood lipids in a multi-ethnic sample of 16,265 subjects. We identify 148, 35, and 4 novel associations among Europeans, African Americans, and Hispanics, respectively, and an additional 186 novel associations through a trans-ethnic meta-analysis. We observe a high concordance in the direction of effects across racial/ethnic groups, a high correlation of effect sizes between high-density lipoprotein and triglycerides, a modest overlap of associations with epigenome-wide association studies of other cardio-metabolic traits, and a largely non-overlap with lipid loci identified to date through genome-wide association studies. Thirty CpGs reached significance in at least 2 racial/ethnic groups including 7 that showed association with the expression of an annotated gene. CpGs annotated to CPT1A showed evidence of being influenced by triglycerides levels. DNA methylation levels of circulating leukocytes show robust and consistent association with blood lipid levels across multiple racial/ethnic groups.

Multiethnic Genome-Wide Association Study of Subclinical Atherosclerosis in Individuals With Type 2 Diabetes. - Lu, Yingchang; Dimitrov, Latchezar; Chen, Shyh-Huei; Bielak, Lawrence F; Bis, Joshua C; Feitosa, Mary F; Lu, Lingyi; Kavousi, Maryam; Raffield, Laura M; Smith, Albert V; Wang, Lihua; Weiss, Stefan; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Coronary artery calcification (CAC) and carotid artery intima-media thickness (cIMT) are measures of subclinical atherosclerosis in asymptomatic individuals and strong risk factors for cardiovascular disease. Type 2 diabetes (T2D) is an independent cardiovascular disease risk factor that accelerates atherosclerosis. METHODS: We performed meta-analyses of genome-wide association studies in up to 2500 T2D individuals of European ancestry (EA) and 1590 T2D individuals of African ancestry with or without exclusion of prevalent cardiovascular disease, for CAC measured by cardiac computed tomography, and 3608 individuals of EA and 838 individuals of African ancestry with T2D for cIMT measured by ultrasonography within the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium. RESULTS: We replicated 2 loci (rs9369640 and rs9349379 near and rs10757278 near ) for CAC and one locus for cIMT (rs7412 and rs445925 near ) that were previously reported in the general EA populations. We identified one novel CAC locus (rs8000449 near at 13q13.3) at =2.0×10 in EA. No additional loci were identified with the meta-analyses of EA and African ancestry. The expression quantitative trait loci analysis with nearby expressed genes derived from arterial wall and metabolic tissues from the Genotype-Tissue Expression project pinpoints , encoding a matricellular protein involved in bone formation and bone matrix organization, as the potential candidate gene at this locus. In addition, we found significant associations (<3.1×10) for 3 previously reported coronary artery disease loci for these subclinical atherosclerotic phenotypes (rs2891168 near and rs11170820 near for CAC, and rs7412 near for cIMT). CONCLUSIONS: Our results provide potential biological mechanisms that could link CAC and cIMT to increased cardiovascular disease risk in individuals with T2D.

n-3 Fatty Acid Biomarkers and Incident Type 2 Diabetes: An Individual Participant-Level Pooling Project of 20 Prospective Cohort Studies - Qian, F.; Ardisson Korat, A. V.; Imamura, F.; Marklund, M.; Tintle, N.; Virtanen, J. K.; Zhou, X.; Bassett, J. K.; Lai, H.; Hirakawa, Y.; Chien, K. L.; Wood, A. C.; et al. (Diabetes Care, 2021)
-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with T2D risk through an individual participant-level pooled analysis.\ For our analysis we incorporated data from a global consortium of 20 prospective studies from 14 countries. We included 65,147 participants who had blood measurements of ALA, EPA, DPA, or DHA and were free of diabetes at baseline. De novo harmonized analyses were performed in each cohort following a prespecified protocol, and cohort-specific associations were pooled using inverse variance-weighted meta-analysis.\ 0.001). ALA was not associated with T2D (HR 0.97 [95% CI 0.92, 1.02]) per interquintile range. Associations were robust across prespecified subgroups as well as in sensitivity analyses.\ Higher circulating biomarkers of seafood-derived n-3 fatty acids, including EPA, DPA, DHA, and their sum, were associated with lower risk of T2D in a global consortium of prospective studies. The biomarker of plant-derived ALA was not significantly associated with T2D risk.

Nonesterified Fatty Acids and Kidney Function Decline in Older Adults: Findings From the Cardiovascular Health Study. - Walther, Carl P; Ix, Joachim H; Biggs, Mary L; Kizer, Jorge R; Navaneethan, Sankar D; Djoussé, Luc; Mukamal, Kenneth J (Am J Kidney Dis, 2021)
RATIONALE & OBJECTIVE: Circulating non-esterified fatty acids (NEFAs) make up a small portion of circulating lipids but are a metabolically important energy source. Excessive circulating NEFAs may contribute to lipotoxicity in many tissues, including the kidneys. We investigated the relationship between total circulating NEFA concentration and kidney outcomes in older, community-dwelling adults. STUDY DESIGN: Prospective cohort study. SETTING & PARTICIPANTS: 4,698 participants ≥65 years of age in the Cardiovascular Health Study who underwent total fasting serum NEFA concentration measurements in 1992-1993. EXPOSURE: Fasting serum NEFA concentration at one timepoint. OUTCOMES: Three primary outcomes: estimated glomerular filtration rate (eGFR) decline of >30%; the composite of eGFR decline ≥30% or kidney failure with replacement therapy (KFRT); and change in eGFR. These outcomes were assessed over 4- and 13-year periods. ANALYTICAL APPROACH: Logistic regression for the dichotomous outcomes and mixed effects models for the continuous outcome, with sequential adjustment for baseline covariates. Inverse probability of attrition weighting was implemented to account for informative attrition during the follow-up periods. RESULTS: Serum NEFA concentrations were not independently associated with kidney outcomes. In unadjusted and partially adjusted analyses, the highest quartile of serum NEFA concentration (compared to lowest) was associated with a higher risk of ≥30% eGFR decline at 4 years and faster rate of decline of eGFR. No associations were evident after adjustment for comorbidities, lipid levels, insulin sensitivity, medications, and vital signs: odds ratio 1.33 (95%CI 0.83-2.13); estimated glomerular filtration rate change per year, Q4 vs Q1: -0.15 ml/min/1.73m/year (95%CI -0.36 to 0.06). LIMITATIONS: Single NEFA measurements, no measurements of post-glucose load NEFA concentrations or individual NEFA species, no measurement of baseline urine albumin. CONCLUSIONS: A single fasting serum NEFA concentration was not independently associated with long-term adverse kidney outcomes in a cohort of older community-living adults.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

Serum Individual Nonesterified Fatty Acids and Risk of Heart Failure in Older Adults. - Djoussé, Luc; Biggs, Mary L; Matthan, Nirupa R; Ix, Joachim H; Fitzpatrick, Annette L; King, Irena; Lemaitre, Rozenn N; McKnight, Barbara; Kizer, Jorge R; Lichtenstein, Alice H; Mukamal, Kenneth J; Siscovick, David S (Cardiology, 2021)
BACKGROUND: Heart failure (HF) is highly prevalent among older adults and is associated with high costs. Although serum total nonesterified fatty acids (NEFAs) have been positively associated with HF risk, the contribution of each individual NEFA to HF risk has not been examined. OBJECTIVE: The aim of this study was to examine the association of individual fasting NEFAs with HF risk in older adults. METHODS: In this prospective cohort study of older adults, we measured 35 individual NEFAs in 2,140 participants of the Cardiovascular Health Study using gas chromatography. HF was ascertained using review of medical records by an endpoint committee. RESULTS: The mean age was 77.7 ± 4.4 years, and 38.8% were male. During a median follow-up of 9.7 (maximum 19.0) years, 655 new cases of HF occurred. In a multivariable Cox regression model controlling for demographic and anthropometric variables, field center, education, serum albumin, glomerular filtration rate, physical activity, alcohol consumption, smoking, hormone replacement therapy, unintentional weight loss, and all other measured NEFAs, we observed inverse associations (HR [95% CI] per standard deviation) of nonesterified pentadecanoic (15:0) (0.73 [0.57-0.94]), γ-linolenic acid (GLA) (0.87 [0.75-1.00]), and docosahexaenoic acid (DHA) (0.73 [0.61-0.88]) acids with HF, and positive associations of nonesterified stearic (18:0) (1.30 [1.04-1.63]) and nervonic (24:1n-9) (1.17 [1.06-1.29]) acids with HF. CONCLUSION: Our data are consistent with a higher risk of HF with nonesterified stearic and nervonic acids and a lower risk with nonesterified 15:0, GLA, and DHA in older adults. If confirmed in other studies, specific NEFAs may provide new targets for HF prevention.

Serum non-esterified fatty acid levels and hip fracture risk: The Cardiovascular Health Study. - Barzilay, J I; Bůžková, P; Djoussé, L; Ix, J; Kizer, J; Cauley, J; Matthan, N; Lichtenstein, A H; Mukamal, K J (Osteoporos Int, 2021)
Among elderly participants from the Cardiovascular Health Study, we found that non-esterified trans fatty acid levels had a significant prospective association with hip fracture risk. Other non-esterified fatty acid classes were not associated with hip fracture risk. INTRODUCTION: Serum non-esterified fatty acids (NEFAs) are bioactive metabolic intermediates that can be taken up by bone tissue. Their associations with hip fracture risk have not been previously examined. METHODS: Thirty-five individual NEFAs in five classes (saturated [SFA], mono-un-saturated [MUFA], poly-unsaturated n-6 and n-3 [PUFA], and trans-FA) were measured in Cardiovascular Health Study participants (n = 2139, mean age 77.8 years) without known diabetes. The multivariable associations of NEFA levels with hip fracture risk were evaluated in Cox hazards models. RESULTS: We documented 303 incident hip fractures during 11.1 years of follow-up. Among the five NEFA classes, total trans FA levels were positively associated with higher hip fracture risk (HR 1.17 [95% CI, 1.04, 1.31; p = 0.01] per one standard deviation higher level). The SFA lignoceric acid (24:0) was positively associated with higher risk (HR 1.09 [1.04, 1.1]; p < 0.001), while behenic (22:0) and docosatetraenoic (22:4 n6) acids were associated with lower risk (HR 0.76 [0.61, 0.94]; p = 0.01; 0.84 [0.70, 1.00]; p = 0.05, respectively). CONCLUSION: Total plasma trans NEFA levels are related to hip fracture risk, suggesting an unrecognized benefit of their systematic removal from food. Novel associations of individual NEFAs with hip fracture risk require confirmation in other cohort studies.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; Mägi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; M?gi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

Sugar-Sweetened Beverage Consumption May Modify Associations Between Genetic Variants in the CHREBP (Carbohydrate Responsive Element Binding Protein) Locus and HDL-C (High-Density Lipoprotein Cholesterol) and Triglyceride Concentrations. - Haslam, Danielle E; Peloso, Gina M; Guirette, Melanie; Imamura, Fumiaki; Bartz, Traci M; Pitsillides, Achilleas N; Wang, Carol A; Li-Gao, Ruifang; Westra, Jason M; Pitkänen, Niina; Young, Kristin L; Graff, Mariaelisa; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: ChREBP (carbohydrate responsive element binding protein) is a transcription factor that responds to sugar consumption. Sugar-sweetened beverage (SSB) consumption and genetic variants in the locus have separately been linked to HDL-C (high-density lipoprotein cholesterol) and triglyceride concentrations. We hypothesized that SSB consumption would modify the association between genetic variants in the locus and dyslipidemia. METHODS: Data from 11 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (N=63 599) and the UK Biobank (N=59 220) were used to quantify associations of SSB consumption, genetic variants, and their interaction on HDL-C and triglyceride concentrations using linear regression models. A total of 1606 single nucleotide polymorphisms within or near were considered. SSB consumption was estimated from validated questionnaires, and participants were grouped by their estimated intake. RESULTS: In a meta-analysis, rs71556729 was significantly associated with higher HDL-C concentrations only among the highest SSB consumers (β, 2.12 [95% CI, 1.16-3.07] mg/dL per allele; <0.0001), but not significantly among the lowest SSB consumers (=0.81; <0.0001). Similar results were observed for 2 additional variants (rs35709627 and rs71556736). For triglyceride, rs55673514 was positively associated with triglyceride concentrations only among the highest SSB consumers (β, 0.06 [95% CI, 0.02-0.09] ln-mg/dL per allele, =0.001) but not the lowest SSB consumers (=0.84; =0.0005). CONCLUSIONS: Our results identified genetic variants in the locus that may protect against SSB-associated reductions in HDL-C and other variants that may exacerbate SSB-associated increases in triglyceride concentrations. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00005133, NCT00005121, NCT00005487, and NCT00000479.

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

Urine creatinine concentration and clinical outcomes in older adults: The Cardiovascular Health Study. - Barzilay, Joshua I; Bůzková, Petra; Shlipak, Michael G; Lyles, Mary F; Bansal, Nisha; Garimella, Pranav S; Ix, Joachim H; Kizer, Jorge R; Strotmeyer, Elsa S; Djoussé, Luc; Biggs, Mary L; Siscovick, David; et al. (J Am Geriatr Soc, 2021)
PURPOSE: Loss of muscle mass and strength are associated with long-term adverse health outcomes in older adults. Urine creatinine concentrations (Ucr; mg/dl) are a measure of muscle tissue mass and turnover. This study assessed the associations of a spot Ucr level with muscle mass and with risk of hospitalization, mortality, and diabetes mellitus in older adults. METHODS: We examined 3424 participants from the Cardiovascular Health Study who provided spot urine samples in 1996-1997 and who were followed through June 2015. All participants underwent baseline measurement of grip strength. In a sub-cohort, 1331 participants underwent dual energy X-ray absorptiometry (DEXA) scans, from which lean muscle mass was derived. Participants were followed for a median of 10 years for hospitalizations and mortality, and 9 years for diabetes mellitus. RESULTS: In linear regression analysis, a one standard deviation higher Ucr concentration (64.6 mg/dl) was associated with greater grip strength (kg force) β = 0.44 [0.16, 0.72]; p = 0.002) and higher lean muscle mass (kg) (β = 0.43 [0.08, 0.78]; p = 0.02). In Cox regression analyses, each standard deviation greater Ucr concentration was associated with lower rates of hospitalizations (0.94 [95% confidence interval, 0.90, 0.98]; p < 0.001) and lower mortality risk (0.92 [0.88, 0.97]; p < 0.001), while a one standard deviation increase in muscle mass derived from DEXA had no such significant association. Ucr levels were not associated with incident diabetes mellitus risk (0.97 [0.85, 1.11]; p = 0.65). CONCLUSION: A higher spot Ucr concentration was favorably associated with muscle mass and strength and with health outcomes in older community-living adults. The ease of obtaining a spot Ucr makes it an attractive analyte to use for gauging the health of older adults.

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

The Associations of Individual and Subclasses of Non-Esterified Fatty Acids with Disability, and Mobility Limitation in Older Adults: the Cardiovascular Health Study. - Ahiawodzi, Peter; Bůzková, Petra; Lichtenstein, Alice H; Matthan, Nirupa R; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Arnold, Alice; Newman, Anne B; Siscovick, David; Djoussé, Luc; Mukamal, Kenneth J (J Gerontol A Biol Sci Med Sci, 2022)
BACKGROUND: We sought to determine the associations between individual non-esterified fatty acids (NEFAs) and disability and mobility limitation. METHODS: We studied 1734 participants in the Cardiovascular Health Study (CHS), an ongoing population-based cohort study of community-living older American adults. We measured 35 individual NEFA species in fasting serum samples obtained at the 1996-1997 clinic visit. Using yearly assessments of activities of daily living and self-reported mobility, we identified participants with incident disability or mobility limitation during 15 years of follow-up. Cox proportional hazards regression models were used to determine the associations between per-SD increment in the individual NEFAs and incident disability and mobility limitations with adjustment for potential confounding factors. RESULTS: Higher concentrations of total and a broad range of individual NEFA species were associated with risk of disability and mobility limitation [disability: HR per SD of total NEFA (SD=174.70) =1.11, 95%CI=1.04-1.18, p=0.001; mobility limitation: HR per SD of total NEFA=1.09, 95%CI=1.02-1.16, p=0.01). Among individual saturated NEFAs (SFAs), myristic (14:0) and palmitic (16:0) acids were significantly associated with higher risk of both disability and mobility limitations, but longer-chain FAs were not. Most individual monounsaturated (MUFA), n-6 polyunsaturated fatty acids (PUFAs), and trans FAs were positively significantly associated with higher risks of both disability and mobility limitation. In contrast, most n-3 PUFA species were not associated with disability or mobility limitation. CONCLUSIONS: Higher risks of disability and mobility limitation were observed for pro-inflammatory intermediate-chain SFAs, MUFAs, n-6 PUFAs, and trans FAs. Our findings indicated no significant association for anti-inflammatory n-3 PUFAs.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Correlations between complex human phenotypes vary by genetic background, gender, and environment. - Elgart, Michael; Goodman, Matthew O; Isasi, Carmen; Chen, Han; Morrison, Alanna C; de Vries, Paul S; Xu, Huichun; Manichaikul, Ani W; Guo, Xiuqing; Franceschini, Nora; Psaty, Bruce M; Rich, Stephen S; et al. (Cell Rep Med, 2022)
We develop a closed-form Haseman-Elston estimator for genetic and environmental correlation coefficients between complex phenotypes, which we term HEc, that is as precise as GCTA yet ∼20× faster. We estimate genetic and environmental correlations between over 7,000 phenotype pairs in subgroups from the Trans-Omics in Precision Medicine (TOPMed) program. We demonstrate substantial differences in both heritabilities and genetic correlations for multiple phenotypes and phenotype pairs between individuals of self-reported Black, Hispanic/Latino, and White backgrounds. We similarly observe differences in many of the genetic and environmental correlations between genders. To estimate the contribution of genetics to the observed phenotypic correlation, we introduce "fractional genetic correlation" as the fraction of phenotypic correlation explained by genetics. Finally, we quantify the enrichment of correlations between phenotypic domains, each of which is comprised of multiple phenotypes. Altogether, we demonstrate that the observed correlations between complex human phenotypes depend on the genetic background of the individuals, their gender, and their environment.
Keywords: Female; Genetic Background; Humans; Male; Phenotype

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

{DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, M.; Mandaviya, P. R.; Kuehnel, B.; Joehanes, R.; Mustafa, R.; Robinson, O.; Zhang, Y.; Bodinier, B.; Walton, E.; Mishra, P. P.; Schlosser, P.; Wilson, R.; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2022)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at approximately 450,000 CpG sites in 9,732 middle-aged to older adults from 14 community-based studies. Single-CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single-CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5), and colocalized with FOLH1 expression in brain (posterior probability =0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single-CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis, and multi-omics colocalization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug repositioning analysis indicated antihyperlipidemic agents, more specifically peroxisome proliferator-activated receptor alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood brain barrier disruption.

Fasting and Postload Nonesterified Fatty Acids and Glucose Dysregulation in Older Adults. - Shitole, Sanyog G; Biggs, Mary L; Ix, Joachim H; Fretts, Amanda M; Tracy, Russell P; Siscovick, David S; Djoussé, Luc; Mukamal, Kenneth J; Kizer, Jorge R (Am J Epidemiol, 2022)
To evaluate the association of nonesterified fatty acids (NEFA) with dysglycemia in older adults, NEFA levels were measured among participants in the Cardiovascular Health Study (United States; enrolled 1989-1993). Associations with insulin sensitivity and pancreatic β-cell function, and with incident type 2 diabetes mellitus (DM), were examined. The sample comprised 2,144 participants (aged 77.9 (standard deviation, 4.5) years). Participant data from the Cardiovascular Health Study visit in 1996-1997 was used with prospective follow-up through 2010. Fasting and postload NEFA showed significant associations with lower insulin sensitivity and pancreatic β-cell function, individually and on concurrent adjustment. Over median follow-up of 9.7 years, 236 cases of DM occurred. Postload NEFA were associated with risk of DM (per standard deviation, hazard ratio = 1.18, 95% confidence interval: 1.08, 1.29), but fasting NEFA were not (hazard ratio = 1.12, 95% confidence interval: 0.97, 1.29). The association for postload NEFA persisted after adjustment for putative intermediates, and after adjustment for fasting NEFA. Sex and body mass index modified these associations, which were stronger for fasting NEFA with DM in men but were accentuated for postload NEFA in women and among leaner individuals. Fasting and postload NEFA were related to lower insulin sensitivity and pancreatic β-cell function, but only postload NEFA were associated with increased DM. Additional study into NEFA metabolism could uncover novel potential targets for diabetes prevention in elders.
Keywords: Aged; Blood Glucose; Diabetes Mellitus, Type 2; Fasting; Fatty Acids, Nonesterified; Female; Glucose; Humans; Insulin; Insulin Resistance; Male; Prospective Studies

{Gene Set Enrichment Analsyes Identify Pathways Involved in Genetic Risk for Diabetic Retinopathy - Sobrin, L.; Susarla, G.; Stanwyck, L.; Rouhana, J. M.; Li, A.; Pollack, S.; Igo, R. P.; Jensen, R. A.; Li, X.; Ng, M. C. Y.; Smith, A. V.; Kuo, J. Z.; et al. (Am J Ophthalmol, 2022)
{To identify functionally related genes associated with diabetic retinopathy (DR) risk using gene set enrichment analyses applied to genome-wide association study meta-analyses.\ .05.\ .05) in the other method. These pathways were regulation of the lipid catabolic process (2-fold enrichment

{Gene-mapping study of extremes of cerebral small vessel disease reveals TRIM47 as a strong candidate - Mishra, A.; Duplaà, C.; Vojinovic, D.; Suzuki, H.; Sargurupremraj, M.; Zilhao, N. R.; Li, S.; Bartz, T. M.; Jian, X.; Zhao, W.; Hofer, E.; Wittfeld, K.; et al. (Brain, 2022)
Cerebral small vessel disease is a leading cause of stroke and a major contributor to cognitive decline and dementia, but our understanding of specific genes underlying the cause of sporadic cerebral small vessel disease is limited. We report a genome-wide association study and a whole-exome association study on a composite extreme phenotype of cerebral small vessel disease derived from its most common MRI features: white matter hyperintensities and lacunes. Seventeen population-based cohorts of older persons with MRI measurements and genome-wide genotyping (n = 41 326), whole-exome sequencing (n = 15 965), or exome chip (n = 5249) data contributed 13 776 and 7079 extreme small vessel disease samples for the genome-wide association study and whole-exome association study, respectively. The genome-wide association study identified significant association of common variants in 11 loci with extreme small vessel disease, of which the chr12q24.11 locus was not previously reported to be associated with any MRI marker of cerebral small vessel disease. The whole-exome association study identified significant associations of extreme small vessel disease with common variants in the 5' UTR region of EFEMP1 (chr2p16.1) and one probably damaging common missense variant in TRIM47 (chr17q25.1). Mendelian randomization supports the causal association of extensive small vessel disease severity with increased risk of stroke and Alzheimer's disease. Combined evidence from summary-based Mendelian randomization studies and profiling of human loss-of-function allele carriers showed an inverse relation between TRIM47 expression in the brain and blood vessels and extensive small vessel disease severity. We observed significant enrichment of Trim47 in isolated brain vessel preparations compared to total brain fraction in mice, in line with the literature showing Trim47 enrichment in brain endothelial cells at single cell level. Functional evaluation of TRIM47 by small interfering RNAs-mediated knockdown in human brain endothelial cells showed increased endothelial permeability, an important hallmark of cerebral small vessel disease pathology. Overall, our comprehensive gene-mapping study and preliminary functional evaluation suggests a putative role of TRIM47 in the pathophysiology of cerebral small vessel disease, making it an important candidate for extensive in vivo explorations and future translational work.

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Genetic and clinical determinants of abdominal aortic diameter: genome-wide association studies, exome array data and Mendelian randomization study - Portilla-Fernandez, E.; Klarin, D.; Hwang, S. J.; Biggs, M. L.; Bis, J. C.; Weiss, S.; Rospleszcz, S.; Natarajan, P.; Hoffmann, U.; Rogers, I. S.; Truong, Q. A.; lker, U.; et al. (Hum Mol Genet, 2022)
0.0001), known risk factors for AAA, consistent with a causal association with AAD. Our findings point to new biology as well as highlighting gene regions in mechanisms that have previously been implicated in the genetics of other vascular diseases.

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome-wide analyses identify as a susceptibility locus for premature atrial contraction frequency. - Thériault, Sébastien; Imboden, Medea; Biggs, Mary L; Austin, Thomas R; Aeschbacher, Stefanie; Schaffner, Emmanuel; Brody, Jennifer A; Bartz, Traci M; Risch, Martin; Grossmann, Kirsten; Lin, Henry J; Soliman, Elsayed Z; et al. (iScience, 2022)
Premature atrial contractions (PACs) are frequently observed on electrocardiograms and are associated with increased risks of atrial fibrillation (AF), stroke, and mortality. In this study, we aimed to identify genetic susceptibility loci for PAC frequency. We performed a genome-wide association study meta-analysis with PAC frequency obtained from ambulatory cardiac monitoring in 4,831 individuals of European ancestry. We identified a genome-wide significant locus at the gene. The lead variant, rs7373862, located in an intron of , was associated with an increase of 0.12 [95% CI 0.08-0.16] standard deviations of the normalized PAC frequency per risk allele. Among genetic variants previously associated with AF, there was a significant enrichment in concordance of effect for PAC frequency (n = 73/106, p = 5.1 × 10). However, several AF risk loci, including , were not associated with PAC frequency. These findings suggest the existence of both shared and distinct genetic mechanisms for PAC frequency and AF.

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

{Obesity Partially Mediates the Diabetogenic Effect of Lowering LDL Cholesterol - Wu, P.; Moon, J. Y.; Daghlas, I.; Franco, G.; Porneala, B. C.; Ahmadizar, F.; Richardson, T. G.; Isaksen, J. L.; Hindy, G.; Yao, J.; Sitlani, C. M.; Raffield, L. M.; et al. (Diabetes Care, 2022)
LDL cholesterol (LDLc)-lowering drugs modestly increase body weight and type 2 diabetes risk, but the extent to which the diabetogenic effect of lowering LDLc is mediated through increased BMI is unknown.\ We conducted summary-level univariable and multivariable Mendelian randomization (MR) analyses in 921,908 participants to investigate the effect of lowering LDLc on type 2 diabetes risk and the proportion of this effect mediated through BMI. We used data from 92,532 participants from 14 observational studies to replicate findings in individual-level MR analyses.\ A 1-SD decrease in genetically predicted LDLc was associated with increased type 2 diabetes odds (odds ratio [OR] 1.12 [95% CI 1.01, 1.24]) and BMI (β = 0.07 SD units [95% CI 0.02, 0.12]) in univariable MR analyses. The multivariable MR analysis showed evidence of an indirect effect of lowering LDLc on type 2 diabetes through BMI (OR 1.04 [95% CI 1.01, 1.08]) with a proportion mediated of 38% of the total effect (P = 0.03). Total and indirect effect estimates were similar across a number of sensitivity analyses. Individual-level MR analyses confirmed the indirect effect of lowering LDLc on type 2 diabetes through BMI with an estimated proportion mediated of 8% (P = 0.04).\ These findings suggest that the diabetogenic effect attributed to lowering LDLc is partially mediated through increased BMI. Our results could help advance understanding of adipose tissue and lipids in type 2 diabetes pathophysiology and inform strategies to reduce diabetes risk among individuals taking LDLc-lowering medications.

Plasma Levels of Advanced Glycation Endproducts and Risk of Cardiovascular Events: Findings From 2 Prospective Cohorts. - Lamprea-Montealegre, Julio A; Arnold, Alice M; McClelland, Robyn L; Mukamal, Kenneth J; Djoussé, Luc; Biggs, Mary L; Siscovick, David S; Tracy, Russell P; Beisswenger, Paul J; Psaty, Bruce M; Ix, Joachim H; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Advanced glycation endproducts (AGEs) have been linked to cardiovascular disease (CVD) in cohorts with and without diabetes. Data are lacking on prospective associations of various α-dicarbonyl-derived AGEs and incident CVD in the general population. We tested the hypothesis that major plasma AGEs are associated with new-onset CVD in 2 population-based cohorts of differing age and comorbidities. Methods and Results Analyses involved a random subcohort (n=466) from the Cardiovascular Health Study and a case-cohort sample (n=1631) from the Multi-Ethnic Study of Atherosclerosis. Five AGEs and 2 oxidative products were measured by liquid chromatography tandem mass spectrometry. Associations with CVD (myocardial infarction and stroke) were evaluated with Cox regression. Participants in the Cardiovascular Health Study were older than the Multi-Ethnic Study of Atherosclerosis, and had more comorbidities, along with higher levels of all AGEs. During median follow-up of 11 years, 439 participants in the Multi-Ethnic Study of Atherosclerosis and 200 in the Cardiovascular Health Study developed CVD. After multivariable adjustment, carboxymethyl-lysine, 3-deoxyglucosone hydroimidazolones and a summary variable of all measured AGEs (principal component 1) were significantly associated with incident CVD in the Cardiovascular Health Study (HRs [95% CI]: 1.20 [1.01, 1.42], 1.45 [1.23, 1.72], and 1.29 [1.06, 1.56], respectively), but not the Multi-Ethnic Study of Atherosclerosis. Oxidative products were not associated with CVD in either cohort. Conclusions We found α-dicarbonyl-derived AGEs to be associated with CVD in an older cohort, but not in a healthier middle-aged/older cohort. Our results suggest that AGEs may exert detrimental cardiovascular effects only under conditions of marked dicarbonyl and oxidative stress. Further investigation of α-dicarbonyl derivatives could lead to potential new strategies for CVD prevention in high-risk older populations.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Glycation End Products, Advanced; Humans; Middle Aged; Risk Factors

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

{Trans Fatty Acid Biomarkers and Incident Type 2 Diabetes: Pooled Analysis of 12 Prospective Cohort Studies in the Fatty Acids and Outcomes Research Consortium (FORCE) - Lai, H. T. M.; Imamura, F.; Korat, A. V. A.; Murphy, R. A.; Tintle, N.; Bassett, J. K.; Chen, J.; ger, J.; Chien, K. L.; Senn, M.; Wood, A. C.; Forouhi, N. G.; et al. (Diabetes Care, 2022)
Trans fatty acids (TFAs) have harmful biologic effects that could increase the risk of type 2 diabetes (T2D), but evidence remains uncertain. We aimed to investigate the prospective associations of TFA biomarkers and T2D by conducting an individual participant-level pooled analysis.\ 18 years without prevalent diabetes. Each cohort conducted de novo harmonized analyses using a prespecified protocol, and findings were pooled using inverse-variance weighted meta-analysis. Heterogeneity was explored by prespecified between-study and within-study characteristics.\ 0.1).\ Circulating individual trans-18:2 TFA biomarkers were not associated with risk of T2D, while trans-16:1n-9, total trans-18:1, and total trans-18:2 were inversely associated. Findings may reflect the influence of mixed TFA sources (industrial vs. natural ruminant), a general decline in TFA exposure due to policy changes during this period, or the relatively limited range of TFA levels.

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Whole-Exome Sequencing Study Identifies Four Novel Gene Loci Associated with Diabetic Kidney Disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Metcalf, Ginger; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2022)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease (CKD) and diabetes. Our two-stage whole-exome sequencing study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort (CRIC) and Atherosclerosis Risk in Communities (ARIC) studies (stage-1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine (TOPMed) participants (stage-2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex, and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test (SKAT-O) implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds (95% confidence interval: 33.6, 1105) of DKD compared with non-carriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% confidence interval: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

The Association of Tryptophan and Its Metabolites With Incident Hip Fractures, Mortality, and Prevalent Frailty in Older Adults: The Cardiovascular Health Study. - Carbone, Laura; Bůzková, Petra; Fink, Howard A; Robbins, John A; Barzilay, Joshua I; Elam, Rachel E; Isales, Carlos (JBMR Plus, 2023)
Amino acids are the building blocks of proteins, and sufficient protein intake is important for skeletal health. We utilized stored serum from the Cardiovascular Health Study in 1992-1993 to examine the relationship between levels of the essential amino acid tryptophan (trp) and its oxidized and nonoxidized metabolites to risk for incident hip fractures and mortality over 12 years of follow-up. We included 131 persons who sustained a hip fracture during this time period and 131 without a hip fracture over these same 12 years of follow-up; 58% female and 95% White. Weighted multivariable Cox hazards models were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of incident hip fracture associated with a one standard deviation (SD) higher trp or its metabolites exposure. Relative risk regression was used to evaluate the cross-sectional association of trp and its metabolites with frailty. Higher serum levels of trp were significantly associated with lower risk of incident hip fractures (HR = 0.75 per SD of trp (95% CI 0.57-0.99) but were not significantly associated with mortality or frailty status by Freid's frailty index. There were no statistically significant associations between any of the oxidized or nonoxidized products of trp with incident hip fractures ( ≥ 0.64), mortality ( ≥ 0.20), or cross-sectional frailty status ( ≥ 0.13) after multiple testing adjustment. Randomized clinical trials examining whether increasing trp intake is beneficial for osteoporosis are needed. © 2023 The Authors. published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.

Cardiac Mechanics and Kidney Function Decline in the Cardiovascular Health Study. - Mehta, Rupal; Bůzková, Petra; Patel, Harnish; Cheng, Jeanette; Kizer, Jorge R; Gottdiener, John S; Psaty, Bruce; Khan, Sadiya S; Ix, Joachim H; Isakova, Tamara; Shlipak, Michael G; Bansal, Nisha; et al. (Kidney360, 2023)
BACKGROUND: Clinical heart failure frequently coexists with chronic kidney disease (CKD) and may precipitate kidney function decline. However, whether earlier-stage myocardial dysfunction assessable by speckle tracking echocardiography is a contributor to kidney function decline remains unknown. METHODS: We studied 2135 Cardiovascular Health Study (CHS) participants who were free of clinical heart failure and had Year 2-baseline 2D speckle tracking echocardiography and two measurements of estimated glomerular filtration rate (eGFR) (Year 2 and Year 9). "Archival" speckle tracking of digitized echocardiogram videotapes was utilized to measure left ventricular longitudinal strain (LVLS), LV early diastolic strain rate (EDSR), left atrial reservoir strain (LARS), right ventricular free wall strain (RVFWS), and mitral annular velocity (e'). Multivariable Poisson regression models that adjusted for demographics and cardiovascular risk factors were used to investigate the independent associations of cardiac mechanics indices and decline in kidney function defined as a 30% decline in eGFR over 7 years. RESULTS: In risk factor (RF) models LVLS, EDSR, RVFWS, and e' were all significantly associated with the prevalence of kidney disease. After multivariable adjustment, left atrial dysfunction (RR 1.18 [95% CI 1.01, 1.38] per SD lower LARS] and left ventricular diastolic dysfunction (RR 1.21 [95% CI 1.04, 1.41] per SD lower EDSR) were each significantly associated with 30% decline in eGFR. CONCLUSIONS: Subclinical myocardial dysfunction suggesting abnormal diastolic function detected by 2D speckle-tracking echocardiography was independently associated with decline in kidney function over time. Further studies are needed to understand the mechanisms of these associations and to test whether interventions that may improve subclinical myocardial dysfunction can prevent decline of kidney function.

Complexities of cerebral small vessel disease, blood pressure, and dementia relationship: new insights from genetics. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (medRxiv, 2023)
IMPORTANCE: There is increasing recognition that vascular disease, which can be treated, is a key contributor to dementia risk. However, the contribution of specific markers of vascular disease is unclear and, as a consequence, optimal prevention strategies remain unclear. OBJECTIVE: To disentangle the causal relation of several key vascular traits to dementia risk: (i) white matter hyperintensity (WMH) burden, a highly prevalent imaging marker of covert cerebral small vessel disease (cSVD); (ii) clinical stroke; and (iii) blood pressure (BP), the leading risk factor for cSVD and stroke, for which efficient therapies exist. To account for potential epidemiological biases inherent to late-onset conditions like dementia. DESIGN SETTING AND PARTICIPANTS: This study first explored the association of genetically determined WMH, BP levels and stroke risk with AD using summary-level data from large genome-wide association studies (GWASs) in a two-sample Mendelian randomization (MR) framework. Second, leveraging individual-level data from large longitudinal population-based cohorts and biobanks with prospective dementia surveillance, the association of weighted genetic risk scores (wGRSs) for WMH, BP, and stroke with incident all-cause-dementia was explored using Cox-proportional hazard and multi-state models. The data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined levels of WMH volume and BP (systolic, diastolic and pulse blood pressures) and genetic liability to stroke. MAIN OUTCOMES AND MEASURES: The summary-level MR analyses focused on the outcomes from GWAS of clinically diagnosed AD (n-cases=21,982) and GWAS additionally including self-reported parental history of dementia as a proxy for AD diagnosis (AD , n-cases=53,042). For the longitudinal analyses, individual-level data of 157,698 participants with 10,699 incident all-cause-dementia were studied, exploring AD, vascular or mixed dementia in secondary analyses. RESULTS: In the two-sample MR analyses, WMH showed strong evidence for a causal association with increased risk of AD (OR, 1.16; 95%CI:1.05-1.28; P=.003) and AD (OR, 1.28; 95%CI:1.07-1.53; P=.008), after accounting for genetically determined pulse pressure for the latter. Genetically predicted BP traits showed evidence for a protective association with both clinically defined AD and AD , with evidence for confounding by shared genetic instruments. In longitudinal analyses the wGRSs for WMH, but not BP or stroke, showed suggestive association with incident all-cause-dementia (HR, 1.02; 95%CI:1.00-1.04; P=.06). BP and stroke wGRSs were strongly associated with mortality but there was no evidence for selective survival bias during follow-up. In secondary analyses, polygenic scores with more liberal instrument definition showed association of both WMH and stroke with all-cause-dementia, AD, and vascular or mixed dementia; associations of stroke, but not WMH, with dementia outcomes were markedly attenuated after adjusting for interim stroke. CONCLUSION: These findings provide converging evidence that WMH is a leading vascular contributor to dementia risk, which may better capture the brain damage caused by BP (and other etiologies) than BP itself and should be targeted in priority for dementia prevention in the population. KEY POINTS: Do instrumental variable analyses leveraging genetic information provide evidence for a causal association of various vascular traits with Alzheimer's disease (AD) and all-cause-dementia? How do these associations compare for white matter hyperintensity (WMH) burden, a highly prevalent marker of covert cerebral small vessel disease (cSVD), stroke, and blood pressure traits, the strongest known risk factor for cSVD and stroke? Using Mendelian randomization (MR) leveraging large, published genome-wide association studies, this study showed a putative causal association of larger WMH burden with increased AD risk after accounting for pulse pressure effects, and some evidence for association of lower BP with AD risk with possible confounding by shared genetic instruments. Longitudinal analyses on individual-level data also supported association of genetically determined WMH with incident all-cause-dementia and AD, independently of interim stroke. This study using complementary genetic epidemiology approaches, identified increasing WMH burden to be associated with dementia and AD risk, suggesting the association as specific for cSVD and independent of BP and stroke.

The determinants of fasting and post-load non-esterified fatty acids in older adults: The cardiovascular health study. - Bene-Alhasan, Yakubu; Siscovick, David S; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell; Djoussé, Luc; Mukamal, Kenneth J (Metabol Open, 2023)
AIM: Non-esterified fatty acids (NEFA) are potential targets for prevention of key cardiometabolic diseases of aging, but their population-level correlates remain uncertain. We sought to identify modifiable factors associated with fasting and post-load NEFA levels in older adults. METHODS: We used linear regression to determine the cross-sectional associations of demographic, anthropometric, and lifestyle characteristics and medication use with serum fasting and post-load NEFA concentrations amongst community-dwelling older adults enrolled in the Cardiovascular Health Study (n = 1924). RESULTS: Fasting NEFA levels generally demonstrated a broader set of determinants, while post-load NEFA were more consistently associated with metabolic factors. Waist circumference and weight were associated with higher fasting and post-load NEFA. Cigarette smoking and caffeine intake were associated with lower levels of both species, and moderate alcohol intake was associated with higher fasting levels whereas greater consumption was associated with lower post-load levels. Unique factors associated with higher fasting NEFA included female sex, higher age, loop and thiazide diuretic use and calcium intake, while factors associated with lower fasting levels included higher educational attainment, beta-blocker use, and protein intake. Hours spent sleeping during the daytime were associated with higher post-load NEFA, while DASH score was associated with lower levels. CONCLUSION: Fasting and post-load NEFA have both common and unique modifiable risk factors, including sociodemographics, anthropometric, medications, and diet. Post-load NEFA were particularly sensitive to metabolic factors, while a broader range of determinants were associated with fasting levels. These factors warrant study as targets for lowering levels of NEFA in older adults.

{Early-onset Alzheimer's disease explained by polygenic risk of late-onset disease? - Mantyh, W. G.; Cochran, J. N.; Taylor, J. W.; Broce, I. J.; Geier, E. G.; Bonham, L. W.; Anderson, A. G.; Sirkis, D. W.; Joie, R.; Iaccarino, L.; Chaudhary, K.; Edwards, L.; et al. (Alzheimers Dement (Amst), 2023)
There is a unique genetic architecture of early- versus late-onset Alzheimer's disease (AD).Late-onset AD polygenic risk is not an explanation for early-onset AD.Polygenic risk of late-onset AD does not predict early-onset AD biology.Unique genetic architecture of early- versus late-onset AD parallels AD heterogeneity.

Evaluating the use of blood pressure polygenic risk scores across race/ethnic background groups. - Kurniansyah, Nuzulul; Goodman, Matthew O; Khan, Alyna T; Wang, Jiongming; Feofanova, Elena; Bis, Joshua C; Wiggins, Kerri L; Huffman, Jennifer E; Kelly, Tanika; Elfassy, Tali; Guo, Xiuqing; Palmas, Walter; et al. (Nat Commun, 2023)
We assess performance and limitations of polygenic risk scores (PRSs) for multiple blood pressure (BP) phenotypes in diverse population groups. We compare "clumping-and-thresholding" (PRSice2) and LD-based (LDPred2) methods to construct PRSs from each of multiple GWAS, as well as multi-PRS approaches that sum PRSs with and without weights, including PRS-CSx. We use datasets from the MGB Biobank, TOPMed study, UK biobank, and from All of Us to train, assess, and validate PRSs in groups defined by self-reported race/ethnic background (Asian, Black, Hispanic/Latino, and White). For both SBP and DBP, the PRS-CSx based PRS, constructed as a weighted sum of PRSs developed from multiple independent GWAS, perform best across all race/ethnic backgrounds. Stratified analysis in All of Us shows that PRSs are better predictive of BP in females compared to males, individuals without obesity, and middle-aged (40-60 years) compared to older and younger individuals.
Keywords: Blood Pressure; Ethnicity; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Population Health; Risk Factors

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Boerwinkle, Eric; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Gibbs, Richard; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Large-scale exome array summary statistics resources for glycemic traits to aid effector gene prioritization. - Willems, Sara M; Ng, Natasha H J; Fernandez, Juan; Fine, Rebecca S; Wheeler, Eleanor; Wessel, Jennifer; Kitajima, Hidetoshi; Marenne, Gaelle; Sim, Xueling; Yaghootkar, Hanieh; Wang, Shuai; Chen, Sai; et al. (Wellcome Open Res, 2023)
BACKGROUND: Genome-wide association studies for glycemic traits have identified hundreds of loci associated with these biomarkers of glucose homeostasis. Despite this success, the challenge remains to link variant associations to genes, and underlying biological pathways. METHODS: To identify coding variant associations which may pinpoint effector genes at both novel and previously established genome-wide association loci, we performed meta-analyses of exome-array studies for four glycemic traits: glycated hemoglobin (HbA1c, up to 144,060 participants), fasting glucose (FG, up to 129,665 participants), fasting insulin (FI, up to 104,140) and 2hr glucose post-oral glucose challenge (2hGlu, up to 57,878). In addition, we performed network and pathway analyses. RESULTS: Single-variant and gene-based association analyses identified coding variant associations at more than 60 genes, which when combined with other datasets may be useful to nominate effector genes. Network and pathway analyses identified pathways related to insulin secretion, zinc transport and fatty acid metabolism. HbA1c associations were strongly enriched in pathways related to blood cell biology. CONCLUSIONS: Our results provided novel glycemic trait associations and highlighted pathways implicated in glycemic regulation. Exome-array summary statistic results are being made available to the scientific community to enable further discoveries.

Multi-ancestry genome-wide study identifies effector genes and druggable pathways for coronary artery calcification. - Kavousi, Maryam; Bos, Maxime M; Barnes, Hanna J; Lino Cardenas, Christian L; Wong, Doris; Lu, Haojie; Hodonsky, Chani J; Landsmeer, Lennart P L; Turner, Adam W; Kho, Minjung; Hasbani, Natalie R; de Vries, Paul S; et al. (Nat Genet, 2023)
Coronary artery calcification (CAC), a measure of subclinical atherosclerosis, predicts future symptomatic coronary artery disease (CAD). Identifying genetic risk factors for CAC may point to new therapeutic avenues for prevention. Currently, there are only four known risk loci for CAC identified from genome-wide association studies (GWAS) in the general population. Here we conducted the largest multi-ancestry GWAS meta-analysis of CAC to date, which comprised 26,909 individuals of European ancestry and 8,867 individuals of African ancestry. We identified 11 independent risk loci, of which eight were new for CAC and five had not been reported for CAD. These new CAC loci are related to bone mineralization, phosphate catabolism and hormone metabolic pathways. Several new loci harbor candidate causal genes supported by multiple lines of functional evidence and are regulators of smooth muscle cell-mediated calcification ex vivo and in vitro. Together, these findings help refine the genetic architecture of CAC and extend our understanding of the biological and potential druggable pathways underlying CAC.

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Non-esterified fatty acids and risk of peripheral artery disease in older adults: The cardiovascular health study. - Ahiawodzi, Peter; Solaru, Khendi White; Chaves, Paulo H M; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne; Siscovick, David; Djoussé, Luc; Mukamal, Kenneth J (Atherosclerosis, 2023)
BACKGROUND AND AIMS: Non-esterified fatty acids have been implicated in the pathogenesis of diabetes and cardiovascular disease. No longitudinal study has assessed their effects on peripheral artery disease (PAD). We determined the relationships between NEFAs and incident clinical PAD and abnormal ankle-brachial index (ABI) in a population-based cohort of older persons. METHODS: We evaluated 4575 community living participants aged >65 years who underwent measurement of circulating NEFAs in fasting specimens and ABI in 1992-1993. Participants were assessed annually for clinical PAD until 2015 and underwent repeat ABI in 1998-1999. We used Cox proportional hazards regression to model the associations between NEFAs and risk of clinical PAD and logistic regression to model the associations of NEFAs with incident abnormal ABI. RESULTS: Mean age was 74.8 years, 59% were female, and 17% were Black. NEFAs were associated with higher risk of clinical PAD in unadjusted and adjusted models. The adjusted hazard ratios for incident clinical PAD were 1.51 (95%CI = 1.06-2.13, p = 0.02) across extreme tertiles, and 1.14 (95%CI = 0.99-1.31, p = 0.08) per standard deviation higher NEFA. The corresponding odds ratios for abnormal ABI were 0.95 (95%CI = 0.69-1.32, p = 0.76) across extreme tertiles, and 1.03 (95%CI = 0.89-1.20, p = 0.68) per standard deviation higher NEFA. Relationships appeared similar irrespective of sex, race, or pre-existing cardiovascular disease, but were stronger later than earlier in follow-up. CONCLUSIONS: Higher serum levels of NEFAs are significantly associated with increased likelihood of clinical PAD over long-term follow-up but not with 6-year decline in ABI. NEFAs may offer a potential target for intervention against clinical PAD.

Plasma Levels of Branched Chain Amino Acids, Incident Hip Fractures and Bone Mineral Density of the Hip and Spine. - Carbone, Laura; Bůzková, Petra; Fink, Howard A; Robbins, John A; Barzilay, Joshua I; Elam, Rachel E; Isales, Carlos; Connelly, Margery A; Mukamal, Kenneth J (J Clin Endocrinol Metab, 2023)
OBJECTIVE: Branched chain amino acids (BCAA) are building blocks for protein, an essential component of bone. However, the association of plasma levels of BCAA with fractures in populations outside of Hong Kong or with hip fractures in particular is not known. The purpose of these analyses was to determine the relationship of BCAA including valine, leucine and isoleucine and total BCAA (standard deviation of the sum of Z-scores for each BCAA) with incident hip fractures and bone mineral density (BMD) of the hip and lumbar spine in older African American and Caucasian men and women in the Cardiovascular Health Study (CHS). DESIGN: Longitudinal analyses of association of plasma levels of BCAA with incident hip fractures and cross-sectional BMD of the hip and lumbar spine from the CHS. SETTING: Community. PARTICIPANTS: 1850 men (38% of cohort) and women; mean age 73. MAIN OUTCOME MEASURES: Incident hip fractures and cross-sectional BMD of the total hip, femoral neck and lumbar spine. RESULTS: In fully adjusted models, over 12 years of follow-up, we observed no significant association between incident hip fracture and plasma values of valine, leucine, isoleucine or total BCAA per 1 standard deviation higher of each BCAA. Plasma values of leucine but not valine, isoleucine or total BCAA, were positively and significantly associated with BMD of the total hip (p = 0.03) and femoral neck (p = 0.02), but not the lumbar spine (p = 0.07). CONCLUSIONS: Plasma levels of the BCAA leucine may be associated with higher BMD in older men and women. However, given lack of a significant association with hip fracture risk, further information is needed to determine whether BCAAs would be novel targets for osteoporosis therapies.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People with Type 2 Diabetes Mellitus. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (medRxiv, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2D) confers a two- to three-fold increased risk of cardiovascular disease (CVD). However, the mechanisms underlying increased CVD risk among people with T2D are only partially understood. We hypothesized that a genetic association study among people with T2D at risk for developing incident cardiovascular complications could provide insights into molecular genetic aspects underlying CVD. METHODS: From 16 studies of the Cohorts for Heart & Aging Research in Genomic Epidemiology (CHARGE) Consortium, we conducted a multi-ancestry time-to-event genome-wide association study (GWAS) for incident CVD among people with T2D using Cox proportional hazards models. Incident CVD was defined based on a composite of coronary artery disease (CAD), stroke, and cardiovascular death that occurred at least one year after the diagnosis of T2D. Cohort-level estimated effect sizes were combined using inverse variance weighted fixed effects meta-analysis. We also tested 204 known CAD variants for association with incident CVD among patients with T2D. RESULTS: A total of 49,230 participants with T2D were included in the analyses (31,118 European ancestries and 18,112 non-European ancestries) which consisted of 8,956 incident CVD cases over a range of mean follow-up duration between 3.2 and 33.7 years (event rate 18.2%). We identified three novel, distinct genetic loci for incident CVD among individuals with T2D that reached the threshold for genome-wide significance ( <5.0×10 ): rs147138607 (intergenic variant between and ) with a hazard ratio (HR) 1.23, 95% confidence interval (CI) 1.15 - 1.32, =3.6×10 , rs11444867 (intergenic variant near ) with HR 1.89, 95% CI 1.52 - 2.35, =9.9×10 , and rs335407 (intergenic variant between and ) HR 1.25, 95% CI 1.16 - 1.35, =1.5×10 . Among 204 known CAD loci, 32 were associated with incident CVD in people with T2D with <0.05, and 5 were significant after Bonferroni correction ( <0.00024, 0.05/204). A polygenic score of these 204 variants was significantly associated with incident CVD with HR 1.14 (95% CI 1.12 - 1.16) per 1 standard deviation increase ( =1.0×10 ). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D. CLINICAL PERSPECTIVE: We conducted a large-scale multi-ancestry time-to-event GWAS to identify genetic variants associated with CVD among people with T2D. Three variants were significantly associated with incident CVD in people with T2D: rs147138607 (intergenic variant between and ), rs11444867 (intergenic variant near ), and rs335407 (intergenic variant between and ). A polygenic score composed of known CAD variants identified in the general population was significantly associated with the risk of CVD in people with T2D. There are genetic risk factors specific to T2D that could at least partially explain the excess risk of CVD in people with T2D.In addition, we show that people with T2D have enrichment of known CAD association signals which could also explain the excess risk of CVD.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Whole genome sequence analysis of apparent treatment resistant hypertension status in participants from the Trans-Omics for Precision Medicine program. - Armstrong, Nicole D; Srinivasasainagendra, Vinodh; Ammous, Farah; Assimes, Themistocles L; Beitelshees, Amber L; Brody, Jennifer; Cade, Brian E; Ida Chen, Yii-Der; Chen, Han; de Vries, Paul S; Floyd, James S; Franceschini, Nora; et al. (Front Genet, 2023)
Apparent treatment-resistant hypertension (aTRH) is characterized by the use of four or more antihypertensive (AHT) classes to achieve blood pressure (BP) control. In the current study, we conducted single-variant and gene-based analyses of aTRH among individuals from 12 Trans-Omics for Precision Medicine cohorts with whole-genome sequencing data. Cases were defined as individuals treated for hypertension (HTN) taking three different AHT classes, with average systolic BP ≥ 140 or diastolic BP ≥ 90 mmHg, or four or more medications regardless of BP ( = 1,705). A normotensive control group was defined as individuals with BP < 140/90 mmHg ( = 22,079), not on AHT medication. A second control group comprised individuals who were treatment responsive on one AHT medication with BP < 140/ 90 mmHg ( = 5,424). Logistic regression with kinship adjustment using the Scalable and Accurate Implementation of Generalized mixed models (SAIGE) was performed, adjusting for age, sex, and genetic ancestry. We assessed variants using SKAT-O in rare-variant analyses. Single-variant and gene-based tests were conducted in a pooled multi-ethnicity stratum, as well as self-reported ethnic/racial strata (European and African American). One variant in the known HTN locus, , was a top finding in the multi-ethnic analysis ( = 8.23E-07) for the normotensive control group [rs12476527, odds ratio (95% confidence interval) = 0.80 (0.74-0.88)]. This variant was replicated in the Vanderbilt University Medical Center's DNA repository data. Aggregate gene-based signals included the genes and . Additional work validating these loci in larger, more diverse populations, is warranted to determine whether these regions influence the pathobiology of aTRH.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

Alzheimer's Disease Sequencing Project Release 4 Whole Genome Sequencing Dataset - Leung, Y. Y.; Lee, W. P.; Kuzma, A. B.; Nicaretta, H.; Valladares, O.; Gangadharan, P.; Qu, L.; Zhao, Y.; Ren, Y.; Cheng, P. L.; Kuksa, P. P.; Wang, H.; et al. (medRxiv, 2024)
The Alzheimer's Disease Sequencing Project (ADSP) is a national initiative to understand the genetic architecture of Alzheimer's Disease and Related Dementias (AD/ADRD) by sequencing whole genomes of affected participants and age-matched cognitive controls from diverse populations. The Genome Center for Alzheimer's Disease (GCAD) processed whole-genome sequencing data from 36,361 ADSP participants, including 35,014 genetically unique participants of which 45% are from non-European ancestry, across 17 cohorts in 14 countries in this fourth release (R4). This sequencing effort identified 387 million bi-allelic variants, 42 million short insertions/deletions, and 2.2 million structural variants. Annotations and quality control data are available for all variants and samples. Additionally, detailed phenotypes from 15,927 participants across 10 domains are also provided. A linkage disequilibrium panel was created using unrelated AD cases and controls. Researchers can access and analyze the genetic data via NIAGADS Data Sharing Service, the VariXam tool, or NIAGADS GenomicsDB.

Association of Coagulation Factor XI Level With Cardiovascular Events and Cardiac Function in Community-Dwelling Adults: From ARIC and CHS. - Ji, Yuekai; Zhang, Michael J; Wang, Wendy; Norby, Faye L; Eaton, Anne A; Inciardi, Riccardo M; Alonso, Alvaro; Sedaghat, Sanaz; Ganz, Peter; Van't Hof, Jeremy; Solomon, Scott D; Chaves, Paulo H M; et al. (Circulation, 2024)
BACKGROUND: Coagulation factor XI (FXI) inhibitors are a promising and novel class of anticoagulants, but a recent animal study found that FXI inhibition exacerbated diastolic dysfunction and heart failure (HF). In the ARIC study (Atherosclerosis Risk in Communities), we investigated whether plasma FXI level was associated with cardiovascular events and cardiac function. METHODS: ARIC was our primary analytic cohort. We included 4471 participants (median age, 75 years; 57% female; 17% Black) who attended visit 5 (2011-2013) with Somalogic-quantified plasma FXI levels and echocardiographic cardiac function. Prevalent HF and atrial fibrillation (AF) cases were defined as having HF or AF diagnosed at or before each participant's visit 5 exam date. Incident HF and AF events were ascertained through 2021. Associations were assessed using Cox, logistic, and linear regression models. Primary prospective associations were also validated in the CHS (Cardiovascular Health Study) using an orthogonal FXI assay (enzyme-linked immunosorbent assay). RESULTS: At ARIC visit 5, there were 665 and 419 participants with prevalent HF and AF, respectively. During a median follow-up of 9 years, there were 580 and 788 incident HF and AF events, respectively. Lower FXI level was associated prospectively with higher incidence of HF (hazard ratio [HR], 1.36 [for each 1-unit decrement of log-transformed FXI level] [95% CI, 1.01-1.83]) but not incident AF, and cross-sectionally with increased odds of AF (odds ratio [OR], 1.96 [95% CI, 1.23-3.07]) but not HF. In age-stratified analyses, decreased FXI was associated with higher incidence of HF in participants ≥75 years of age (HR, 1.57 [95% CI, 1.08-2.28]) but not <75 years of age (HR, 1.11 [95% CI, 0.68-1.79]). The inverse FXI-HF association was validated in CHS (HR, 1.18 [95% CI, 1.02-1.36]). At ARIC visit 5, lower FXI level was also associated with higher prevalence of diastolic dysfunction and worse E/A ratio, left atrial (LA) volume index, LA function, and left ventricular mass index, but not left ventricular ejection fraction or global longitudinal strain. CONCLUSIONS: Decreased FXI level is associated with greater incidence of HF, especially in older adults. It is also associated with prevalent AF, worse diastolic function, worse LA function, and greater LA size. More research is needed to assess potential unwanted effects of FXI inhibition on the risk of cardiovascular events and cardiac function.

Association of Fibroblast Growth Factor 23 and Cardiac Mechanics in the Cardiovascular Health Study. - Jain, Keertana; Katz, Ronit; Isakova, Tamara; Kizer, Jorge R; Sharma, Shilpa; Psaty, Bruce M; Shah, Sanjiv; Ix, Joachim; Mehta, Rupal (Kidney360, 2024)
BACKGROUND: Elevated levels of fibroblast growth factor 23 (FGF23) are associated with left ventricular hypertrophy and heart failure (HF) in individuals with and without kidney disease. Prior studies investigated the association of FGF23 and structural cardiac changes using conventional echocardiography, which is limited in its ability to detect early cardiac dysfunction. We investigated the relationship between FGF23 levels and cardiac dynamics using two-dimensional speckle tracking echocardiography (2D-STE), a novel imaging modality. METHODS: This was a cross-sectional analysis of data from the Cardiovascular Health Study, an ongoing prospective, population-based cohort study. The study population included 506 participants from CHS with available c-terminal (cFGF23) and intact FGF23 (iFGF23) measurements from 1996-1997 and 2D-STE images from 1994-1995. Forty two percent of the study population had CKD, defined as an eGFR < 60 ml/min/1.73m2, and the mean eGFR was 63 ml/min/1.73m2. The primary exposures were cFGF23 and iFGF23. The primary outcomes were six 2D-STE parameters performed at the 1994-1995 study visit. Linear regression models were used to examine the independent associations of FGF23 with six cardiac 2D-STE indices adjusting for demographics, cardiovascular risk factors, markers of kidney disease severity, and inflammation. RESULTS: cFGF23 levels were moderately correlated with iFGF23 levels in the CHS population. In fully adjusted models, cFGF23 was associated with left atrial dysfunction, but no other cardiac imaging parameter (β estimate -2.47; 95% Confidence Interval -4.68, -0.25; Table 2 ). iFGF23 was not associated with any of the six 2D-STE indices. Limitations include small sample size and noncurrent FGF23 measurements and 2D-STE imaging. CONCLUSIONS: In a limited sample of individuals enrolled in the CHS with c- and i-FGF23 measurements, we did not find consistent associations between FGF23 levels and 2D-STE parameters. Further investigations in a larger population with concurrent 2D-STE are needed to better understand the associations of FGF23 with early changes in cardiac mechanics.

Association of serum levels of phenylalanine and tyrosine with hip fractures and frailty in older adults: The cardiovascular health study. - Carbone, Laura; Bůzková, Petra; Robbins, John A; Fink, Howard A; Barzilay, Joshua I; Elam, Rachel E; Isales, Carlos (Arch Osteoporos, 2024)
UNLABELLED: This study examined if the amino acids phenylalanine or tyrosine contribute to risk of hip fracture or frailty in older adults. We determined that neither phenylalanine nor tyrosine are important predictors of hip fracture or frailty. We suggest advice on protein intake for skeletal health consider specific amino acid composition. PURPOSE: Protein is essential for skeletal health, but the specific amino acid compositions of protein may have differential associations with fracture risk. The aim of this study was to determine the association of serum levels of the aromatic amino acids phenylalanine and tyrosine with risk for incident hip fractures over twelve years of follow-up and cross sectional associations with frailty. METHODS: We included 131 older men and women from the Cardiovascular Health Study (CHS) who sustained a hip fracture over twelve years of follow-up and 131 men and women without an incident hip fracture over this same period of time. 42% of this cohort were men and 95% were Caucasian. Weighted multivariable Cox hazards molecules were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of incident hip fracture associated with a one standard deviation (SD) higher serum level of phenylalanine or tyrosine. Relative risk regression was used to determine the cross-sectional association of these amino acids with Freid's frailty index. RESULTS: Neither serum levels of phenylalanine (HR 0.85 (95% CI 0.62-1.16) or tyrosine (HR 0.82 (95% CI 0.62-1.1) were significantly associated with incident hip fractures or cross sectionally with frailty (frail compared with prefrail/not frail) (HR 0.92 (95% CI 0.48-1.76) and HR (0.86 (95% CI 0.46-1.61) respectively. CONCLUSION: Phenylalanine and tyrosine are not significant contributors to hip fractures or frailty in older men and women.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Frail Elderly; Frailty; Hip Fractures; Humans; Male; Phenylalanine; Risk Factors; Tyrosine

{Cohort Profile: Dementia Risk Prediction Project (DRPP) - Krefman, A. E.; Stephen, J.; Carolan, P.; Sedaghat, S.; Mansolf, M.; Soumare, A.; Gross, A. L.; Aiello, A. E.; Singh-Manoux, A.; Ikram, M. A.; Helmer, C.; Tzourio, C.; et al. (Int J Epidemiol, 2024)

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.

{Genetic associations with dementia-related proteinopathy: Application of item response theory - Katsumata, Y.; Fardo, D. W.; Shade, L. M. P.; Wu, X.; Karanth, S. D.; Hohman, T. J.; Schneider, J. A.; Bennett, D. A.; Farfel, J. M.; Gauthreaux, K.; Mock, C.; Kukull, W. A.; et al. (Alzheimers Dement, 2024)
Although dementia-related proteinopathy has a strong negative impact on public health, and is highly heritable, understanding of the related genetic architecture is incomplete.\ -synuclein, and TDP-43.\ -synuclein/Lewy bodies. Novel suggestive proteinopathy-linked alleles were also discovered, including several (SDHAF1, TMEM68, and ARHGEF28) with colocalization analyses and/or high degrees of biologic credibility.\ A novel methodology using GPCM enabled insights into gene candidates for driving misfolded proteinopathies.\ Latent factor scores for proteinopathies were estimated using a generalized partial credit model. The three latent continuous scores corresponded well with proteinopathy severity. Novel genes associated with proteinopathies were identified. Several genes had high degrees of biologic credibility for dementia risk factors.

Genetic Complexities of Cerebral Small Vessel Disease, Blood Pressure, and Dementia. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Vascular disease is a treatable contributor to dementia risk, but the role of specific markers remains unclear, making prevention strategies uncertain. OBJECTIVE: To investigate the causal association between white matter hyperintensity (WMH) burden, clinical stroke, blood pressure (BP), and dementia risk, while accounting for potential epidemiologic biases. DESIGN, SETTING, AND PARTICIPANTS: This study first examined the association of genetically determined WMH burden, stroke, and BP levels with Alzheimer disease (AD) in a 2-sample mendelian randomization (2SMR) framework. Second, using population-based studies (1979-2018) with prospective dementia surveillance, the genetic association of WMH, stroke, and BP with incident all-cause dementia was examined. Data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined WMH burden and BP levels, as well as genetic liability to stroke derived from genome-wide association studies (GWASs) in European ancestry populations. MAIN OUTCOMES AND MEASURES: The association of genetic instruments for WMH, stroke, and BP with dementia was studied using GWASs of AD (defined clinically and additionally meta-analyzed including both clinically diagnosed AD and AD defined based on parental history [AD-meta]) for 2SMR and incident all-cause dementia for longitudinal analyses. RESULTS: In 2SMR (summary statistics-based) analyses using AD GWASs with up to 75 024 AD cases (mean [SD] age at AD onset, 75.5 [4.4] years; 56.9% women), larger WMH burden showed evidence for a causal association with increased risk of AD (odds ratio [OR], 1.43; 95% CI, 1.10-1.86; P = .007, per unit increase in WMH risk alleles) and AD-meta (OR, 1.19; 95% CI, 1.06-1.34; P = .008), after accounting for pulse pressure for the former. Blood pressure traits showed evidence for a protective association with AD, with evidence for confounding by shared genetic instruments. In the longitudinal (individual-level data) analyses involving 10 699 incident all-cause dementia cases (mean [SD] age at dementia diagnosis, 74.4 [9.1] years; 55.4% women), no significant association was observed between larger WMH burden and incident all-cause dementia (hazard ratio [HR], 1.02; 95% CI, 1.00-1.04; P = .07). Although all exposures were associated with mortality, with the strongest association observed for systolic BP (HR, 1.04; 95% CI, 1.03-1.06; P = 1.9 × 10-14), there was no evidence for selective survival bias during follow-up using illness-death models. In secondary analyses using polygenic scores, the association of genetic liability to stroke, but not genetically determined WMH, with dementia outcomes was attenuated after adjusting for interim stroke. CONCLUSIONS: These findings suggest that WMH is a primary vascular factor associated with dementia risk, emphasizing its significance in preventive strategies for dementia. Future studies are warranted to examine whether this finding can be generalized to non-European populations.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Blood Pressure; Cerebral Small Vessel Diseases; Dementia; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Mendelian Randomization Analysis; Prospective Studies; Risk Factors; Stroke

The Genetic Determinants and Genomic Consequences of Non-Leukemogenic Somatic Point Mutations. - Weinstock, Joshua S; Chaudhry, Sharjeel A; Ioannou, Maria; Viskadourou, Maria; Reventun, Paula; Jakubek, Yasminka A; Alexander Liggett, L; Laurie, Cecelia; Broome, Jai G; Khan, Alyna; Taylor, Kent D; Guo, Xiuqing; et al. (medRxiv, 2024)
Clonal hematopoiesis (CH) is defined by the expansion of a lineage of genetically identical cells in blood. Genetic lesions that confer a fitness advantage, such as point mutations or mosaic chromosomal alterations (mCAs) in genes associated with hematologic malignancy, are frequent mediators of CH. However, recent analyses of both single cell-derived colonies of hematopoietic cells and population sequencing cohorts have revealed CH frequently occurs in the absence of known driver genetic lesions. To characterize CH without known driver genetic lesions, we used 51,399 deeply sequenced whole genomes from the NHLBI TOPMed sequencing initiative to perform simultaneous germline and somatic mutation analyses among individuals without leukemogenic point mutations (LPM), which we term CH-LPMneg. We quantified CH by estimating the total mutation burden. Because estimating somatic mutation burden without a paired-tissue sample is challenging, we developed a novel statistical method, the Genomic and Epigenomic informed Mutation (GEM) rate, that uses external genomic and epigenomic data sources to distinguish artifactual signals from true somatic mutations. We performed a genome-wide association study of GEM to discover the germline determinants of CH-LPMneg. After fine-mapping and variant-to-gene analyses, we identified seven genes associated with CH-LPMneg ( , , ), and one locus associated with a sex-associated mutation pathway ( . We performed a secondary analysis excluding individuals with mCAs, finding that the genetic architecture was largely unaffected by their inclusion. Functional analyses of and implicated altered HSC self-renewal and proliferation as the primary mediator of mutation burden in blood. We then performed comprehensive multi-tissue transcriptomic analyses, finding that the expression levels of 404 genes are associated with GEM. Finally, we performed phenotypic association meta-analyses across four cohorts, finding that GEM is associated with increased white blood cell count and increased risk for incident peripheral artery disease, but is not significantly associated with incident stroke or coronary disease events. Overall, we develop GEM for quantifying mutation burden from WGS without a paired-tissue sample and use GEM to discover the genetic, genomic, and phenotypic correlates of CH-LPMneg.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

Genome-wide analysis in over 1 million individuals of European ancestry yields improved polygenic risk scores for blood pressure traits. - Keaton, Jacob M; Kamali, Zoha; Xie, Tian; Vaez, Ahmad; Williams, Ariel; Goleva, Slavina B; Ani, Alireza; Evangelou, Evangelos; Hellwege, Jacklyn N; Yengo, Loic; Young, William J; Traylor, Matthew; et al. (Nat Genet, 2024)
Hypertension affects more than one billion people worldwide. Here we identify 113 novel loci, reporting a total of 2,103 independent genetic signals (P < 5 × 10) from the largest single-stage blood pressure (BP) genome-wide association study to date (n = 1,028,980 European individuals). These associations explain more than 60% of single nucleotide polymorphism-based BP heritability. Comparing top versus bottom deciles of polygenic risk scores (PRSs) reveals clinically meaningful differences in BP (16.9 mmHg systolic BP, 95% CI, 15.5-18.2 mmHg, P = 2.22 × 10) and more than a sevenfold higher odds of hypertension risk (odds ratio, 7.33; 95% CI, 5.54-9.70; P = 4.13 × 10) in an independent dataset. Adding PRS into hypertension-prediction models increased the area under the receiver operating characteristic curve (AUROC) from 0.791 (95% CI, 0.781-0.801) to 0.826 (95% CI, 0.817-0.836, ∆AUROC, 0.035, P = 1.98 × 10). We compare the 2,103 loci results in non-European ancestries and show significant PRS associations in a large African-American sample. Secondary analyses implicate 500 genes previously unreported for BP. Our study highlights the role of increasingly large genomic studies for precision health research.

Iron Deficiency and Incident Heart Failure in Older Community-Dwelling Individuals. - Sharma, Shilpa; Katz, Ronit; Chaves, Paulo H M; Hoofnagle, Andrew N; Kizer, Jorge R; Bansal, Nisha; Ganz, Tomas; Ix, Joachim H (ESC Heart Fail, 2024)
AIMS: Among persons with prevalent heart failure (HF), iron deficiency has been linked to HF admissions, and intravenous iron replacement improves HF outcomes. Recent studies in persons with chronic kidney disease (CKD) demonstrate that iron deficiency is associated with incident HF. This study aimed to determine the relationship of iron status with incident HF in community-dwelling older adults irrespective of their kidney function. METHODS: In this case-cohort study, 1,006 Cardiovascular Health Study participants (785 from the random sub-cohort [including 193 HF cases] and 221 additional HF cases [N = 414 total HF cases]) aged ≥ 65 years without HF (41% with CKD), we used weighted Cox models to evaluate associations of iron status with incident HF. Participants were categorized based on quartiles of transferrin saturation and ferritin as "iron replete" (27.3%), "functional iron deficiency" (7.7%), "iron deficiency" (11.8%), "mixed iron deficiency" (5.6%), "high iron" (9.3%) and "non-classified" (38.1%), consistent with prior studies. RESULTS: Compared to older persons who were iron replete, those with iron deficiency were at higher risk of incident HF (HR 1.47; 1.02-2.11) in models adjusting for demographics, HF risk factors, and estimated glomerular filtration rate. Other iron categories did not associate with incident HF. The relationship of iron deficiency with incident HF did not differ by CKD status (interaction P value 0.2). CONCLUSIONS: Among community-dwelling elders, iron deficiency is independently associated with incident HF, an association that was similar irrespective of CKD status. Our findings support conduct of clinical trials of iron replacement for prevention of HF in older adults with iron deficiency.

A multi-cohort genome-wide association study in African ancestry individuals reveals risk loci for primary open-angle glaucoma. - Verma, Shefali S; Gudiseva, Harini V; Chavali, Venkata R M; Salowe, Rebecca J; Bradford, Yuki; Guare, Lindsay; Lucas, Anastasia; Collins, David W; Vrathasha, Vrathasha; Nair, Rohini M; Rathi, Sonika; Zhao, Bingxin; et al. (Cell, 2024)
Primary open-angle glaucoma (POAG), the leading cause of irreversible blindness worldwide, disproportionately affects individuals of African ancestry. We conducted a genome-wide association study (GWAS) for POAG in 11,275 individuals of African ancestry (6,003 cases; 5,272 controls). We detected 46 risk loci associated with POAG at genome-wide significance. Replication and post-GWAS analyses, including functionally informed fine-mapping, multiple trait co-localization, and in silico validation, implicated two previously undescribed variants (rs1666698 mapping to DBF4P2; rs34957764 mapping to ROCK1P1) and one previously associated variant (rs11824032 mapping to ARHGEF12) as likely causal. For individuals of African ancestry, a polygenic risk score (PRS) for POAG from our mega-analysis (African ancestry individuals) outperformed a PRS from summary statistics of a much larger GWAS derived from European ancestry individuals. This study quantifies the genetic architecture similarities and differences between African and non-African ancestry populations for this blinding disease.
Keywords: Black People; Genetic Predisposition to Disease; Genome-Wide Association Study; Glaucoma, Open-Angle; Humans; Polymorphism, Single Nucleotide

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

{Multi-trait analysis characterizes the genetics of thyroid function and identifies causal associations with clinical implications - Sterenborg, R. B. T. M.; Steinbrenner, I.; Li, Y.; Bujnis, M. N.; Naito, T.; Marouli, E.; Galesloot, T. E.; Babajide, O.; Andreasen, L.; Astrup, A.; svold, B. O.; Bandinelli, S.; et al. (Nat Commun, 2024)
T3, whereas the FT4 associations represent the thyroid hormone metabolism. Polygenic risk score and Mendelian randomization analyses showed the effects of genetically determined variation in thyroid function on various clinical outcomes, including cardiovascular risk factors and diseases, autoimmune diseases, and cancer. In conclusion, our results improve the understanding of thyroid hormone physiology and highlight the pleiotropic effects of thyroid function on various diseases.

NIAGADS: A Comprehensive National Data Repository for Alzheimer's Disease and Related Dementia Genetics and Genomics Research - Kuzma, A.; Valladares, O.; Greenfest-Allen, E.; Nicaretta, H.; Kirsch, M.; Ren, Y.; Katanic, Z.; White, H.; Wilk, A.; Bass, L.; Brettschneider, J.; Carter, L.; et al. (medRxiv, 2024)
NIAGADS is the National Institute on Aging (NIA) designated national data repository for human genetics research on Alzheimer's Disease and related dementia (ADRD). NIAGADS maintains a high-quality data collection for ADRD genetic/genomic research and supports genetics data production and analysis. NIAGADS hosts whole genome and exome sequence data from the Alzheimer's Disease Sequencing Project (ADSP) and other genotype/phenotype data, encompassing 209,000 samples. NIAGADS shares these data with hundreds of research groups around the world via the Data Sharing Service, a FISMA moderate compliant cloud-based platform that fully supports the NIH Genome Data Sharing Policy. NIAGADS Open Access consists of multiple knowledge bases with genome-wide association summary statistics and rich annotations on the biological significance of genetic variants and genes across the human genome. NIAGADS stands as a keystone in promoting collaborations to advance the understanding and treatment of Alzheimer's disease.

Proteogenomics in cerebrospinal fluid and plasma reveals new biological fingerprint of cerebral small vessel disease. - Debette, Stephanie; Caro, Ilana; Western, Daniel; Namba, Shinichi; Sun, Na; Kawaguchi, Shuji; He, Yunye; Fujita, Masashi; Roshchupkin, Gennady; D'Aoust, Tim; Duperron, Marie-Gabrielle; Sargurupremraj, Murali; et al. (Res Sq, 2024)
Cerebral small vessel disease (cSVD) is a leading cause of stroke and dementia with no specific mechanism-based treatment. We used Mendelian randomization to combine a unique cerebrospinal fluid (CSF) and plasma pQTL resource with the latest European-ancestry GWAS of MRI-markers of cSVD (white matter hyperintensities, perivascular spaces). We describe a new biological fingerprint of 49 protein-cSVD associations, predominantly in the CSF. We implemented a multipronged follow-up, across fluids, platforms, and ancestries (Europeans and East-Asian), including testing associations of direct plasma protein measurements with MRI-cSVD. We highlight 16 proteins robustly associated in both CSF and plasma, with 24/4 proteins identified in CSF/plasma only. cSVD-proteins were enriched in extracellular matrix and immune response pathways, and in genes enriched in microglia and specific microglial states (integration with single-nucleus RNA sequencing). Immune-related proteins were associated with MRI-cSVD already at age twenty. Half of cSVD-proteins were associated with stroke, dementia, or both, and seven cSVD-proteins are targets for known drugs (used for other indications in directions compatible with beneficial therapeutic effects. This first cSVD proteogenomic signature opens new avenues for biomarker and therapeutic developments.

Rare variant contribution to the heritability of coronary artery disease. - Rocheleau, Ghislain; Clarke, Shoa L; Auguste, Gaëlle; Hasbani, Natalie R; Morrison, Alanna C; Heath, Adam S; Bielak, Lawrence F; Iyer, Kruthika R; Young, Erica P; Stitziel, Nathan O; Jun, Goo; Laurie, Cecelia; et al. (Nat Commun, 2024)
Whole genome sequences (WGS) enable discovery of rare variants which may contribute to missing heritability of coronary artery disease (CAD). To measure their contribution, we apply the GREML-LDMS-I approach to WGS of 4949 cases and 17,494 controls of European ancestry from the NHLBI TOPMed program. We estimate CAD heritability at 34.3% assuming a prevalence of 8.2%. Ultra-rare (minor allele frequency ≤ 0.1%) variants with low linkage disequilibrium (LD) score contribute ~50% of the heritability. We also investigate CAD heritability enrichment using a diverse set of functional annotations: i) constraint; ii) predicted protein-altering impact; iii) cis-regulatory elements from a cell-specific chromatin atlas of the human coronary; and iv) annotation principal components representing a wide range of functional processes. We observe marked enrichment of CAD heritability for most functional annotations. These results reveal the predominant role of ultra-rare variants in low LD on the heritability of CAD. Moreover, they highlight several functional processes including cell type-specific regulatory mechanisms as key drivers of CAD genetic risk.
Keywords: Case-Control Studies; Coronary Artery Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; White People; Whole Genome Sequencing

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

Single-Ancestry versus Multi-Ancestry Polygenic Risk Scores for CKD in Black American Populations. - Jones, Alana C; Patki, Amit; Srinivasasainagendra, Vinodh; Tiwari, Hemant K; Armstrong, Nicole D; Chaudhary, Ninad S; Limdi, Nita A; Hidalgo, Bertha A; Davis, Brittney; Cimino, James J; Khan, Atlas; Kiryluk, Krzysztof; et al. (J Am Soc Nephrol, 2024)

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People With Type 2 Diabetes. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (Diabetes Care, 2024)
OBJECTIVE: To identify genetic risk factors for incident cardiovascular disease (CVD) among people with type 2 diabetes (T2D). RESEARCH DESIGN AND METHODS: We conducted a multiancestry time-to-event genome-wide association study for incident CVD among people with T2D. We also tested 204 known coronary artery disease (CAD) variants for association with incident CVD. RESULTS: Among 49,230 participants with T2D, 8,956 had incident CVD events (event rate 18.2%). We identified three novel genetic loci for incident CVD: rs147138607 (near CACNA1E/ZNF648, hazard ratio [HR] 1.23, P = 3.6 × 10-9), rs11444867 (near HS3ST1, HR 1.89, P = 9.9 × 10-9), and rs335407 (near TFB1M/NOX3, HR 1.25, P = 1.5 × 10-8). Among 204 known CAD loci, 5 were associated with incident CVD in T2D (multiple comparison-adjusted P < 0.00024, 0.05/204). A standardized polygenic score of these 204 variants was associated with incident CVD with HR 1.14 (P = 1.0 × 10-16). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D.

Transcriptome-wide association study and Mendelian randomization in pancreatic cancer identifies susceptibility genes and causal relationships with type 2 diabetes and venous thromboembolism. - Tan, Marcus C B; Isom, Chelsea A; Liu, Yangzi; Trégouët, David-Alexandre; Wu, Lang; Zhou, Dan; Gamazon, Eric R (EBioMedicine, 2024)
BACKGROUND: Two important questions regarding the genetics of pancreatic adenocarcinoma (PDAC) are 1. Which germline genetic variants influence the incidence of this cancer; and 2. Whether PDAC causally predisposes to associated non-malignant phenotypes, such as type 2 diabetes (T2D) and venous thromboembolism (VTE). METHODS: In this study of 8803 patients with PDAC and 67,523 controls, we first performed a large-scale transcriptome-wide association study to investigate the association between genetically determined gene expression in normal pancreas tissue and PDAC risk. Secondly, we used Mendelian Randomization (MR) to analyse the causal relationships among PDAC, T2D (74,124 cases and 824,006 controls) and VTE (30,234 cases and 172,122 controls). FINDINGS: Sixteen genes showed an association with PDAC risk (FDR <0.10), including six genes not yet reported for PDAC risk (PPIP5K2, TFR2, HNF4G, LRRC10B, PRC1 and FBXL20) and ten previously reported genes (INHBA, SMC2, ABO, PDX1, MTMR6, ACOT2, PGAP3, STARD3, GSDMB, ADAM33). MR provided support for a causal effect of PDAC on T2D using genetic instruments in the HNF4G and PDX1 loci, and unidirectional causality of VTE on PDAC involving the ABO locus (OR 2.12, P < 1e). No evidence of a causal effect of PDAC on VTE was found. INTERPRETATION: These analyses identified candidate susceptibility genes and disease relationships for PDAC that warrant further investigation. HNF4G and PDX1 may induce PDAC-associated diabetes, whereas ABO may induce the causative effect of VTE on PDAC. FUNDING: National Institutes of Health (USA).
Keywords: Diabetes Mellitus, Type 2; Female; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Mendelian Randomization Analysis; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Transcriptome; Venous Thromboembolism

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins

Association Between Cigarette Smoking and Subclinical Markers of Cardiovascular Harm. - Yao, Zhiqi; Tasdighi, Erfan; Dardari, Zeina A; Jha, Kunal K; Osuji, Ngozi; Rajan, Tanuja; Boakye, Ellen; Rodriguez, Carlos J; Matsushita, Kunihiro; Simonsick, Eleanor M; Lima, João A C; Widome, Rachel; et al. (J Am Coll Cardiol, 2025)
BACKGROUND: Cigarette smoking is a strong risk factor for cardiovascular harm. OBJECTIVES: The study sought to explore the detailed relationships between smoking intensity, pack-years, and time since cessation with inflammation, thrombosis, and subclinical atherosclerosis markers of cardiovascular harm. METHODS: We included 182,364 participants (mean age 58.2 years, 69.0% female) from 22 cohorts of the Cross Cohort Collaboration with self-reported smoking status, including smoking intensity and/or pack-years, and concurrent subclinical marker measurements. Markers were categorized into 3 domains: inflammation (high-sensitivity C-reactive protein, interleukin-6, glycoprotein acetylation), thrombosis (fibrinogen, D-dimer), and subclinical atherosclerosis (coronary artery calcium, carotid intima-media thickness, carotid plaque, and ankle-brachial index). Utilizing multivariate regression models and restricted cubic splines, we assessed associations of smoking status, intensity, pack-years, time since cessation, and subclinical markers. RESULTS: A total of 15.3% of participants currently smoke (mean 16.7 cigarettes/day, mean 30.0 pack-years), and 34.6% of participants formerly smoked (median 19.0 years since quitting, mean 22.4 pack-years). Participants with a history of smoking showed higher levels of all subclinical markers compared with those who have never smoked, with stronger associations observed in those currently smoke. Among participants who currently smoke, smoking intensity showed a clear dose-response relationship with all markers, except for D-dimer, specifically with incremental 1% to 9% higher levels of subclinical markers per 10 cigarettes. After 20 cigarettes, the patterns appeared to plateau for blood markers, while they continued to increase for atherosclerosis markers. Among those who have ever smoked, robust dose-response relationships were observed for pack-years with all subclinical markers, with incremental 1% to 9% higher levels per 10 pack-years. The dose-response effects persisted after 20 pack-years for all markers, though with a milder slope. Among participants who smoked formerly, there were substantially lower levels of biomarkers with longer time since quitting, and most markers were not different compared with those who have never smoked by 30 years, except for the coronary artery calcium score, which remained 19% higher even beyond quitting after 30 years. CONCLUSIONS: Smoking-relevant parameters show strong and dose-response relationships across 3 domains of subclinical markers of cardiovascular harm. The sensitivity of the tested subclinical markers to small increments in cigarette exposure suggests potential value in the regulation of new and existing tobacco products.
Keywords: Aged; Atherosclerosis; Biomarkers; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cigarette Smoking; Cohort Studies; Female; Humans; Male; Middle Aged; Risk Factors

Cardiovascular Risk Factors and Genetic Risk in Transthyretin V142I Carriers. - Shetty, Naman S; Gaonkar, Mokshad; Pampana, Akhil; Patel, Nirav; Morrison, Alanna C; Reiner, Alexander P; Carson, April P; Yu, Bing; Psaty, Bruce M; Kooperberg, Charles; Fatkin, Diane; Boerwinkle, Eric; et al. (JACC Heart Fail, 2025)
BACKGROUND: Nearly 3% to 4% of Black individuals in the United States carry the transthyretin V142I variant, which increases their risk of heart failure. However, the role of cardiovascular (CV) risk factors (RFs) in influencing the risk of clinical outcomes among V142I variant carriers is unknown. OBJECTIVES: This study aimed to assess the impact of CV RFs on the risk of heart failure in V142I carriers. METHODS: This study included self-identified Black individuals without prevalent heart failure from 6 TOPMed (Trans-Omics for Precision Medicine) cohorts, the REGARDS (Reasons for Geographic And Racial Differences in Stroke) study, and the All of Us Research Program. The cohort was stratified based on the V142I genotype and the number of CV RFs (hypertension, diabetes, obesity, and hypercholesterolemia). Adjusted Cox models were used to assess the association of heart failure with the V142I genotype and CV RF profile, taking noncarriers with a favorable CV RF profile as reference. RESULTS: The cross-sectional analysis, including 1,625 V142I carriers among 48,365 Black individuals, found that the prevalence of CV RFs did not vary by V142I carrier status. In the longitudinal analysis, there were 587 (3.2%) V142I carriers among 18,407 Black individuals (median age: 60 years [Q1-Q3: 52-68 years], 63.0% female). Among carriers, the heart failure risk was attenuated with a favorable (0 or 1 RF) CV RF profile (adjusted HR: 2.26; 95% CI: 1.58-3.23) compared with an unfavorable (3 or 4 RFs) CV RF profile (adjusted HR: 4.14; 95% CI: 2.79-6.14). CONCLUSIONS: A favorable CV RF profile lowers but does not abrogate V142I variant-associated heart failure risk. This study highlights the importance of having a favorable CV RF profile among V142I carriers for risk reduction of heart failure.
Keywords: Aged; Black or African American; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Mellitus; Female; Genotype; Heart Disease Risk Factors; Heart Failure; Heterozygote; Humans; Hypercholesterolemia; Hypertension; Male; Middle Aged; Obesity; Prealbumin; Risk Factors; United States

Circulating non-esterified fatty acids, risk of dementia and cognitive decline: The cardiovascular health study and multi-ethnic study of atherosclerosis. - Moseholm, Kristine F; Jensen, Majken K; Bůzková, Petra; Aroner, Sarah A; Fitzpatrick, Annette L; Longstreth, W T; Lopez, Oscar; Siscovick, David S; Kizer, Jorge R; Ix, Joachim H; Hughes, Timothy M; Hayden, Kathleen M; et al. (Neurobiol Aging, 2025)
Circulating non-esterified fatty acids (NEFAs) have toxic effects on a variety of organs central to cardiometabolic disease and can cross the blood-brain barrier. Whether NEFAs associate with cognitive decline or dementia remains unknown. Circulating total NEFA levels were measured in 3242 participants without dementia among older adults of the Cardiovascular Health Study (CHS) and related to adjudicated dementia over 6 years (n = 456 cases) and annually assessed cognitive decline. For confirmation, we related circulating NEFAs to cognition assessed 10 years later among 4361 participants in the Multi-Ethnic Study of Atherosclerosis (MESA). In CHS participants, each SD higher NEFA levels were associated with a hazard ratio (HR) for all-cause dementia of 1.11 (95 % CI: 1.01; 1.22). Baseline NEFA levels were also associated with more rapid decline in cognition over 6 years of follow-up. In MESA, circulating NEFA measurements were associated with lower cognitive scores measured 10 years later.'
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognitive Dysfunction; Cohort Studies; Dementia; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Male; Middle Aged; Risk; Risk Factors

Clinical and Imaging Markers of Cardiac Function and Brain Health: A Meta-Analysis of Community-Based Studies. - Yaqub, Amber; Bis, Joshua C; Frenzel, Stefan; Koini, Marisa; Mbangdadji, Djass; Peloso, Gina M; Talluri, Rajesh; Alonso, Alvaro; Bahls, Martin; Bülow, Robin; Dörr, Marcus; Felix, Stephan; et al. (Neurology, 2025)
BACKGROUND AND OBJECTIVES: Cardiac dysfunction and heart failure are linked to cognitive impairment, but the underlying brain pathology remains undetermined. We investigated associations between cardiac function (measured by echocardiography or cardiac MRI), clinical heart failure, and structural markers on brain MRI, including volumes of gray and white matter (WM), the hippocampus, and white matter hyperintensities (WMHs). METHODS: We leverage data from 7 prospective, community-based cohorts across Europe and the United States, all part of the Cross-Cohort Collaboration. The included cohorts were the Age, Gene/Environment Susceptibility-Reykjavik Study, Atherosclerosis Risk in Communities study, Austrian Stroke Prevention Study, Cardiovascular Health Study, Framingham Heart Study, Rotterdam Study, and Study of Health in Pomerania (SHIP-START and SHIP-TREND). Each cohort performed cross-sectional multivariable linear regression analyses, after which estimates were pooled through random-effects meta-analysis. Heterogeneity was assessed by the index (%). RESULTS: Among 10,889 participants (mean age: 66.8 years, range 52.0-76.0; 56.7% women), markers of systolic dysfunction were consistently associated with smaller total brain volume (TBV) (e.g., adjusted standardized mean difference for moderate to severe dysfunction -0.19, 95% CI -0.31 to -0.07, = 20%). Impaired relaxation and restrictive diastolic dysfunction were also associated with smaller TBV (e.g., for impaired relaxation -0.08, 95% CI -0.15 to -0.01, = 32%) and hippocampal volume (-0.18, 95% CI -0.33 to -0.03, = 0%), with similar results for the E/A-ratio. Systolic and diastolic dysfunction was not consistently associated with volume of WMHs. Among 5 cohorts with available data, 302 (3.4%) participants had clinical heart failure, which was associated with smaller brain volumes, particularly in the hippocampus (-0.13, 95% CI -0.23 to -0.02, = 1%). DISCUSSION: In this large study among community-dwelling adults, subclinical cardiac dysfunction was associated with brain imaging markers of neurodegeneration. These findings encourage longitudinal investigations on the effect of maintaining cardiac function on brain health.
Keywords: Aged; Brain; Cohort Studies; Echocardiography; Female; Heart Failure; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies; White Matter

Genome-wide association study meta-analysis provides insights into the etiology of heart failure and its subtypes. - Henry, Albert; Mo, Xiaodong; Finan, Chris; Chaffin, Mark D; Speed, Doug; Issa, Hanane; Denaxas, Spiros; Ware, James S; Zheng, Sean L; Mälarstig, Anders; Gratton, Jasmine; Bond, Isabelle; et al. (Nat Genet, 2025)
Heart failure (HF) is a major contributor to global morbidity and mortality. While distinct clinical subtypes, defined by etiology and left ventricular ejection fraction, are well recognized, their genetic determinants remain inadequately understood. In this study, we report a genome-wide association study of HF and its subtypes in a sample of 1.9 million individuals. A total of 153,174 individuals had HF, of whom 44,012 had a nonischemic etiology (ni-HF). A subset of patients with ni-HF were stratified based on left ventricular systolic function, where data were available, identifying 5,406 individuals with reduced ejection fraction and 3,841 with preserved ejection fraction. We identify 66 genetic loci associated with HF and its subtypes, 37 of which have not previously been reported. Using functionally informed gene prioritization methods, we predict effector genes for each identified locus, and map these to etiologic disease clusters through phenome-wide association analysis, network analysis and colocalization. Through heritability enrichment analysis, we highlight the role of extracardiac tissues in disease etiology. We then examine the differential associations of upstream risk factors with HF subtypes using Mendelian randomization. These findings extend our understanding of the mechanisms underlying HF etiology and may inform future approaches to prevention and treatment.

Genomic and phenotypic correlates of mosaic loss of chromosome Y in blood. - Jakubek, Yasminka A; Ma, Xiaolong; Stilp, Adrienne M; Yu, Fulong; Bacon, Jason; Wong, Justin W; Aguet, Francois; Ardlie, Kristin; Arnett, Donna K; Barnes, Kathleen; Bis, Joshua C; Blackwell, Tom; et al. (Am J Hum Genet, 2025)
Mosaic loss of Y (mLOY) is the most common somatic chromosomal alteration detected in human blood. The presence of mLOY is associated with altered blood cell counts and increased risk of Alzheimer disease, solid tumors, and other age-related diseases. We sought to gain a better understanding of genetic drivers and associated phenotypes of mLOY through analyses of whole-genome sequencing (WGS) of a large set of genetically diverse males from the Trans-Omics for Precision Medicine (TOPMed) program. We show that haplotype-based calling methods can be used with WGS data to successfully identify mLOY events. This approach enabled us to identify differences in mLOY frequencies across populations defined by genetic similarity, revealing a higher frequency of mLOY in the European (EUR) ancestry group compared to other ancestries. We identify multiple loci associated with mLOY susceptibility and show that subsets of human hematopoietic stem cells are enriched for the activity of mLOY susceptibility variants. Finally, we found that certain alleles on chromosome Y are more likely to be lost than others in detectable mLOY clones.
Keywords: Alleles; Chromosome Deletion; Chromosomes, Human, Y; Genomics; Haplotypes; Humans; Male; Mosaicism; Phenotype; Whole Genome Sequencing

The impact of common and rare genetic variants on bradyarrhythmia development. - Weng, Lu-Chen; Rämö, Joel T; Jurgens, Sean J; Khurshid, Shaan; Chaffin, Mark; Hall, Amelia Weber; Morrill, Valerie N; Wang, Xin; Nauffal, Victor; Sun, Yan V; Beer, Dominik; Lee, Simon; et al. (Nat Genet, 2025)
To broaden our understanding of bradyarrhythmias and conduction disease, we performed common variant genome-wide association analyses in up to 1.3 million individuals and rare variant burden testing in 460,000 individuals for sinus node dysfunction (SND), distal conduction disease (DCD) and pacemaker (PM) implantation. We identified 13, 31 and 21 common variant loci for SND, DCD and PM, respectively. Four well-known loci (SCN5A/SCN10A, CCDC141, TBX20 and CAMK2D) were shared for SND and DCD, while others were more specific for SND or DCD. SND and DCD showed a moderate genetic correlation (r = 0.63). Cardiomyocyte-expressed genes were enriched for contributions to DCD heritability. Rare-variant analyses implicated LMNA for all bradyarrhythmia phenotypes, SMAD6 and SCN5A for DCD and TTN, MYBPC3 and SCN5A for PM. These results show that variation in multiple genetic pathways (for example, ion channel function, cardiac developmental programs, sarcomeric structure and cellular homeostasis) appear critical to the development of bradyarrhythmias.
Keywords: Bradycardia; Cardiac Conduction System Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Pacemaker, Artificial; Phenotype; Polymorphism, Single Nucleotide; Sick Sinus Syndrome

Meta-analysis of genome-wide associations and polygenic risk prediction for atrial fibrillation in more than 180,000 cases. - Roselli, Carolina; Surakka, Ida; Olesen, Morten S; Sveinbjornsson, Gardar; Marston, Nicholas A; Choi, Seung Hoan; Holm, Hilma; Chaffin, Mark; Gudbjartsson, Daniel; Hill, Matthew C; Aegisdottir, Hildur; Albert, Christine M; et al. (Nat Genet, 2025)
Atrial fibrillation (AF) is the most common heart rhythm abnormality and is a leading cause of heart failure and stroke. This large-scale meta-analysis of genome-wide association studies increased the power to detect single-nucleotide variant associations and found more than 350 AF-associated genetic loci. We identified candidate genes related to muscle contractility, cardiac muscle development and cell-cell communication at 139 loci. Furthermore, we assayed chromatin accessibility using assay for transposase-accessible chromatin with sequencing and histone H3 lysine 4 trimethylation in stem cell-derived atrial cardiomyocytes. We observed a marked increase in chromatin accessibility for our sentinel variants and prioritized genes in atrial cardiomyocytes. Finally, a polygenic risk score (PRS) based on our updated effect estimates improved AF risk prediction compared to the CHARGE-AF clinical risk score and a previously reported PRS for AF. The doubling of known risk loci will facilitate a greater understanding of the pathways underlying AF.
Keywords: Atrial Fibrillation; Chromatin; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Myocytes, Cardiac; Polymorphism, Single Nucleotide; Risk Factors

Non-Esterified Fatty Acid Profiles and Cause-Specific Mortality: The Cardiovascular Health Study. - Bene-Alhasan, Yakubu; Shitole, Sanyog G; Bůzková, Petra; Hirsch, Calvin H; Ix, Joachim H; Kizer, Jorge R; Siscovick, David S; Matthan, Nirupa R; Lichtenstein, Alice H; Djoussé, Luc; Mukamal, Kenneth J (J Clin Endocrinol Metab, 2025)
CONTEXT: Total fasting non-esterified fatty acid (NEFA) levels have been associated with mortality. The corresponding associations with NEFA levels following an oral glucose tolerance test (OGTT) and with individual fasting NEFA species are unclear. OBJECTIVE: We evaluated the associations of post-load NEFA, fasting subclasses and individual NEFA with mortality. DESIGN AND SETTING: The Cardiovascular Health Study is a population-based cohort study of community-dwelling adults over 64 years from four US communities that began in 1989-1990. Participants had total NEFA measured enzymatically before and two hours after an OGTT from archived serum samples collected in 1996-1997. Fasting individual NEFA were also measured using gas chromatography. Cox proportional hazard models were used to evaluate adjusted hazard ratios (aHR) for mortality associated with fasting and post-load total NEFA, and fasting individual and fatty acid subclasses (saturated, monounsaturated, n-3 and n-6 polyunsaturated, and trans). RESULTS: The final population included 1996 participants with a mean age of 78 years. 60.5% were female. Over a median 11-year follow-up period, 1678 participants died. Total fasting NEFA was associated with higher risk of all-cause mortality (aHR per standard deviation: 1.17, 95% CI [1.10-1.23]). Total post-load NEFA was not associated with mortality. Among subclasses, only monounsaturated fatty acid (MUFA) was associated with total mortality (aHR 1.24, 95% CI [1.09-1.41]). For individual NEFAs, nervonic acid (aHR 1.06, 95% CI [1.01-1.12]), petroselaidic acid (aHR 1.21, 95% CI [1.03-1.42]) and eicosapentaenoic acid (aHR 0.90, 95% CI [0.82-0.99]) were associated with all-cause mortality. CONCLUSION: Individual fasting NEFAs represent attractive candidates for medical and public health interventions aimed at improving survivorship in older adults and should be investigated further.

A statistical framework for multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Jiang, Min-Zhi; DiCorpo, Daniel; Gaynor, Sheila M; et al. (Nat Comput Sci, 2025)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally scalable analytical pipeline for functionally informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits in 61,838 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered and replicated new associations with lipid traits missed by single-trait analysis.
Keywords: Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Whole Genome Sequencing